Study of Central Exclusive Production of π+π−, K+K− and pairs in proton-proton collisions at GeV with the STAR detector at RHIC - STAR Collaboration (Journal of High Energy Physics, 2026)
A bstract We report on the first measurement of the Central Exclusive Production process in proton-proton collisions: pp → ph + h − p (where h = π , K , p ) at the center-of-mass energy $$\sqrt{s}=510$$ GeV with the STAR experiment at RHIC. At this energy, the process is dominated by a double Pomeron exchange mechanism. Hence, it provides a clean environment for investigating Pomeron interactions by measuring fully reconstructed final states involving only two hadrons and two forward scattered protons. The oppositely charged hadron pairs are measured within the central detector of STAR. The forward scattered protons are measured in the Roman Pot system allowing the verification of the event’s exclusivity. Differential fiducial cross sections within the STAR acceptance are presented as a function of the difference in the azimuthal angle between the outgoing protons. The invariant masses of the charged hadron pairs are measured up to approximately 3 GeV and the square of the four-momentum transfer ( t 1 and t 2 ) of the two forward-scattered protons in the range 0.3 GeV 2 < − t 1 , − t 2 < 1.6 GeV 2 . The differential fiducial cross sections of the forward protons as a function of the | t 1 + t 2 | are also presented. All results for the π + π − pair are presented in three mass ranges. A comparison with GRANIITTI Monte Carlo predictions are also presented, where the spectra include continuum and resonant contributions. The observed spectra are consistent with double Pomeron exchange, including resonances seen in previous studies.
Keywords: dept.phy

Measurement of inclusive J/ψ production in Au+Au collisions at sNN=54.4 GeV at STAR - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2026)
This article presents measurements of inclusive J / ψ production at midrapidity (| y | < 1.0) in Au+Au collisions at sNN=54.4 GeV with the STAR detector at the Relativistic Heavy Ion Collider. A suppression of the J / ψ yield, quantified using the nuclear modification factors ( R AA, R CP), is observed with respect to the scaled production in p+p collisions. The dependence of R AA on collision centrality and J / ψ transverse momentum is measured with improved precision compared to previous measurements at 39 and 62.4 GeV, while the centrality dependence of R CP is measured and compared to the same results at 39, 62.4, and 200 GeV. In central collisions, no significant collision energy dependence of R AA is found within uncertainties for collision energies between 17.3 and 200 GeV. Two transport model calculations that include dissociation and regeneration contributions are consistent with the experimental results within uncertainties. Although no significant collision energy dependence of the J / ψ suppression in high energy heavy-ion collisions up to sNN=200 GeV is observed within uncertainties, the newly measured results at 54.4 GeV Au+Au collisions provide additional constraints on theoretical calculations of the hot medium evolution and cold nuclear matter effects. © 2026 The Authors.
Keywords: Nuclear modification factor; Quark-gluon plasma; Quarkonium; dept.phy

Evidence of Spin-Interference Effects in Exclusive 𝐽/𝜓 → 𝑒+⁢𝑒− Photoproduction in Ultraperipheral Heavy-Ion Collisions - STAR Collaboration (Physical Review Letters, 2026)
Here, we report the first evidence of spin interference in exclusive 𝐽/𝜓 → 𝑒+⁢𝑒− photoproduction in ultraperipheral heavy-ion collisions at STAR at $\sqrt{𝑠_{𝑁⁢𝑁}}$ = 200 GeV. In Au + Au collisions, a negative cos⁡(2⁢𝜙) modulation is found for 𝑝𝑇 < 120 MeV/𝑐 with a significance of 3.2⁢𝜎, while the isobar data (Ru + Ru, Zr + Zr) show a consistent negative modulation with a significance of 1.9⁢𝜎, opposite in sign to that in 𝜌0 → 𝜋+⁢𝜋− photoproduction. This establishes for the first time that the interference sign is controlled by the spin structure of the final-state daughters, resolving the ambiguity present in the all-boson 𝜌0 channel. The compact 𝐽/𝜓 probes gluon distributions at perturbative scales, resulting in a weaker modulation and providing stringent constraints on color glass condensate calculations. These findings demonstrate that spin-dependent interference in heavy vector mesons provides a new, experimentally accessible handle on gluon structure beyond traditional cross-section measurements.
Number: BNL-229705-2026-JAAM
Keywords: dept.phy

First Observation of Deuteron-Λ Correlations at RHIC - STAR Collaboration (Physical Review Letters, 2026)
Precise experimental information on hyperon-nucleon interactions is scarce but of paramount importance to our understanding of the inner structure of compact stars. In this Letter, we report the first experimental results of correlation functions between deuterons (𝑑) and Λ hyperons in Au+Au collisions at √𝑠NN=3.0 GeV measured by the STAR experiment at the Relativistic Heavy Ion Collider. A clear enhancement at small relative momenta has been observed in the correlation function. Through a Bayesian inference analysis, the source size parameters as a function of collision centrality and the spin-dependent strong interaction parameters (scattering length 𝑓0 and effective range 𝑑0) are extracted using the Lednický-Lyuboshitz formalism. The derived doublet spin state parameters (𝑓0, 𝑑0) lead to a novel method to precisely determine Λ separation energy for the weakly bounded hypertriton 3ΛH.
Keywords: dept.phy

Measurement of transverse polarization of Λ and hyperons inside jets in unpolarized proton-proton collisions at GeV - STAR Collaboration (Journal of High Energy Physics, 2026)
A surprisingly large transverse polarization of Λ hyperons in unpolarized hadron-nucleon/nucleus collisions has been observed for 50 years, and the origin of this polarization remains an important open question. Recently, theoretical frameworks have advanced in describing this puzzle with the polarizing fragmentation function (PFF). We report the first measurement of Λ and transverse polarization inside jets in unpolarized proton-proton collisions, which is directly attributed to the PFF. The polarization is measured as a function of the jet transverse momentum, the fraction of the jet momentum carried by hyperons, and the transverse momentum of hyperons relative to the jet axis. Covering a wide jet-energy range, these data provide the first constraints on the gluon PFF and allow tests of TMD evolution and its universality. © The Author(s) 2026.
Keywords: Hadron-Hadron Scattering; Jets; Polarization; Proton-Proton Scattering; dept.phy

Measurement of fifth- and sixth-order fluctuations of (net-)proton number in Au + Au collisions from phase II of the beam energy scan program at RHIC - STAR Collaboration (Physical review. C, 2026)
Keywords: Beam (structure); Beam energy; Energy (signal processing); Measure (data warehouse); Phase (matter); dept.phy

Identified charged hadron production in Au + Au collisions at s N N = 54.4 GeV with the STAR detector - STAR Collaboration (Physical review. C, 2026)
We present results on the production of $π{\pm}$, $K{\pm}$, $p$, and $\bar{p}$ in Au+Au collisions at $\sqrt{s_\mathrm{NN}}$ = 54.4~GeV using the STAR detector at RHIC, at midrapidity ($|y| <$ 0.1). Invariant yields of these particles as a function of transverse momentum are shown. We determine bulk properties such as integrated particle yields ($dN/dy$), mean transverse momentum ($\langle p_{T} \rangle$), particle ratios, which provide insight into the particle production mechanisms. Additionally, the kinetic freezeout parameters ($T_\text{kin}$ and $\langle β_{T} \rangle$), which provide information about the dynamics of the system at the time of freezeout, are obtained. The Bjorken energy density ($ε_{\rm{BJ}}$), which gives an estimate of the energy density in the central rapidity region of the collision zone at the formation time $τ$, is calculated and presented as a function of multiplicity for various energies. The results are compared with those from the models such as A Multi-Phase Transport (AMPT) and Heavy Ion Jet INteraction Generator (HIJING) for further insights.
Keywords: Detector; Hadron; Large Hadron Collider; Production (economics); Star (game theory)

The solar neighborhood LIV: 54 orbits of M dwarf multiples within 30 pc with speckle interferometry at SOAR - Vrijmoet, Eliot; Tokovinin, Andrei; Henry, Todd; Winters, Jennifer; Jao, Wei‐Chun; Horch, Elliott (The Astronomical Journal, 2026)
Abstract We present 1066 speckle measurements of M dwarf multiples observed over 2021–2024, all taken with HRCam on the Southern Astrophysical Research 4.1 m telescope. Among these, 900 observations resolve companions in 212 pairs, with separations spanning 17 mas to 3 . ″ 4 and brightness differences ranging from 0 to 4.9 mag in the I filter. We have characterized the orbits of 54 of these companions, spanning periods of 0.67–30 yr, by combining our data with literature astrometry, radial velocities, and, in four cases, Hipparcos–Gaia accelerations. Among the orbits presented here are 28 that are the first-ever such characterizations for their systems and 26 that revise previously published orbits, thus providing a significant update to the observed dynamics of M dwarfs in the solar neighborhood. From these orbits, we provide new and updated dynamical total masses for these systems, precise to 0.7%–7% in nearly all cases. Future mass derivations for components in these systems will contribute to efforts in refining the mass–luminosity relation for the smallest stars and will enhance investigations of age, magnetism, and metallicity effects on luminosities at a given mass.
Keywords: Brightness; Interferometry; Metallicity; Radial velocity; Solar System; Speckle imaging; Speckle pattern; Stars; dept.phy

A New velocity-dispersion profile for the Core of 47Tuc - Petroski, Alexander; Casetti‐Dinescu, Dana; Girard, Terrence; Baena-Gallé, Roberto (Research Notes of the AAS, 2025)
Abstract As part of an effort to identify astrometric evidence of an intermediate-mass black hole in 47Tuc, we construct a new velocity-dispersion profile for the innermost 30 ″ of the cluster using WFPC2 and WFC3 images spanning an unprecedented 22 yr time baseline. The WFPC2 exposures were processed using a deep-learning centering procedure as well as an improved astrometric calibration of the camera. The resulting velocity-dispersion profile has a 1 ″ spatial resolution and error bars that compare very favorably to prior studies.
Keywords: Calibration; Cluster (spacecraft); Construct (python library); Core (optical fiber); Field (mathematics); Resolution (logic); dept.phy

Nanoelectronics, nanophotonics, and quantum technologies - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, Haifeng (World Scientific, 2025)
Keywords: Field (mathematics); Quantum; Quantum computer; Quantum dot; Quantum entanglement; Quantum technology; dept.phy

Measurement of In-Medium jet modification using direct Photon+Jet and π0+Jet correlations in p+p and central Au+Au collisions at sNN=200 GeV - STAR Collaboration (Physical Review Letters, 2025)
Keywords: Atomic physics; Hadron; Jet (fluid); Jet quenching; Materials science; Nuclear physics; Optics; Photon; Physics; Quark–gluon plasma; Quenching (fluorescence); Range (aeronautics); Thermodynamics; dept.phy

Measuring spin correlation between quarks during QCD confinement - STAR Collaboration (Nature, 2026)
The vacuum is now understood to have a rich and complex structure, characterized by fluctuating energy fields^1 and a condensate of virtual quark-antiquark pairs. The spontaneous breaking of the approximate chiral symmetry^2, signalled by the nonvanishing quark condensate ⟨ q q ¯ ⟩ , is dynamically generated through topologically nontrivial gauge configurations such as instantons^3. The precise mechanism linking the chiral symmetry breaking to the mass generation associated with quark confinement^4 remains a profound open question in quantum chromodynamics (QCD)-the fundamental theory of strong interaction. High-energy proton-proton collisions could liberate virtual quark-antiquark pairs from the vacuum that subsequently undergo confinement to form hadrons, whose properties could serve as probes into QCD confinement and the quark condensate. Here we report evidence of spin correlations in Λ Λ ¯ hyperon pairs inherited from spin-correlated strange quark-antiquark virtual pairs. Measurements by the STAR experiment at the Relativistic Heavy Ion Collider (RHIC) at Brookhaven National Laboratory reveal a relative polarization signal of (18 ± 4)% that links the virtual spin-correlated quark pairs from the QCD vacuum to their final-state hadron counterparts. Crucially, this correlation vanishes when the hyperon pairs are widely separated in angle, consistent with the decoherence of the quantum system. Our findings provide a new experimental model for exploring the dynamics and interplay of quark confinement and entanglement.
Keywords: Chiral symmetry breaking; Color confinement; Hadron; Hyperon; QCD vacuum; Quantum chromodynamics; Quark; Spontaneous symmetry breaking; Symmetry breaking; Top quark; dept.phy

Energy independence of the Collins asymmetry in p ↑ p collisions - STAR Collaboration (Physical Review Letters, 2025)
The STAR experiment reports new, high-precision measurements of the transverse single-spin asymmetries for π{±} within jets, namely the Collins asymmetries, from transversely polarized p{↑}p collisions at sqrt[s]=510 GeV. The energy-scaled distribution of jet transverse momentum, x_{T}=2p_{T,jet}/sqrt[s], shows a remarkable consistency for Collins asymmetries of π{±} in jets between sqrt[s]=200 GeV and 510 GeV. This indicates that the Collins asymmetries are nearly energy independent, with, at most, a very weak scale dependence in p{↑}p collisions. These results extend to high-momentum scales (Q{2}≤3400 GeV{2}) and enable unique tests of evolution and universality in the transverse-momentum-dependent formalism, thus providing important constraints for the Collins fragmentation functions.
Keywords: Asymmetry; Consistency (knowledge bases); Fragmentation (computing); High energy; Independence (probability theory); Polarization (electrochemistry); Transverse plane; Universality (dynamical systems); dept.phy

Probing late-stage hadronic interactions at high baryon density via K⁎0 production in the RHIC beam energy scan program - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2026)
A precision measurement of the K ⁎0 meson yield is reported in Au+Au collisions at sNN=7.7,11.5,14.6,19.6, and 27 GeV using the high-statistics data sample collected by the STAR experiment during the Beam Energy Scan II (BES-II) program at RHIC. The transeverse momentum ( pT )-integrated yield ratios (K*0+K*0‾)/(K++K−) in central collisions show a suppression relative to peripheral collisions at the (1.7–3.6) σ level, while a thermal model without final-stage rescattering overpredicts this ratio with a deviation of (6.9–8.2) σ . These results indicate a loss of the measured K ⁎0 signal in central collisions due to re-scattering of its hadronic decay products in the hadronic phase. The pT -integrated yield of charged kaons exhibits an approximate scaling with charged-particle multiplicity, independent of collision energy and system size. A similar trend is observed for the short-lived K ⁎0 resonance, although significant deviations emerge at lower energies. At BES energies, the K ⁎0/ K ratio shows stronger suppression than at the highest RHIC and LHC energies within a given multiplicity bin, particularly in central and mid-central collisions. This behavior is consistent with changes in the effective hadronic interaction cross section and is supported by transport model calculations, which indicate dominant meson–baryon interactions at lower energies and meson–meson interactions at higher energies. Copyright © 2026. Published by Elsevier B.V.
Keywords: BES; Hadronic phase; Heavy ion collisions; Re-scattering; Resonance

Measurement of the longitudinal flow-plane decorrelation using multiplane cumulants in (Formula presented.) = 200 GeV Au + Au, Ru + Ru, and Zr + Zr collisions - STAR Collaboration (Physical Review C, 2026)
Measurements of the variation of anisotropic flow-plane angles (Ψn) with rapidity, commonly known as the flow-plane decorrelation, provide important insights into the initial conditions of the matter produced in heavyion collisions. In this paper, using data collected by the STAR experiment, we report the first measurement of the four-plane correlator observable (Formula presented.), where superscripts a, b, c, and d denote sequential pseudorapidity (η) regions with a corresponding to the most backward region, b and c close to midrapidity with nb < 0 and nc > 0, and d being the most forward. The measurement is performed for the elliptic and triangular flow (i.e., n = 2 and 3) in Au + Au and isobar (Ru + Ru, Zr + Zr) collisions at (Formula presented.) = 200 GeV. The goal of calculating the correlation of the flow-plane angle variations from backward to midcentral, and from midcentral to forward regions, is to probe the systematic variation of flow angle over a wide П range. In midcentral collisions (10-30 % centrality), we find T2{ba; dc} = —0.004 ± 0.001 (stat) ± 0.002(syst) independent of the collision system. Such a small value of T2 favors a “random-walk” variation of the flow-plane angles, where the rapidity correlation length is smaller than the entire region under study. These measurements provide new information on the decorrelation patterns in the system and offer a quantitative estimate of possible systematic variations in anisotropic flow angles such as “twist” between forward and backward regions. This opens new opportunities for understanding the three-dimensional structure and the time evolution of the quarkgluon plasma created in heavy-ion collisions. © 2026 American Physical Society
Keywords: Calibration; Cumulant; Decorrelation; Noise (video); Signal processing; dept.phy

Lignin-derived carbon dots from leaf waste as sustainable plant sunscreens and UV-protective foliar coatings - Thangavelu, Raja; Gray, Sarah; Wu, Binlin; Pellegrino, Richard; da Silva, Washington; Zuverza-Mena, Nubia; Dimkpa, Christian; White, Jason (Environmental Science Nano, 2026)
Keywords: Agricultural waste; Agriculture; Carbon fibers; Lignin; Maple; Sustainable agriculture; Sustainable production; dept.phy

Beam-energy dependence of correlations between mean transverse momentum and anisotropic flow of charged particles in Au+Au collisions at RHIC - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2026)
The correlation between the mean transverse momentum, [p T], and the squared anisotropic flow, vn2, on an event-by-event basis has been suggested to be influenced by the initial conditions in heavy-ion collisions. We present measurements of the variances and covariance of [p T] and vn2, along with their dimensionless ratio, for Au+Au collisions at various beam energies: sNN = 14.6, 19.6, 27, 54.4, and 200 GeV. Our measurements reveal a distinct energy-dependent behavior in the variances and covariances. In addition, the dimensionless ratio displays a similar behavior across different beam energies. We compare our measurements with hydrodynamic models and similar measurements from Pb+Pb collisions at the Large Hadron Collider (LHC). These findings provide valuable insights into the beam energy dependence of the specific shear viscosity (η / s) and initial-state effects, allowing for differentiating between different initial-state models. © 2026 The Authors.
Keywords: Collectivity; Correlation; Shear viscosity; Transverse momentum correlations; dept.phy

Search for the chiral magnetic effect through beam energy dependence of charge separation using event shape selection - STAR Collaboration (Physical Review C, 2026)
High-energy, heavy-ion collisions can create local domains of chirality-imbalanced quarks, reflecting the topological features of quantum chromodynamics. The chiral magnetic effect (CME) predicts an electric charge separation of quarks in such topological domains along the magnetic field (B) generated by the passing of two high-Z nuclei. We use a correlation observable Δγ112 between charged meson pairs to detect the CME-induced charge separation and a novel event shape selection (ESS) method to mitigate the background effects related to elliptic flow (v2). The ESS method classifies events based on the emission pattern of final-state particles and determines Δγ(Formula presented) from the zero-flow limit. We reconstruct the B field direction from the spectator nucleons, which minimizes backgrounds unrelated to the collective motion of the system. In this work, we report the measurements of Δγ112 and a background indicator Δγ132 in Au + Au collisions from the Brookhaven National Laboratory Relativistic Heavy Ion Collider (RHIC) Beam Energy Scan phase II and at the top RHIC energy. After background suppression, Δγ(Formula presented) aligns with zero, and Δγ(Formula presented) is reduced to no more than 20% of Δγ112. We observe a finite residual charge separation with 2.5σ, 3σ, and 3.2σ significance in the 20-50% centrality range of Au + Au collisions at 11.5, 14.6, and 19.6 GeV. The results at 17.3 and 27 GeV also show positive values but with a lower significance of 1.3σ and 1.1σ, respectively. The corresponding ΔγΈ5ΕΕ values at 7.7, 9.2, and 200 GeV are consistent with zero within uncertainties. © (2026), (American Physical Society). All right reserved.
Keywords: Beam (structure); Charge (physics); Energy (signal processing); Event (particle physics); Magnetic field; Selection (genetic algorithm); dept.phy

Measurement of kaon directed flow in Au+Au collisions in the high baryon density region - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2026)
Rapidity-odd directed flow v 1 measurements are presented for K ± and KS0 in Au + Au collisions for sNN from 3.0 to 3.9 GeV with the STAR experiment. For comparison, v 1 of π ± , protons, and Λ from the same collisions are also discussed. The mid-rapidity v 1 slope dv1/dy|y=0 for protons and Λ is positive in these collisions. On the other hand, v 1 slope of kaons exhibits a strong pT dependence: negative at pT< 0.6 GeV/ c and positive at higher pT. A similar pT dependence is also evident for the v 1 slope of charged pions. Compared to the spectator-removed calculations in Au+Au collisions at sNN= 3.0–3.9 GeV, the JAM model demonstrates a pronounced shift of the v 1 slopes of mesons towards the negative direction. It suggests that the shadowing effect of the spectators plays an important role in the observed kaon anti-flow at low pT in the high baryon density region of non-central collisions. © 2026 The Authors.
Keywords: Directed flow; Heavy-ion collisions; High baryon density region; Kaon potential; QCD phase structure; Spectator effect; dept.phy

Interface-Induced Polarization and Inhibition of Ferroelectricity in Epitaxial SrTiO3/Si - Kolpak, A.M.; Walker, F.J.; Reiner, J.W.; Segal, Y.; Su, D.; Sawicki, M.S.; Broadbridge, C.C.; Zhang, Z.; Zhu, Y.; Ahn, C.H.; Ismail-Beigi, S. (Handbook Of Molecular Beam Epitaxy Of Oxide Materials (In 3 Volumes), 2025)
We use SrTiO3/Si as a model system to elucidate the effect of the interface on ferroelectric behavior in epitaxial oxide films on silicon. Using both first-principles computations and synchrotron x-ray diffraction measurements, we show that structurally imposed boundary conditions at the interface stabilize a fixed (pinned) polarization in the film but inhibit ferroelectric switching. We demonstrate that the interface chemistry responsible for these phenomena is general to epitaxial silicon-oxide interfaces, impacting on the design of silicon-based functional oxide devices. © 2026 by World Scientific Publishing Co. Pte. Ltd.
Keywords: Antiferroelectricity; Epitaxy; Ferroelectricity; Induced polarization; Polarization (electrochemistry); dept.phy

Characterizing TESS-identified Quadruple- and Higher-order Eclipsing Binaries. I. Speckle Imaging with DSSI and HRCam - Majewski, Steven; Davidson, James; Wilson, Robert; Horch, Elliott; McKee, P.; Fagan, Evan; Hartwell, Gary; Kostov, Veselin; Adams, C.; Sutherland, Torrie; Tokovinin, Andreï; Wilson, John (The Astrophysical Journal, 2025)
Abstract NASA’s TESS mission has unveiled a plethora of eclipsing binaries (EBs), among them hundreds of triples and higher-order, hierarchical systems. These complex targets require follow-up observations to enable full characterization of system architectures and identify the most compact multiples expected to undergo the most dramatic dynamical evolution. We report first results from a long-term effort to perform such follow-up, focusing here on multiband speckle imaging of a majority (57) of the sample of 97 quadruple- and higher-order eclipsing binaries (Q+EBs) identified via TESS light curves by V. B. Kostov et al. Diffraction-limited imaging with the Differential Speckle Survey Instrument on the Astrophysical Research Consortium 3.5 m telescope and HRCam on the Southern Astrophysical Research 4.1 m telescope reveals nearly 60% of the 57 to resolve into two sources separated by ≥0 . ″ 03. For these partly resolved systems, we report derived characteristics (e.g., relative position angle, angular separation, and magnitude differences in multiple passbands) from the speckle imaging. We find those Q+EBs partly resolved with 4 m class telescopes to have significantly inflated Gaia parallax errors and large Gaia renormalized unit weight errors, particularly for systems with separations comparable to Gaia’s resolution limit (∼0 . ″ 6). For unresolved systems we report upper limits on angular and linear projected separations. We find two partly resolved Q+EBs with wide linear separations having eclipse timing variations that are therefore candidates of higher-than-quadruple multiplicity. Finally, we demonstrate how speckle imaging of resolved Q+EBs during an eclipse can clarify which speckle-resolved Q+EB subsystem is associated with a particular set of TESS eclipses.
Keywords: Angular resolution (graph drawing); Astrometry; Eclipse; Parallax; Speckle imaging; Speckle pattern; Telescope; dept.phy

Observation of Charmonium Sequential Suppression in Heavy-Ion Collisions at the Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review Letters, 2026)
We report measurements of charmonium sequential suppression in Ru+Ru and Zr+Zr collisions at sNN=200 GeV with the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The inclusive yield ratio of ψ(2S) to J/ψ as a function of transverse momentum is reported, along with the centrality dependence of the double ratio, defined as the ψ(2S) to J/ψ ratio in heavy-ion collisions relative to that in p+p collisions. In the 0-80% centrality class, the double ratio is found to be 0.41±0.10 (stat)±0.03 (syst)±0.02 (ref), lower than unity with a significance of 5.6 standard deviations. This provides experimental evidence that ψ(2S) is significantly more suppressed than J/ψ in heavy-ion collisions at RHIC. This sequential suppression pattern seems to increase from peripheral to central collisions, but with no significant dependence on the transverse momentum. © 2026 American Physical Society.
Keywords: dept.phy

Semi-inclusive direct photon + jet and π0+jet correlations measured in p + p and central Au + Au collisions at √sNN = 200 GeV - STAR Collaboration (Physical Review C, 2026)
The Solenoidal Tracker at RHIC (STAR) experiment at the Relativistic Heavy Ion Collider reports new measurements of jet quenching based on the semi-inclusive distribution of charged-particle jets recoiling from direct photon (γdir) and neutral pion (π0) triggers in pp and central Au + Au collisions at √sNN = 200 GeV for triggers in the range 9 < ET trig < 20 GeV. The datasets have integrated luminosities of 3.9 nb−1 for Au + Au and 23 pb−1 for pp collisions. Jets are reconstructed using the anti-kT algorithm with resolution parameters R = 0.2 and 0.5. The large uncorrelated jet background in central Au + Au collisions is corrected using a mixed-event approach, which enables precise charged-particle jet measurements at low transverse momentum pch T,jet and large R. Recoil-jet distributions are reported in the range pch T,jet < 25 GeV/c. Comparison of the distributions measured in pp and Au + Au collisions reveals strong medium-induced jet yield suppression for R = 0.2 with markedly less suppression for R = 0.5. Comparison is also made to theoretical models incorporating jet quenching. These data provide new insight into the mechanisms underlying jet quenching and the angular dependence of medium-induced jet-energy transport and provide new constraints on modeling such effects. © 2025 American Physical Society
Keywords: Jet (fluid); Mathematics; Physics; Thermodynamics; dept.phy

Nanoelectronics, Nanophotonics, And Quantum Technologies: Devices And Applications - Jain, Faquir C.; Broadbridge, C.; Gherasimova, M.; Tang, Hong (World Scientific, 2025)
This timely compendium provides state-of-the-art articles covering research areas in Nanoelectronics, Nanophotonics and Quantum Technologies.Composed of contributions by renowned researchers from both the academia and industry, this useful reference text broadly illustrates relevant aspects of high-performance materials and emerging quantum and nanoscale devices for implementing high-speed electronic systems.
Google-Books-ID: h_K0EQAAQBAJ
Keywords: Computers / Quantum Computing; Technology & Engineering / Nanotechnology & MEMS; dept.phy

Optical Molecular Signatures of IDH Genotype for Classification of Human Glioma Using Visible Resonance Raman Spectroscopy - Zhang, Liang; Zhou, Yan; Wu, Binlin; Zhang, Shengjia; Zhu, Ke; Liu, C.; Alfano, Robert; Yu, Xinguang (Journal of Biophotonics, 2026)
Keywords: Biomarker; Gene; Genotype; Glioma; IDH mutation; IDH1; Isocitrate dehydrogenase; Mutation; Raman spectroscopy; Resonance Raman spectroscopy; dept.phy; glioma; optical molecular biopsy; visible resonance Raman spectroscopy

Mass-luminosity anomalies: Plausible evidence of recent stellar interaction in the extraordinary blue straggler S1082 - Quitral-Pierart, Amanda; Leigh, Nathan; Mathieu, Robert; Latham, David; Sandquist, Eric; Horch, Elliott (Astronomy and Astrophysics, 2025)
Context. We present an observational and theoretical study of the complex stellar system S1082 in the open cluster M67. This system consists of at least four stars: a blue straggler in a 1.07-day eclipsing binary with a main sequence star (binary A) and another blue straggler in a 1185-day orbit with an unknown companion (binary B). Aims. We analyzed observational data to obtain the orbital and stellar parameters of the components of the eclipsing system. We then explored mass transfer and dynamical encounter scenarios that could explain the derived properties of all of the components of S1082. Methods. We combined high-precision photometry from K2 and TESS with archival light curves, new radial-velocity measurements, and speckle imaging to refine the orbital and physical parameters of the system. To explore the formation pathways, we conducted binary evolution simulations with MESA and dynamical scattering experiments with FEWBODY, followed by a tidal evolution modeling procedure. Results. Our revised radial-velocity solutions yield significantly changed dynamical masses for binary A, reducing the tension with the cluster turnoff mass compared to previous studies. Speckle imaging shows two resolved components separated by 390 AU in projection and, in combination with the two spectroscopic orbits, this is suggestive of a hierarchical quadruple configuration. Our results suggest that the two blue stragglers formed separately, with later dynamical encounters assembling the present configuration. This work underscores the importance of stellar dynamics in shaping the evolution of complex stellar systems within cluster environments such as M67.
Keywords: Binary number; Binary star; Blue straggler; Blue stragglers; Cluster (spacecraft); Open clusters and associations: individual: M67; Photometry (optics); Speckle imaging; Star cluster; Stars: individual: S1082; Stellar evolution; Stellar mass; dept.phy

Measurement of medium-induced acoplanarity in central Au-Au and pp collisions at √sNN = 200 GeV using direct-photon+jet and π+ jet correlations - STAR Collaboration (Physical Review C, 2026)
The STAR Collaboration reports measurements of acoplanarity using semi-inclusive distributions of charged-particle jets recoiling from direct photon and π triggers, in central Au–Au and pp collisions at √sNN = 200 GeV. Significant medium-induced acoplanarity broadening is observed for large but not small recoil jet resolution parameter, corresponding to recoil jet yield enhancement up to a factor of ≈20 for trigger-recoil azimuthal separation far from π. This phenomenology is indicative of the response of the quark-gluon plasma to excitation, but not the scattering of jets off of its quasiparticles. The measurements are not well described by current theoretical models which incorporate jet quenching. © (2026), (American Physical Society). All rights reserved.
Keywords: Component (thermodynamics); Field (mathematics); Measure (data warehouse); Noise (video); Work (physics); dept.phy

Erratum: Disappearance of partonic collectivity in √ sNN = 3 GeV Au+Au collisions at RHIC (Physics Letters B, (2022), 827, 137003) - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2025)
We report on the measurements of directed flow v1 and elliptic flow v2 for hadrons (π±, K±, KS0, p, ϕ, Λ and Ξ−) from Au+Au collisions at sNN = 3 GeV and v2 for (π±, K±, p and p‾) at 27 and 54.4 GeV with the STAR experiment. While at the two higher energy midcentral collisions the number-of-constituent-quark (NCQ) scaling holds, at 3 GeV the v2 at midrapidity is negative for all hadrons and the NCQ scaling is absent. In addition, the v1 slopes at midrapidity for almost all observed hadrons are found to be positive, implying dominant repulsive baryonic interactions. The features of negative v2 and positive v1 slope at 3 GeV can be reproduced with a baryonic mean-field in transport model calculations. These results imply that the medium in such collisions is likely characterized by baryonic interactions. © 2025 The Authors.
Keywords: Baryonic interactions; Collectivity; High baryon density; NCQ scaling; STAR experiment; dept.phy

Temperature measurement of Quark-Gluon plasma at different stages - STAR Collaboration (Nature Communications, 2025)
In a Quark-Gluon Plasma (QGP), the fundamental building blocks of matter, quarks and gluons, are under extreme conditions of temperature and density. A QGP could exist in the early stages of the Universe, and in various objects and events in the cosmos. The thermodynamic and hydrodynamic properties of the QGP are described by Quantum Chromodynamics (QCD) and can be studied in heavy-ion collisions. Despite being a key thermodynamic parameter, the QGP temperature is still poorly known. Thermal lepton pairs (e+e− and μ+μ−) are ideal penetrating probes of the true temperature of the emitting source, since their invariant-mass spectra suffer neither from strong final-state interactions nor from blue-shift effects due to rapid expansion. Here we measure the QGP temperature using thermal e+e− production at the Relativistic Heavy Ion Collider (RHIC). The average temperature from the low-mass region (in-medium ρ0 vector-meson dominant) is (2.01 ± 0.23) × 1012 K, consistent with the chemical freeze-out temperature from statistical models and the phase transition temperature from Lattice QCD. The average temperature from the intermediate mass region (above the ρ0 mass, QGP dominant) is significantly higher at (3.25 ± 0.60) × 1012 K. This work provides essential experimental thermodynamic measurements to map out the QCD phase diagram and understand the properties of matter under extreme conditions. © The Author(s) 2025.
Keywords: Measure (data warehouse); Phase diagram; Plasma; Quantum chromodynamics; Quark–gluon plasma; Temperature measurement; Thermal; Transition temperature; Work (physics); dept.phy

Measurements of ϒ states production in p + p collisions at √s = 500 GeV with STAR: Cross sections, ratios, and multiplicity dependence - STAR Collaboration (Physical Review D, 2025)
We report measurements of ϒ(1S), ϒ(2S) and ϒ(3S) production in p + p collisions at √s = 500 GeV ffiffi by the STAR experiment in year 2011, corresponding to an integrated luminosity Lint = 13 pb−1. The results provide precise cross sections, transverse momentum (pT) and rapidity (y) spectra, as well as cross section ratios for pT < 10 GeV=c and |y| < 1. The dependence of the ϒ yield on charged particle multiplicity has also been measured, offering new insights into the mechanisms of quarkonium production. The data are compared to various theoretical models: the color evaporation model (CEM) accurately describes the ϒ(1S) production, while the color glass condensate + nonrelativistic quantum chromodynamics (CGC + NRQCD) model overestimates the data, particularly at low pT. Conversely, the color singlet model (CSM) underestimates the rapidity dependence. These discrepancies highlight the need for further development in understanding the production dynamics of heavy quarkonia in high-energy hadronic collisions. The trend in the multiplicity dependence is consistent with CGC/saturation and string percolation models or ϒ production happening in multiple parton interactions modeled by PYTHIA8. © 2025 American Physical Society
Keywords: Algorithm; Mathematics; dept.phy

Precision measurement of the longitudinal double-spin asymmetry for dijet production at intermediate pseudorapidity ffiffi in polarized pp collisions at √s = 200 GeV - STAR Collaboration (Physical Review D, 2025)
The STAR Collaboration reports precise measurements of the longitudinal double-spin asymmetry, ALL, for dijet production with at least one jet at intermediate pseudorapidity 0.8 < ηjet < 1.8 in polarized proton-proton collisions at a center-of-mass energy of 200 GeV. This study explores partons scattered with a longitudinal momentum fraction (x) from 0.01 to 0.5, which are predominantly characterized by interactions between high-x valence quarks and low-x gluons. The results are in good agreement with previous measurements at 200 GeV with improved precision and are found to be consistent with the predictions of global analyses that find the gluon polarization to be positive. In contrast, the negative gluon polarization solution from the JAM Collaboration is found to be strongly disfavored. © 2025 American Physical Society
Keywords: Asymmetry; Computer science; Particle physics; Physics; Production (economics); Pseudorapidity; Spin (aerodynamics)

Hyperon global polarization in isobar Ru+Ru and Zr+Zr collisions at sNN=200GeV - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2025)
The polarization of Λ , Λ ¯ , Ξ − , and Ξ ¯ + hyperons along the angular momentum of the system has been measured in isobar collisions of Ru+Ru and Zr+Zr at s N N = 200 GeV with the STAR detector at RHIC. The polarization dependence on collision centrality exhibits an increasing trend in more peripheral collisions. Λ and Λ ¯ polarization dependence on the transverse momentum and pseudorapidity have been investigated, but no significant dependence was observed. The polarizations of Λ and Λ ¯ are found to be consistent with each other, indicating little contribution of the spin-magnetic coupling to the measured polarization. Comparison to previously measured polarization in Au+Au collisions show no obvious system size dependence. The results are qualitatively consistent with hydrodynamic calculations including contributions from shear-induced polarization and thermal vorticity. For the first time in heavy-ion collisions, the dependence of the global polarization on the hyperon’s emission azimuthal angle relative to the second-order event plane has been measured, indicating stronger polarization for the in-plane emitted hyperons at the level of 2.4 σ significance in 20–50 % centrality. The Ξ hyperon polarization measurements via polarization transfer analysis yield finite positive values with 2.9 σ significance in 20–50 % centrality, slightly larger compared to the inclusive Λ polarization. © 2025 The Authors.
Keywords: Global polarization; Hyperon; Vorticity; dept.phy

Precision Measurement of Net-Proton-Number Fluctuations in Au+Au Collisions at RHIC - STAR Collaboration (Physical review letters, 2025)
We report precision measurements on cumulants (C_{n}) and factorial cumulants (κ_{n}) of (net) proton number distributions up to fourth order in Au+Au collisions over center-of-mass energies sqrt[s_{NN}]=7.7-27 GeV from phase II of the Beam Energy Scan program at RHIC. (Anti)protons are selected at midrapidity (|y|<0.5) within a transverse momentum range of 0.4<p_{T}<2.0 GeV/c. Relative to various noncritical-point model calculations and peripheral collision 70%-80% data, the net proton C_{4}/C_{2} measurement in 0%-5% collisions shows a minimum around 19.6 GeV for significance of deviation at ∼2-5σ. A minimum in C_{4}/C_{2} with respect to a noncritical baseline is expected to be a characteristic feature of the signature associated with a critical point in the QCD phase diagram. In addition, deviations from noncritical baselines around the same collision energy region are also seen in proton factorial cumulant ratios, especially in κ_{2}/κ_{1} and κ_{3}/κ_{1}. Dynamical model calculations including a critical point are called for in order to understand these precision measurements.
Keywords: Net (polyhedron); Nuclear physics; Physics; Proton; dept.phy

HST Proper Motions of Andromeda V and Andromeda VI - Casetti-Dinescu, Dana I.; Pawlowski, Marcel S.; Girard, Terrence M.; Kanehisa, Kosuke Jamie; Martone, Max; Petroski, Alexander (Astrophysical Journal, 2025)
We measure the absolute proper motions of Andromeda V (And V) and Andromeda VI/Pegasus (And VI) dwarf galaxies, satellites of M31 located near its galactic plane. And VI is located the farthest from M31 among the six satellites with currently measured proper motions. A combination of Advanced Camera for Surveys/wide filed channel (WFC) and WFPC2 exposures is utilized, spanning a 20 yr time baseline. The WFPC2 exposures are processed using a recently developed deep-learning centering procedure as well as the most up-to-date astrometric calibration of the camera. We use on the order of 100 background galaxies per satellite to determine the correction to absolute proper motion. For And V, we obtain an absolute proper motion of (μα, μδ)And V= (26.1 ± 21.5 , − 74.2 ± 19.1) μ as yr−1. For And VI, we obtain an absolute proper motion of (μα, μδ)And VI= (− 1.6 ± 12.3 , − 52.6 ± 11.2) μ as yr−1. Orbit integrations and analyses are made for these two Andromeda satellites using two estimates of both the mass and proper motion of M31. It is found that And V has an orbit consistent within errors with alignment with M31’s disk and counter orbiting it, although this alignment is not well constrained. And VI’s orbit is better determined and is very much consistent with coorbiting with M31’s disk. While currently at a distance of ∼280 kpc from M31, And VI will remain beyond a distance of ∼90 kpc from M31, thus experiencing low tidal influence compared to the other M31 satellites with known orbits. Both satellites are determined to be well-bound to M31. © 2025. The Author(s). Published by the American Astronomical Society.
Keywords: dept.phy

Measurement of Two-Point Energy Correlators within Jets in p+p Collisions at sqrt[s]=200 GeV - STAR Collaboration (Physical review letters, 2025)
Hard-scattered partons ejected from high-energy proton-proton collisions undergo parton shower and hadronization, resulting in collimated collections of particles that are clustered into jets. A substructure observable that highlights the transition between the perturbative and nonperturbative regimes of jet evolution in terms of the angle between two particles is the two-point energy correlator (EEC). In this Letter, the first measurement of the EEC at RHIC is presented, using data taken from 200 GeV p+p collisions by the STAR experiment. The EEC is measured both for all the pairs of particles in jets and separately for pairs with like and opposite electric charges. These measurements demonstrate that the transition between perturbative and nonperturbative effects occurs within an angular region that is consistent with expectations of a universal hadronization regime that scales with jet momentum for a given initiator flavor. Additionally, a deviation from Monte Carlo predictions at small angles in the charge-selected sample could result from mechanics of hadronization not fully captured by current models.
Keywords: Collimated light; Hadronization; Jet (fluid); Momentum (technical analysis); Monte Carlo method; Observable; Parton; Parton shower; Substructure; dept.phy

Onset of Constituent Quark Number Scaling in Heavy-Ion Collisions at RHIC - STAR Collaboration (Physical review letters, 2025)
Partonic collectivity is one of the necessary signatures for the formation of quark-gluon plasma in high-energy nuclear collisions. Number of constituent quarks (NCQ) scaling has been observed for hadron elliptic flow v_{2} in top energy nuclear collisions at the Relativistic Heavy Ion Collider and the LHC, and this has been theoretically suggested as strong evidence for partonic collectivity. In this Letter, a systematic analysis of v_{2} of π{±}, K{±}, K_{S}{0}, p, and Λ in Au+Au collisions at sqrt[s_{NN}]=3.2, 3.5, 3.9, and 4.5 GeV, with the STAR experiment at the Relativistic Heavy Ion Collider, is presented. NCQ scaling is markedly violated at 3.2 GeV, consistent with a hadronic-interaction dominated equation of state. However, as the collision energy increases, a gradual evolution to NCQ scaling is observed. This beam-energy dependence of v_{2} for all hadrons studied provides evidence for the onset of dominant partonic interactions by sqrt[s_{NN}]=4.5 GeV.
Keywords: Heavy ion; Ion; Nuclear physics; Particle physics; Physics; Quark; Scaling; Scaling law; dept.phy

The fire blight pathogen Erwinia amylovora enters apple leaves through naturally occurring wounds from the abscission of trichomes - Millett, Felicia; Standish, James; Scanley, Jules; Miller, Katelyn; Inguagiato, John; Zuverza‐Mena, Nubia; Abril, Maritza; Robinson, Victoria; Li, Yan; Sundin, George; Zeng, Quan (The Plant Journal, 2025)
The plant epidermis is a single layer of cells covering all plant organs. How pathogens overcome this barrier and enter plants is an important aspect of plant-pathogen interactions. For bacterial plant pathogens, known entry points include natural openings, such as stomata, hydathodes, and mechanical injuries caused by insect feeding, wind damage, or hailstorms. Here, we report that the fire blight pathogen Erwinia amylovora enters apple leaves through naturally occurring wounds caused by the abscission of trichomes during the course of leaf development. Through macroscopic and microscopic observations, we depicted a clear invasion path for E. amylovora cells, from epiphytic growth on glandular trichomes (GT) and non-glandular trichomes (NT) to entry through wounds caused by abscised trichomes, into the epithem, and subsequent spread through xylem. We further observed that GT and NT undergo an abscission process, and that the amount of naturally occurring wounds during abscission is associated with the increase in E. amylovora population. Key genes important for the colonization of GT and NT were identified. The contribution of the type III secretion system and amylovoran biosynthesis during GT colonization was validated. Our findings propose a novel host entry mechanism of plant pathogenic bacteria through naturally occurring wounds during the abscission of plant surface structures.
Keywords: Abscission; Blight; Colonization; Erwinia; Erwinia amylovora; Fire blight; Trichome; abscission; dept.phy; fire blight; host entry points; trichomes; type III secretion system

Effect of binder concentration on ternary MnO2/CuS/reduced graphene oxide material for supercapacitor applications - Chaudhary, Manika; Oyelola, Lekan; Glidden, Thomas; Broadbridge, C.; LeMaire, Peter; Sharma, Rakesh; Singh, Vinamrita; Sahi, Vikhyat; Singhal, Rahúl (Journal of Solid State Electrochemistry, 2025)
Keywords: Capacitance; Chemical engineering; Chemistry; Electrochemistry; Electrode; Energy storage; Graphene; Inorganic chemistry; Materials science; Metallurgy; Nanotechnology; Oxide; Physical chemistry; Supercapacitor; Synthesis; Ternary operation; Thermodynamics; X-ray diffraction; dept.phy

Photon counting in stellar intensity interferometry: current status and future prospects - Horch, Elliott P. (Advanced Photon Counting Techniques XIX, 2025)
Intensity interferometry, also known as the Hanbury Brown and Twiss effect, has seen significant interest in astronomy in recent years. The method involves recording timing correlations between photons received at two or more telescopes in order to derive extremely high spatial resolution information about an astronomical object, potentially including imaging stellar surfaces and other objects at unprecedented scales. This paper will briefly review the technique, discuss the performance characteristics of the of photon counters used in modern intensity interferometers, and describe opportunities for the future. As an example of photon counting with a working instrument, observing experiences with the Southern Connecticut Stellar Interferometer (SCSI), a three-station instrument using single-photon avalanche diode (SPAD) detectors, will be described. The recent lessons learned with this and other instruments in use today give a clear picture of the next steps needed to upgrade efficiency and successfully observe fainter objects. If successful, these improvements would provide a strong argument for creating situations where intensity interferometers can have baselines of one to several kilometers, which would unlock the spatial detail needed to address several exciting astrophysical questions.
Keywords: Astronomy; Current (fluid); Intensity (physics); Interferometry; Optics; Photon; Photon counting; Physics; dept.phy

The Qz5 Survey. I. How the H i Mass Density of the Universe Evolves with Cosmic Time - Oyarzún, Grecco A.; Rafelski, Marc; Christensen, Lise; Ozyurt, Fiona; Jorgenson, Regina A.; Neeleman, M.; Fumagalli, Michele; Prochaska, J. Xavier; Worseck, G.; Wisz, M. E.; Becker, George D.; López, Sebastián (The Astrophysical Journal, 2025)
We report that the neutral hydrogen (H i) mass density of the Universe (ρH i) increases with cosmic time since z ∼ 5, peaks at z ∼ 3, and then decreases toward z ∼ 0. This is the first result of Qz5, our spectroscopic survey of 63 quasars at z ≳ 5 with VLT/X-SHOOTER and Keck/ESI aimed at characterizing intervening H i gas absorbers at z ∼ 5. The main feature of Qz5 is the high resolution (R ∼ 7000–9000) of the spectra, which allows us to (1) accurately detect high column density H i gas absorbers in an increasingly neutral intergalactic medium at z ∼ 5 and (2) determine the reliability of previous ρH i measurements derived with lower resolution spectroscopy. We find five intervening damped Lyα absorbers (DLAs) at z > 4.5, which corresponds to the lowest DLA incidence rate () at z ≳ 2. We also measure the lowest ρH i at z ≳ 2 from our sample of DLAs and subDLAs, corresponding to ρH i Mpc−3 at z ∼ 5. Taking into account our measurements at z ∼ 5 and systematic biases in the DLA detection rate at lower spectral resolutions, we conclude that ρH i doubles from z ∼ 5 to z ∼ 3. From these results emerges a qualitative agreement between how the cosmic densities of H i gas mass, molecular gas mass, and star formation rate build up with cosmic time.
Keywords: dept.phy; peer-reviewed

Light nuclei femtoscopy and baryon interactions in 3 GeV Au+Au collisions at RHIC - STAR Collaboration (Physics Letters B, 2025)
We report the measurements of proton-deuteron (p-d) and deuteron-deuteron (d-d) correlation functions in Au+Au collisions at sNN = 3 GeV using fixed-target mode with the STAR experiment at the Relativistic Heavy-Ion Collider (RHIC). For the first time, the source size (RG), scattering length (f0), and effective range (d0) are extracted from the measured correlation functions with a simultaneous fit. The spin-averaged f0 for p-d and d-d interactions are determined to be -5.28 ± 0.11(stat.) ± 0.82(syst.) fm and -2.62 ± 0.02(stat.) ± 0.24(syst.) fm, respectively. The measured p-d interaction is consistent with theoretical calculations and low-energy scattering experiment results, demonstrating the feasibility of extracting interaction parameters using the femtoscopy technique. The reasonable agreement between the experimental data and the calculations from the transport model indicates that deuteron production in these collisions is primarily governed by nucleon coalescence.
Keywords: dept.phy; peer-reviewed

The Solar Neighborhood. LII. M Dwarf Twin Binaries—Presumed Identical Twins Appear Fraternal in Variability, Rotation, Hα, and X-Rays - Couperus, Andrew A.; Henry, Todd J.; Osten, Rachel A.; Jao, Wei-Chun; Vrijmoet, Eliot Halley; Kar, Aman; Horch, Elliott (The Astronomical Journal, 2024)
We present an investigation into the rotation and stellar activity of four fully convective M dwarf “twin” wide binaries. Components in each pair have (1) astrometry confirming they are common-proper-motion binaries, (2) Gaia BP, RP, and 2MASS J, H, and K s magnitudes matching within 0.10 mag, and (3) presumably the same age and composition. We report long-term photometry, rotation periods, multiepoch Hα equivalent widths, X-ray luminosities, time series radial velocities, and speckle observations for all components. Although it might be expected for the twin components to have matching magnetic attributes, this is not the case. Decade-long photometry of GJ 1183 AB indicates consistently higher spot activity on A than B, a trend matched by A appearing 58% ± 9% stronger in L X and 26% ± 9% stronger in Hα on average—this is despite similar rotation periods of A = 0.86 day and B = 0.68 day, thereby informing the range in activity for otherwise identical and similarly rotating M dwarfs. The young β Pic Moving Group member 2MA 0201+0117 AB displays a consistently more active B component that is 3.6 ± 0.5 times stronger in L X and 52% ± 19% stronger in Hα on average, with distinct rotation at A = 6.01 days and B = 3.30 days. Finally, NLTT 44989 AB displays remarkable differences with implications for spindown evolution—B has sustained Hα emission while A shows absorption, and B is ≥39 ± 4 times stronger in L X, presumably stemming from the surprisingly different rotation periods of A = 38 days and B = 6.55 days. The last system, KX Com, has an unresolved radial velocity companion, and is therefore not a twin system.
Keywords: dept.phy; peer-reviewed

Plant-engineered ZnO and CuO nanoparticles exhibit pesticidal activity and mitigate Fusarium infestation in soybean: A mechanistic understanding - Karmous, Inès; Elmer, Wade; Zuverza‐Mena, Nubia; Vaidya, Shital; Tlahig, Samir; Scanley, Jules; Bharadwaj, Anuja; White, Jason; Dimkpa, Christian (Plant Physiology and Biochemistry, 2025)
Keywords: Antifungal activity; Artemisia vulgaris; Biogenic copper and Zn oxide nanoparticles; Biology; Botany; Chemistry; Fusarium; Infestation; Materials science; Nanoparticle; Nanotechnology; Soybean; dept.phy; peer-reviewed

Electric-charge-dependent directed flow splitting of produced quarks in Au+Au collisions - STAR Collaboration (Physics Letters B, 2025)
We report directed flow (v1) of multistrange baryons (Ξ and Ω) and improved v1 data for K−, p¯, Λ¯ and ϕ in Au+Au collisions at sNN=27 and 200 GeV from the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). We focus on particles whose constituent quarks are not transported from the incoming nuclei but instead are produced in the collisions. At intermediate impact parameters, we examine quark coalescence behavior for particle combinations with identical quark content, and search for any departure from this behavior (“splitting”) for combinations having non-identical quark content. Under the assumption of quark coalescence for produced quarks, the splitting strength appears to increase with the electric charge difference of the constituent quarks in the combinations, consistent with electromagnetic effect expectations.
Keywords: Directed flow; Electric charge; Electromagnetic field; Heavy-ion collisions; Strangeness; dept.phy; peer-reviewed

Energy dependence of polarized 𝛾⁢𝛾→𝑒+⁢𝑒− in peripheral Au+Au collisions at √𝑠𝑁⁢𝑁=54.4 and 200 GeV with the STAR experiment at RHIC - STAR Collaboration (Physical Review C, 2025)
We report the differential yields at mid-rapidity of the Breit-Wheeler process (𝛾⁢𝛾→𝑒+⁢𝑒−) in peripheral Au+Au collisions at √𝑠𝑁⁢𝑁=54.4 and 200 GeV with the STAR experiment at the Relativistic Heavy Ion Collider (RHIC), as a function of energy √𝑠𝑁⁢𝑁, 𝑒+⁢𝑒− transverse momentum 𝑝T, 𝑝2T, invariant mass 𝑀𝑒⁢𝑒, and azimuthal angle. In the invariant mass range of 0.4<𝑀𝑒⁢𝑒<2.6GeV/𝑐2 at low transverse momentum (𝑝T<0.15GeV/𝑐), the yields increase while the pair √⟨𝑝2T⟩ decreases with increasing √𝑠𝑁⁢𝑁, a feature that is correctly predicted by the QED calculation. The energy dependencies of the measured quantities are sensitive to the nuclear form factor, infrared divergence and photon polarization. The data are compiled and used to extract the charge radius of the Au nucleus.
Keywords: Computer science; dept.phy; peer-reviewed

Measurement of directed flow in Au+Au collisions at √𝑠𝑁⁢𝑁=19.6 and 27 GeV with the STAR event plane detector - STAR Collaboration (Physical Review C, 2025)
In heavy-ion collision experiments, the global collectivity of final-state particles can be quantified by anisotropic flow coefficients (𝑣𝑛). The first-order flow coefficient, also referred to as the directed flow (𝑣1), describes the collective sideward motion of produced particles and nuclear fragments in heavy-ion collisions. It carries information on the very early stage of the collision, especially at large pseudorapidity (𝜂), where it is believed to be generated during the nuclear passage time. Directed flow therefore probes the onset of bulk collective dynamics during thermalization, providing valuable experimental guidance to models of the pre-equilibrium stage. In 2018, the Event Plane Detector (EPD) was installed in STAR and used for the Beam Energy Scan phase-II (BES-II) data taking. The combination of EPD (2.1<|𝜂|<5.1) and high-statistics BES-II data enables us to extend the 𝑣1 measurement to the forward and backward 𝜂 regions. In this paper, we present the measurement of 𝑣1 over a wide 𝜂 range in Au+Au collisions at √𝑠𝑁⁢𝑁= 19.6 and 27 GeV using the STAR EPD. The results of the analysis at √𝑠𝑁⁢𝑁= 19.6 GeV exhibit excellent consistency with the previous PHOBOS measurement, while elevating the precision of the overall measurement. The increased precision of the measurement also revealed finer structures in heavy-ion collisions, including a potential observation of the first-order event-plane decorrelation. Multiple physics models were compared to the experimental results. Only a transport model and a three-fluid hybrid model can reproduce a sizable 𝑣1 at large 𝜂 as was observed experimentally. The model comparison also indicates 𝑣1 at large 𝜂 might be sensitive to the QGP phase transition.
Keywords: Algorithm; Atomic physics; Charged particle; Computer science; Flow (mathematics); Ion; Mechanics; Nuclear physics; Physics; Pseudorapidity; Thermalisation; dept.phy; peer-reviewed

Production of protons and light nuclei in Au +Au collisions at √𝑠𝑁⁢𝑁=3 GeV with the STAR detector - STAR Collaboration (Physical Review C, 2024)
We report the systematic measurement of protons and light nuclei production in Au +Au collisions at √𝑠𝑁⁢𝑁=3GeV by the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The transverse momentum (𝑝𝑇) spectra of protons (𝑝), deuterons (𝑑), tritons (𝑡), 3He, and 4He have been measured from midrapidity to target rapidity for different collision centralities. We present the rapidity and centrality dependence of particle yields (𝑑⁢𝑁/𝑑⁢𝑦), average transverse momentum (⟨𝑝𝑇⟩), yield ratios (𝑑/𝑝, 𝑡/𝑝,3He/𝑝, 4He/𝑝), as well as the coalescence parameters (𝐵2, 𝐵3). The 4⁢𝜋 yields for various particles are determined by utilizing the measured rapidity distributions, 𝑑⁢𝑁/𝑑⁢𝑦. Furthermore, we present the energy, centrality, and rapidity dependence of the compound yield ratios (𝑁𝑝×𝑁𝑡/𝑁2𝑑) and compare them with various model calculations. The physics implications of these results on the production mechanism of light nuclei and the QCD phase structure are discussed.
Keywords: dept.phy; peer-reviewed

Measurement of flow coefficients in high-multiplicity 𝑝+Au, 𝑑+Au, and 3 He +Au collisions at √𝑠𝑁⁢𝑁=200 GeV - STAR Collaboration (Physical Review C, 2024)
Flow coefficients (𝑣2 and 𝑣3) are measured in high-multiplicity 𝑝+Au, 𝑑+Au, and 3He+Au collisions at a center-of-mass energy of √𝑠𝑁⁢𝑁=200 GeV using the STAR detector. The measurements utilize two-particle correlations with a pseudorapidity requirement of |𝜂|< 0.9 and a pair gap of |Δ⁢𝜂|>1.0. The primary focus is on analysis methods, particularly the subtraction of nonflow contributions. Four established nonflow subtraction methods are applied to determine 𝑣𝑛, validated using the HIJING event generator. 𝑣𝑛 values are compared across the three collision systems at similar multiplicities; this comparison cancels the final-state effects and isolates the impact of initial geometry. While 𝑣2 values show differences among these collision systems, 𝑣3 values are largely similar, consistent with expectations of subnucleon fluctuations in the initial geometry. The ordering of 𝑣𝑛 differs quantitatively from previous measurements using two-particle correlations with a larger rapidity gap, which, according to model calculations, can be partially attributed to the effects of longitudinal flow decorrelations. The prospects for future measurements to improve our understanding of flow decorrelation and subnucleonic fluctuations are also discussed.
Keywords: dept.phy; peer-reviewed

Correlations of event activity with hard and soft processes in p+Au collisions at sNN =200 GeV at the RHIC STAR experiment - STAR Collaboration (Physical Review C, 2024)
With the STAR experiment at the BNL Relativistic Heavy Ion Collider, we characterize sNN=200GeV p+Au collisions by event activity (EA) measured within the pseudorapidity range ηϵ[-5,-3.4] in the Au-going direction and report correlations between this EA and hard- and soft-scale particle production at midrapidity (ηϵ[-1,1]). At the soft scale, charged particle production in low-EA p+Au collisions is comparable to that in p+p collisions and increases monotonically with increasing EA. At the hard scale, we report measurements of high transverse momentum (pT) jets in events of different EAs. In contrast with the soft particle production, high-pT particle production and EA are found to be inversely related. To investigate whether this is a signal of jet quenching in high-EA events, we also report ratios of pT imbalance and azimuthal separation of dijets in high- and low-EA events. Within our measurement precision, no significant differences are observed, disfavoring the presence of jet quenching in the highest 30% EA p+Au collisions at sNN=200GeV. © 2024 American Physical Society.
Keywords: dept.phy; peer-reviewed

La Silla-QUEST RR Lyrae star survey II: the Crater II tidal streams - Coppi, P S; Zinn, R; Baltay, C; Rabinowitz, D; Girard, T; Howard, R; Ment, K; Rahman, R (Monthly Notices of the Royal Astronomical Society, 2024)
We describe photometry improvements in the La Silla-Quest RR Lyrae star (RRLS) survey that enable it to reach distances from the Sun (d⊙) ∼140 kpc. We report the results of surveying ∼300 deg2 of sky around the large, low-surface-brightness Crater II dwarf spheroidal galaxy. At d⊙ >80 kpc, we find a large overdensity of RRLS that extends beyond the traditional isophotal contours used for Crater II. The majority of these RRLS (34) have a linear distribution on the sky, extending over 15°, that runs through Crater II and is oriented along Crater II’s proper motion vector. We hypothesize that this unlikely distribution traces extended tidal streams associated with Crater II. To test this, we search for other Crater II stellar populations that should be in the streams. Using Gaia proper motion data, we isolate ≈ 17 candidate stars outside of Crater II that are consistent with being luminous stars from the Crater II Red Giant Branch (RGB). Their spatial distribution is consistent with the RRLS one. The inferred streams are long, spanning a distance range ∼80–135 kpc from the Galactic Centre. They are oriented at a relatively small-angle relative to our line of sight (∼25°), which means some stream stars are likely projected onto the main body of the galaxy. Comparing the numbers of RRLS and RGB candidate stars found in the streams to those in the main galaxy, we estimate Crater II has lost $\gtrsim 30~{{\rm per\ cent}}$ of its stellar mass.
Keywords: dept.phy; peer-reviewed

Imaging shapes of atomic nuclei in high-energy nuclear collisions - STAR Collaboration (Nature, 2024)
Atomic nuclei are self-organized, many-body quantum systems bound by strong nuclear forces within femtometre-scale space. These complex systems manifest a variety of shapes1–3, traditionally explored using non-invasive spectroscopic techniques at low energies4,5. However, at these energies, their instantaneous shapes are obscured by long-timescale quantum fluctuations, making direct observation challenging. Here we introduce the collective-flow-assisted nuclear shape-imaging method, which images the nuclear global shape by colliding them at ultrarelativistic speeds and analysing the collective response of outgoing debris. This technique captures a collision-specific snapshot of the spatial matter distribution within the nuclei, which, through the hydrodynamic expansion, imprints patterns on the particle momentum distribution observed in detectors6,7. We benchmark this method in collisions of ground-state uranium-238 nuclei, known for their elongated, axial-symmetric shape. Our findings show a large deformation with a slight deviation from axial symmetry in the nuclear ground state, aligning broadly with previous low-energy experiments. This approach offers a new method for imaging nuclear shapes, enhances our understanding of the initial conditions in high-energy collisions and addresses the important issue of nuclear structure evolution across energy scales. © The Author(s) 2024.
Keywords: dept.phy; peer-reviewed

HST Proper Motion of Andromeda III. Another Satellite Coorbiting the M31 Satellite Plane - Casetti-Dinescu, Dana I.; Pawlowski, Marcel S.; Girard, Terrence M.; Kanehisa, Kosuke Jamie; Petroski, Alexander; Martone, Max; Kozhurina-Platais, Vera; Platais, Imants (The Astrophysical Journal, 2024)
We measure the absolute proper motion of Andromeda III (And III) using Advanced Camera for Surveys/Wide Field Channel and WFPC2 exposures spanning an unprecedented 22 yr time baseline. The WFPC2 exposures have been processed using a deep-learning centering procedure recently developed as well as an improved astrometric calibration of the camera. The absolute proper motion zero point is given by 98 galaxies and 16 Gaia EDR3 stars. The resulting proper motion is (μ α , μ δ ) = (−10.5 ± 12.5, 47.5 ± 12.5) μas yr−1. We perform an orbit analysis of And III using two estimates of M31's mass and proper motion. We find that And III’s orbit is consistent with dynamical membership to the Great Plane of Andromeda system of satellites although with some looser alignment compared to the previous two satellites NGC 147 and NGC 185. And III is bound to M31 if M31's mass is M vir ≥ 1.5 × 1012 M ⊙.
Keywords: dept.phy; peer-reviewed

Precision Measurement of the Proton Flux in Primary Cosmic Rays from Rigidity 1 GV to 1.8 TV with the Alpha Magnetic Spectrometer on the International Space Station - AMS Collaboration; Finch, Evan (Physical Review Letters, 2015)
A precise measurement of the proton flux in primary cosmic rays with rigidity (momentum/charge) from 1 GV to 1.8 TV is presented based on 300 million events. Knowledge of the rigidity dependence of the proton flux is important in understanding the origin, acceleration, and propagation of cosmic rays. We present the detailed variation with rigidity of the flux spectral index for the first time. The spectral index progressively hardens at high rigidities.
Keywords: dept.phy

Precision Measurement of the Longitudinal Double-Spin Asymmetry for Inclusive Jet Production in Polarized Proton Collisions at √𝑠=200 GeV - STAR Collaboration (Physical Review Letters, 2015)
We report a new measurement of the midrapidity inclusive jet longitudinal double-spin asymmetry, 𝐴𝐿⁢𝐿, in polarized 𝑝⁢𝑝 collisions at center-of-mass energy √𝑠=200 GeV. The STAR data place stringent constraints on polarized parton distribution functions extracted at next-to-leading order from global analyses of inclusive deep-inelastic scattering (DIS), semi-inclusive DIS, and RHIC 𝑝⁢𝑝 data. The measured asymmetries provide evidence at the 3⁢𝜎 level for positive gluon polarization in the Bjorken-𝑥 region 𝑥>0.05.
Keywords: dept.phy

Beam-energy-dependent two-pion interferometry and the freeze-out eccentricity of pions measured in heavy ion collisions at the STAR detector - STAR Collaboration (Physical Review C, 2015)
We present results of analyses of two-pion interferometry in Au+Au collisions at √𝑠𝑁𝑁=7.7, 11.5, 19.6, 27, 39, 62.4, and 200 GeV measured in the STAR detector as part of the BNL Relativistic Heavy Ion Collider Beam Energy Scan program. The extracted correlation lengths (Hanbury-Brown–Twiss radii) are studied as a function of beam energy, azimuthal angle relative to the reaction plane, centrality, and transverse mass (𝑚𝑇) of the particles. The azimuthal analysis allows extraction of the eccentricity of the entire fireball at kinetic freeze-out. The energy dependence of this observable is expected to be sensitive to changes in the equation of state. A new global fit method is studied as an alternate method to directly measure the parameters in the azimuthal analysis. The eccentricity shows a monotonic decrease with beam energy that is qualitatively consistent with the trend from all model predictions and quantitatively consistent with a hadronic transport model.
Keywords: dept.phy

Precision Measurement of the Helium Flux in Primary Cosmic Rays of Rigidities 1.9 GV to 3 TV with the Alpha Magnetic Spectrometer on the International Space Station - AMS Collaboration (Physical Review Letters, 2015)
Knowledge of the precise rigidity dependence of the helium flux is important in understanding the origin, acceleration, and propagation of cosmic rays. A precise measurement of the helium flux in primary cosmic rays with rigidity (momentum/charge) from 1.9 GV to 3 TV based on 50 million events is presented and compared to the proton flux. The detailed variation with rigidity of the helium flux spectral index is presented for the first time. The spectral index progressively hardens at rigidities larger than 100 GV. The rigidity dependence of the helium flux spectral index is similar to that of the proton spectral index though the magnitudes are different. Remarkably, the spectral index of the proton to helium flux ratio increases with rigidity up to 45 GV and then becomes constant; the flux ratio above 45 GV is well described by a single power law.
Keywords: dept.phy

Antiproton Flux, Antiproton-to-Proton Flux Ratio, and Properties of Elementary Particle Fluxes in Primary Cosmic Rays Measured with the Alpha Magnetic Spectrometer on the International Space Station - AMS Collaboration (Physical Review Letters, 2016)
A precision measurement by AMS of the antiproton flux and the antiproton-to-proton flux ratio in primary cosmic rays in the absolute rigidity range from 1 to 450 GV is presented based on 3.49×1⁢05 antiproton events and 2.42×1⁢09 proton events. The fluxes and flux ratios of charged elementary particles in cosmic rays are also presented. In the absolute rigidity range ∼60 to ∼500 GV, the antiproton ¯𝑝, proton 𝑝, and positron 𝑒+ fluxes are found to have nearly identical rigidity dependence and the electron 𝑒− flux exhibits a different rigidity dependence. Below 60 GV, the (¯𝑝/𝑝), (¯𝑝/𝑒+), and (𝑝/𝑒+) flux ratios each reaches a maximum. From ∼60 to ∼500 GV, the (¯𝑝/𝑝), (¯𝑝/𝑒+), and (𝑝/𝑒+) flux ratios show no rigidity dependence. These are new observations of the properties of elementary particles in the cosmos.
Keywords: dept.phy

Precision Measurement of the Boron to Carbon Flux Ratio in Cosmic Rays from 1.9 GV to 2.6 TV with the Alpha Magnetic Spectrometer on the International Space Station - AMS Collaboration (Physical Review Letters, 2016)
Knowledge of the rigidity dependence of the boron to carbon flux ratio (B/C) is important in understanding the propagation of cosmic rays. The precise measurement of the B/C ratio from 1.9 GV to 2.6 TV, based on 2.3 million boron and 8.3 million carbon nuclei collected by AMS during the first 5 years of operation, is presented. The detailed variation with rigidity of the B/C spectral index is reported for the first time. The B/C ratio does not show any significant structures in contrast to many cosmic ray models that require such structures at high rigidities. Remarkably, above 65 GV, the B/C ratio is well described by a single power law 𝑅Δ with index Δ=−0.333±0.014⁢(fit)±0.005⁢(syst), in good agreement with the Kolmogorov theory of turbulence which predicts Δ=−1/3 asymptotically.
Keywords: dept.phy

Strangeness production in sNN = 3 GeV Au+Au collisions at RHIC - STAR Collaboration (Journal of High Energy Physics, 2024)
We report multi-differential measurements of strange hadron production ranging from mid- to target-rapidity in Au+Au collisions at a center-of-momentum energy per nucleon pair of sNN = 3 GeV with the STAR experiment at RHIC. KS0 meson and Λ hyperon yields are measured via their weak decay channels. Collision centrality and rapidity dependences of the transverse momentum spectra and particle ratios are presented. Particle mass and centrality dependence of the average transverse momenta of Λ and KS0 are compared with other strange particles, providing evidence of the development of hadronic rescattering in such collisions. The 4π yields of each of these strange hadrons show a consistent centrality dependence. Discussions on radial flow, the strange hadron production mechanism, and properties of the medium created in such collisions are presented together with results from hadronic transport and thermal model calculations. © The Author(s) 2024.
Keywords: Fixed Target Experiments; Relativistic Heavy Ion Physics; dept.phy; peer-reviewed

JWST/NIRCam 4–5 μm Imaging of the Giant Planet AF Lep b - Franson, Kyle; Balmer, William O.; Bowler, Brendan P.; Pueyo, Laurent; Zhou, Yifan; Rickman, Emily; Zhang, Zhoujian; Mukherjee, Sagnick; Pearce, Tim D.; Gagliuffi, Daniella C. Bardalez; Biddle, Lauren I.; Brandt, Timothy D.; et al. (The Astrophysical Journal Letters, 2024)
With a dynamical mass of 3 M Jup, the recently discovered giant planet AF Lep b is the lowest-mass imaged planet with a direct mass measurement. Its youth and spectral type near the L/T transition make it a promising target to study the impact of clouds and atmospheric chemistry at low surface gravities. In this work, we present JWST/NIRCam imaging of AF Lep b. Across two epochs, we detect AF Lep b in F444W (4.4 μm) with signal-to-noise ratios of 9.6 and 8.7, respectively. At the planet’s separation of 320 mas during the observations, the coronagraphic throughput is ≈7%, demonstrating that NIRCam’s excellent sensitivity persists down to small separations. The F444W photometry of AF Lep b affirms the presence of disequilibrium carbon chemistry and enhanced atmospheric metallicity. These observations also place deep limits on wider-separation planets in the system, ruling out 1.1 M Jup planets beyond 15.6 au (0.″58), 1.1 M Sat planets beyond 27 au (1″), and 2.8 M Nep planets beyond 67 au (2.″5). We also present new Keck/NIRC2 imaging of AF Lep b; combining this with the two epochs of F444W photometry and previous Keck photometry provides limits on the long-term 3–5 μm variability of AF Lep b on timescales of months to years. AF Lep b is the closest-separation planet imaged with JWST to date, demonstrating that planets can be recovered well inside the nominal (50% throughput) NIRCam coronagraph inner working angle.
Keywords: dept.phy

Measurements of charged-particle multiplicity dependence of higher-order net-proton cumulants in p + p collisions at s=200 GeV from STAR at RHIC - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2024)
We report on the charged-particle multiplicity dependence of net-proton cumulant ratios up to sixth order from s=200 GeV p+p collisions at the Relativistic Heavy Ion Collider (RHIC). The measured ratios C4/C2, C5/C1, and C6/C2 decrease with increased charged-particle multiplicity and rapidity acceptance. Neither the Skellam baselines nor PYTHIA8 calculations account for the observed multiplicity dependence. In addition, the ratios C5/C1 and C6/C2 approach negative values in the highest-multiplicity events, which implies that thermalized QCD matter may be formed in p+p collisions. © 2024 The Author(s)
Keywords: Crossover; Event-by-event fluctuation; Higher-order cumulant; QCD phase diagram; dept.phy; peer-reviewed

Astronomical PSF characterization using grammar evolution and symbolic regression - Sarmiento, R.; Baena-Galle, R.; de la Cruz Echeandía, M.; de la Puente, A.O.; Girard, T.M.; Casetti-Dinescu, D.; Cervantes-Rovira, A. (2024)
Symbolic regression techniques are promising approaches to learning mathematical models that fit experimental data. One of the most powerful techniques for symbolic regression is Grammatical Evolution (GE). This evolutionary computation technique explores a space of candidate models that are ensured to be syntactically correct expressions built from a set of arbitrary building blocks and operators. In GE the syntax for these expressions is defined by a problem-specific formal grammar. Therefore, GE can produce an explainable solution (e.g. a formula), not a black-box model. The current contribution assesses the viability of GE for PSF characterization, using real datasets from HST/WFPC2. Our experiments show that our method is able to find the most likely candidate mathematical expression for the PSF shape, and can also model combinations of shapes taken from a predefined family of functions commonly used in astronomy (Gaussian and Moffat PSFs). These results support the hypothesis that the expressive power of GE can be used to tackle the problem of characterization of complex PSF functions, for example, as a necessary step in the prediction of intra-pixel position of stars. © 2024 SPIE.
Keywords: Grammatical evolution; Hubble Space Telescope; WFPC2; astrometry; dept.phy; point spread function; symbolic regression

Observation of the antimatter hypernucleus H¯Λ¯4 - STAR Collaboration (Nature, 2024)
At the origin of the Universe, an asymmetry between the amount of created matter and antimatter led to the matter-dominated Universe as we know it today. The origins of this asymmetry remain unknown so far. High-energy nuclear collisions create conditions similar to the Universe microseconds after the Big Bang, with comparable amounts of matter and antimatter1–6. Much of the created antimatter escapes the rapidly expanding fireball without annihilating, making such collisions an effective experimental tool to create heavy antimatter nuclear objects and to study their properties7–14, hoping to shed some light on the existing questions on the asymmetry between matter and antimatter. Here we report the observation of the antimatter hypernucleus $${}_{\bar{\Lambda }}{}{4}\bar{{\rm{H}}}$$, composed of a $$\bar{\Lambda }$$, an antiproton and two antineutrons. The discovery was made through its two-body decay after production in ultrarelativistic heavy-ion collisions by the STAR experiment at the Relativistic Heavy Ion Collider15,16. In total, 15.6 candidate $${}_{\bar{\Lambda }}{}{4}\bar{{\rm{H}}}$$antimatter hypernuclei are obtained with an estimated background count of 6.4. The lifetimes of the antihypernuclei $${}_{\bar{\Lambda }}{}{3}\bar{{\rm{H}}}$$and $${}_{\bar{\Lambda }}{}{4}\bar{{\rm{H}}}$$are measured and compared with the lifetimes of their corresponding hypernuclei, testing the symmetry between matter and antimatter. Various production yield ratios among (anti)hypernuclei (hypernuclei and/or antihypernuclei) and (anti)nuclei (nuclei and/or antinuclei) are also measured and compared with theoretical model predictions, shedding light on their production mechanisms.
Keywords: Experimental nuclear physics; Experimental particle physics; dept.phy; peer-reviewed

The orbit and dynamical mass of polaris: Observations with the CHARA array - Evans, Nancy Remage; Schaefer, Gail H.; Gallenne, Alexandre; Torres, Guillermo; Horch, Elliott P.; Anderson, Richard I.; Monnier, John D.; Roettenbacher, Rachael M.; Baron, Fabien; Anugu, Narsireddy; Davidson, James W.; Kervella, Pierre; et al. (The Astrophysical Journal, 2024)
The 30 yr orbit of the Cepheid Polaris has been followed with observations by the Center for High Angular Resolution Astronomy (CHARA) Array from 2016 through 2021. An additional measurement has been made with speckle interferometry at the Apache Point Observatory. Detection of the companion is complicated by its comparative faintness—an extreme flux ratio. Angular diameter measurements appear to show some variation with pulsation phase. Astrometric positions of the companion were measured with a custom grid-based model-fitting procedure and confirmed with the CANDID software. These positions were combined with the extensive radial velocities (RVs) discussed by Torres to fit an orbit. Because of the imbalance of the sizes of the astrometry and RV data sets, several methods of weighting are discussed. The resulting mass of the Cepheid is 5.13 ± 0.28 M ⊙. Because of the comparatively large eccentricity of the orbit (0.63), the mass derived is sensitive to the value found for the eccentricity. The mass combined with the distance shows that the Cepheid is more luminous than predicted for this mass from evolutionary tracks. The identification of surface spots is discussed. This would give credence to the identification of a radial velocity variation with a period of approximately 120 days as a rotation period. Polaris has some unusual properties (rapid period change, a phase jump, variable amplitude, and unusual polarization). However, a pulsation scenario involving pulsation mode, orbital periastron passage, and low pulsation amplitude can explain these characteristics within the framework of pulsation seen in Cepheids.
Keywords: dept.phy; peer-reviewed

Exclusive J/ψ, ψ(2s), and e+e- pair production in Au+Au ultraperipheral collisions at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2024)
Measurements of exclusive J/ψ, ψ(2s), and electron-positron (e+e-) pair photoproduction in Au+Au ultraperipheral collisions are reported by the STAR experiment at sNN=200GeV. We report several first measurements at the BNL Relativistic Heavy Ion Collider, which are (i) J/ψ photoproduction with large momentum transfer up to 2.2(GeV/c)2, (ii) coherent J/ψ photoproduction associated with neutron emissions from nuclear breakup, (iii) the rapidity dependence of incoherent J/ψ photoproduction, (iv) the ψ(2s) photoproduction cross section at midrapidity, and (v) e+e- pair photoproduction up to high invariant mass of 6GeV/c2. For measurement (ii), the coherent J/ψ total cross section of γ+Au→J/ψ+Au as a function of the center-of-mass energy WγN has been obtained without photon energy ambiguities. The data are quantitatively compared with the Monte Carlo models STARlight, Sartre, BeAGLE, and theoretical calculations of gluon saturation with color glass condensate, nuclear shadowing with leading twist approximation, quantum electrodynamics, and the next-to-leading-order perturbative QCD. At the photon-nucleon center-of-mass energy of 25.0 GeV, the coherent and incoherent J/ψ cross sections of Au nuclei are found to be 71%±10% and 36%±7%, respectively, of that of free protons. These data provide an important experimental constraint for nuclear parton distribution functions and a unique opportunity to advance the understanding of the nuclear modification effect at the top RHIC energy. © 2024 American Physical Society.
Keywords: dept.phy; peer-reviewed

Upper limit on the chiral magnetic effect in isobar collisions at the Relativistic Heavy-Ion Collider - STAR Collaboration (Physical Review Research, 2024)
The chiral magnetic effect (CME) is a phenomenon that arises from the QCD anomaly in the presence of an external magnetic field. The experimental search for its evidence has been one of the key goals of the physics program of the Relativistic Heavy-Ion Collider. The STAR Collaboration has previously presented the results of a blind analysis of isobar collisions (Ru4496+Ru4496, Zr4096+Zr4096) in the search for the CME. The isobar ratio (Y) of CME-sensitive observable, charge separation scaled by elliptic anisotropy, is close to but systematically larger than the inverse multiplicity ratio, the naive background baseline. This indicates the potential existence of a CME signal and the presence of remaining nonflow background due to two- and three-particle correlations, which are different between the isobars. In this postblind analysis, we estimate the contributions from those nonflow correlations as a background baseline to Y, utilizing the isobar data as well as Heavy Ion Jet Interaction Generator simulations. This baseline is found consistent with the isobar ratio measurement, and an upper limit of 10% at 95% confidence level is extracted for the CME fraction in the charge separation measurement in isobar collisions at sNN=200 GeV. © 2024 authors. Published by the American Physical Society. Published by the American Physical Society under the terms of the Creative Commons Attribution 4.0 International license. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI.
Keywords: dept.phy; peer-reviewed

Estimate of background baseline and upper limit on the chiral magnetic effect in isobar collisions at sNN =200 GeV at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2024)
For the search of the chiral magnetic effect (CME), STAR previously presented the results from isobar collisions (Ru4496+Ru4496, Zr4096+Zr4096) obtained through a blind analysis. The ratio of results in Ru+Ru to Zr+Zr collisions for the CME-sensitive charge-dependent azimuthal correlator (Δγ), normalized by elliptic anisotropy (v2), was observed to be close to but systematically larger than the inverse multiplicity ratio. The background baseline for the isobar ratio, Y=(Δγ/v2)Ru(Δγ/v2)Zr, is naively expected to be (1/N)Ru(1/N)Zr; however, genuine two- and three-particle correlations are expected to alter it. We estimate the contributions to Y from those correlations, utilizing both the isobar data and hijing simulations. After including those contributions, we arrive at a final background baseline for Y, which is consistent with the isobar data. We extract an upper limit for the CME fraction in the Δγ measurement of approximately 10% at a 95% confidence level on in isobar collisions at sNN=200GeV, with an expected 15% difference in their squared magnetic fields. © 2024 American Physical Society.
Keywords: dept.phy; peer-reviewed

Collision-energy dependence of deuteron cumulants and proton-deuteron correlations in Au+Au collisions at RHIC - STAR Collaboration (Physics Letters B, 2024)
We report the first measurements of cumulants, up to 4th order, of deuteron number distributions and proton-deuteron correlations in Au+Au collisions recorded by the STAR experiment in phase-I of Beam Energy Scan (BES) program at the Relativistic Heavy Ion Collider. Deuteron cumulants, their ratios, and proton-deuteron mixed cumulants are presented for different collision centralities covering a range of center-of-mass energy per nucleon pair sNN=7.7 to 200 GeV. It is found that the cumulant ratios at lower collision energies favor a canonical ensemble over a grand canonical ensemble in thermal models. An anti-correlation between proton and deuteron multiplicity is observed across all collision energies and centralities, consistent with the expectation from global baryon number conservation. The UrQMD model coupled with a phase-space coalescence mechanism qualitatively reproduces the collision-energy dependence of cumulant ratios and proton-deuteron correlations.
Keywords: Coalescence; Critical point; Deuteron production; Heavy-ion collisions; Higher moments; Thermal model; dept.phy; peer-reviewed

Optical spectroscopic analysis of cerebrospinal fluid of human brain tumor using visible resonance Raman spectroscopy - Zhou, Y.; Wu, B.; Zhang, L.; Zhu, K.; Zhang, S.; Wang, X.; Zhang, C.; Liu, C.-H.; Yu, X.; Alfano, R.R. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2024)
Currently, liquid biopsy method is mainly used for tumor detection based on genomic molecular alterations in vitro. Liquid biopsy is superior to traditional tissue biopsy techniques and its diagnosis time of disease and repeated diagnosis of liquid biopsy are new breakthroughs in clinical application. Liquid biopsy method can be used to detect most human disease based on genetic biomarkers from body fluids, among which, special biomarkers in blood and cerebrospinal fluid (CSF) samples are the main research objects, and have made good achievements in preliminary clinical applications. The application of optical spectroscopy in the field of liquid biopsy has aroused great interest among researchers and demonstrated the potential of its clinical application for oncology. The aim of this study is to reveal the optical spectroscopic characteristics of the main biochemical components of CSF of brain tumor using visible resonance Raman (VRR) spectroscopy ex vivo. Tumor-associated proteins, glucose, lactate and other metabolites released to CSF can be used as markers for liquid biopsy. We studied the VRR spectra of CSF samples from 7 types of brain tumor patients. The characteristic VRR modes that were found and may be used as a combination of multiple analyte biomarkers include amyloid-β and tau protein, excess neurotransmitters such as glutamic acid derived from the exchange with interstitial fluid (ISF), DNA, glucose, lactate, etc. for optical liquid biopsy analyses. Another interesting finding was that CSF of different types of tumors showed different images similar to the crystallization of water under the optical microscope. Considering our previous study, the current study on CSF provides another proof that the VRR system can provide a complete scan region of 200 - 4000cm-1 as a clinical tool for non-invasive diagnosis of brain disease. © 2024 SPIE.
Keywords: Optical liquid biopsy; amyloid-β (Aβ); cerebrospinal fluid (CSF) ex vivo; dept.phy; glioblastoma (GBM); human brain tumor; tau proteins; visible resonance Raman (VRR) spectroscopy

Star image centering with deep learning. II. HST/WFPC2 full field of view - Casetti-Dinescu, D.I.; Baena-Gallé, R.; Girard, T.M.; Cervantes-Rovira, A.; Todeasa, S. (Publications of the Astronomical Society of the Pacific, 2024)
We present an expanded and improved deep-learning (DL) methodology for determining centers of star images on Hubble Space Telescope/Wide-Field Planetary Camera 2 (WFPC2) exposures. Previously, we demonstrated that our DL model can eliminate the pixel-phase bias otherwise present in these undersampled images; however that analysis was limited to the central portion of each detector. In the current work we introduce the inclusion of global positions to account for the point-spread function (PSF) variation across the entire chip and instrumental magnitudes to account for nonlinear effects such as charge transfer efficiency. The DL model is trained using a unique series of WFPC2 observations of globular cluster 47 Tuc, data sets comprising over 600 dithered exposures taken in each of two filters—F555W and F814W. It is found that the PSF variations across each chip correspond to corrections of the order of ∼100 mpix, while magnitude effects are at a level of ∼10 mpix. Importantly, pixel-phase bias is eliminated with the DL model; whereas, with a classic centering algorithm, the amplitude of this bias can be up to ∼40 mpix. Our improved DL model yields star-image centers with uncertainties of 8-10 mpix across the full field of view of WFPC2. © 2024. The Astronomical Society of the Pacific. All rights reserved.
Keywords: dept.phy; peer-reviewed

Measurements of the Z0/γ⁎ cross section and transverse single spin asymmetry in 510 GeV p + p collisions - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2024)
The differential cross section for Z0 production, measured as a function of the boson's transverse momentum (pT), provides important constraints on the evolution of the transverse momentum dependent parton distribution functions (TMDs). The transverse single spin asymmetry (TSSA) of the Z0 is sensitive to one of the polarized TMDs, the Sivers function, which is predicted to have the opposite sign in p+p →W/Z+X from that which enters in semi-inclusive deep inelastic scattering. In this Letter, the STAR Collaboration reports the first measurement of the Z0/γ⁎ differential cross section as a function of its pT in p+p collisions at a center-of-mass energy of 510 GeV, together with the Z0/γ⁎ total cross section. We also report the measurement of Z0/γ⁎ TSSA in transversely polarized p+p collisions at 510 GeV. © 2024
Keywords: Cross section; Sivers function; Transverse momentum dependent parton distribution functions (TMDs); Transverse single spin asymmetry (TSSA; AN); Z0; dept.phy; peer-reviewed

Reaction plane correlated triangular flow in Au + Au collisions at √ s N N = 3 GeV - STAR Collaboration (Physical Review C, 2024)
We measure triangular flow relative to the reaction plane at 3 GeV center-of-mass energy in Au+Au collisions at the BNL Relativistic Heavy Ion Collider. A significant v3 signal for protons is observed, which increases for higher rapidity, higher transverse momentum, and more peripheral collisions. The triangular flow is essentially rapidity-odd with a slope at midrapidity, dv3/dy|(y=0), opposite in sign compared to the slope for directed flow. No significant v3 signal is observed for charged pions and kaons. Comparisons with models suggest that a mean field potential is required to describe these results, and that the triangular shape of the participant nucleons is the result of stopping and nuclear geometry.
Keywords: dept.phy; peer-reviewed

Human glioma tumor diagnosis using visible resonance Raman spectroscopy and deep learning - Llanos, N.E.; Zhou, Y.; Yu, X.; Zhang, S.; Zhu, K.; Liu, C.-H.; Wu, B.; Alfano, R.R. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2024)
Convolutional neural network (CNN) based deep learning is used to analyze spectral data collected by visible resonance Raman (VRR) spectroscopy to distinguish human glioma tumors from healthy brain tissues using binary classification and identify the cancer grades of the glioma tumors using multi-class classification. Classification was performed using both raw spectral data and baseline-subtracted data for comparison. The classification using both datasets yielded high accuracy, with the results obtained from baseline subtracted spectra slightly better than that obtained from raw spectra. The study showed VRR combined with deep learning provides a robust molecular diagnostic tool for accurately distinguishing glioma tumors from normal tissues and glioma tumor tissues at different cancer grades. Deep learning aided VRR technique may be used for in-situ intraoperative diagnosis of brain cancer. It may help a surgeon to identify cancer margins and even cancer grades during surgery. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.
Keywords: cancer grading; convolutional neural network; deep learning; dept.phy; glioma tumor; human brain tissues; machine learning; optical molecular pathology; peer-reviewed; visible resonance Raman (VRR)

Results on elastic cross sections in proton–proton collisions at s=510 GeV with the STAR detector at RHIC - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2024)
We report results on an elastic cross section measurement in proton–proton collisions at a center-of-mass energy s=510 GeV, obtained with the Roman Pot setup of the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The elastic differential cross section is measured in the four-momentum transfer squared range 0.23≤−t≤0.67 GeV2. This is the only measurement of the proton-proton elastic cross section in this t range for collision energies above the Intersecting Storage Rings (ISR) and below the Large Hadron Collider (LHC) colliders. We find that a constant slope B does not fit the data in the aforementioned t range, and we obtain a much better fit using a second-order polynomial for B(t). This is the first measurement below the LHC energies for which the non-constant behavior B(t) is observed. The t dependence of B is also determined using six subintervals of t in the STAR measured t range, and is in good agreement with the phenomenological models. The measured elastic differential cross section dσ/dt agrees well with the results obtained at s=540 GeV for proton–antiproton collisions by the UA4 experiment. We also determine that the integrated elastic cross section within the STAR t-range is σelfid=462.1±0.9(stat.)±1.1(syst.)±11.6(scale) μb. © 2024
Keywords: B-slope; Diffraction; Elastic scattering; Proton–proton collisions; dept.phy; peer-reviewed

Jet-hadron correlations with respect to the event plane in sNN =200 GeV Au+Au collisions in STAR - STAR Collaboration (Physical Review C, 2024)
Angular distributions of charged particles relative to jet axes are studied in sNN=200 GeV Au+Au collisions as a function of the jet orientation with respect to the event plane. This differential study tests the expected path-length dependence of energy loss experienced by a hard-scattered parton as it traverses the hot and dense medium formed in heavy-ion collisions. A second-order event plane is used in the analysis as an experimental estimate of the reaction plane formed by the collision impact parameter and the beam direction. Charged-particle jets with 15<pT,jet<20 and 20<pT,jet<40GeV/c were reconstructed with the anti-kT algorithm with radius parameter setting of R=0.4 in the 20-50% centrality bin to maximize the initial-state eccentricity of the interaction region. The reaction plane fit method is implemented to remove the flow-modulated background with better precision than prior methods. Yields and widths of jet-associated charged-hadron distributions are extracted in three angular bins between the jet axis and the event plane. The event-plane (EP) dependence is further quantified by ratios of the associated yields in different EP bins. No dependence on orientation of the jet axis with respect to the event plane is seen within the uncertainties in the kinematic regime studied. This finding is consistent with a similar experimental observation by ALICE in sNN = 2.76 TeV Pb-Pb collision data. © 2024 American Physical Society.
Keywords: dept.phy; peer-reviewed

Observation of the electromagnetic field effect via charge-dependent directed flow in heavy-ion collisions at the relativistic heavy ion collider - STAR Collaboration (Physical Review X, 2024)
The deconfined quark-gluon plasma (QGP) created in relativistic heavy-ion collisions enables the exploration of the fundamental properties of matter under extreme conditions. Noncentral collisions can produce strong magnetic fields on the order of 1018 G, which offers a probe into the electrical conductivity of the QGP. In particular, quarks and antiquarks carry opposite charges and receive contrary electromagnetic forces that alter their momenta. This phenomenon can be manifested in the collective motion of final-state particles, specifically in the rapidity-odd directed flow, denoted as v1(y). Here, we present the charge-dependent measurements of dv1/dy near midrapidities for π±, K±, and p(¯p) in Au+Au and isobar (9644Ru+9644Ru and 9640Zr+9640Zr) collisions at √sNN=200 GeV, and in Au+Au collisions at 27 GeV, recorded by the STAR detector at the Relativistic Heavy Ion Collider. The combined dependence of the v1 signal on collision system, particle species, and collision centrality can be qualitatively and semiquantitatively understood as several effects on constituent quarks. While the results in central events can be explained by the u and d quarks transported from initial-state nuclei, those in peripheral events reveal the impacts of the electromagnetic field on the QGP. Our data put valuable constraints on the electrical conductivity of the QGP in theoretical calculations.
Keywords: dept.phy; peer-reviewed

Observations with the Differential Speckle Survey Instrument. XI. First uear of observations from Apache Point Observatory - Davidson, James W.; Horch, Elliott P.; Majewski, Steven R.; Fagan, Evan; Shea, Melissa A.; Sutherland, Torrie; Wilson, Robert F.; Lesley, D. Xavier; Pellegrino, Richard A.; Leonard, Jonathan P.; Wilson, John C.; Chanover, Nancy J.; et al. (The Astronomical Journal, 2024)
The Differential Speckle Survey Instrument (DSSI) was relocated to the Astrophysical Research Consortium 3.5 m telescope at Apache Point Observatory (APO) in early 2022. Here we present results from the first year of observations along with an updated instrument description for DSSI at APO, including a detailed description of a new internal slit mask assembly used to measure the instrument plate scale from first principles. Astrometric precision for DSSI at APO during this time was measured to be 2.06 ± 0.11 mas, with a photometric precision of 0.14 ± 0.04 mag. Results of 40 resolved binary systems are reported, including two that were previously unknown to be binaries: HIP 7535 and HIP 9603. We also present updated orbital fits for two systems: HIP 93903 and HIP 100714. Finally, we report updated or confirmed dispositions for five Kepler Objects of Interest (KOIs) that were previously explored in Colton et al., using speckle imaging to discern common proper motions pairs from line of sight companions: KOI-270, KOI-959, KOI-1613, KOI-1962, and KOI-3214AB.
Keywords: dept.phy

Near-resonance in a System of Sub-Neptunes from TESS - Quinn, Samuel N.; Becker, Juliette C.; Rodriguez, Joseph E.; Hadden, Sam; Huang, Chelsea X.; Morton, Timothy D.; Adams, Fred C.; Armstrong, David; Eastman, Jason D.; Horner, Jonathan; Kane, Stephen R.; Lissauer, Jack J.; et al. (The Astronomical Journal, 2019)
We report the Transiting Exoplanet Survey Satellite detection of a multi-planet system orbiting the V = 10.9 K0 dwarf TOI-125. We find evidence for up to five planets, with varying confidence. Three transit signals with high signal-to-noise ratio correspond to sub-Neptune-sized planets (2.76, 2.79, and 2.94 R⊕), and we statistically validate the planetary nature of the two inner planets (Pb = 4.65 days, Pc = 9.15 days). With only two transits observed, we report the outer object (P.03 = 19.98 days) as a planet candidate with high signal-to-noise ratio. We also detect a candidate transiting super-Earth (1.4 R⊕) with an orbital period of only 12.7 hr and a candidate Neptune-sized planet (4.2 R⊕) with a period of 13.28 days, both at low signal-to-noise ratio. This system is amenable to mass determination via radial velocities and transit-timing variations, and provides an opportunity to study planets of similar size while controlling for age and environment. The ratio of orbital periods between TOI-125 b and c (Pc/Pb = 1.97) is slightly lower than an exact 2:1 commensurability and is atypical of multiple planet systems from Kepler, which show a preference for period ratios just wide of first-order period ratios. A dynamical analysis refines the allowed parameter space through stability arguments and suggests that despite the nearly commensurate periods, the system is unlikely to be in resonance.
Keywords: dept.phy; peer-reviewed

Speckle Interferometers - Horch, Elliott P. (The WSPC Handbook of Astronomical Instrumentation, 2021)
Keywords: dept.phy

The POKEMON Speckle Survey of nearby M Dwarfs. II. Observations of 1125 targets - Clark, Catherine A.; Belle, Gerard T. van; Horch, Elliott P.; Lund, Michael B.; Ciardi, David R.; Braun, Kaspar von; Winters, Jennifer G.; Everett, Mark E.; Hartman, Zachary D.; Llama, Joe (The Astronomical Journal, 2024)
Stellar multiplicity is correlated with many stellar properties, yet multiplicity measurements have proven difficult for the M dwarfs—the most common type of star in our galaxy—due to their faintness and the fact that a reasonably complete inventory of later M dwarfs did not exist until recently. We have therefore carried out the Pervasive Overview of “Kompanions” of Every M dwarf in Our Neighborhood (POKEMON) survey, which made use of the Differential Speckle Survey Instrument on the 4.3 m Lowell Discovery Telescope, along with the NN-EXPLORE Exoplanet Stellar Speckle Imager on the 3.5 m WIYN telescope. The POKEMON sample is volume limited from M0V through M9V out to 15 pc, with additional brighter targets at larger distances. In total, 1125 targets were observed. New discoveries were presented in the first paper in the series. In this second paper in the series, we present all detected companions, gauge our astrometric and photometric precision, and compare our filtered and filterless speckle observations. We find that the majority (58.9%) of the companions we detect in our speckle images are not resolved in Gaia, demonstrating the need for high-resolution imaging in addition to long-term astrometric monitoring. Additionally, we find that the majority (73.2%) of simulated stellar companions would be detectable by our speckle observations. Specifically within 100 au, we find that 70.3% of simulated companions are recovered. Finally, we discuss future directions of the POKEMON survey.
Keywords: dept.phy; peer-reviewed

Longitudinal and transverse spin transfer to Λ and ¯Λ hyperons in polarized p+p collisions at √s=200 GeV - STAR Collaboration (Physical Review D, 2024)
The longitudinal and transverse spin transfers to Λ (¯Λ) hyperons in polarized proton-proton collisions are expected to be sensitive to the helicity and transversity distributions, respectively, of (anti)strange quarks in the proton, and to the corresponding polarized fragmentation functions. We report improved measurements of the longitudinal spin transfer coefficient, DLL, and the transverse spin transfer coefficient, DTT, to Λ and ¯Λ in polarized proton-proton collisions at √s=200 GeV by the STAR experiment at RHIC. The dataset includes longitudinally polarized proton-proton collisions with an integrated luminosity of 52pb−1, and transversely polarized proton-proton collisions with a similar integrated luminosity. Both datasets have about twice the statistics of previous results and cover a kinematic range of |η Λ(¯Λ)|<1.2 and transverse momentum pT,Λ(¯Λ) up to 8 GeV/c. We also report the first measurements of the hyperon spin transfer coefficients DLL and DTT as a function of the fractional jet momentum z carried by the hyperon, which can provide more direct constraints on the polarized fragmentation functions.
Keywords: dept.phy; peer-reviewed

Studies of reduced graphene oxide (rGO)/CuS nanocomposite for supercapacitor applications - Singhal, R.; Thorne, D.; Chaudhary, M.; Kumar, A.; Bhardwaj, S.; Abazi, R.; Colon, A.; Gupta, R.K.; Scanley, J.; Broadbridge, C.C.; Singh, B.P.; LeMaire, P.K.; et al. (AIP Advances, 2023)
We have prepared CuS and CuS-rGO nanocomposites via the hydrothermal method. The physical properties of the synthesized materials were studied through x-ray diffraction and scanning electron microscopy. The supercapacitor characteristics were evaluated by cyclic voltammetric and galvanostatic charge–discharge studies. The cyclic voltammetric studies conform the pseudocapacitive nature of CuS and CuS-rGO electrodes. The specific capacitance of CuS was obtained as 207, 150, and 97 F/g at a current density of 0.5, 5, and 20 A/g, respectively. The rGO-CuS nanocomposite showed improved specific capacitance of 350, 251, and 149 F/g at current densities of 0.5, 5, and 20 A/g, respectively. © 2023 Author(s).
Keywords: dept.phy; peer-reviewed

Optimization of manganese dioxide-multiwall carbon nanotube composite electrodes for supercapacitor applications - Singhal, R.; Sadowski, T.; Chaudhary, M.; Tucci, R.V.; Scanley, J.; Patel, R.; Kumar Patel, P.; Gagnon, S.; Koni, A.; Singhal, K.; LeMaire, P.K.; Kumar Sharma, R.; et al. (Materials Science for Energy Technologies, 2024)
Manganese dioxide-multiwall carbon nanotube (MnO2-MWCNT) nanocomposites were synthesized via one-pot synthesis method with varying concentrations of 1 mg/ml, 4 mg/ml, and 10 mg/ml MWCNT. The synthesized nanocomposites were characterized using x-ray diffraction (XRD), transmission electron microscopy (TEM), and electrochemical measurements. The intent of studying different concentrations is, ultimately, to correlate the effect of the concentration of multiwall carbon nanotube on the electrochemical performance of the MnO2-MWCNT nanocomposites. Two primary phenomena were observed as CNT concentration increased. First, less crystalline MnO2 adsorption onto individual CNTs occurred. Subsequently, CNT agglomeration became the primary feature of the nanostructures of high CNT concentration. The electrochemical studies reveal that the specific capacitance of MnO2 increases from 124 F/g to 145 F/g by the addition of 1 mg/ml MWCNTs and decreases to 102 F/g for MnO2-10 mg/ml MWCNT nanocomposite. © 2023
Keywords: Carbon nanotube; MnO2; Specific capacitance; Supercapacitor; TEM; dept.phy; peer-reviewed

Hyperon polarization along the beam direction relative to the second and third harmonic event planes in isobar collisions at √sNN=200 gev - STAR Collaboration (Physical Review Letters, 2023)
The polarization of Λ and ¯Λ hyperons along the beam direction has been measured relative to the second and third harmonic event planes in isobar Ru+Ru and Zr+Zr collisions at √sNN=200 GeV. This is the first experimental evidence of the hyperon polarization by the triangular flow originating from the initial density fluctuations. The amplitudes of the sine modulation for the second and third harmonic results are comparable in magnitude, increase from central to peripheral collisions, and show a mild pT dependence. The azimuthal angle dependence of the polarization follows the vorticity pattern expected due to elliptic and triangular anisotropic flow, and qualitatively disagrees with most hydrodynamic model calculations based on thermal vorticity and shear induced contributions. The model results based on one of existing implementations of the shear contribution lead to a correct azimuthal angle dependence, but predict centrality and pT dependence that still disagree with experimental measurements. Thus, our results provide stringent constraints on the thermal vorticity and shear-induced contributions to hyperon polarization. Comparison to previous measurements at RHIC and the LHC for the second-order harmonic results shows little dependence on the collision system size and collision energy.
Keywords: dept.phy

Effect of reduce graphene oxide (Rgo) on electrochemical performance of Cus for supercapacitor applications - Singhal, Rahul; Thorne, David; Chaudhary, Manika; Bhardwaj, Shiva; Abazi, Rilind; Gupta, Ram K.; Scanley, Jules; Broadbridge, Christine C.; Singh, B. P.; LeMaire, Peter K.; Sharma, Rakesh K. (2023)
CuS and CuS-rGO nanocomposites were synthesized by the hydrothermal method. The synthesized CuS and rGO-CuS nanocomposite materials were physically characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM) and were evaluated electrochemically for supercapacitor applications. The specific capacitance of CuS was determined to be 207 F/g, 150 F/g, and 97 F/g at a current density of 0.5 A/g, 5 A/g, and 20 A/g, respectively. The rGO-CuS nanocomposite showed improved specific capacitance of 350 F/g, 251 F/g, and 149 F/g at a current density of 0.5 A/g, 5 A/g, and 20 A/g, respectively.
Keywords: CuS; SEM; Supercapacitors; dept.phy; rGO; specific capacitance

A New Stellar Companion to GJ 835 - Clark, Catherine A.; Horch, Elliott; Davidson, James W. (Research notes of the AAS, 2023)
Num Pages: 1
Keywords: dept.phy

Back Matter - Jain, F.; Broadbridge, C.; Gherasimova, M.; Hong, X. Tang (Selected topics in electronics and systems, 2023)
Num Pages: 1
Keywords: dept.phy

Front Matter - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, Haiming (Selected topics in electronics and systems, 2023)
Keywords: dept.phy

Nanotechnology in Electronics, Photonics, Biosensors and Energy Systems - Jain, F.; Braodbridge, C.; Gherasimova, M.; Hong, X. Tang (2023)
Pages: undefined Publication Title: Selected topics in electornics and systems
Keywords: dept.phy

Experimental Status of the Chiral Magnetic Effect - Finch, Evan (Epj Web of Conferences, 2023)
Num Pages: 1
Keywords: dept.phy

The 24 Aqr triple system: A closer look at its unique high-eccentricity hierarchical architecture - Abushattal, Ahmad A.; Al-Wardat, Mashhoor A.; Horch, Elliott P.; Georgakarakos, Nikolaos; Al-Ameryeen, Hatem A.; Abu-Alrob, Enas M.; Hussein, Abdallah M. (Advances in Space Research, 2023)
As its periastron passage occurred during the third quarter of 2020, system 24 Aqr is of particular significance. New visual solutions for the latest speckle interferometry observations collected by the Lowell Discovery Telescope (LTD) with its new QWSSI speckle camera are presented here. A variety of techniques were used to analyze the system, including ORBITX code for orbital solution, Al-Wardat’s method for analyzing multiple stellar systems, and Edwards’ method for analyzing visual and spectroscopic binaries. We derive precise masses and the complete set of its fundamental parameters for the three components, and we introduce a new orbital solution, and a new dynamical parallax, which is very close to the measured value given by Hipparcos 2007 and from that of Gaia DR2. In the next section, we discuss the possibility of a coplanar orbit. In conclusion, we demonstrate that we need a 65-m telescope to resolve the inner binary visually, although an array of telescopes could be used instead.
Keywords: Atmospheric Modeling-Synthetic Photometry; Hierarchical Triple System; Multiple stars; Observational Astronomy; Spectroscopic Binary Stars; Stars: binaries: close; Visual Binary Stars; dept.phy; peer-reviewed

Speckle Imaging with an Electron-multiplying CCD Camera at the WIYN Telescope - Horch, Elliott; Anderson, L.; DeSousa, M.; van Altena, W. F. (Bulletin of the American Astronomical Society, 2009)
Electron-multiplying CCD (EMCCD) cameras have extremely strong characteristics for speckle imaging including high quantum efficiency, extremely low effective read noise, and high bandwidth. We report on our first results for binary star astrometry and photometry using an Andor iXon EMCCD at the WIYN 3.5-m Telescope at Kitt Peak. We find that diffraction-limited image reconstructions can be achieved to approximately 15th magnitude and that the device appears to deliver reliable differential photometry of the components of binary star systems. Some implications for stellar astrophysics are discussed.
Conference Name: AAS/Division of Dynamical Astronomy Meeting #40 ADS Bibcode: 2009DDA....40.1604H
Keywords: ⛔ No DOI found

Revisiting Intensity Interferometry Using Picosecond Timescale Resolution - Camarata, Matthew A.; Horch, E. P. (Bulletin of the American Astronomical Society, 2011)
After the success of Hanbury Brown, Davis, and their collaborators in measuring all stellar diameters resolvable by the 166-m interferometer at Narrabri nearly four decades ago, research into optical intensity interferometry was largely discontinued. Signal-to-noise ratios and timing resolutions limited the technique to relatively bright stars over a narrow bandwidth. Modern photon-correlation electronics, however, may help to revive the technique, allowing for increased temporal resolution and longer baselines. In this paper, the PicoHarp 300 Time-Correlated Single Photon Counting System is characterized in order to demonstrate its ability to perform interferometric measurements. Time correlations of coherent and incoherent source apertures are measured and their autocorrelations compared with theory. The speed of light is also directly measured using the shift in temporal correlation between offset detectors. Finally, the possibility of two independent systems, linked between two large-aperture telescopes, is discussed with the goal of determining whether longer baselines can be achieved.
Conference Name: American Astronomical Society Meeting Abstracts #218 ADS Bibcode: 2011AAS...21840904C
Keywords: dept.phy; ⛔ No DOI found

Optimizing Speckle Data Reduction for Analysis of Faint Sources - Gaulin, Joseph; Horch, E.; Howell, S.; Ciardi, D. (2011)
Electron-multiplying CCD cameras are now being widely used in speckle imaging, and have been shown to deliver excellent photometric precision under good observing conditions. Successful image reconstructions have been made on binary stars fainter than 14th magnitude. However, improving the speckle signal-to-noise ratio and the fidelity of image reconstructions for faint sources would be extremely helpful in several areas of research where diffraction-limited images are required, including our own ongoing speckle observations of Kepler exoplanet candidate stars using the WIYN Telescope at Kitt Peak. In this paper, we investigate (1) robust cosmic ray rejection and (2) removal of low signal-to-noise frames as two ways to maximize data quality for faint source observations. Cosmic ray rejection is not normally a major concern in speckle imaging due to the brightness of the targets traditionally observed and the short frame times. Nonetheless, when imaging faint targets, more frames are needed to achieve a given signal-to-noise ratio, increasing the chance of cosmic ray events on the detector, and even a single cosmic ray hit in the frame sequence can significantly affect the source detection ability and photometry obtained in the observation. Similarly, faint sources often exhibit some frames with a well-defined image core while in other frames it is difficult to tell if the source is even present, primarily due to seeing variation during the observation. A new speckle reduction algorithm has been created that removes cosmic rays without throwing out frames and rejects frames with bad seeing, and its performance is investigated to determine to what extent this can improve source detection and photometric reliability in the final reconstructed image. Funding for this work was provided by the Kepler Science Center and by NSF Grant AST-0908125.
Conference Name: American Astronomical Society Meeting Abstracts #218 ADS Bibcode: 2011AAS...21840912G
Keywords: dept.phy

Minor Planet Observations with the Differential Speckle Survey Instrument - Bouvier, Jean-Claude; Horch, E. (2011)
The Differential Speckle Survey Instrument (DSSI) is a dual-channel speckle imaging system that takes speckle patterns in two colors simultaneously using two electron-multiplying CCD cameras. The system has been shown to deliver excellent photometry of binary stars under good observing conditions, which raises the question of whether results of similar quality can be obtained on extended objects such as minor planets, and if so, to what limiting magnitude. In this study, we present speckle image reconstructions of images of 2 Pallas, 216 Kleopatra, and 283 Emma made from data taken at the WIYN 3.5-m Telescope at Kitt Peak. We compare two different phase reconstruction algorithms: (1) an iterative technique, and (2) a relaxation technique. Since Pallas is a flattened disk, Kleopatra has a dumbbell shape, and Emma is a binary asteroid with known orbital parameters, these three targets represent three distinct image morphologies that allow for a robust comparison of the two phase reconstruction programs. Prospects for future work in this area with DSSI are discussed. This work is funded by NSF grant AST-0908125.
Conference Name: American Astronomical Society Meeting Abstracts #218 ADS Bibcode: 2011AAS...21840914B
Keywords: dept.phy

High-Resolution Speckle Imaging at Gemini-North: Exoplanets and Beyond - Howell, Steve B.; Horch, E.; Everett, M. E.; Ciardi, D. (2013)
Using our state-of-the-art 2-channel speckle imaging instrument, we have recently obtained diffraction-limited optical images at the 8-m Gemini-N telescope. The primary science goal was to search for faint (delta_mag = 4-6 mag) and nearby (<0.05") stellar companions around potential planet hosting stars as part of the small small exoplanet validation for the NASA Kepler and ESA CoRoT missions. As a demonstration of the instrument capabilities on Gemini, we achieved an angular resolution of ~20 mas which yielded the highest resolution ground-based optical image of the Pluto-Charon system ever obtained. Our instrument is likely to return to Gemini-N in mid-2013 for observations by general community programs
Conference Name: American Astronomical Society Meeting Abstracts #221 ADS Bibcode: 2013AAS...22114208H
Keywords: dept.phy

The Relation Between Radius, Mass, and Incident Flux of Exoplanets - Weiss, Lauren M.; Marcy, G. W.; Rowe, J.; Isaacson, H. T.; Howard, A.; Fortney, J. J.; Miller, N.; Demory, B.; Fischer, D.; Adams, E. A.; Dupree, A. K.; Howell, S. B.; et al. (2013)
We measure the mass of a modestly irradiated giant or "warm Jupiter," KOI-94d, in order to calculate its density. We wish to determine whether this planet, which is in a 22 day orbit and receives 107 times as much incident flux as the Earth, is bloated like "hot Jupiters" or as dense as our own Jupiter. In addition to its warm Jupiter, KOI-94 hosts at least 3 smaller planets, all of which were detected through transits by the Kepler Mission. This presents the opportunity to characterize a multi-planet system and to test dynamic stability and formation theory through observations of the masses and orbital elements of these planets. With 26 radial velocity measurements of KOI-94 from the W. M. Keck Observatory/HIRES, we measure the mass of the giant planet and upper limits to the masses of the three smaller planets. Transit timing variations will allow us to hone the mass measurements of the three smaller planets. Using the KOI-94 system and all other planets with published values for both mass and radius, we establish two fundamental planes for exoplanets that relate their mass, incident flux, and radius from a few Earth masses up to ten Jupiter masses: log(Rp/RE) = 0.007 + 0.53 log(M/ME) - 0.001 log(F/[erg/s/cm2]) for Mp < 150ME; log(Rp/RE) = 0.67 - 0.036 log(M/ME) + 0.06 log(F/[erg/s/cm2]) for Mp > 150ME. We also solve these planes in density-mass-flux space: log(ρp/[g/cm3]) = 0.69 - 0.57 log(M/ME) + 0.02 log(F/[erg/s/cm2]) for Mp < 150ME; log(ρp/[g/cm3]) = -1.23 + 1.10 log(M/ME) - 0.18 log(F/[erg/s/cm2]) for Mp > 150ME.
Conference Name: American Astronomical Society Meeting Abstracts #221 ADS Bibcode: 2013AAS...22140705W
Keywords: dept.phy

Exoplanet Characterization by Proxy for Kepler-61b: How a Nearby Star Bumped a Planet Out of the Habitable Zone - Ballard, Sarah; Charbonneau, D.; Fressin, F.; Torres, G.; Irwin, J.; Desert, J.; Ciardi, D.; Crepp, J. R.; Henze, C.; Bryson, S.; Howell, S. B.; Horch, E.; et al. (2013)
We present the validation and characterization of Kepler-61b: a 2.5 R_Earth planet orbiting near the inner edge of the habitable zone of a low-mass star. Our characterization of the host star Kepler-61 is based upon our identification of a spectroscopically similar star located 4.9 pc from Earth. This proxy star to Kepler-61 has a published direct interferometric radius and effective temperature measurement, which we apply in tandem with the Kepler photometry to characterize the planet Kepler-61b. The technique of identifying a nearby proxy star with directly measured properties allows for an independent check on stellar characterization via the traditional measurements with stellar spectra and evolutionary models. In this case, such a check had profound implications for the putative habitability of Kepler-61b. This work was performed in part under contract with the California Institute of Technology (Caltech) funded by NASA through the Sagan Fellowship Program
Conference Name: American Astronomical Society Meeting Abstracts #221 ADS Bibcode: 2013AAS...22140707B
Keywords: dept.phy

Validation of Twelve Small Kepler Transiting Planets in the Habitable Zone - Caldwell, Douglas A.; Torres, Guillermo; Kipping, David M.; Ballard, Sarah; Batalha, Natalie; Borucki, William J.; Bryson, Steve; Ciardi, David R.; Crepp, Justin R.; Everett, Mark; Fressin, Francois; Henze, Christopher; et al. (2015)
We report on the work to validate twelve candidate-transiting planets from Kepler with orbital periods ranging from 34 to 207 days initially identified in the pipeline search of three years of Kepler data from quarters 1 to 12. The candidates were selected based on pipeline Data Validation models indicating that they are small and potentially in the habitable zone (HZ) of their parent stars. As their expected Doppler signals are too small for a direct measure of their masses, we verify their planetary nature by validating them statistically using the BLENDER technique. BLENDER simulates large numbers of false-positive scenarios and compares the resulting light curves with the Kepler photometry, taking into account additional information from the analysis of Kepler flux centroids and new follow-up observations, including high-resolution optical and NIR spectroscopy, adaptive optics imaging, and speckle imaging. For eleven of the candidates we show that the likelihood they are true planets is far greater than that of a false positive, to a 99.73% confidence level. For the twelfth candidate, the planet confidence level is about 99.2%. Using improved stellar parameters for the host stars, we derive planetary radii ranging from 1.12 to 2.73 R⊕. All twelve objects are confirmed to be in the HZ, and nine are small enough to be rocky. Excluding three of the candidates that have been previously validated by others, our study doubles the number of known potentially rocky planets in the HZ.
Conference Name: American Astronomical Society Meeting Abstracts #225 ADS Bibcode: 2015AAS...22543802C
Keywords: dept.phy

Stellar Multiples Among the KOIs - Alyse Hirsch, Lea; Everett, Mark; Ciardi, David; Furlan, Elise; Horch, Elliott; Howell, Steve; Teske, Johanna; Marcy, Geoffrey W. (Bulletin of the American Astronomical Society, 2015)
We examine high-resolution follow-up imaging data for 84 KOIs with stellar companions detected within 2”. These stars were observed in the optical using speckle interferometry (Gemini/DSSI or WIYN/DSSI) and/or in the near-infrared with adaptive optics imaging (Keck/NIRC2, Palomar/PHARO, or Lick/IRCAL), and all have imaging results in at least two filters. Their companions are all unresolved in the Kepler images, and fall on the same pixel of the Kepler detector; thus the planet radii calculated for planet candidates in these systems are subject to upward revision due to contamination of the target star’s light by the stellar companion. We calculate updated planet radii for these 84 planet candidates, assuming the planet orbits the brighter of the two stars. We also use isochrone models and distance estimates to assess the likelihood that the companion is bound. This analysis complements galaxy models that determine the probability of a chance alignment of a background star for each system (Everett et al., in prep.). Together, these data allow us to isolate a sub-population of Kepler planets and planet candidates that reside in physical binary systems, for comparison to the wider Kepler planet population.
Conference Name: AAS/Division for Extreme Solar Systems Abstracts ADS Bibcode: 2015ESS.....311708A
Keywords: dept.phy; ⛔ No DOI found

Twinkle Twinkle Little Star - Speckle Imaging for Exoplanet Characterization - Howell, Steve B.; Scott, Nic; Horch, Elliott (2016)
The NASA K2 mission is finding many high-value exoplanets and world-wide follow-up is ensuing. The NASA TESS mission will soon be launched, requiring additional ground-based observations as well. As a part of the NASA-NSFNN-EXPLORE program to enable exoplanet research, our group is building two new speckle interferometry cameras for the Kitt Peak WIYN 3.5-m telescope and the Gemini-N 8-m telescope. Modeled after the successful DSSI visitor instrument that has been used at these telescopes for many years, speckle observations provide the highest resolution images available today from any ground- or space-based single telescope. They are the premier method through which small, rocky exoplanets can be validated. Available for public use in early 2017, WIYNSPKL and GEMSPKL will obtain simultaneous images in two filters with fast EMCCD readout, "speckle" and “wide-field” imaging modes, and user support for proposal writing, observing, and data reduction. We describe the new cameras, their design, and their benefits for exoplanet follow-up, characterization, and validation. Funding for this project comes from the NASA Exoplanet Exploration Program and NASA HQ.
Conference Name: American Astronomical Society Meeting Abstracts #228 ADS Bibcode: 2016AAS...22811702H

Speckle Interferometry at Lowell's Discovery Channel Telescope - van Belle, Gerard; Horch, Elliott (2017)
The high-spatial-resolution technique of speckle interferometry has been in use at Lowell Observatory's Discovery Channel Telescope since 2014 with the Dual-channel Stellar Speckle Imager (DSSI; Horch et al. 2009) as a visiting instrument. Using its standard bandpasses of 692 and 880nm, we have used highly efficient DSSI instrument to inspect over a thousand stellar systems over the course of 2014 (Horch et al. 2015). We have also demonstrated the usefulness of the DSSI@DCT system for resolved observations of high-altitude (>1,000 miles) man-made satellites in highly non-sidereal rate orbits.
Conference Name: American Astronomical Society Meeting Abstracts #229 ADS Bibcode: 2017AAS...22912609V

Instruments at the Lowell Observatory Discovery Channel Telescope (DCT) - Jacoby, George H.; Bida, Thomas A.; Fischer, Debra; Horch, Elliott; Kutyrev, Alexander; Mace, Gregory N.; Massey, Philip; Roe, Henry G.; Prato, Lisa A. (2017)
The Lowell Observatory Discovery Channel Telescope (DCT) has been in full science operation for 2 years (2015 and 2016). Five instruments have been commissioned during that period, and two additional instruments are planned for 2017. These include:+ Large Monolithic Imager (LMI) - a CCD imager (12.6 arcmin FoV)+ DeVeny - a general purpose optical spectrograph (2 arcmin slit length, 10 grating choices)+ NIHTS - a low resolution (R=160) YJHK spectrograph (1.3 arcmin slit)+ DSSI - a two-channel optical speckle imager (5 arcsec FoV)+ IGRINS - a high resolution (45,000) HK spectrograph, on loan from the University of Texas.In the upcoming year, instruments will be delivered from the University of Maryland (RIMAS - a YJHK imager/spectrograph) and from Yale University (EXPRES - a very high resolution stabilized optical echelle for PRV).Each of these instruments will be described, along with their primary science goals.
Conference Name: American Astronomical Society Meeting Abstracts #229 ADS Bibcode: 2017AAS...22915502J
Keywords: dept.phy

K-KIDS: Companioins to K Dwarfs Within 50 Parsecs - Nusdeo, Daniel Anthony; Winters, Jennifer; Paredes-Alvarez, Leonardo; Horch, Elliott; Jao, Wei-Chun; Henry, Todd J.; RECONS Institute (2017)
How many K dwarfs have “kids?” Stellar multiplicity fractions have been obtained for most spectral types, most recently by Raghavan et al. (2010) and Winters et al. (2015), finding rates of 50% for solar-type stars and 27% for M dwarfs, respectively. These findings will be crucial to improving our understanding of solar-system formation, but there has not yet been a statistically significant survey for K dwarfs to bridge the gap between G and M stars. To create a sample for a robust multiplicity survey, an initial set of 1048 K dwarfs was built using the Hipparcos and 2MASS catalogs, the companions of which are called “K-KIDS.” Future releases from Gaia will help us to expand K-KIDS into a volume-complete sample out to 50-pc, and we project that the final sample will contain over 3000 stars, making this the largest volume-complete multiplicity survey ever undertaken. For observational purposes, the targeted K dwarfs are confined equatorially to -30 < DEC < +30 to ensure all stars are observable from either hemisphere. The survey for K-KIDS is split into three companion-separation regimes: small (0.02 - 2.00 arcseconds), medium (2.00 - 10.00 arcseconds), and distant (10.00+ arcseconds). Small separation companions are resolved using the Differential Speckle Survey Instrument, with which we have observed 964 out of 1048 systems to date, already finding 135 new K-KIDS. Medium separation companions are observed via a series of three observations per star at the CTIO 0.9-m telescope, integrating for 3, 30, and 300 seconds to reveal companions of various brightnesses. Finally, a common proper-motion search is used to find companions at distant separations via blinking of digitialized images in the SuperCOSMOS archive, in addition to a large-scale literature survey for previously-discovered multiples. The small and distant surveys are nearing completion, and continued progress on the medium survey ensures that a statistically significant multiplicity rate for K dwarfs will soon be in achieved. Furthermore, a new RV survey is planned using the CHIRON high-resolution spectrograph to find companions that cannot be directly imaged. This effort has been supported by the NSF through grants AST-1412026 and AST-1517413.
Conference Name: American Astronomical Society Meeting Abstracts #229 ADS Bibcode: 2017AAS...22934412N
Keywords: dept.phy

Erratum: “The Kepler Follow-up Observation Program. I. A Catalog of Companions to Kepler Stars from High-resolution Imaging” (2017, AJ, 153, 71) - Furlan, E.; Ciardi, D. R.; Everett, M. E.; Saylors, M.; Teske, J. K.; Horch, E. P.; Howell, S. B.; Belle, G. T. van; Hirsch, L. A.; Gautier, T. N.; Adams, E. R.; Barrado, D.; et al. (The Astronomical Journal, 2017)
We have added references to Tables 3 and 8 (last column in each table). Below is a sample of both tables; the full tables are available in machine-readable form.
Keywords: dept.phy

Sixteen Years of Speckle Interferometry at the WIYN Observatory - Van Altena, Wm. F.; Horch, Elliott; Casetti-Dinescu, Dana I. (2017)
Speckle interferometry at Yale started in 1994 with a three-year program of observations at the Yale Southern Observatory at El Leoncito, Argentina. After this experience, we began a long-term program of speckle observations at the WIYN 3.5-m telescope at Kitt Peak National Observatory, first using a MAMA detector, then CCD and finally EMCCD technology. We describe the evolution of the program, its main results in terms of discovered components, orbital parameters and masses. While the Yale program ended in 2013, it provided the springboard for continued speckle efforts at WIYN, the Discovery Channel 4.3-m Telescope, and the Gemini 8.1-m Telescopes for binary star research, exoplanet science, and other projects. An important outcome of this research will be the incorporation of the soon to be released high-precision Gaia parallaxes into our observations.
Conference Name: AAS/Division of Dynamical Astronomy Meeting #48 ADS Bibcode: 2017DDA....4820303V

Fundamental Stellar Parameters and Multiplicity Rates of M-Dwarfs through Optical Speckle and NIR AO Imaging - Hahne, Frederick; Horch, Elliott; Ciardi, David R.; van Belle, Gerard; Clark, Catherine; Winters, Jennifer; Henry, Todd J. (Bulletin of the American Astronomical Society, 2019)
We present preliminary fundamental stellar parameters and multiplicity rates of M dwarf stars using a combination of speckle imaging and adaptive optics. Our survey mainly uses the Differential Speckle Survey Instrument (DSSI) at Lowell Observatory's Discovery Channel Telescope (DCT). DSSI observes speckle patterns simultaneously at two separate wavelengths and the data for this project are composed of observations which span from 2016 to 2018. More recently, the speckle data for some of the target stars that have been found to be binary have been supplemented with observations using Adaptive Optics (AO) at Palomar Observatory. The combination of speckle data in the visible and AO data in the near-infrared allows us to make robust determinations of the luminosities and effective temperatures of the components in each case. Using the known Mass-Luminosity Relation, we also estimate the component masses. A discussion of interesting systems will be given.
Conference Name: American Astronomical Society Meeting Abstracts #234 ADS Bibcode: 2019AAS...23430301H
Keywords: dept.phy; ⛔ No DOI found

Understanding the Multiplicity of TESS Exoplanet Host Candidates - Clark, Catherine; van Belle, Gerard; Horch, Elliott; von Braun, Kaspar (Bulletin of the American Astronomical Society, 2019)
While at first glance multi-star systems seem quite extreme, they are in fact the most common type of star system in our galaxy, throughout the stellar mass distribution. In particular, 40 to 50% of exoplanet host stars reside within multiple star systems. Given the degree to which initially undetected multiplicity has skewed Kepler results, high-resolution imaging of our nearby low-mass neighbors is necessary for both accurate characterization of transiting exoplanets, as well as a better understanding of stellar astrophysics. To address this frequent gap in our knowledge of exoplanet hosts, we will utilize speckle interferometry to directly image TESS exoplanet host candidates to complete our knowledge of individual star multiplicity. Our investigation will expand upon the speckle observations taken as a part of the POKEMON speckle survey of nearby M-dwarfs to better constrain the multiplicity of low-mass TESS exoplanet host candidates, and to constrain M-dwarf multiplicity by subtype across the entire M-dwarf sequence.
Conference Name: AAS/Division for Extreme Solar Systems Abstracts ADS Bibcode: 2019ESS.....431603C
Keywords: dept.phy; ⛔ No DOI found

Exoplanet Host Star Characterization with QWSSI - van Belle, Gerard; Clark, Catherine; Horch, Elliott; Trilling, David (Bulletin of the American Astronomical Society, 2019)
QWSSI, the Quad-camera Wavefront-Sensing Speckle Imager, is a next-generation speckle imager that is being developed for Lowell Observatory's 4.3-meter Discovery Channel Telescopes. The principle behind QWSSI is to extend the capabilities of the speckle camera currently resident at Lowell, the Differential Speckle Survey Instrument (DSSI), in two ways. First, while DSSI currently observes in two visible channels, QWSSI will simultaneously observe in six narrow-band channels: four in the visible (0.5-0.9um), and one each in J- and H-band (1.2 and 1.6um). Second, the visible light unused for speckle imaging is carefully preserved and feeds a wavefront sensor (WFS), which is also run simultaneously with the speckle imaging. Simulations by Löbb (2016) indicate WFS data will provide significant gains in exploring stellar multiplicity, with marked improvements in primary-secondary contrast ratios and inner working angle (Horch et al. 2018). QWSSI will also be mountable on one of the three 1-meter telescopes being installed on the NPOI Array for engineering tests and preliminary science observations. QWSSI will expand on the already considerable exoplanetary work of the speckle imagers DSSI, NESSI (@ WIYN), Alopeke (Gemini-N), and Zorro (Gemini-S), improving the discovery space for existing targets, as well opening up new regions of that discovery space with its NIR channels.
Conference Name: AAS/Division for Extreme Solar Systems Abstracts ADS Bibcode: 2019ESS.....433017V
Keywords: dept.phy; ⛔ No DOI found

Orbital Architectures of M Dwarf Systems: Building the Mass-Luminosity Relation in the I-Band - Vrijmoet, E. H.; Henry, T.; Tokovinin, A.; Horch, E.; Jao, W.; Winters, J.; Recons Team (Bulletin of the American Astronomical Society, 2021)
M dwarfs dominate the solar neighborhood population, accounting for three of every four stars. Their broad mass range — from 62% down to 8% that of the Sun — creates a rich dynamical laboratory that can be used to challenge stellar and binary formation models. Our Orbital Architectures project is constructing a large sample of orbits for nearby M dwarf systems to establish their distributions in period, mass ratio, semimajor axis, and eccentricity, with the goal of building crucial empirical evidence that will constrain models of multi-star formation and evolution. These orbits have been observed during the 20+ year RECONS astrometry program at the CTIO/SMARTS 0.9m, enhanced by a new speckle interferometry campaign at SOAR with HRCam+SAM to map the shorter-period orbits. Together, these observing efforts will map ~120 orbits of nearby M dwarfs with orbital periods spanning 0 to 30 years, providing the richest set of data ever collected for these ubiquitous stars. The speckle observations at SOAR resolve systems and provide magnitude differences between components, many of which already have orbits mapped by the RECONS astrometry program. The synergy of 0.9m and SOAR observations allows us to determine individual component masses, and to compare those masses to their fluxes in the Kron-Cousins I band. Here we present a new mass-luminosity relation for M dwarfs in the I band, populated with 40 masses focused on the low-mass end of the M dwarf sequence. This work has been supported by NSF grants AST-0507711, AST-0908402, AST-1109445, AST-141206, and AST-1715551.
Conference Name: American Astronomical Society Meeting Abstracts ADS Bibcode: 2021AAS...23753002V
Keywords: dept.phy; ⛔ No DOI found

Understanding stars close to the gap - Jao, Wei-Chun; Henry, Todd; Horch, Elliott; Vrijmoet, Eliot; Gemini Speckle Team (2021)
Theoretical models show the main sequence gap is a result of the mixing of 3He during the merger of envelope and core convection zones. Unlike stars the either side of the gap, stars in a narrow mass range will go through instability phases, where their dynamos could switch between the αΩ dynamo like the Sun and Ω2 dynamo like late M dwarfs. At the same time, they show radial pulsation and their fluxes fluctuate, which resemble the pulsations observed in evolved stars like red giants and asymptotic giant branch stars. Consequently, they are a unique type of dwarf like no other on the main sequence. In this work, we would like to know 1) will the unstable interior structures result in observable characteristics such as flaring and spots, and 2) what is the mass range for these stars observationally? Here we present our preliminary results: 1) stars in the gap have higher percentage rate of activities than their adjacent regions, and 2) high resolution speckle results yield promising close binaries to yield dynamical masses in the future.
Conference Name: The 20.5th Cambridge Workshop on Cool Stars, Stellar Systems, and the Sun (CS20.5) Pages: 26 ADS Bibcode: 2021csss.confE..26J
Keywords: Cool Stars On The Main Sequence; Gaia; Low Mass Stars; TESS; speckle

The Multiple-component Binary Hyad, vA 351 - Benedict, G. Fritz; Franz, Otto; Horch, Elliot; Torres, Guillermo; Prato, L. (2021)
We extend results first announced by Franz et al. (1998), that identified vA351 = H346 in the Hyades as a multiple star system containing a white dwarf. With Hubble Space Telescope Fine Guidance Sensor fringe tracking and scanning, and more recent speckle observations, all spanning 20.7 years, we establish a parallax, relative orbit, and mass fraction for two components, with a period, P = 2.70y and total mass 2.1M⊙. With ground-based radial velocities, we find that component B consists of BC, two M dwarf stars orbiting with a very short period (PBC = 0.749 days), having a mass ratio MC/MB=0.95. We confirm that the total mass of the system can only be reconciled with the distance and component photometry by including a fainter, higher mass component. The quadruple system consists of three M dwarfs (A,B,C) and one white dwarf (D); MA=0.57M⊙, MB=0.48M⊙, and MC=0.45M⊙. The WD mass, 0.53M⊙, comes from cooling models, an assumed Hyades age of 670My, and consistency with all previous and derived astrometric, photometric, and RV results. Velocities from Hα and He I emission lines confirm the BC period derived from absorption lines, with similar (HeI) and higher (Hα) velocity amplitudes. We ascribe the larger Hα amplitude to emission from a region each component shadows from the other, depending on the line of sight.
Conference Name: The 20.5th Cambridge Workshop on Cool Stars, Stellar Systems, and the Sun (CS20.5) Pages: 29 ADS Bibcode: 2021csss.confE..29B

Solar System Realms: Stars Taking Up Space Where Planets Could Be - Henry, Todd J.; Paredes, Leonardo A.; Vrijmoet, Eliot; Couperus, Andrew C.; James, Hodari-Sadiki; Jao, Wei-Chun; Kar, Aman; Lesley, DeAndre X.; Casetti-Dinescu, Dana I.; Horch, Elliott P.; Winters, Jennifer G. (2021)
The RECONS (REsearch Consortium On Nearby Stars, www.recons.org) team continues to explore the solar neighborhood by evaluating the nearest stars, both individually and as a population. Key points are becoming clear: we now know that 86% of all stars are K and M dwarfs, and we need to reach to 50 pc and 25 pc, respectively, to create samples of 5000 and 3000 primaries each. These two sizable samples allow us to understand the outcome of the star formation process across a factor of ten in mass as never before. Here we focus on one crucial area of research — stellar companions — with results of our surveys combining radial velocities, astrometry, high-resolution imaging, and trawls of catalogs and the literature. The surveys are carried out primarily at the CTIO/SMARTS 0.9m and 1.5m, the SOAR 4.1m, and both Gemini 8.1m telescopes. We reveal companions at separations from less than 1 AU to more than 1000 AU from the K and M dwarfs, with the key result that these stellar partners are found most often at separations similar to our Solar System. Thus, the star and planet formation processes work on the same spatial scales ... a fact that we must keep in mind as our solar neighborhood becomes enriched with planetary discoveries at distances comparable to where stellar companions are found. This work has been supported by NSF grants AST-0507711, AST-0908402, AST-1109445, AST-1411206, and AST-1715551, AST-1910130, and the SMARTS Consortium.
Conference Name: The 20.5th Cambridge Workshop on Cool Stars, Stellar Systems, and the Sun (CS20.5) Pages: 183 ADS Bibcode: 2021csss.confE.183H
Keywords: K dwarf stars (876) M dwarf stars (982) Multiple stars (1081) Stellar populations (1622); dept.phy

First Results from the POKEMON Speckle Survey of Nearby M-dwarfs - Clark, Catherine; van Belle, Gerard; Horch, Elliott; von Braun, Kaspar (2021)
We present the first results from the POKEMON (Pervasive Overview of Kompanions of Every M-dwarf in Our Neighborhood) survey, the largest speckle survey of stellar multiplicity ever produced for the objects that comprise over 70% of the stars in our galaxy: the M-dwarfs. We have conducted a volume-limited survey through M9 that inspected, at diffraction-limited resolution, every M-dwarf out to 15pc, with additional brighter targets to 25pc. POKEMON utilized the Differential Speckle Survey Instrument (DSSI) at the 4.3m Lowell Discovery Telescope, along with the NN-Explore Exoplanet Stellar Speckle Imager (NESSI) on the 3.5-m WIYN telescope. We report the discovery of 30+ new companions to these nearby M-dwarfs. Given the priority these targets have for exoplanet studies with TESS, and in the future JWST - and the degree to which initially undetected multiplicity has skewed Kepler results - a comprehensive survey of our nearby low-mass neighbors provides a homogeneous, complete catalog of fundamental utility. Prior knowledge of secondary objects - or robust non-detections, as captured by this survey - immediately clarify the nature of exoplanet transit detections from these current and upcoming missions.
Conference Name: The 20.5th Cambridge Workshop on Cool Stars, Stellar Systems, and the Sun (CS20.5) Pages: 236 ADS Bibcode: 2021csss.confE.236C
Keywords: Binary; M-dwarf; Speckle Imaging; dept.phy

Orbital Architectures of M Dwarf Systems: Building the P vs. e Diagram - Vrijmoet, Eliot Halley; Henry, Todd; Jao, Wei-Chun; Tokovinin, Andrei; Dieterich, Serge; Winters, Jennifer; Horch, Elliott (2021)
Comprising three out of every four stars, the M dwarfs form a unique sample that can host companions orbiting at Solar System scales and spanning a factor of 100,000 in mass. Targeting 120 M dwarf binaries within 25 parsecs, we are determining the period vs. eccentricity distribution for M dwarf stellar companions with orbital periods up to 6 years and semimajor axes up to 5 AU. This range is enabled by our combination of multiple observational methods: long-term astrometry from our RECONS program at the CTIO/SMARTS 0.9m is characterizing orbits on decades-long timescales, while our speckle interferometry survey at SOAR with HRCAM+SAM maps shorter orbits of systems identified from Gaia DR2, while also providing resolutions and masses for our long-period astrometric binaries. We will supplement these results with orbits from the literature, from both radial velocity and high-resolution imaging surveys, to ensure that our sample is rich with companions of all types orbiting within 5 AU. Initial results of this work so far suggest a notable paucity of M dwarf stellar companions with circular orbits greater than 5 years in period, showcasing the additional leverage provided by this combination of long-term astrometry and high-resolution imaging. Ultimately, when compared to the orbits of brown dwarf and planetary companions, such structures will be critical to understanding the formation mechanisms of these systems.
Conference Name: The 20.5th Cambridge Workshop on Cool Stars, Stellar Systems, and the Sun (CS20.5) Pages: 259 ADS Bibcode: 2021csss.confE.259V
Keywords: Binary stars; Low-mass stars; M dwarf stars; M dwarfs; Orbits; Stellar systems; and associations; clusters; dept.phy

Orbits of M Dwarf Binaries Big and Small: Revealing Their Sizes and Shapes Via a Multi-Pronged Observing Campaign - Vrijmoet, Eliot; Henry, Todd; Tokovinin, Andrei; Dieterich, Serge; Horch, Elliott; Jao, Wei-Chun; Winters, Jennifer; Team, Recons (Bulletin of the American Astronomical Society, 2022)
Presentation #205.10 in the session Binary Stellar System - iPoster Session.
Keywords: dept.phy; ⛔ No DOI found

The RKSTAR Concert — A RECONS Survey of the 5000 Nearest K Dwarfs - Henry, Todd; Casetti-Dinescu, Dana; Horch, Elliott; Hubbard-James, Hodari-Sadiki; Jao, Wei-Chun; Lesley, D. Xavier; Paredes, Leonardo; Shea, Melissa; Sutherland, Torrie; Team, Recons (Bulletin of the American Astronomical Society, 2022)
Presentation #305.15 in the session Stars, Cool Dwarfs, Brown Dwarfs — iPoster Session.
Keywords: dept.phy; ⛔ No DOI found

A search for wide companions of nearby K dwarf stars - Shea, Melissa; Hansen, Caitlin; Horch, Elliott; Casetti-Dinescu, Dana; Henry, Todd (Bulletin of the American Astronomical Society, 2023)
Results from the Gaia satellite provide a new way to obtain a comprehensive assessment of local stellar populations, including, for example, a determination of how frequently nearby stars have orbiting stellar companions. The RECONS K Star (RKSTAR) Survey is attempting to answer this question by examining the multiplicity of more than 5000 systems with K dwarf primaries within 50 parsecs of our Solar System. Three surveys (Wide Field, Speckle, and Radial Velocity) will detect stellar and planetary companions to K dwarfs at separations of 0.1 to 1000 AU. This poster will detail the Wide Field portion using Gaia data releases to assemble a list of stellar companion candidates at separations larger than 1 arcsecond from their primary stars, and has revealed nearly 500 companions. These are then cross-referenced with the Washington Double Star Catalogue, the most comprehensive catalog of known multiple stars available, to confirm about 400 known companions and reveal that about 80 are new discoveries. Preliminary findings of this cross-catalogue comparison will be presented. This assessment of the nearest K dwarfs will be helpful in future exoplanet surveys and will serve to inform theories on stellar and planetary formation. This work has been supported by NSF grant AST-1909560.
Conference Name: American Astronomical Society Meeting Abstracts ADS Bibcode: 2023AAS...24130203S
Keywords: dept.phy; ⛔ No DOI found

Mapping the Orbits of K Dwarf Multiples as a Part of RECONS - Lesley, D. Xavier; Horch, Elliott P.; Henry, Todd J.; Recons Team (Bulletin of the American Astronomical Society, 2023)
With observations from data sets available to the REsearch Consortium On Nearby Stars (RECONS, http://www.recons.org), we seek to define the orbits of several K dwarf multiple star systems. When compared to their more massive and less massive counterparts in G and M dwarfs, respectively, K dwarfs remain chiefly overlooked, merely due to the scarcity of data obtained on this stellar type. We address the sizes and shapes of the orbits, as established by their periods and eccentricities. The use of system separation, position angle, and magnitude, obtained from both our program measurements and the literature, will allow orbital construction, from which we ultimately derive the fundamental parameter, the mass. This work has been supported by NSF grants AST-1909560 and AST-1910130.
Conference Name: American Astronomical Society Meeting Abstracts ADS Bibcode: 2023AAS...24130243L
Keywords: dept.phy; ⛔ No DOI found

A New Home for an Old Hand: The Differential Speckle Survey Instrument Goes to Apache Point - Horch, Elliott P.; Davidson, Jr., James W.; Majewski, Steven R.; Sutherland, Torrie; Shea, Melissa; Henry, Todd J. (Bulletin of the American Astronomical Society, 2023)
The Differential Speckle Survey Instrument (DSSI) was built in 2008 and in its first 14 years saw substantial use in diffraction-limited imaging projects at the WIYN Telescope, Gemini-N and Gemini-S, and the Lowell Discovery Telescope. However, the completion and commissioning of the QWSSI speckle camera at Lowell Observatory has recently created the opportunity to move DSSI to the ARC 3.5-m Telescope at Apache Point Observatory (APO) in New Mexico. We report here on the commissioning of DSSI at APO and discuss some of the early science results, which represent the first diffraction-limited images in the visible range ever obtained at the ARC Telescope. Our initial observations appear to be comparable to DSSI's earlier use at WIYN in that we can obtain 0.05-arcsecond resolution at 692 nm for stars as faint as 12th magnitude in five minutes of observing or less, and we can detect companions with magnitude differences of 4 to 5 relative to their primary stars. In the near term, the instrument will be used (1) to supplement observations for the RECONS K Stars project to survey nearby K dwarfs for companions and (2) to obtain follow-up observations of binaries identified by Kepler, TESS, APOGEE, and other sources. It will also provide a testbed for simultaneous visible and infrared speckle imaging and speckle imaging through coherent fiber bundles. The potential advantages of these two innovations include better photometry in the diffraction-limited regime and higher-quality image reconstructions overall. We gratefully acknowledge support from National Science Foundation grants AST-1909560 and AST-1910130, as well as a SEED grant from the Research Corporation for Science Advancement, in the completion of this work.
Conference Name: American Astronomical Society Meeting Abstracts ADS Bibcode: 2023AAS...24130506H
Keywords: dept.phy; ⛔ No DOI found

Optical + Near-IR Speckle Imaging With The Differential Speckle Survey Instrument at Apache Point Observatory - Davidson, James; Horch, Elliott; Majewski, Steven (Bulletin of the American Astronomical Society, 2023)
The Differential Speckle Survey Instrument (DSSI) has been successfully operating at the ARC 3.5-m telescope at Apache Point Observatory in New Mexico for over a year, providing diffraction-limited imaging in the optical. We report on commissioning efforts for two new upgrades to DSSI: 1) an internal slit mask for astrometric calibration, and 2) a near-infrared channel configuration for the instrument operating at ~1.5µm. The near-infrared channel takes the place of one of the original optical channels, while the second channel of the instrument remains configured for optical observations. However, a two-position stage has been added to this optical channel, allowing for both of the original 692nm and 880nm filters. This represents the first near-infrared diffraction-limited imaging ever performed with DSSI, and the first for the ARC 3.5-m telescope, and a major step toward routine optical+NIR simultaneous speckle imaging for a range of science projects. The benefits of the internal slit mask and near-infrared channel configuration include improved astrometric precision, reduced time on-sky for calibrations, improved detection of lower luminosity companions including brown dwarfs, and a greater wavelength span for more robust source color determinations and H-R diagram positioning of system components.
Conference Name: American Astronomical Society Meeting Abstracts ADS Bibcode: 2023AAS...24220302D
Keywords: dept.phy; ⛔ No DOI found

Speckle Imaging at Gemini and the DCT - Horch, E. P.; Löbb, J.; Howell, S. B.; van Altena, W. F.; Henry, T. J.; van Belle, G. T. (Revista Mexicana de Astronomía y Astrofísica, 2018)
A program of speckle observations at Lowell Observatory's Discovery Channel Telescope (DCT) and the Gemini North and South Telescopes will be described. It has featured the Differential Speckle Survey Instrument (DSSI), built at Southern Connecticut State University in 2008. DSSI is a dual-port system that records speckle images in two colors simultaneously and produces diffraction limited images to V∼ 16.5 mag at Gemini and V∼ 14.5 mag at the DCT. Of the several science projects that are being pursued at these telescopes, three will be highlighted here. The first is high-resolution follow-up observations for Kepler and K2 exoplanet missions, the second is a study of metal-poor spectroscopic binaries in an attempt to resolve these systems and determine their visual orbits en route to making mass determinations, and the third is a systematic survey of nearby late-type dwarfs, where the multiplicity fraction will be directly measured and compared to that of G dwarfs. The current status of these projects is discussed and some representative results are given.
Conference Name: Revista Mexicana de Astronomia y Astrofisica Conference Series ADS Bibcode: 2018RMxAC..50...19H
Keywords: binaries: visual; dept.phy; techniques: high angular resolution; techniques: interferometric; techniques: photometric; ⛔ No DOI found

An Optical System for Multi-wavelength Intensity Interferometry with the Southern Connecticut Stellar Interferometer - Dever, Matthew; Horch, Elliott (Bulletin of the American Astronomical Society, 2019)
The Southern Connecticut Stellar Interferometer is an astronomical intensity interferometer consisting of two telescopes. Each is currently equipped with a single-photon avalanche diode (SPAD) detector, and an ultra-fast timing module correlates counts between both photon detectors. The interferometer has previously demonstrated intensity correlations using the 1-pixel SPADs and extremely narrow band pass filters but was limited in the amount of light that could be collected, and therefore the signal-to-noise ratio that could be achieved. SCSU's recent acquisition of an 8-pixel SPAD detector has allowed for a new possibility: a different wavelength of light could be directed towards each of the 8 pixels of the detector, thus conducting 8 independent intensity interferometry experiments at the same time, if this could be implemented at both telescopes. Using materials and resources available in the Astronomical Instrumentation Laboratory at Southern Connecticut State University, an optical system has been developed to work toward this goal but outfitting the first telescope in this way. The light from the telescope is collimated and directed toward a reflective diffraction grating. This is then re-imaged using a second lens and directed onto the pixels of the photon detector. These optical components have been placed inside an aluminum housing and can be mounted to the telescope for test observations. A status report will be given on the observations so far. If this can be replicated at the other telescope, the signal-to-noise ratio achievable with the instrument could be improved by a factor of 2.8.
Conference Name: American Astronomical Society Meeting Abstracts #234 ADS Bibcode: 2019AAS...23410303D
Keywords: ⛔ No DOI found

Elliptic flow of heavy-flavor decay electrons in Au+Au collisions at sNN = 27 and 54.4 GeV at RHIC - STAR Collaboration (Physics Letters B, 2023)
We report on new measurements of elliptic flow (v2) of electrons from heavy-flavor hadron decays at mid-rapidity (|y|<0.8) in Au+Au collisions at sNN = 27 and 54.4 GeV from the STAR experiment. Heavy-flavor decay electrons (eHF) in Au+Au collisions at sNN = 54.4 GeV exhibit a non-zero v2 in the transverse momentum (pT) region of pT< 2 GeV/c with the magnitude comparable to that at sNN=200 GeV. The measured eHF v2 at 54.4 GeV is also consistent with the expectation of their parent charm hadron v2 following number-of-constituent-quark scaling as other light and strange flavor hadrons at this energy. These suggest that charm quarks gain significant collectivity through the evolution of the QCD medium and may reach local thermal equilibrium in Au+Au collisions at sNN=54.4 GeV. The measured eHF v2 in Au+Au collisions at sNN= 27 GeV is consistent with zero within large uncertainties. The energy dependence of v2 for different flavor particles (π,ϕ,D0/eHF) shows an indication of quark mass hierarchy in reaching thermalization in high-energy nuclear collisions.
Keywords: Charm quark spatial diffusion coefficient; Elliptic flow; Heavy-flavor decay electron; dept.phy; peer-reviewed

Modeling the topographic lateral resolution of interferometers - Groot, P. J. de; Kramer, J. W.; Sutherland, T. P. (Modeling Aspects in Optical Metrology IX, 2023)
Performance characteristics for interferometers that measure surface topography include the ability to resolve closely spaced surface features, referred to as topographic spatial resolution. Within well-defined limits, scalar diffraction theory and classical Fourier optics provide a software model for prediction of the resolution and spatial frequency response for interference phase-based measurements of surface topography. Analytical solutions and adaptive sampling allow for rapid simulation of both the nominal linear transfer function and an estimate of intrinsic residual nonlinearities.
0 citations (Crossref) [2023-10-31]
Keywords: SCSU-student; dept.phy

Energy dependence of intermittency for charged hadrons in Au+Au collisions at RHIC - STAR Collaboration (Physics Letters B, 2023)
Density fluctuations near the QCD critical point can be probed via an intermittency analysis in relativistic heavy-ion collisions. We report the first measurement of intermittency in Au+Au collisions at sNN = 7.7-200 GeV measured by the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The scaled factorial moments of identified charged hadrons are analyzed at mid-rapidity and within the transverse momentum phase space. We observe a power-law behavior of scaled factorial moments in Au+Au collisions and a decrease in the extracted scaling exponent (ν) from peripheral to central collisions. The ν is consistent with a constant for different collisions energies in the mid-central (10-40%) collisions. Moreover, the ν in the 0-5% most central Au+Au collisions exhibits a non-monotonic energy dependence that reaches a minimum around sNN = 27 GeV. The physics implications on the QCD phase structure are discussed.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Event-by-event correlations between Λ ( ¯¯¯ Λ ) hyperon global polarization and handedness with charged hadron azimuthal separation in Au + Au collisions at √ s N N = 27 GeV from STAR - STAR Collaboration (Physical Review C, 2023)
Global polarizations (P) of Λ (¯¯¯Λ) hyperons have been observed in noncentral heavy-ion collisions. The strong magnetic field primarily created by the spectator protons in such collisions would split the Λ and ¯¯¯Λ global polarizations (ΔP=PΛ−P¯¯¯Λ<0). Additionally, quantum chromodynamics predicts topological charge fluctuations in vacuum, resulting in a chirality imbalance or parity violation in a local domain. This would give rise to an imbalance (Δn=NL−NR⟨NL+NR⟩≠0) between left- and right-handed Λ (¯¯¯Λ) as well as a charge separation along the magnetic field, referred to as the chiral magnetic effect (CME). This charge separation can be characterized by the parity-even azimuthal correlator (Δγ) and parity-odd azimuthal harmonic observable (Δa1). Measurements of ΔP, Δγ, and Δa1 have not led to definitive conclusions concerning the CME or the magnetic field, and Δn has not been measured previously. Correlations among these observables may reveal new insights. This paper reports measurements of correlation between Δn and Δa1, which is sensitive to chirality fluctuations, and correlation between ΔP and Δγ sensitive to magnetic field in Au+Au collisions at 27 GeV. For both measurements, no correlations have been observed beyond statistical fluctuations.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Search for the chiral magnetic wave using anisotropic flow of identified particles at energies available at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2023)
The chiral magnetic wave (CMW) has been theorized to propagate in the deconfined nuclear medium formed in high-energy heavy-ion collisions and to cause a difference in elliptic flow (v2) between negatively and positively charged hadrons. Experimental data consistent with the CMW have been reported by the STAR Collaboration at the Relativistic Heavy Ion Collider (RHIC), based on the charge asymmetry dependence of the pion v2 from Au+Au collisions at √sNN=27 to 200 GeV. In this comprehensive study, we present the STAR measurements of elliptic flow and triangular flow of charged pions, along with the v2 of charged kaons and protons, as a function of charge asymmetry in Au+Au collisions at √sNN=27, 39, 62.4, and 200 GeV. The slope parameters extracted from the linear dependence of the v2 difference on charge asymmetry for different particle species are reported and compared in different centrality intervals. In addition, the slopes of v2 for charged pions in small systems, i.e., p+Au and d+Au at √sNN=200 GeV, are also presented and compared with those in large systems, i.e., Au+Au at √sNN=200 GeV and U+U at 193 GeV. Our results provide new insights for the possible existence of the CMW and further constrain the background contributions in heavy-ion collisions at RHIC energies.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Global polarization of Λ and ¯¯¯ Λ hyperons in Au + Au collisions at √ s N N = 19.6 and 27 GeV - STAR Collaboration (Physical Review C, 2023)
In relativistic heavy-ion collisions, a global spin polarization, PH, of Λ and ¯¯¯Λ hyperons along the direction of the system angular momentum was discovered and measured across a broad range of collision energies and demonstrated a trend of increasing PH with decreasing √sNN. A splitting between Λ and ¯¯¯Λ polarization may be possible due to their different magnetic moments in a late-stage magnetic field sustained by the quark-gluon plasma which is formed in the collision. The results presented in this study find no significant splitting at the collision energies of √sNN=19.6 and 27 GeV in the BNL Relativistic Heavy Ion Collisions Beam Energy Scan Phase II using the STAR detector, with an upper limit of P¯¯¯Λ−PΛ<0.24% and P¯¯¯Λ−PΛ<0.35%, respectively, at a 95% confidence level. We derive an upper limit on the naive extraction of the late-stage magnetic field of B<9.4×1012 T and B<1.4×1013 T at √sNN=19.6 and 27 GeV, respectively, although more thorough derivations are needed. Differential measurements of PH were performed with respect to collision centrality, transverse momentum, and rapidity. With our current acceptance of |y|<1 and uncertainties, we observe no dependence on transverse momentum and rapidity in this analysis. These results challenge multiple existing model calculations following a variety of different assumptions which have each predicted a strong dependence on rapidity in this collision-energy range.
1 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (Nanostructures For Electronics, Photonics, Biosensors, And Emerging Systems Applications, 2022)
0 citations (Crossref) [2023-10-31] ISBN: 9789811270796
Keywords: dept.phy

Erratum to: Evidence of mass ordering of charm and bottom quark energy loss in Au+Au collisions at RHIC - STAR Collaboration (The European Physical Journal C, 2023)
2 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2023)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

The Effect of Pressure on Pellet Formation of Polycrystaline Superconductors Ybco Versus Ybcago. - Bidarian, Abe (1999)
Keywords: dept.phy; faculty_collection; sabbatical_report

Laboratory Research in Spectral Attenuation in Optical Fibers. - Dolan, James (1995)
Keywords: dept.phy; faculty_collection; sabbatical_report

[ Development of a Device That Would Continuously Monitor Build-up of Fluid in the Lungs ] - Wolf, Elizabeth (1990)
Keywords: dept.phy; faculty_collection; sabbatical_report

Interactions between two adjacent convection rolls in turbulent Rayleigh-Bénard convection - Brown, Eric; Ji, Dandan (Physical Review Fluids, 2023)
We seek to develop a low-dimensional model for the interactions between horizontally adjacent turbulent convection rolls. This was tested in Rayleigh-Bénard convection experiments with two adjacent cubic cells with a partial wall in between. Observed stable states include both counterrotating and corotating states for Rayleigh number 7.6×107< Ra <3.5×109 and Prandtl number 6.41. The stability of each of these states and their dynamics can be modeled low-dimensionally by stochastic ordinary differential equations of motion in terms of the orientation, amplitude, and mean temperature of each convection roll. The form of the interaction terms is predicted based on an effective turbulent diffusion of temperature between the adjacent rolls, which is projected onto the neighboring rolls with sinusoidal temperature profiles. With measurements of a constant coefficient for effective thermal turbulent diffusion, quantitative predictions are made for the nine forcing terms which affect stable fixed points of the corotating and counterrotating states for 5.5×108< Ra <3.5×109. Predictions are found to be accurate within a factor of 3 of experiments. This suggests that the same turbulent thermal diffusivity that describes macroscopically averaged heat transport also controls the interactions between neighboring convection rolls. The surprising stability of corotating states is due to the temperature difference between the neighboring rolls becoming large enough that the heat flux between the rolls stabilizes the temperature profile of aligned corotating states. This temperature difference can be driven with an asymmetry, for example, by heating the plates of the two cells to different mean temperatures. When such an asymmetry is introduced, it also shifts the orientations of the rolls of counterrotating states in opposite directions away from their preferred orientation, which is otherwise due to the geometry of the cell. As the temperature difference between the plates of the different cells is increased, the shift in orientation increases until the counterrotating states become unstable and only corotating states are stable. At very large temperature differences between cells, both the counterrotating and predicted corotating states become unstable; instead we observe a corotating state with much larger temperature difference between the rolls that cannot be explained by turbulent thermal diffusion. Spontaneous switching between corotating and counterrotating states is also observed, including in nominally symmetric systems. Switching to counterrotating states occurs mainly due to cessation (a significant weakening of a convection roll), which reduces damping on changes in orientation, allowing the orientation to change rapidly due to diffusive fluctuations. Switching to corotating states is mainly driven by smaller diffusive fluctuations in the orientation, amplitude, and mean temperature of rolls, which have a positive feedback that destabilizes the counterrotating state. © 2023 American Physical Society.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Measurements of the Elliptic and Triangular Azimuthal Anisotropies in Central He 3 +Au, d+Au and p+Au Collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2023)
The elliptic (v2) and triangular (v3) azimuthal anisotropy coefficients in central He3+Au, d+Au, and p+Au collisions at sNN=200 GeV are measured as a function of transverse momentum (pT) at midrapidity (|η|<0.9), via the azimuthal angular correlation between two particles both at |η|<0.9. While the v2(pT) values depend on the colliding systems, the v3(pT) values are system independent within the uncertainties, suggesting an influence on eccentricity from subnucleonic fluctuations in these small-sized systems. These results also provide stringent constraints for the hydrodynamic modeling of these systems. © 2023 American Physical Society.
1 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Measurement of electrons from open heavy-flavor hadron decays in Au+Au collisions at √sNN = 200 GeV with the STAR detector - STAR Collaboration (Journal of High Energy Physics, 2023)
We report a new measurement of the production of electrons from open heavy-flavor hadron decays (HFEs) at mid-rapidity (|y| < 0.7) in Au+Au collisions at sNN = 200 GeV. Invariant yields of HFEs are measured for the transverse momentum range of 3.5 < p T < 9 GeV/c in various configurations of the collision geometry. The HFE yields in head-on Au+Au collisions are suppressed by approximately a factor of 2 compared to that in p + p collisions scaled by the average number of binary collisions, indicating strong interactions between heavy quarks and the hot and dense medium created in heavy-ion collisions. Comparison of these results with models provides additional tests of theoretical calculations of heavy quark energy loss in the quark-gluon plasma. [Figure not available: see fulltext.] © 2023, The Author(s).
0 citations (Crossref) [2023-10-31]
Keywords: Heavy Ion Experiments; Heavy Quark Production; Heavy-Ion Collision; dept.phy; peer-reviewed

Nanotechnology for Electronics, Photonics, Biosensors, and Emerging Technologies - Jain, F.; Broadbridge, C. C.; Gherasimova, M.; Tang, H.; Connecticut Microelectronics and Optoelectronics Consortium New Haven, Conn) (World Scientific, 2021)
Keywords: Congresses; Congresses; Biosensors; Congresses; Nanoelectronics; Congresses; Nanophotonics; Congresses; Optoelectronics; Nanotechnology; dept.phy; faculty_collection

A Theoretical Study of Correlated Electron in the Frustrated Hubbard Model: Summary Report: Sabbatical Leave Spring 2010 - Enjalran, Matthew (2010)
This sabbatical leave was devoted to conducting theoretical, computational studies of correlated electrons with frustrated interactions and focus on the Hubbard model on the two-dimensional triangular and kagome lattices. Secondly, two Quantum Monte Carlo (QMC) methods were developed and applied to the models of the constrained path/phase QMC, and the determinant QMC methods.
Keywords: dept.phy; faculty_collection; sabbatical_report

Understanding Physics - Cummings, Karen (Wiley, 2004)
Keywords: Physics; dept.phy; faculty_collection

Understanding Physics: Students Solutions Manual - Cummings, Karen (Wiley, 2004)
Keywords: Physics; Physics; Problems; exercises; etc; dept.phy; faculty_collection

Measurements of dielectron production in Au + Au collisions at √ s N N = 27 , 39, and 62.4 GeV from the STAR experiment - STAR Collaboration (Physical Review C, 2023)
We report systematic measurements of dielectron (e+e−) invariant-mass Mee spectra at midrapidity in Au+Au collisions at √sNN = 27, 39, and 62.4 GeV taken with the STAR detector at the Relativistic Heavy Ion Collider. For all energies studied, a significant excess yield of dielectrons is observed in the low-mass region (0.40<Mee<0.75 MeV/c2) compared to hadronic cocktail simulations at freeze-out. Models that include an in-medium broadening of the ρ-meson spectral function consistently describe the observed excess. In addition, we report acceptance-corrected dielectron-excess spectra for Au+Au collisions at midrapidity (|yee|< 1) in the 0–80% centrality bin for each collision energy. The integrated excess yields for 0.4<Mee<0.75GeV/c2, normalized by the charged particle multiplicity at midrapidity, are compared with previously published measurements for Au+Au at √sNN1 = 19.6 and 200 GeV. Models that include an in-medium broadening of the ρ-meson spectral function consistently describe the observed excess. The normalized excess yields in the low-mass region show no significant collision energy dependence. The data, however, are consistent with model calculations that demonstrate a modest energy dependence.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Beam energy dependence of triton production and yield ratio ( N t × N p / N 2 d ) in Au + Au Collisions at RHI - STAR Collaboration (Physical Review Letters, 2023)
We report the triton (t) production in midrapidity (|y|<0.5) Au+Au collisions at √sNN=7.7–200 GeV measured by the STAR experiment from the first phase of the beam energy scan at the Relativistic Heavy Ion Collider. The nuclear compound yield ratio (Nt×Np/N2d), which is predicted to be sensitive to the fluctuation of local neutron density, is observed to decrease monotonically with increasing charged-particle multiplicity (dNch/dη) and follows a scaling behavior. The dNch/dη dependence of the yield ratio is compared to calculations from coalescence and thermal models. Enhancements in the yield ratios relative to the coalescence baseline are observed in the 0%-10% most central collisions at 19.6 and 27 GeV, with a significance of 2.3σ and 3.4σ, respectively, giving a combined significance of 4.1σ. The enhancements are not observed in peripheral collisions or model calculations without critical fluctuation, and decreases with a smaller pT acceptance. The physics implications of these results on the QCD phase structure and the production mechanism of light nuclei in heavy-ion collisions are discussed.
6 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Star-image Centering with Deep Learning: HST/WFPC2 Images - Casetti-Dinescu, Dana I.; Girard, Terrence M.; Baena-Gallé, Roberto; Martone, Max; Schwendemann, Kate (Publications of the Astronomical Society of the Pacific, 2023)
A deep learning (DL) algorithm is built and tested for its ability to determine centers of star images in HST/WFPC2 exposures, in filters F555W and F814W. These archival observations hold great potential for proper-motion studies, but the undersampling in the camera’s detectors presents challenges for conventional centering algorithms. Two exquisite data sets of over 600 exposures of the cluster NGC 104 in these filters are used as a testbed for training and evaluating the DL code. Results indicate a single-measurement standard error from 8.5 to 11 mpix, depending on the detector and filter. This compares favorably to the ∼20 mpix achieved with the customary “effective point spread function (PSF)” centering procedure for WFPC2 images. Importantly, the pixel-phase error is largely eliminated when using the DL method. The current tests are limited to the central portion of each detector; in future studies, the DL code will be modified to allow for the known variation of the PSF across the detectors.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

TFAW survey II: Six newly validated planets and 13 planet candidates from K2 - Del Ser, D.; Fors, O.; Del Alcázar, M.; Dyachenko, V.; Horch, E.P.; Tokovinin, A.; Ziegler, C.; Van Belle, G.T.; Clark, C.A.; Hartman, Z.D. (Monthly Notices of the Royal Astronomical Society, 2023)
Searching for Earth-sized planets in data from Kepler's extended mission (K2) is a niche that still remains to be fully exploited. The TFAW survey is an ongoing project that aims to re-analyse all light curves in K2 C1-C8 and C12-C18 campaigns with a wavelet-based detrending and denoising method, and the period search algorithm TLS to search for new transit candidates not detected in previous works. We have analysed a first subset of 24 candidate planetary systems around relatively faint host stars (10.9 < Kp < 15.4) to allow for follow-up speckle imaging observations. Using vespa and TRICERATOPS, we statistically validate six candidates orbiting four unique host stars by obtaining false-positive probabilities smaller than 1 per cent with both methods. We also present 13 vetted planet candidates that might benefit from other, more precise follow-up observations. All of these planets are sub-Neptune-sized with two validated planets and three candidates with sub-Earth sizes, and have orbital periods between 0.81 and 23.98 d. Some interesting systems include two ultra-short-period planets, three multiplanetary systems, three sub-Neptunes that appear to be within the small planet Radius Gap, and two validated and one candidate sub-Earths (EPIC 210706310.01, K2-411 b, and K2-413 b) orbiting metal-poor stars. © 2022 The Author(s) Published by Oxford University Press on behalf of Royal Astronomical Society.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy; instrumentation: high angular resolution; methods: data analysis; peer-reviewed; planets and satellites: general; planets and satellites: terrestrial planets; techniques: photometric

K * 0 production in Au + Au collisions at √ s N N = 7.7 , 11.5, 14.5, 19.6, 27, and 39 GeV from the RHIC beam energy scan - STAR Collaboration (Physical Review C, 2023)
We report the measurement of K*0 meson at midrapidity (|y|< 1.0) in Au+Au collisions at √sNN=7.7, 11.5, 14.5, 19.6, 27, and 39 GeV collected by the STAR experiment during the Relativistic Heavy Ion Collider (RHIC) beam energy scan program. The transverse momentum spectra, yield, and average transverse momentum of K*0 are presented as functions of collision centrality and beam energy. The K*0/K yield ratios are presented for different collision centrality intervals and beam energies. The K*0/K ratio in heavy-ion collisions are observed to be smaller than that in small-system collisions (e+e and p+p). The K*0/K ratio follows a similar centrality dependence to that observed in previous RHIC and Large Hadron Collider measurements. The data favor the scenario of the dominance of hadronic rescattering over regeneration for K*0 production in the hadronic phase of the medium.
1 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Measurement of Sequential Υ Suppression in Au + Au Collisions at √ s N N = 200 GeV with the STAR Experiment - STAR Collaboration (Physical Review Letters, 2023)
We report on measurements of sequential Υ suppression in Au+Au collisions at √sNN=200 GeV with the STAR detector at the Relativistic Heavy Ion Collider (RHIC) through both the dielectron and dimuon decay channels. In the 0%–60% centrality class, the nuclear modification factors (RAA), which quantify the level of yield suppression in heavy-ion collisions compared to p+p collisions, for Υ(1S) and Υ(2S) are 0.40±0.03(stat)±0.03(sys)±0.09(norm) and 0.26±0.08(stat)±0.02(sys)±0.06(norm), respectively, while the upper limit of the Υ(3S) RAA is 0.17 at a 95% confidence level. This provides experimental evidence that the Υ(3S) is significantly more suppressed than the Υ(1S) at RHIC. The level of suppression for Υ(1S) is comparable to that observed at the much higher collision energy at the Large Hadron Collider. These results point to the creation of a medium at RHIC whose temperature is sufficiently high to strongly suppress excited Υ states.
5 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Amyloid beta and tau protein metabolic changes detected by visible resonance Raman scattering microscopy in Alzheimer's disease mouse model - Shi, Lingyan; Zhou, Yan; Wu, Binlin; Zhu, Ke; Zhang, Shengjia; Boydston-White, Susie; Zhang, Lin; Pei, Zhe; Nguyen, Thien An; Liu, Cheng-Hui; Alfano, Robert R. (Optical Biopsy XXI: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2023)
Alzheimer’s disease (AD) pathogenesis is widely believed to be associated with the production and deposition of the β-amyloid peptide (Aβ) and neurofibrillary tangles (NFTs) which are composed of a highly-phosphorylated form of the microtubule-associated protein tau. Based on the above hypothesis, there are currently no sufficiently effective technologies and drugs for early detection and treatment of AD. Even the most promising new drug Lecanemab that is based on an anti-amyloid monoclonal antibody therapy, has only partially slowed down the cognitive performance of patients with mild impairment caused by Alzheimer's disease. The main symptoms of AD brain tissue lesions in patients are the deposition of β-amyloid peptide and the hyperphosphorylation of tau protein, which aggregates the microtubule structure of neurons. Therefore, Aβ deposition and hyperphosphorylation of Tau are important pathological biomarkers of Alzheimer's disease. Therefore, the main targets of research for AD prevention, detection and pharmaceuticals are still Aβ and Tau protein. The aim of this study was to detect the changes of Aβ and Tau proteins in the mouse brain tissue with AD and control samples using Visible Resonance Raman (VRR) spectroscopic technology. An attempt was made to develop criteria for the detection of early AD lesions by optical spectroscopy technology. The VRR spectra of AD, the control mouse brain tissues, and Aβ and Tau proteins were recorded and analyzed. The AD and the control mouse brain tissue samples were selected from the thalamus, frontal lobe cortex and hippocampus brain areas. VRR technology with high spatial resolution and the resonance-enhanced features of certain protein molecules is first used in this study to detect and characterize the changes of Aβ and Tau proteins in AD mouse brain model. The optical spectroscopy biomarkers of AD and Control brain tissue were identified in fingerprint and the high-wavenumber regions. The Raman spectra of the secondary structure of protein in amide (I-II-III-B-A) are detected and analyzed. The results indicate that the intensity of Amide I decreased at the 1666 cm^-1 corresponding to the β-sheet structure, and the intensity of the amide III bands (1220- 1320 cm^-1) increased in all AD brain tissues. It was also observed that the Raman peaks of 1448 and 980 cm^-1 related to the abundance of proline, serine, and threonine at tau phosphorylation sites were significantly enhanced in the frontal lobe cortex and hippocampus of AD brain tissues. The intensity ratio biomarker of high phosphorylation in the high wavenumber range from 2898 to 2932 cm-1 increased in all AD brain tissues. Changes of protein secondary conformation and abnormally phosphorylated tau or tauopathies were observed. In summary, VRR is a sensitive tool for characterizing protein structural changes and monitoring the tau phosphorylation. It may potentially be used for early detection of AD.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Evaluation of chemotherapeutic retinoic acid effects on malignant cells using fluorescence spectroscopy with selective excitation wavelengths and machine learning - Wu, Binlin; Tang, Guichen; Pu, Yang; Alfano, Robert (Optical Biopsy XXI: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2023)
Native fluorescence spectra of retinoic acid (RA)-treated and untreated human breast cancer cells were measured using selective wavelengths of 300 nm and 340 nm for excitation. The spectral data of the two types of cells were analyzed using machine learning algorithms for linear unmixing and classification which yielded high accuracy. The results show that the concentrations of the native fluorophores such as tryptophan, NADH and flavins in the human malignant breast cells change when they are treated with RA. The study shows the dual-wavelength fluorescence spectroscopy aided by machine learning has potential clinical applications in drug development and chemotherapeutic studies.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

A handheld visible resonance raman analyzer used in intraoperative detection of human glioma - Zhang, Liang; Zhou, Yan; Wu, Binlin; Zhang, Shengjia; Zhu, Ke; Liu, Cheng-Hui; Yu, Xinguang; Alfano, Robert R. (Cancers, 2023)
There is still a lack of reliable intraoperative tools for glioma diagnosis and to guide the maximal safe resection of glioma. We report continuing work on the optical biopsy method to detect glioma grades and assess glioma boundaries intraoperatively using the VRR-LRRTM Raman analyzer, which is based on the visible resonance Raman spectroscopy (VRR) technique. A total of 2220 VRR spectra were collected during surgeries from 63 unprocessed fresh glioma tissues using the VRR-LRRTM Raman analyzer. After the VRR spectral analysis, we found differences in the native molecules in the fingerprint region and in the high-wavenumber region, and differences between normal (control) and different grades of glioma tissues. A principal component analysis–support vector machine (PCA-SVM) machine learning method was used to distinguish glioma tissues from normal tissues and different glioma grades. The accuracy in identifying glioma from normal tissue was over 80%, compared with the gold standard of histopathology reports of glioma. The VRR-LRRTM Raman analyzer may be a new label-free, real-time optical molecular pathology tool aiding in the intraoperative detection of glioma and identification of tumor boundaries, thus helping to guide maximal safe glioma removal and adjacent healthy tissue preservation.
0 citations (Crossref) [2023-10-31] Number: 6
Keywords: dept.phy; glioma; human brain; intraoperative; optical biopsy; optical molecular pathology; peer-reviewed; portable optical-fiber-probe Raman analyzer; visible resonance Raman (VRR)

Higher-order cumulants and correlation functions of proton multiplicity distributions in √ s N N = 3 GeV Au + Au collisions at the RHIC STAR experiment - STAR Collaboration (Physical Review C, 2023)
We report a measurement of cumulants and correlation functions of event-by-event proton multiplicity distributions from fixed-target Au+Au collisions at √sNN = 3 GeV measured by the STAR experiment. Protons are identified within the rapidity (y) and transverse momentum (pT) region −0.9<y<0 and 0.4<pT<2.0 GeV/c in the center-of-mass frame. A systematic analysis of the proton cumulants and correlation functions up to sixth order as well as the corresponding ratios as a function of the collision centrality, pT, and y are presented. The effect of pileup and initial volume fluctuations on these observables and the respective corrections are discussed in detail. The results are compared to calculations from the hadronic transport UrQMD model as well as a hydrodynamic model. In the most central 5% collisions, the value of proton cumulant ratio C4/C2 is negative, drastically different from the values observed in Au+Au collisions at higher energies. Compared to model calculations including lattice QCD, a hadronic transport model, and a hydrodynamic model, the strong suppression in the ratio of C4/C2 at 3 GeV Au+Au collisions indicates an energy regime dominated by hadronic interactions.
3 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Azimuthal anisotropy measurement of (multi)strange hadrons in Au+Au collisions at sNN =54.4 GeV - STAR Collaboration (Physical Review C, 2023)
Azimuthal anisotropy of produced particles is one of the most important observables used to access the collective properties of the expanding medium created in relativistic heavy-ion collisions. In this paper, we present second (v2) and third (v3) order azimuthal anisotropies of KS0, φ, Λ, Ξ, and ω at midrapidity (|y|<1) in Au+Au collisions at sNN=54.4 GeV measured by the STAR detector. The v2 and v3 are measured as a function of transverse momentum and centrality. Their energy dependence is also studied. v3 is found to be more sensitive to the change in the center-of-mass energy than v2. Scaling by constituent quark number is found to hold for v2 within 10%. This observation could be evidence for the development of partonic collectivity in 54.4 GeV Au+Au collisions. Differences in v2 and v3 between baryons and antibaryons are presented, and ratios of v3/v23/2 are studied and motivated by hydrodynamical calculations. The ratio of v2 of φ mesons to that of antiprotons [v2(φ)/v2(p¯)] shows centrality dependence at low transverse momentum, presumably resulting from the larger effects from hadronic interactions on antiproton v2. © 2023 American Physical Society.
2 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Pion, kaon, and (anti)proton production in U+U collisions at sNN =193 GeV measured with the STAR detector - STAR Collaboration (Physical Review C, 2023)
We present the first measurements of transverse momentum spectra of π±, K±, p(p¯) at midrapidity (|y|<0.1) in U+U collisions at sNN= 193 GeV with the STAR detector at the Relativistic Heavy Ion Collider (RHIC). The centrality dependence of particle yields, average transverse momenta, particle ratios and kinetic freeze-out parameters are discussed. The results are compared with the published results from Au+Au collisions at sNN= 200 GeV in STAR. The results are also compared to those from A Multi-Phase Transport (ampt) model. © 2023 American Physical Society.
1 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Beam energy dependence of fifth- and sixth-order net-proton number fluctuations in Au+Au collisions at RHIC - STAR Collaboration (Physical Review Letters, 2023)
We report the beam energy and collision centrality dependence of fifth and sixth order cumulants (C5, C6) and factorial cumulants (κ5, κ6) of net-proton and proton number distributions, from center-of-mass energy (sNN) 3 GeV to 200 GeV Au+Au collisions at RHIC. Cumulant ratios of net-proton (taken as proxy for net-baryon) distributions generally follow the hierarchy expected from QCD thermodynamics, except for the case of collisions at 3 GeV. The measured values of C6/C2 for 0%-40% centrality collisions show progressively negative trend with decreasing energy, while it is positive for the lowest energy studied. These observed negative signs are consistent with QCD calculations (for baryon chemical potential, μB≤110 MeV) which contains the crossover transition range. In addition, for energies above 7.7 GeV, the measured proton κn, within uncertainties, does not support the two-component (Poisson+binomial) shape of proton number distributions that would be expected from a first-order phase transition. Taken in combination, the hyperorder proton number fluctuations suggest that the structure of QCD matter at high baryon density, μB∼750 MeV at sNN=3 GeV is starkly different from those at vanishing μB∼24 MeV at sNN=200 GeV and higher collision energies. © 2023 American Physical Society.
6 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Search for the chiral magnetic effect in Au+Au collisions at sNN=27 GeV with the STAR forward event plane detectors - STAR Collaboration (Physics Letters B, 2023)
A decisive experimental test of the Chiral Magnetic Effect (CME) is considered one of the major scientific goals at the Relativistic Heavy-Ion Collider (RHIC) towards understanding the nontrivial topological fluctuations of the Quantum Chromodynamics vacuum. In heavy-ion collisions, the CME is expected to result in a charge separation phenomenon across the reaction plane, whose strength could be strongly energy dependent. The previous CME searches have been focused on top RHIC energy collisions. In this Letter, we present a low energy search for the CME in Au+Au collisions at sNN=27 GeV. We measure elliptic flow scaled charge-dependent correlators relative to the event planes that are defined at both mid-rapidity |η|<1.0 and at forward rapidity 2.1<|η|<5.1. We compare the results based on the directed flow plane (Ψ1) at forward rapidity and the elliptic flow plane (Ψ2) at both central and forward rapidity. The CME scenario is expected to result in a larger correlation relative to Ψ1 than to Ψ2, while a flow driven background scenario would lead to a consistent result for both event planes. In 10-50% centrality, results using three different event planes are found to be consistent within experimental uncertainties, suggesting a flow driven background scenario dominating the measurement. We obtain an upper limit on the deviation from a flow driven background scenario at the 95% confidence level. This work opens up a possible road map towards future CME search with the high statistics data from the RHIC Beam Energy Scan Phase-II.
2 citations (Crossref) [2023-10-31]
Keywords: Beam energy scan; Chiral magnetic effect; Heavy-ion collisions; dept.phy; peer-reviewed

Beam energy dependence of the linear and mode-coupled flow harmonics in Au+Au collisions - STAR Collaboration (Physics Letters B, 2023)
The linear and mode-coupled contributions to higher-order anisotropic flow are presented for Au+Au collisions at sNN = 27, 39, 54.4, and 200 GeV and compared to similar measurements for Pb+Pb collisions at the Large Hadron Collider (LHC). The coefficients and the flow harmonics' correlations, which characterize the linear and mode-coupled response to the lower-order anisotropies, indicate a beam energy dependence consistent with an influence from the specific shear viscosity (η/s). In contrast, the dimensionless coefficients, mode-coupled response coefficients, and normalized symmetric cumulants are approximately beam-energy independent, consistent with a significant role from initial-state effects. These measurements could provide unique supplemental constraints to (i) distinguish between different initial-state models and (ii) delineate the temperature (T) and baryon chemical potential (μB) dependence of the specific shear viscosity ηs(T,μB).
1 citations (Crossref) [2023-10-31]
Keywords: Collectivity; Correlation; Shear viscosity; dept.phy; peer-reviewed

Stokes shift spectroscopy and machine learning for label-free human prostate cancer detection - Pu, Y.; Wu, B.; Mo, H.; Alfano, R.R. (Optics Letters, 2023)
The Stokes shift spectra (S3) of human cancerous and normal prostate tissues were collected label free at a selected wavelength interval of 40 nm to investigate the efficacy of the approach based on three key molecules—tryptophan, collagen, and reduced nicotinamide adenine dinucleotide (NADH)—as cancer biomarkers. S3 combines both fluorescence and absorption spectra in one scan. The S3 spectra were analyzed using machine learning (ML) algorithms, including principal component analysis (PCA), nonnegative matrix factorization (NMF), and support vector machines (SVMs). The components retrieved from the S3 spectra were considered principal biomarkers. The differences in the weights of the components between the two types of tissues were found to be significant. Sensitivity, specificity, and accuracy were calculated to evaluate the performance of SVM classification. This research demonstrates that S3 spectroscopy is effective for detecting the changes in the relative concentrations of the endogenous fluorophores in tissues due to the development of cancer label free. © 2023 Optica Publishing Group.
1 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Pattern of global spin alignment of ϕ and K*0 mesons in heavy-ion collisions - STAR Collaboration (Nature, 2023)
Notwithstanding decades of progress since Yukawa first developed a description of the force between nucleons in terms of meson exchange1, a full understanding of the strong interaction remains a considerable challenge in modern science. One remaining difficulty arises from the non-perturbative nature of the strong force, which leads to the phenomenon of quark confinement at distances on the order of the size of the proton. Here we show that, in relativistic heavy-ion collisions, in which quarks and gluons are set free over an extended volume, two species of produced vector (spin-1) mesons, namely ϕ and K*0, emerge with a surprising pattern of global spin alignment. In particular, the global spin alignment for ϕ is unexpectedly large, whereas that for K*0 is consistent with zero. The observed spin-alignment pattern and magnitude for ϕ cannot be explained by conventional mechanisms, whereas a model with a connection to strong force fields2–6, that is, an effective proxy description within the standard model and quantum chromodynamics, accommodates the current data. This connection, if fully established, will open a potential new avenue for studying the behaviour of strong force fields. © 2023, The Author(s), under exclusive licence to Springer Nature Limited.
18 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Collision-System and Beam-Energy Dependence of Anisotropic Flow Fluctuations - STAR Collaboration (Physical Review Letters, 2022)
Elliptic flow measurements from two-, four-, and six-particle correlations are used to investigate flow fluctuations in collisions of U+U at √sNN=193 GeV, Cu+Au at √sNN=200 GeV and Au+Au spanning the range √sNN=11.5–200 GeV. The measurements show a strong dependence of the flow fluctuations on collision centrality, a modest dependence on system size, and very little if any, dependence on particle species and beam energy. The results, when compared to similar LHC measurements, viscous hydrodynamic calculations, and trento model eccentricities, indicate that initial-state-driven fluctuations predominate the flow fluctuations generated in the collisions studied.
0 citations (Crossref) [2023-10-31] arXiv: http://arxiv.org/pdf/2201.10365
Keywords: dept.phy; peer-reviewed

Waste Citrus reticulata Assisted Preparation of Cobalt Oxide Nanoparticles for Supercapacitors - Srivastava, Rishabh; Bhardwaj, Shiva; Kumar, Anuj; Singhal, Rahul; Scanley, Jules; Broadbridge, Christine C.; Gupta, Ram K. (Nanomaterials, 2022)
The green, sustainable, and inexpensive creation of novel materials, primarily nanoparticles, with effective energy-storing properties, is key to addressing both the rising demand for energy storage and the mounting environmental concerns throughout the world. Here, an orange peel extract is used to make cobalt oxide nanoparticles from cobalt nitrate hexahydrate. The orange peel extract has Citrus reticulata, which is a key biological component that acts as a ligand and a reducing agent during the formation of nanoparticles. Additionally, the same nanoparticles were also obtained from various precursors for phase and electrochemical behavior comparisons. The prepared Co-nanoparticles were also sulfurized and phosphorized to enhance the electrochemical properties. The synthesized samples were characterized using scanning electron microscopic and X-ray diffraction techniques. The cobalt oxide nanoparticle showed a specific capacitance of 90 F/g at 1 A/g, whereas the cobalt sulfide and phosphide samples delivered an improved specific capacitance of 98 F/g and 185 F/g at 1 A/g. The phosphide-based nanoparticles offer more than 85% capacitance retention after 5000 cycles. This study offers a green strategy to prepare nanostructured materials for energy applications.
3 citations (Crossref) [2023-10-31] Number: 23
Keywords: Citrus reticulata; Co_3O_4 nanoparticles; characterization; charge storage; dept.phy; peer-reviewed; supercapacitors

Projections of two-particle correlations onto transverse rapidity in Au + Au collisions at √ s N N = 200 GeV at STAR - STAR Collaboration (Physical Review C, 2022)
Two-particle correlation measurements projected onto two-dimensional, transverse rapidity coordinates (yT1,yT2) provide an independent, orthogonal view of the multidimensional correlation distribution that is most often studied via angular projections. As such, these independent transverse projections allow access to manifestations of dynamical fluctuations in relativistic heavy-ion collisions that angular-correlation measurements may not be sensitive to. We report nonidentified charged-particle correlations for Au+Au minimum-bias collisions at √sNN=200 GeV taken by the STAR experiment at the Relativistic Heavy-Ion Collider (RHIC). Correlations are presented as two-dimensional functions of transverse rapidity for like-sign, unlike-sign, and all charged-particle pairs, as well as for particle pairs whose relative azimuthal angles lie on the near-side, the away-side, or at all relative azimuth. The correlations are constructed using charged particles with transverse momentum pT≥0.15 GeV/c, pseudorapidity from −1 to 1, and azimuthal angles from −π to π. The significant correlation structures that are observed evolve smoothly with collision centrality. The major correlation features include a saddle shape plus a broad peak with maximum near yT≈3, corresponding to pT≈1.5 GeV/c. The broad peak is observed in both like- and unlike-sign charge combinations and in near- and away-side relative azimuthal angles. The all-charge, all-azimuth correlation measurements are compared with the predictions of hijing and epos to provide theoretical context for these new measurements. The results indicate that the correlations for peripheral to mid-central collisions can be approximately described as a superposition of nucleon + nucleon collisions with minimal effects from the quantum chromodynamics medium. Strong medium effects are indicated in mid- to most-central collisions.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Azimuthal transverse single-spin asymmetries of inclusive jets and identified hadrons within jets from polarized p p collisions at √ s = 200 GeV - STAR Collaboration (Physical Review D, 2022)
The STAR Collaboration reports measurements of the transverse single-spin asymmetries, AN, for inclusive jets and identified “hadrons within jets” production at midrapidity from transversely polarized pp collisions at √s=200 GeV, based on data recorded in 2012 and 2015. The inclusive jet asymmetry measurements include AN for inclusive jets and AN for jets containing a charged pion carrying a momentum fraction z>0.3 of the jet momentum. The identified hadron within jet asymmetry measurements include the Collins effect for charged pions, kaons, and protons, and the Collins-like effect for charged pions. The measured asymmetries are determined for several distinct kinematic regions characterized by the jet transverse momentum pT and pseudorapidity η, as well as the hadron momentum fraction z and momentum transverse to the jet axis jT. These results probe higher momentum scales (Q2 up to ∼900 GeV2) than current, semi-inclusive deep-inelastic scattering measurements, and they provide new constraints on quark transversity in the proton and enable tests of evolution, universality, and factorization breaking in the transverse-momentum-dependent formalism.
3 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Pair invariant mass to isolate background in the search for the chiral magnetic effect in Au + Au collisions at √ s NN = 200 GeV - STAR Collaboration (Physical Review C, 2022)
Quark interactions with topological gluon configurations can induce local chirality imbalance and parity violation in quantum chromodynamics, which can lead to the chiral magnetic effect (CME)—an electric charge separation along the strong magnetic field in relativistic heavy-ion collisions. The CME-sensitive azimuthal correlator observable (Δγ) is contaminated by background arising, in part, from resonance decays coupled with elliptic anisotropy (v2). We report here differential measurements of the correlator as a function of the pair invariant mass (minv) in 20–50% centrality Au+Au collisions at √sNN=200 GeV by the STAR experiment at the BNL Relativistic Heavy Ion Collider. Strong resonance background contributions to Δγ are observed. At large minv where this background is significantly reduced, the Δγ value is found to be significantly smaller. An event-shape-engineering technique is deployed to determine the v2 background shape as a function of minv. We extract a v2-independent and minv-averaged signal Δγsig=(0.03±0.06±0.08)×10−4, or (2±4±5)% of the inclusive Δγ(minv>0.4 GeV/c2)=(1.58±0.02±0.02)×10−4, within pion pT=0.2–0.8 GeV/c and averaged over pseudorapidity ranges of −1<η<−0.05 and 0.05<η<1. This represents an upper limit of 0.23×10−4, or 15% of the inclusive result, at 95% confidence level for the minv-integrated CME contribution.
4 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Chapter 15 - Tryptophan fluorescence and machine learning to study the aggressiveness of prostate cancer cell lines: A pilot study - Xue, Jianpeng; Mo, Haiding; Tian, Yuke; Tang, Rui; Wu, Binlin (Biophotonics, Tryptophan and Disease, 2022)
We report on the use of label-free, native fluorescence (NFL) spectroscopy and machine learning (ML) algorithms to study the correlation of relative tryptophan levels with prostate cancer aggressiveness. Three extensively studied prostate cancer cell lines were used; PC3, an aggressive, androgen-resistant line, with a high tendency to metastasize in vivo, DU-145, a less aggressive cancer cell line, also androgen-resistant, and LNCaP, an androgen sensitive line, which has a low tendency to metastasize. Using an excitation of 300nm, differences in the NFL spectral profiles from these cell lines were found to correlate with changes in the relative concentrations of tryptophan and reduced nicotinamide adenine dinucleotide (NADH). The use of ML may present a powerful tool for the assessment of the likelihood of a cancer to metastasize. This technique could aid in the decision whether to use highly aggressive adjuvant chemotherapy or radiation therapy after surgical resection of a prostate cancer.
Keywords: Fluorescence spectroscopy; Machine learning; Metastatic cancer; Native fluorescence; Prostate cancer; Support vector machine; Tryptophan; dept.phy

The Solar Neighborhood L: Spectroscopic Discovery of K Dwarfs Younger Than 1 Gyr and New Binaries within 30 pc - Hubbard-James, Hodari-Sadiki; Lesley, D. Xavier; Henry, Todd J.; Paredes, Leonardo A.; Nisak, Azmain H. (The Astronomical Journal, 2022)
As part of a comprehensive effort to characterize the nearest stars, the CHIRON echelle spectrograph on the CTIO/SMARTS 1.5 m telescope is being used to acquire high-resolution (R = 80,000) spectra of K dwarfs within 50 pc. This paper provides spectral details about 35 K dwarfs from five benchmark sets with estimated ages spanning 20 Myr–5.7 Gyr. Four spectral age and activity indicators are tested, three of which aligned with the estimated ages of the benchmark groups—the Na i doublet (5889.95 and 5895.92 Å), the Hα line (6562.8 Å), and the Li i resonance line (6707.8 Å). The benchmark stars are then used to evaluate seven field K dwarfs exhibiting variable radial velocities for which initial CHIRON data did not show obvious companions. Two of these stars are estimated to be younger than 700 Myr, while one exhibits stellar activity unusual for older K-dwarf field stars and is possibly young. The four remaining stars turn out to be spectroscopic binaries, two of which are being reported here for the first time with orbital periods found using CHIRON data. Spectral analysis of the combined sample of 42 benchmark and variable radial velocity stars indicates temperatures ranging from 3900 to 5300 K and metallicities from −0.4 < [Fe/H] < +0.2. We also determine for main-sequence K dwarfs. Ultimately, this study will target several thousand of the nearest K dwarfs and provide results that will serve present and future studies of stellar astrophysics and exoplanet habitability.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Measurement of HΛ4 and HeΛ4 binding energy in Au+Au collisions at sNN = 3 GeV - STAR Collaboration (Physics Letters B, 2022)
Measurements of mass and Λ binding energy of Λ4H and Λ4He in Au+Au collisions at sNN=3 GeV are presented, with an aim to address the charge symmetry breaking (CSB) problem in hypernuclei systems with atomic number A = 4. The Λ binding energies are measured to be 2.22±0.06(stat.)±0.14(syst.) MeV and 2.38±0.13(stat.)±0.12(syst.) MeV for Λ4H and Λ4He, respectively. The measured Λ binding-energy difference is 0.16±0.14(stat.)±0.10(syst.) MeV for ground states. Combined with the γ-ray transition energies, the binding-energy difference for excited states is −0.16±0.14(stat.)±0.10(syst.) MeV, which is negative and comparable to the value of the ground states within uncertainties. These new measurements on the Λ binding-energy difference in A = 4 hypernuclei systems are consistent with the theoretical calculations that result in ΔBΛ4(1exc+)≈−ΔBΛ4(0g.s.+)<0 and present a new method for the study of CSB effect using relativistic heavy-ion collisions.
2 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Resolving the Core of R136 in the Optical - Kalari, V.M.; Horch, E.P.; Salinas, R.; Vink, J.S.; Andersen, M.; Bestenlehner, J.M.; Rubio, M. (Astrophysical Journal, 2022)
The sharpest optical images of the R136 cluster in the Large Magellanic Cloud are presented, allowing us for the first time to resolve members of the central core, including R136a1, the most-massive star known. These data were taken using the Gemini speckle imager Zorro in medium-band filters with effective wavelengths similar to BVRI achieving angular resolutions between 30-40 mas. All stars previously known in the literature, having V < 16 mag within the central 2″ × 2″, were recovered. Visual companions (≥40 mas; 2000 au) were detected for the WN5h stars R136 a1 and a3. Photometry of the visual companion of a1 suggests it is of mid-O spectral type. Based on new photometric luminosities using the resolved Zorro imaging, the masses of the individual WN5h stars are estimated to be between 150 and 200 M ⊙, lowering significantly the present-day masses of some of the most-massive stars known. These mass estimates are critical anchor points for establishing the stellar upper-mass function. © 2022. The Author(s). Published by the American Astronomical Society.
10 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Evidence for Nonlinear Gluon Effects in QCD and Their Mass Number Dependence at STAR - STAR Collaboration (Physical Review Letters, 2022)
The STAR Collaboration reports measurements of back-to-back azimuthal correlations of di-π0s produced at forward pseudorapidities (2.6<η<4.0) in p+p, p+Al, and p+Au collisions at a center-of-mass energy of 200 GeV. We observe a clear suppression of the correlated yields of back-to-back π0 pairs in p+Al and p+Au collisions compared to the p+p data. The observed suppression of back-to-back pairs as a function of transverse momentum suggests nonlinear gluon dynamics arising at high parton densities. The larger suppression found in p+Au relative to p+Al collisions exhibits a dependence of the saturation scale Q2s on the mass number A. A linear scaling of the suppression with A1/3 is observed with a slope of −0.09±0.01.
3 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2022)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Effect of multi-wall carbon nanotubes on electrochemical performances of MnO2 - Singhal, Rahul; Saini, Bhagirath; Kiehnle-Benitez, Monica; Sadowski, Thomas; Broadbridge, Christine; Scanley, Jules; LeMaire, Peter K.; Sharma, Rakesh K. (AIP Advances, 2022)
Composites of MnO2/multi-wall carbon nanotubes (MWCNTs) were prepared using different weight ratios of MWCNTs: KMnO4 (1:2, 1:5, 1:10, 1:15, 1:20, and 1:25) using a one-pot hydrothermal method. The synthesized materials were physically characterized by x-ray diffraction, transmission electron microscopy (TEM), field emission-scanning electron microscopy (FE-SEM), (Brunauer–Emmett–Teller) BET, and thermogravimetric analysis. TEM and SEM studies indicate that MnO2 is homogeneously entangled with MWCNTs. The electrochemical performance evaluation was performed in a 3-electrode system using MnO2/MWCNT electrodes coated onto a Ni mesh as the working electrode, a Pt foil as the counter electrode, and Ag/AgCl as the reference electrode. The specific capacitance was obtained from charge–discharge studies at varying current densities between 0.5 and 5 A/g. The specific capacitance of MWCNT-KMnO4 (1:10, 1:15, and 1:25) samples was obtained as 114, 164, and 100 F/g, respectively, at a current density of 1 A/g.
2 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Centrality and transverse-momentum dependence of higher-order flow harmonics of identified hadrons in Au+Au collisions at sNN =200 GeV - STAR Collaboration (Physical Review C, 2022)
We present high-precision measurements of elliptic, triangular, and quadrangular flow v2, v3, and v4, respectively, at midrapidity for identified hadrons π, p, K, φ, Ks, Λ as a function of centrality and transverse momentum in Au+Au collisions at the center-of-mass energy sNN=200 GeV. We observe similar vn trends between light and strange mesons which indicates that the heavier strange quarks flow as strongly as the lighter up and down quarks. The number-of-constituent-quark scaling for v2, v3, and v4 is found to hold within statistical uncertainty for 0-10%, 10-40%, and 40-80% collision centrality intervals. The results are compared to several viscous hydrodynamic calculations with varying initial conditions, and could serve as an additional constraint to the development of hydrodynamic models. © 2022 American Physical Society.
6 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

The POKEMON Speckle Survey of Nearby M Dwarfs. I. New Discoveries - Clark, C.A.; Van Belle, G.T.; Horch, E.P.; Von Braun, K.; Ciardi, D.R.; Winters, J.G.; Kiman, R. (Astronomical Journal, 2022)
M dwarfs are favorable targets for exoplanet detection with current instrumentation, but stellar companions can induce false positives and inhibit planet characterization. Knowledge of stellar companions is also critical to our understanding of how binary stars form and evolve. We have therefore conducted a survey of stellar companions around nearby M dwarfs, and here we present our new discoveries. Using the Differential Speckle Survey Instrument at the 4.3 m Lowell Discovery Telescope, and the similar NN-EXPLORE Exoplanet Stellar Speckle Imager at the 3.5 m WIYN telescope, we carried out a volume-limited survey of M-dwarf multiplicity to 15 parsecs, with a special emphasis on including the later M dwarfs that were overlooked in previous surveys. Additional brighter targets at larger distances were included for a total sample size of 1070 M dwarfs. Observations of these 1070 targets revealed 26 new companions; 22 of these systems were previously thought to be single. If all new discoveries are confirmed, then the number of known multiples in the sample will increase by 7.6%. Using our observed properties, as well as the parallaxes and 2MASS K magnitudes for these objects, we calculate the projected separation, and estimate the mass ratio and component spectral types, for these systems. We report the discovery of a new M-dwarf companion to the white dwarf Wolf 672 A, which hosts a known M-dwarf companion as well, making the system trinary. We also examine the possibility that the new companion to 2MASS J13092185-2330350 is a brown dwarf. Finally, we discuss initial insights from the POKEMON survey. © 2022. The Author(s). Published by the American Astronomical Society.
4 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Probing strangeness canonical ensemble with K−, ϕ(1020) and Ξ− production in Au+Au collisions at sNN=3 GeV - STAR Collaboration (Physics Letters B, 2022)
We report the first multi-differential measurements of strange hadrons of K−, ϕ and Ξ− yields as well as the ratios of ϕ/K− and ϕ/Ξ− in Au+Au collisions at sNN=3 GeV with the STAR experiment fixed target configuration at RHIC. The ϕ mesons and Ξ− hyperons are measured through hadronic decay channels, ϕ→K+K− and Ξ−→Λπ−. Collision centrality and rapidity dependence of the transverse momentum spectra for these strange hadrons are presented. The 4π yields and ratios are compared to thermal model and hadronic transport model predictions. At this collision energy, thermal model with grand canonical ensemble (GCE) under-predicts the ϕ/K− and ϕ/Ξ− ratios while the result of canonical ensemble (CE) calculations reproduce ϕ/K−, with the correlation length rc∼2.7 fm, and ϕ/Ξ−, rc∼4.2 fm, for the 0-10% central collisions. Hadronic transport models including high mass resonance decays could also describe the ratios. While thermal calculations with GCE work well for strangeness production in high energy collisions, the change to CE at 3 GeV implies a rather different medium property at high baryon density.
10 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Measurements of Proton High-Order Cumulants in √ s N N = 3 GeV Au + Au Collisions and Implications for the QCD Critical Point - STAR Collaboration (Physical Review Letters, 2022)
We report cumulants of the proton multiplicity distribution from dedicated fixed-target Au+Au collisions at √sNN=3.0 GeV, measured by the STAR experiment in the kinematic acceptance of rapidity (y) and transverse momentum (pT) within −0.5<y<0 and 0.4<pT<2.0 GeV/c. In the most central 0%–5% collisions, a proton cumulant ratio is measured to be C4/C2=−0.85±0.09 (stat)±0.82 (syst), which is 2σ below the Poisson baseline with respect to both the statistical and systematic uncertainties. The hadronic transport UrQMD model reproduces our C4/C2 in the measured acceptance. Compared to higher energy results and the transport model calculations, the suppression in C4/C2 is consistent with fluctuations driven by baryon number conservation and indicates an energy regime dominated by hadronic interactions. These data imply that the QCD critical region, if created in heavy-ion collisions, could only exist at energies higher than 3 GeV.
25 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Convolutional Neural Network for Binary Classification of Chromophobe Renal Cell Carcinoma and Oncocytoma - Cheng, Andrew; Icaza, Michael; Judd, Nicholas; Smith, Jason; Mukherjee, Sushmita; Jain, Manu; Wu, Binlin (Frontiers in Optics + Laser Science 2021 (2021), paper JTh5A.80, 2021)
Multiphoton microscopy images of chromophobe renal cell carcinoma and renal oncocytoma were classified using a convolutional neural network inspired by techniques in recent architectures and yielded over 70% accuracy.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Differential measurements of jet substructure and partonic energy loss in Au + Au collisions at √ s N N = 200 GeV - STAR Collaboration (Physical Review C, 2022)
The STAR collaboration presents jet substructure measurements related to both the momentum fraction and the opening angle within jets in p+p and Au+Au collisions at √sNN =200GeV. The substructure observables include SoftDrop groomed momentum fraction (zg), groomed jet radius (Rg), and subjet momentum fraction (zSJ) and opening angle (θSJ). The latter observable is introduced for the first time. Fully corrected subjet measurements are presented for p+p collisions and are compared to leading-order Monte Carlo models. The subjet θSJ distributions reflect the jets leading opening angle and are utilized as a proxy for the resolution scale of the medium in Au+Au collisions. We compare data from Au+Au collisions to those from p+p which are embedded in minimum-bias Au+Au events in order to include the effects of detector smearing and the heavy-ion collision underlying event. The subjet observables are shown to be more robust to the background than zg and Rg. We observe no significant modifications of the subjet observables within the two highest-energy, back-to-back jets, resulting in a distribution of opening angles and the splittings that are vacuumlike. We also report measurements of the differential dijet momentum imbalance (AJ) for jets of varying θSJ. We find no qualitative differences in energy loss signatures for varying angular scales in the range 0.1< θSJ<0.3, leading to the possible interpretation that energy loss in this population of high-momentum dijet pairs, is due to soft medium-induced gluon radiation from a single color charge as it traverses the medium.
5 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Visible resonance Raman spectroscopic ex vivo studies of mouse brain and organs - Pei, Zhe; Wu, Binlin; Shi, Lingyan; Zhang, Lin; Boydston-White, Susie; Liu, Cheng-Hui; Alfano, Robert R. (Optical Biopsy XX: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2022)
The unique advantage of visible resonance Raman (VRR) spectroscopy using 532 nm excitation wavelength for biological samples is the resonance enhancement of vibrational modes of chemical bonds from cells and tissues. The aim of this study is specifically to reveal the VRR characteristic spectra of different organs in mice, find the molecular alterations in the development of white matter and gray matter of mouse embryos at different ages and study the VRR spectral information of the mouse embryo head using VRR technology.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Probing the Gluonic Structure of the Deuteron with J/ψ Photoproduction in d+Au Ultraperipheral Collisions - STAR Collaboration (Physical Review Letters, 2022)
Understanding gluon density distributions and how they are modified in nuclei are among the most important goals in nuclear physics. In recent years, diffractive vector meson production measured in ultraperipheral collisions (UPCs) at heavy-ion colliders has provided a new tool for probing the gluon density. In this Letter, we report the first measurement of J/ψ photoproduction off the deuteron in UPCs at the center-of-mass energy sNN=200 GeV in d+Au collisions. The differential cross section as a function of momentum transfer -t is measured. In addition, data with a neutron tagged in the deuteron-going zero-degree calorimeter is investigated for the first time, which is found to be consistent with the expectation of incoherent diffractive scattering at low momentum transfer. Theoretical predictions based on the color glass condensate saturation model and the leading twist approximation nuclear shadowing model are compared with the data quantitatively. A better agreement with the saturation model has been observed. With the current measurement, the results are found to be directly sensitive to the gluon density distribution of the deuteron and the deuteron breakup process, which provides insights into the nuclear gluonic structure. © 2022 American Physical Society.
6 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

The Solar Neighborhood. XLIX. New Discoveries and Orbits of M-dwarf Multiples with Speckle Interferometry at SOAR - Vrijmoet, E.H.; Tokovinin, A.; Henry, T.J.; Winters, J.G.; Horch, E.; Jao, W.-C. (Astronomical Journal, 2022)
We present the first results of a multiyear program to map the orbits of M-dwarf multiples within 25 pc. The observations were conducted primarily during 2019-2020 using speckle interferometry at the Southern Astrophysical Research Telescope in Chile, using the High-Resolution Camera mounted on the adaptive optics module (HRCam+SAM). The sample of nearby M dwarfs is drawn from three sources: multiples from the RECONS long-term astrometric monitoring program at the SMARTS 0.9 m; known multiples, for which these new observations will enable or improve orbit fits; and candidate multiples flagged by their astrometric fits in Gaia Data Release 2 (DR2). We surveyed 333 of our 338 M dwarfs via 830 speckle observations, detecting companions for 63% of the stars. Most notably, this includes new companions for 76% of the subset selected from Gaia DR2. In all, we report the first direct detections of 97 new stellar companions to the observed M dwarfs. Here we present the properties of those detections, the limits of each nondetection, and five orbits with periods 0.67-29 yr already observed as part of this program. Companions detected have projected separations of 0.″024-2.″0 (0.25-66 au) from their primaries and have ΔI ≲ 5.0 mag. This multiyear campaign will ultimately map complete orbits for nearby M dwarfs with periods up to 3 yr, and provide key epochs to stretch orbital determinations for binaries to 30 yr. © 2022. The Author(s). Published by the American Astronomical Society.
8 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Corridor displays in glass cabinets - Matthews, L.D. (American Journal of Physics, 1976)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Total Reflection in a Moving Medium - Porter, W.S. (American Journal of Physics, 1972)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Improving the Small Hole Air Track and Table - Chonacky, N.J.; Snyder, J.W.; Matthews, L.D. (American Journal of Physics, 1971)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Microcomputer data management in an introductory physics laboratory - Chonacky, N. (American Journal of Physics, 1982)
A microcomputer/mini-floppy disk system is used by students in the laboratory portion of an introductory physics course for science majors. Its purposes are to store their experimental data, do data analyses, and exchange messages with the lab instructor. The system also provides computer-assisted instruction (CAI) simulations of certain lab experiments, and interfaces with measuring equipment in certain experiments. Each student has a personal diskette for data files and basic utility programs for an entire semester. The ease of disk data manipulation under program control is exploited in the following ways: (i) a wide variety of data reduction techniques are introduced that permit quantitative comparisons between experimental results and theoretical expectations; (ii) facile data reduction and analyses permit preliminary processing of experimental data during the course of the lab period, so that decisions can be made by students concerning the course of the remainder of the experiment; (iii) accumulated data from various experiments become a course database permitting subsequent analyses of old data adapted in several different logical ways (e.g., RC curcuit data first treated as energy storage, later as one of a number of exponential relationships); (iv) comprehensive course database formed by merging regarding the reliability of experiments. These considerations favor laboratory goals different from the demonstration and confirmation of given physical laws. Specifically they inculcate critical thinking and hypothetico-deductive reasoning. I discuss several very real problem areas that plagued this novice and compromised implementation. I compare these problems with the qualitative improvements in laboratory learning. © 1982, American Association of Physics Teachers. All rights reserved.
1 citations (Crossref) [2023-10-31]
Keywords: dept.phy

A video technique for the quantitative analysis of the Poisson spot and other diffraction patterns - Wein, G.R. (American Journal of Physics, 1999)
A new approach is presented for the observation and analysis of diffraction phenomena. Using the discussed procedures, direct comparison between measured light intensity and theoretical predictions is possible. A modified version of a Poisson spot experiment where the resulting diffraction pattern is recorded by a Sanyo vidicon camera is presented. A double slit experiment is also discussed, demonstrating the quantitative possibilities while addressing detector linearity. A video signal is connected directly to a computer and analyzed using public domain software. This is an excellent arrangement for demonstrations, student labs, or a more general diffraction experiment. © 1999 American Association of Physics Teachers.
10 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Improving 4H-SiC/SiO2 interface properties by depositing ultra-thin Si nitride layer prior to formation of SiO2 and annealing - Wang, X.W.; Bu, H.M.; Laube, B.L.; Caragianis-Broadbridge, C.; Ma, T.P. (Mater. Sci. Forum, 2002)
We report dramatic improvement in electrical properties of 4H-SiC/SiO2 interface by depositing an ultra-thin layer of silicon nitride on 4H-SiC prior to formation of silicon oxide and annealing. AC conductance measurements reveal interface-trap density equal to or below 1 × 1012/cm2- eV at energies near the conduction band edge. XPS spectra confirm the presence of N at the interface and suggest possible bonding between N and C. © (2002) Trans Tech Publications, Switzerland.
1 citations (Crossref) [2023-10-31] Journal Abbreviation: Mater. Sci. Forum
Keywords: 4H-SiC MOS; Angle-resolved; Angle-resolved x-ray; Annealing; Chemical bonds; Conductance measurement; Conduction band edge; Deposition; Gate dielectrics; Interface trap density; Interfaces (materials); MOS devices; Nitride layers; Nitrides; Photoelectron spectroscopy; Photoelectron spectroscopy (ARXPS); Si-CMOS; SiC/siO2-interfaces; Silica; Silicon carbide; Silicon nitride; Silicon oxides; Ultrathin films; Ultrathin layers; X ray photoelectron spectroscopy; dept.phy

Theory of paramagnetic scattering in highly frustrated magnets with long-range dipole-dipole interactions: The case of the Tb2Ti 2O7 pyrochlore antiferromagnet - Enjalran, M.; Gingras, M.J.P. (Physical Review B - Condensed Matter and Materials Physics, 2004)
Highly frustrated antiferromagnets composed of magnetic rare-earth moments are currently attracting much experimental and theoretical interest. Rare-earth ions generally have small exchange interactions and large magnetic moments. This makes it necessary to understand in detail the role of long-range magnetic dipole-dipole interactions in these systems, in particular, in the context of spin-spin correlations that develop in the paramagnetic phase, but are often unable to condense into a conventional long-range magnetic-ordered phase. This scenario is most dramatically emphasized in the frustrated pyrochlore antiferromagnet material Tb2Ti2O7, which does not order down to 50 mK despite an antiferromagnetic Curie-Weiss temperature TCW∼-20 K. In this paper we report results from mean-field theory calculations of the paramagnetic elastic neutron scattering in highly frustrated magnetic systems with long-range dipole-dipole interactions, focusing on the Tb2Ti2O7 system. Modeling Tb 2Ti2O7 as an antiferromagnetic 〈111〉 Ising pyrochlore, we find that the mean-field paramagnetic scattering is inconsistent with the experimentally observed results. Through simple symmetry arguments we demonstrate that the observed paramagnetic correlations in Tb 2Ti2O7 are precluded from being generated by any spin Hamiltonian that considers only Ising spins, but are qualitatively consistent with Heisenberg-like moments. Explicit calculations of the paramagnetic scattering pattern for both 〈111〉 Ising and Heisenberg models, which include finite single-ion anisotropy, support these claims. We offer suggestions for reconciling the need to restore spin isotropy with the Ising-like structure suggested by the single-ion properties of Tb3+.
74 citations (Crossref) [2023-10-31]
Keywords: anisotropy; antiferromagnets; article; atom; calculation; dept.phy; dipole; magnetism; mathematical analysis; molecular interaction; neutron scattering; oxygen; paramagnetic scattering; temperature; terbium; thallium; theory

Neutron scattering investigation of the spin ice state in Dy 2Ti2O7 - Fennell, T.; Petrenko, O.A.; Fåk, B.; Bramwell, S.T.; Enjalran, M.; Yavors'kii, T.; Gingras, M.J.P.; Melko, R.G.; Balakrishnan, G. (Physical Review B - Condensed Matter and Materials Physics, 2004)
Dy2Ti2O7 has been advanced as an ideal spin ice material. We present a neutron scattering investigation of a single-crystal sample of 162Dy2Ti2O 7. The scattering intensity has been mapped in zero applied field in the h,h,l and h,k,0 planes of reciprocal space at temperatures between 0.05 and 20 K. The measured diffuse scattering has been compared with that predicted by the dipolar spin ice model. The comparison is good, except at the Brillouin-zone boundaries where extra scattering appears in the experimental data. It is concluded that the dipolar spin ice model provides a successful basis for understanding Dy2Ti2O7, but that there are issues which remain to be clarified.
60 citations (Crossref) [2023-10-31]
Keywords: Monte Carlo method; article; crystal; dept.phy; dysprosium; neutron scattering; temperature; temperature dependence; titanium

Electrical properties of mismatched interface between InP and GaP - Li, G.-H.; Sun, Y.-N.; Yulius, A.; Broadbridge, C.C.; Woodall, J.M. (Rengong Jingti Xuebao/Journal of Synthetic Crystals, 2007)
The electrical properties of the mismatched interface between InP and GaP have been investigatedted. High resolution transmission electron microscopy (HRTEM) image shows the presence of strain relieving, 90° misfit dislocations at the InP/GaP interface. Electrochemical capacitance voltage (ECV) profiling indicates the presence of a high-density sheet of carriers at the interface. AFM image shows a pretty good InP epitaxial layer with surface roughness of 2.48 nm has been obtained. A model based on Fermi-level pinning in InP at the interface by misfit dislocations is proposed to account for the observed electrical behavior.
Keywords: Dislocations; InP/GaP interface; Lattice mismatch; dept.phy; ⛔ No DOI found

Normalized change - Marx, J.D.; Cummings, K. (American Journal of Physics, 2007)
Discussions of diagnostic tools that gauge students' conceptual understanding permeate the literature. Many instructors report their class' normalized gain to characterize the change in scores from pre-test to post-test. We describe a new procedure for characterizing these changes. This procedure, which we call the normalized change, c, involves the ratio of the gain to the maximum possible gain or the loss to the maximum possible loss. We also advocate reporting the average of a class' normalized changes and utilizing a particular statistical and graphical approach for comparing average c values. © 2007 American Association of Physics Teachers.
155 citations (Crossref) [2023-10-31]
Keywords: dept.phy

The stellar mass spectrum of the open cluster NGC 3293 - Slawson, R.W.; Ninkov, Z.; Horch, E.P. (Astrophysics and Space Science, 2007)
We have obtained and analyzed UBVRI CCD frames of the young, 4-10 Myr, open cluster NGC 3293 and the surrounding field in order to study its stellar content and determine the cluster's IMF. We found significantly fewer lower mass stars, M≤2.5M ⊙, than expected. This is particularly so if a single age for the cluster of 4.6 Myr is adopted as derived from fitting evolutionary models to the upper main sequence. Some intermediate-mass stars near the main sequence in the HR diagram imply an age for the cluster of about 10 Myr. When compared with the Scalo (The stellar initial mass function. ASP conference series, vol. 24, p. 201, 1998) IMF scaled to the cluster IMF in the intermediate mass range, 2.5≤M/M ⊙≤8.0 where there is good agreement, the high mass stars have a distinctly flatter IMF, indicating an over abundance of these stars, and there is a sharp turnover in the distribution at lower masses. The radial density distribution of cluster stars in the massive and intermediate mass regimes indicate that these stars are more concentrated to the cluster core whereas the lower-mass stars show little concentration. We suggest that this is evidence supporting the formation of massive stars through accretion and/or coagulation processes in denser cluster cores at the expense of the lower mass proto-stars. © 2007 Springer Science+Business Media B.V.
3 citations (Crossref) [2023-10-31]
Keywords: Mass function; Open clusters and associations: individual (NGC 3292); Stars: luminosity function; dept.phy

MOCVD growth and characterization of AlGaInN nanowires and nanostructures - Han, J.; Kim, K.; Su, J.; Gherasimova, M.; Nurmikko, A.V.; Chichibu, S.F.; Broadbridge, C. (Mater Res Soc Symp Proc, 2006)
Growth of GaN and AlGaInN nanowires using metalorganic chemical vapor deposition (MOCVD) is investigated. It is determined that surface kinetics play an important role in non-equilibrium synthesis process such as MOCVD, in contrast to near-equilibrium synthesis by hotwall furnace reactor. Examination of crystallographic properties of GaN nanowires reveals preferential growth directions which are perpendicular to the c-axis. Such a tendency is analyzed by both thermodynamic and kinetic arguments and attributed to the minimization of (side wall) surface energy. Spontaneous formation of Al(Ga)N/GaN coaxial nanowires with distinct emission at 370 nm is observed. It is identified that the interplay between surface kinetics and thermodynamics facilitates the catalytic growth of GaN core while a limited surface diffusion of Al adatoms leads to nonselective, vapor-solid growth of Al(Ga)N sheath. The knowledge of crystallographic alignment is applied to the formation of arrayed GaN nanowires in both vertical and horizontal fashions, resulting in potentially new paradigms for creating nanoscale devices. © 2006 Materials Research Society.
Journal Abbreviation: Mater Res Soc Symp Proc
Keywords: Crystal growth; Crystallography; Diffusion; Growth directions; Interfacial energy; Metallorganic chemical vapor deposition; Nanostructured materials; Nanostructures; Nanotechnology; Nanowires; Semiconductor quantum wires; dept.phy; non equilibrium synthesis

Spin hamiltonian, competing small energy scales, and incommensurate long-range order in the highly frustrated Gd3Ga5O12 garnet antiferromagnet - Yavors'kii, T.; Enjalran, M.; Gingras, M.J.P. (Physical Review Letters, 2006)
Despite the availability of a spin Hamiltonian for the Gd3Ga5O12 garnet (GGG) for over 25 years, there has so far been little theoretical insight regarding the many unusual low temperature properties of GGG. Here we investigate GGG in zero magnetic field using mean-field theory. We reproduce the spin liquid-like correlations and, most importantly, explain the positions of the sharp peaks seen in powder neutron diffraction experiments. We show that it is crucial to treat accurately the long-range nature of the magnetic dipolar interactions to allow for a determination of the small exchange energy scales involved in the selection of the experimental ordering wave vector. Our results show that the incommensurate order in GGG is classical in nature, intrinsic to the microscopic spin Hamiltonian and not caused by weak disorder. © 2006 The American Physical Society.
31 citations (Crossref) [2023-10-31]
Keywords: Antiferromagnetic materials; Electron energy levels; Garnet antiferromagnets; Hamiltonians; Magnetic dipolar interactions; Magnetic fields; Mean field theory; Neutron diffraction; Ordering wave vectors; Quantum theory; dept.phy

A photometric analysis of seventeen binary stars using speckle imaging - Davidson Jr., J.W.; Baptista, B.J.; Horch, E.P.; Franz, O.; Van Altena, W.F. (Astronomical Journal, 2009)
Magnitude differences obtained from speckle imaging are used in combination with other data in the literature to place the components of binary star systems on the H-R diagram. Isochrones are compared with the positions obtained, and a best-fit isochrone is determined for each system, yielding both masses of the components as well as an age range consistent with the system parameters. Seventeen systems are studied, 12 of which were observed with the 0.6 m Lowell-Tololo Telescope at Cerro Tololo Inter-American Observatory and six of which were observed with the WIYN 3.5 m Telescope (The WIYN Observatory is a joint facility of the University of Wisconsin-Madison, Indiana University, Yale University, and the National Optical Astronomy Observatories) at Kitt Peak. One system was observed from both sites. In comparing photometric masses to mass information from orbit determinations, we find that the photometric masses agree very well with the dynamical masses, and are generally more precise. For three systems, no dynamical masses exist at present, and therefore the photometrically determined values are the first mass estimates derived for these components. © 2009 The American Astronomical Society. All rights reserved.
11 citations (Crossref) [2023-10-31]
Keywords: Binaries: visual techniques; High angular resolution techniques; Interferometric techniques; Photometric; dept.phy; peer-reviewed

Binary and multiple stars - Horch, E. (Astrometry for astrophysics: Methods, Models, and Applications, 2009)
Introduction Two or more stars that are located close together in space interact gravitationally, causing deviations from linear motion as each star is accelerated. If we consider the case of two stars with a physical separation of many times the radius of either star (but still close enough to generate significant accelerations), it is sufficient to consider the stars as point masses. The equations of motion for such a system can be solved by assuming the inverse-square law of gravity and applying Newton's laws of motion. Newton's solution elegantly explained Kepler's laws of planetary motion, since one of the general solutions of motion is an ellipse with the more massive body (the Sun, in the case of the Solar System) at one focus. Kepler's third law of planetary motion (i.e. the harmonic law) as applied to the binary-star situation can be written where m1 and m2 are the masses of the two stars in solar units, a is the semi-major axis of the relative orbital ellipse in astronomical units, and P is the orbital period of the system in years. If you can only apply this formula, then it is not possible to obtain individual masses from the observables on the right-hand side, nor is the mass sum possible without an estimate of the parallax of the system (which allows for the conversion of a from an angular measure to astronomical units). Furthermore, while it is usually possible to measure the orbital period to high precision, the application of the formula is complicated by the fact that the semi-major axis, and implicitly the parallax, is raised to the third power. © Cambridge University Press 2013.
Journal Abbreviation: Astrometry for astrophysics: Methods, Models, and Applications
Keywords: dept.phy

An inquiry-based course in nano-photonics - Broadbridge, C.; Calvert, J.; Donnelly, J.; Garofano, J.; Massa, N. (Proc SPIE Int Soc Opt Eng, 2010)
We developed a curriculum to introduce nanotechnology and photonics concepts to community college students enrolled in a program designed to attract and retain students in technology associate degree programs. Working with the Center for Research on Interface Structures and Phenomena, an NSF Materials Research Science and Engineering Center, and the PHOTON projects, funded by the Advanced Technological Education program of NSF, we developed hands-on, inquiry-based activities to address the course goals: improve critical thinking, introduce science and technology concepts common to technology programs and provide opportunity to practice math skills in context. © 2010 SPIE.
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Proc SPIE Int Soc Opt Eng
Keywords: Advanced Technological Education; Associate degree; Community college; Critical thinking; Curricula; Education; Inquiry; Interface structures; Materials research; Math skills; Nano-photonics; Nanotechnology; Photonics; Science and Technology; Science and engineering; Students; Technology programs; dept.phy

Interface-induced polarization and inhibition of ferroelectricity in epitaxial SrTiO3/Si - Kolpak, A.M.; Walker, F.J.; Reiner, J.W.; Segal, Y.; Su, D.; Sawicki, M.S.; Broadbridge, C.C.; Zhang, Z.; Zhu, Y.; Ahn, C.H.; Ismail-Beigi, S. (Physical Review Letters, 2010)
We use SrTiO3/Si as a model system to elucidate the effect of the interface on ferroelectric behavior in epitaxial oxide films on silicon. Using both first-principles computations and synchrotron x-ray diffraction measurements, we show that structurally imposed boundary conditions at the interface stabilize a fixed (pinned) polarization in the film but inhibit ferroelectric switching. We demonstrate that the interface chemistry responsible for these phenomena is general to epitaxial silicon-oxide interfaces, impacting on the design of silicon-based functional oxide devices. © 2010 The American Physical Society.
64 citations (Crossref) [2023-10-31]
Keywords: Epitaxial films; Epitaxial silicon; Ferroelectric behavior; Ferroelectric films; Ferroelectric switching; Ferroelectricity; First-principles; Functional oxides; Induced polarization; Interface chemistry; Mathematical models; Model system; Oxide films; Polarization; Semiconducting silicon compounds; Silicon oxides; Silicon-based; SrTiO; Strontium alloys; Synchrotron x ray diffraction; X ray diffraction; dept.phy

Probing three-dimensional surface force fields with atomic resolution: Measurement strategies, limitations, and artifact reduction - Baykara, M.Z.; Dagdeviren, O.E.; Schwendemann, T.C.; Mönig, H.; Altman, E.I.; Schwarz, U.D. (Beilstein Journal of Nanotechnology, 2012)
Noncontact atomic force microscopy (NC-AFM) is being increasingly used to measure the interaction force between an atomically sharp probe tip and surfaces of interest, as a function of the three spatial dimensions, with picometer and piconewton accuracy. Since the results of such measurements may be affected by piezo nonlinearities, thermal and electronic drift, tip asymmetries, and elastic deformation of the tip apex, these effects need to be considered during image interpretation. In this paper, we analyze their impact on the acquired data, compare different methods to record atomic-resolution surface force fields, and determine the approaches that suffer the least from the associated artifacts. The related discussion underscores the idea that since force fields recorded by using NC-AFM always reflect the properties of both the sample and the probe tip, efforts to reduce unwanted effects of the tip on recorded data are indispensable for the extraction of detailed information about the atomicscale properties of the surface. © 2012 Baykara et al.
24 citations (Crossref) [2023-10-31]
Keywords: Artifact reduction; Atomic force microscopy; Atomic scale; Atomic-resolution; Elasticity; Electronic drift; Force fields; Force spectroscopy; Image interpretation; Interaction forces; Measurement strategies; NC-AFM; Noncontact atomic force microscopy; Probe tips; Spatial dimension; Surface forces; Three dimensional; Three-dimensional atomic force microscopy; Three-dimensional surface; Tip apex; Tip asymmetry; Tip elasticity; dept.phy

The effectiveness of multimedia and activity-based supplemental teaching resources in materials science education - Day, D.A.; Abbasi, E.; Liang, B.; Bhat, S.; DeMeo, S.; Garofano, J.; Grober, L.; Ferrari, N.; Broadbridge, C. (Materials Research Society Symposium Proceedings, 2012)
A comparative study investigating the integration of supplemental teaching resources in materials science education was developed for the purpose of determining the effectiveness of teaching strategies. Digital stories created by students, excerpts from the Nova Making Stuff documentaries, YouTube educational videos and student generated demo-kits were used as part of the investigation whereby two 9th grade science classes (n∼26) were evaluated. Each participant in the study received one period (40-min) of a traditional lesson on Materials Science including specific content, vocabulary, and a pre- and post- lesson assessment. Additionally, the students in each class participated in a 30-min supplemental component, e.g. video or activity-based demonstration using aforementioned kits or video compilation. Pre- and post- evaluations (e.g. open-ended and likert questions) were administered to all of the participants. As hypothesized, the students' feedback and performance on assessment activities reveal that the use of multimedia and activity-based resources may be equally effective teaching methods as traditional methods. © 2012 Materials Research Society.
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Mater Res Soc Symp Proc
Keywords: Activity-based; Assessment activities; Comparative studies; Educational videos; Effective teaching methods; Materials science; Multimedia systems; Students; Teaching resources; Teaching strategy; YouTube; dept.phy

Speckle camera imaging of the planet Pluto - Howell, S.B.; Horch, E.P.; Everett, M.E.; Ciardi, D.R. (Publications of the Astronomical Society of the Pacific, 2012)
We have obtained optical wavelength (692 nm and 880 nm) speckle imaging of the planet Pluto and its largest moon Charon. Using our DSSI speckle camera attached to the Gemini North 8 m telescope, we collected high resolution imaging with an angular resolution of ~20 mas, a value at the Gemini-N telescope diffraction limit. We have produced for this binary system the first speckle reconstructed images, from which we can measure not only the orbital separation and position angle for Charon, but also the diameters of the two bodies. Our measurements of these parameters agree, within the uncertainties, with the current best values for Pluto and Charon. The Gemini-N speckle observations of Pluto are presented to illustrate the capabilities of our instrument and the robust production of high accuracy, high spatial resolution reconstructed images. We hope our results will suggest additional applications of high resolution speckle imaging for other objects within our solar system and beyond. © 2012. The Astronomical Society of the Pacific. All rights reserved.
6 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Atom-specific forces and defect identification on surface-oxidized Cu(100) with combined 3D-AFM and STM measurements - Baykara, M.Z.; Todorović, M.; Mönig, H.; Schwendemann, T.C.; Ünverdi, O.; Rodrigo, L.; Altman, E.I.; Pérez, R.; Schwarz, U.D. (Physical Review B - Condensed Matter and Materials Physics, 2013)
The influence of defects on the local structural, electronic, and chemical properties of a surface oxide on Cu(100) were investigated using atomic resolution three-dimensional force mapping combined with tunneling current measurements and ab initio density functional theory. Results reveal that the maximum attractive force between tip and sample occurs above the oxygen atoms; theory indicates that the tip, in this case, terminates in a Cu atom. Meanwhile, simultaneously acquired tunneling current images emphasize the positions of Cu atoms, thereby, providing species-selective contrast in the two complementary data channels. One immediate outcome is that defects due to the displacement of surface copper are exposed in the current maps, even though force maps only reflect a well-ordered oxygen sublattice. The exact nature of the defects is confirmed by the simulations, which also reveal that the arrangement of the oxygen atoms is not disrupted by the copper displacement. In addition, the experimental force maps uncover a position-dependent modulation of the attractive forces between the surface oxygen and the copper-terminated tips, which is found to reflect the surface's inhomogeneous chemical and structural environment. As a consequence, the demonstrated method has the potential to directly probe how defects affect surface chemical interactions. © 2013 American Physical Society.
36 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Optimizing K-14 instruction to infuse 21st century skills - Day, D.; Guo, C.; Ferrari, N.; Edgecumbe, H.; Broadbridge, C. (Materials Research Society Symposium Proceedings, 2013)
This multi-phased study investigates the learning outcomes of courses taught in the K-14 classroom. Specifically, the methods and practices teachers use to develop and encourage 21st Century Skills including critical thinking skills and technological fluency in all subject areas, STEM and non-STEM related, are of great interest. Currently, these skills are in high demand in fields which develop advanced materials and are the backbone of the National Academies-developed Frameworks for K-12 Science Education. Phase I participants in this study included high school and college educators while Phase II of the study will involve K-14 students. In this study, educators were asked to rate their teaching self-efficacy in two primary areas: critical thinking skills and technological fluency. This included questions related to components in their current curriculum as well as methods of assessment [e.g., rubrics]. The instrument created to measure self-efficacy was based on a modified 'Science Teaching Efficacy Belief Instrument' (STEBI). All participants were from Connecticut. Results indicate that both STEM and non-STEM related subject areas offer an equally rich array of opportunities to effectively teach critical thinking and technological fluency at a variety of educational levels. The impact of Professional Development on teacher self-efficacy was of particular importance, especially in K-12 education. © 2013 Materials Research Society.
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Mater Res Soc Symp Proc
Keywords: Advanced materials; Critical thinking; Critical thinking skills; Curricula; Educational levels; Professional development; Science education; Science teaching; Students; Teaching; Technological fluency; dept.phy

Binaries and multiple stellar systems - Horch, E. (Planets, Stars and Stellar Systems Volume 4: Stellar Structure and Evolution, 2013)
Binary and multiple stellar systems have importance in three main areas of astronomy and astrophysics. First, because of the relatively simple gravitational interaction at work in the case of binary stars, these systems provide a basic check on stellar structure and evolution theory since the masses may be determined through observation. When these masses can be linked to other properties of the two stars, such as luminosity, color, and radius, they can provide very stringent constraints on stellar models. Second, the statistics of binary and multiple star systems provide clues to star formation mechanisms and environmental effects in the galactic gravitational potential and in clusters. Although a number of good results have been obtained in nearby star clusters and associations, knowledge of the field population has been somewhat limited until recently by a lack of large, complete samples of binaries. However, there appears to be a great deal of promise in this area for the coming decade in part due to astrometric satellites such as Hipparcos and Gaia. Third, the binary scenario is invoked to explain several important types of astrophysical phenomena such as Type Ia supernovae, cataclysmic variables, and stellar x-ray sources. Since the first of these mentioned is a standard candle for the extragalactic distance scale, it may even be said binary stars play a minor role in field of cosmology. However, in this chapter, the focus will mainly be on normal stars in binary and multiple-stellar systems. The basic physics of binaries will be reviewed, and the observational methods in use today will be discussed together with their limitations and prospects for the future. Finally, an overview of the current science in the three main areas mentioned where binaries have a significant impact will be given. © Springer Science+Business Media Dordrecht 2013.
Journal Abbreviation: Planets, Stars and Stellar Systems Volume 4: Stellar Structure and Evolution
Keywords: Astrometric; Binary star orbits; Detached binaries; Interacting binaries; Interferometric; Spectroscopic; Star clusters; Star formation; Stellar astrophysics; Stellar masses; dept.phy

Understanding scanning tunneling microscopy contrast mechanisms on metal oxides: A case study - Mönig, H.; Todorović, M.; Baykara, M.Z.; Schwendemann, T.C.; Rodrigo, L.; Altman, E.I.; Pérez, R.; Schwarz, U.D. (ACS Nano, 2013)
A comprehensive analysis of contrast formation mechanisms in scanning tunneling microscopy (STM) experiments on a metal oxide surface is presented with the oxygen-induced (2√2×√2)R45 missing row reconstruction of the Cu(100) surface as a model system. Density functional theory and electronic transport calculations were combined to simulate the STM imaging behavior of pure and oxygen-contaminated metal tips with structurally and chemically different apexes while systematically varying bias voltage and tip-sample distance. The resulting multiparameter database of computed images was used to conduct an extensive comparison with experimental data. Excellent agreement was attained for a large number of cases, suggesting that the assumed model tips reproduce most of the commonly encountered contrast-determining effects. Specifically, we find that depending on the bias voltage polarity, copper-terminated tips allow selective imaging of two structurally distinct surface Cu sites, while oxygen-terminated tips show complex contrasts with pronounced asymmetry and tip-sample distance dependence. Considering the structural and chemical stability of the tips reveals that the copper-terminated apexes tend to react with surface oxygen at small tip-sample distances. In contrast, oxygen-terminated tips are considerably more stable, allowing exclusive surface oxygen imaging at small tip-sample distances. Our results provide a conclusive understanding of fundamental STM imaging mechanisms, thereby providing guidelines for experimentalists to achieve chemically selective imaging by properly selecting imaging parameters. © 2013 American Chemical Society.
49 citations (Crossref) [2023-10-31]
Keywords: Bias voltage; Copper; Copper compounds; DFT simulation; Metal oxides; Metallic compounds; Oxygen; STM contrast; Scanning tunneling microscopy; Tip chemistry; dept.phy; metal oxide; tip asymmetry; tip chemistry; tip oxidation

MOST sub-arcsecond companions of Kepler exoplanet candidate host stars are gravitationally bound - Horch, E.P.; Howell, S.B.; Everett, M.E.; Ciardi, D.R. (Astrophysical Journal, 2014)
Using the known detection limits for high-resolution imaging observations and the statistical properties of true binary and line-of-sight companions, we estimate the binary fraction of Kepler exoplanet host stars. Our speckle imaging programs at the WIYN 3.5 m and Gemini North 8.1 m telescopes have observed over 600 Kepler objects of interest and detected 49 stellar companions within 1 arcsec. Assuming binary stars follow a log-normal period distribution for an effective temperature range of 3000-10,000 K, then the model predicts that the vast majority of detected sub-arcsecond companions are long period (P > 50 yr), gravitationally bound companions. In comparing the model predictions to the number of real detections in both observational programs, we conclude that the overall binary fraction of host stars is similar to the 40%-50% rate observed for field stars. © 2014. The American Astronomical Society. All rights reserved..
97 citations (Crossref) [2023-10-31]
Keywords: Binaries: visual; Planetary systems; Stars: solar-type; Techniques: high angular resolution; Techniques: interferometric; Techniques: photometric; dept.phy

Preface - Jain, F.; Broadbridge, C.; Tang, H. (International Journal of High Speed Electronics and Systems, 2014)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Simultaneous measurement of multiple independent atomic-scale interactions using scanning probe microscopy: Data interpretation and the effect of cross-talk - Baykara, M.Z.; Todorović, M.; Mönig, H.; Schwendemann, T.C.; Rodrigo, L.; Altman, E.I.; Pérez, R.; Schwarz, U.D. (Journal of Physical Chemistry C, 2015)
In high-resolution scanning probe microscopy, it is becoming increasingly common to simultaneously record multiple channels representing different tip-sample interactions to collect complementary information about the sample surface. A popular choice involves simultaneous scanning tunneling microscopy (STM) and noncontact atomic force microscopy (NC-AFM) measurements, which are thought to reflect the chemical and electronic properties of the sample surface. With surface-oxidized Cu(100) as an example, we investigate whether atomic-scale information on chemical interactions can be reliably extracted from frequency shift maps obtained while using the tunneling current as the feedback parameter. Ab initio calculations of interaction forces between specific tip apexes and the surface are utilized to compare experiments with theoretical expectations. The examination reveals that constant-current operation may induce a noticeable influence of topography-feedback-induced cross-talk on the frequency shift data, resulting in misleading interpretations of local chemical interactions on the surface. Consequently, the need to apply methods such as 3D-AFM is emphasized when accurate conclusions about both the local charge density near the Fermi level, as provided by the STM channel, and the site-specific strength of tip-sample interactions (NC-AFM channel) are desired. We conclude by generalizing to the case where multiple atomic-scale interactions are being probed while only one of them is kept constant. © 2015 American Chemical Society.
8 citations (Crossref) [2023-10-31]
Keywords: Ab initio calculations; Atomic force microscopy; Atomic-scale interaction; Calculations; Chemical interactions; Constant current operations; Crosstalk; Electronic properties; High resolution scanning; Hydrophobicity; Noncontact atomic force microscopy; Scanning tunneling microscopy; Simultaneous measurement; Tip-sample interaction; Topography; dept.phy

Preface - Jain, F.; Broadbridge, C.; Tang, H. (International Journal of High Speed Electronics and Systems, 2015)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Three-dimensional interaction force and tunneling current spectroscopy of point defects on rutile TiO2(110) - Baykara, M.Z.; Mönig, H.; Schwendemann, T.C.; Ünverdi, Ö.; Altman, E.I.; Schwarz, U.D. (Applied Physics Letters, 2016)
The extent to which point defects affect the local chemical reactivity and electronic properties of an oxide surface was evaluated with picometer resolution in all three spatial dimensions using simultaneous atomic force/scanning tunneling microscopy measurements performed on the (110) face of rutile TiO2. Oxygen atoms were imaged as protrusions in both data channels, corresponding to a rarely observed imaging mode for this prototypical metal oxide surface. Three-dimensional spectroscopy of interaction forces and tunneling currents was performed on individual surface and subsurface defects as a function of tip-sample distance. An interstitial defect assigned to a subsurface hydrogen atom is found to have a distinct effect on the local density of electronic states on the surface, but no detectable influence on the tip-sample interaction force. Meanwhile, spectroscopic data acquired on an oxygen vacancy highlight the role of the probe tip in chemical reactivity measurements. © 2016 AIP Publishing LLC.
18 citations (Crossref) [2023-10-31]
Keywords: Atoms; Defect density; Electron tunneling; Electronic properties; Interstitial defects; Local density of electronic state; Metals; Oxide minerals; Oxygen vacancies; Picometer resolution; Point defects; Prototypical metal oxide surfaces; Reactivity measurements; Subsurface hydrogens; Surface defects; Three-dimensional interaction; Tip-sample interaction; Titanium dioxide; dept.phy

Multifunctional in vivo imaging of pancreatic islets during diabetes development - Li, G.; Wu, B.; Ward, M.G.; Chong, C.N.; Mukherjee, S.; Chen, S.; Hao, M. (Journal of Cell Science, 2016)
Pancreatic islet dysfunction leading to insufficient glucose-stimulated insulin secretion triggers the clinical onset of diabetes. How islet dysfunction develops is not well understood at the cellular level, partly owing to the lack of approaches to study single islets longitudinally in vivo. Here, we present a noninvasive, high-resolution system to quantitatively image real-time glucose metabolism from single islets in vivo, currently not available with any other method. In addition, this multifunctional system simultaneously reports islet function, proliferation, vasculature and macrophage infiltration in vivo from the same set of images. Applying our method to a longitudinal high-fat diet study revealed changes in islet function as well as alternations in islet microenvironment. More importantly, this label-free system enabled us to image real-time glucose metabolism directly from single human islets in vivo for the first time, opening the door to noninvasive longitudinal in vivo studies of healthy and diabetic human islets. © 2016. Published by The Company of Biologists Ltd.
13 citations (Crossref) [2023-10-31]
Keywords: Animals; Anterior Chamber; Article; Cell Proliferation; Collagen; Computer Systems; Diabetes; Diabetes Mellitus; Diet; High-Fat; Disease Models; Animal; Fluorescence; Glucose; Glucose metabolism; Humans; Imaging; Three-Dimensional; In vivo imaging; Injections; Intraperitoneal; Islets of Langerhans; Macrophages; Male; Mice; Multiphoton microscopy; NAD(P)H; Pancreatic islets; animal; animal cell; animal experiment; anterior eye chamber; autofluorescence imaging; autofluorescence imaging system; cell function; cell infiltration; cell proliferation; collagen; computer system; dept.phy; diabetes mellitus; disease course; disease model; drug effects; fluorescence; glucose; glucose metabolism; human; imaging system; in vivo study; intraperitoneal drug administration; lipid diet; macrophage; male; metabolism; microenvironment; mouse; nonhuman; pancreas islet; pathology; priority journal; three dimensional imaging; vascularization

Coherent diffractive photoproduction of ρ0 mesons on gold nuclei at 200 GeV/nucleon-pair at the Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2017)
The STAR Collaboration reports on the photoproduction of π+π- pairs in gold-gold collisions at a center-of-mass energy of 200 GeV/nucleon-pair. These pion pairs are produced when a nearly real photon emitted by one ion scatters from the other ion. We fit the π+π- invariant-mass spectrum with a combination of ρ0 and ω resonances and a direct π+π- continuum. This is the first observation of the ω in ultraperipheral collisions, and the first measurement of ρ-ω interference at energies where photoproduction is dominated by Pomeron exchange. The ω amplitude is consistent with the measured γp→ωp cross section, a classical Glauber calculation, and the ω→π+π- branching ratio. The ω phase angle is similar to that observed at much lower energies, showing that the ρ-ω phase difference does not depend significantly on photon energy. The ρ0 differential cross section dσ/dt exhibits a clear diffraction pattern, compatible with scattering from a gold nucleus, with two minima visible. The positions of the diffractive minima agree better with the predictions of a quantum Glauber calculation that does not include nuclear shadowing than with a calculation that does include shadowing. © 2017 American Physical Society.
28 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Elliptic flow of electrons from heavy-flavor hadron decays in Au + Au collisions at √sNN =200, 62.4, and 39 GeV - STAR Collaboration (Physical Review C, 2017)
We present measurements of elliptic flow (v2) of electrons from the decays of heavy-flavor hadrons (eHF) by the STAR experiment. For Au+Au collisions at sNN=200 GeV we report v2, for transverse momentum (pT) between 0.2 and 7 GeV/c, using three methods: the event plane method (v2{EP}), two-particle correlations (v2{2}), and four-particle correlations (v2{4}). For Au+Au collisions at sNN=62.4 and 39 GeV we report v2{2} for pT<2GeV/c. v2{2} and v2{4} are nonzero at low and intermediate pT at 200 GeV, and v2{2} is consistent with zero at low pT at other energies. The v2{2} at the two lower beam energies is systematically lower than at sNN=200 GeV for pT<1GeV/c. This difference may suggest that charm quarks interact less strongly with the surrounding nuclear matter at those two lower energies compared to sNN=200 GeV. © 2017 American Physical Society.
17 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Measurement of the cross section and longitudinal double-spin asymmetry for dijet production in polarized pp collisions at s =200 GeV - STAR Collaboration (Physical Review D, 2017)
We report the first measurement of the longitudinal double-spin asymmetry ALL for midrapidity dijet production in polarized pp collisions at a center-of-mass energy of s=200 GeV. The dijet cross section was measured and is shown to be consistent with next-to-leading order (NLO) perturbative QCD predictions. ALL results are presented for two distinct topologies, defined by the jet pseudorapidities, and are compared to predictions from several recent NLO global analyses. The measured asymmetries, the first such correlation measurements, support those analyses that find positive gluon polarization at the level of roughly 0.2 over the region of Bjorken-x>0.05. © 2017 American Physical Society.
21 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Measurements of jet quenching with semi-inclusive hadron+jet distributions in Au+Au collisions at sNN =200 GeV - STAR Collaboration (Physical Review C, 2017)
The STAR Collaboration reports the measurement of semi-inclusive distributions of charged-particle jets recoiling from a high transverse momentum hadron trigger, in central and peripheral Au+Au collisions at sNN=200 GeV. Charged jets are reconstructed with the anti-kT algorithm for jet radii R between 0.2 and 0.5 and with low infrared cutoff of track constituents (pT>0.2 GeV/c). A novel mixed-event technique is used to correct the large uncorrelated background present in heavy ion collisions. Corrected recoil jet distributions are reported at midrapidity, for charged-jet transverse momentum pT,jetch<30 GeV/c. Comparison is made to similar measurements for Pb+Pb collisions at s=2.76 TeV, to calculations for p+p collisions at s=200 GeV based on the pythia Monte Carlo generator and on a next-to-leading order perturbative QCD approach, and to theoretical calculations incorporating jet quenching. The recoil jet yield is suppressed in central relative to peripheral collisions, with the magnitude of the suppression corresponding to medium-induced charged energy transport out of the jet cone of 2.8±0.2(stat)±1.5(sys) GeV/c, for 10<pT,jetch<20 GeV/c and R=0.5. No medium-induced change in jet shape is observed for R<0.5. The azimuthal distribution of low-pT,jetch recoil jets may be enhanced at large azimuthal angles to the trigger axis, due to scattering off quasiparticles in the hot QCD medium. Measurement of this distribution gives a 90% statistical confidence upper limit to the yield enhancement at large deflection angles in central Au+Au collisions of 50±30(sys)% of the large-angle yield in p+p collisions predicted by pythia. © 2017 American Physical Society.
40 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Preface - Jain, F.; Broadbridge, C.; Tang, H. (International Journal of High Speed Electronics and Systems, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Characterization and discrimination of basal cell carcinoma and normal human skin tissues using resonance Raman spectroscopy - Liu, C.-H.; Wu, B.; Boydston-White, S.; Beckman, H.; Sriramoju, V.; Sordillo, L.; Zhang, C.; Smith, J.; Zhang, L.; Shi, L.; Alfano, R.R. (Frontiers in Optics 2017, 2017)
Resonance Raman spectroscopy is used for rapid detection of skin BCC cancer. The cross-validated classification accuracy is achieved to be as high as 98% using nonnegative matrix factorization along with support vector machine statistical method. © OSA 2017.
2 citations (Crossref) [2023-10-31] Journal Abbreviation: Opt. InfoBase Conf. Pap
Keywords: Basal cell carcinoma; Classification accuracy; Factorization; Human skin; Matrix algebra; Nonnegative matrix factorization; Raman spectroscopy; Rapid detection; Resonance Raman spectroscopy; dept.phy

Erratum to: Determination of critical cooling rates in metallic glass forming alloy libraries through laser spike annealing (Scientific Reports, (2017), 7, 1, (7155), 10.1038/s41598-017-07719-2) - Bordeenithikasem, P.; Liu, J.; Kube, S.A.; Li, Y.; Ma, T.; Scanley, B.E.; Broadbridge, C.C.; Vlassak, J.J.; Singer, J.P.; Schroers, J. (Scientific Reports, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper. © 2018, The Author(s).
1 citations (Crossref) [2023-10-31]
Keywords: dept.phy; erratum; error

Speckle imaging through a coherent fiber bundle - Davidson, Jr., J.W.; Horch, E.P.; Majewski, S.R. (Proc SPIE Int Soc Opt Eng, 2018)
Speckle imaging is a well known method to achieve diffraction-limited (DL) imaging from ground-based telescopes. The traditional observing method for speckle has been to observe a single, unresolved, source per telescope pointing over a relatively small field of view (FOV). The need for large DL surveys of targets with high sky density motivates a desire for simultaneous speckle imaging over large FOVs, however it is currently impractical to attain this by covering the entire focal plane with fast readout detectors. An alternative approach is to connect a relatively small number of detector pixels to multiple interesting targets spanning a large FOV through the use of optical fibers, a technique employed in spectroscopy for decades. However, for imaging we require the use of coherent fiber bundles (CFBs). We discuss various design considerations for coherent fiber speckle imaging with an eye toward a multiplexed system using numerous configurable CFBs, and we test its viability with a prototype instrument that uses a single CFB to transport speckle images from the telescope focal plane to a traditionally designed, fast readout speckle camera. Using this device on University of Virginia's Fan Mountain Observatory 40-inch telescope we have for the first time successfully demonstrated speckle imaging through a CFB, using both optical and NIR detectors. Results are presented of DL speckle imaging of well-known close (including subarcsecond) binary stars resolved with this fiber-fed speckle system and compared to both literature results and traditional speckle imaging taken with the same camera directly, with no intervening CFB. © 2018 SPIE.
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Proc SPIE Int Soc Opt Eng
Keywords: Binary star; Cameras; Coherent fiber bundles; Exo-planets; Fiber optics; Focusing; High-resolution imaging; Interferometry; Optical fibers; Speckle; Speckle imaging; Stars; Telescopes; binary stars; coherent fiber bundles; dept.phy; exo-planets; fiber optics; high resolution imaging

Two-color speckle imaging of M-dwarfs with the Discovery Channel telescope - Hahne, F.W.; Horch, E.P.; Van Belle, G.T.; Clark, C.; Winters, J.G.; Henry, T.J. (Proc SPIE Int Soc Opt Eng, 2018)
Lowell Observatory and Southern Connecticut State University are currently involved in a joint project to determine the stellar multiplicity rates and the fundamental stellar parameters of M dwarf stars using the Differential Speckle Survey Instrument (DSSI) at Lowell's Discovery Channel Telescope (DCT). DSSI observes speckle patterns simultaneously at two separate wavelengths, allowing color measurements of the components of a binary system to be made in a single observation. This paper will describe the initial data gathering process, which began in 2016. Since then, over 1000 stars have been observed. We summarize the analysis on these objects so far, and discuss the relevance of these observations for existing and future space missions such as TESS, JWST, and Gaia. © 2018 SPIE.
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Proc SPIE Int Soc Opt Eng
Keywords: Color measurements; Discovery channel telescopes; Image reconstruction; Interferometry; Multiplicity rate; Optical properties; Speckle; Speckle imaging; Speckle patterns; Stars; Stellar parameters; Survey instruments; Telescopes; dept.phy; image reconstruction; stellar properties

Azimuthal anisotropy in Cu+Au collisions at s NN =200 GeV - STAR Collaboration (Physical Review C, 2018)
The azimuthal anisotropic flow of identified and unidentified charged particles has been systematically studied in Cu+Au collisions at sNN=200 GeV for harmonics n=1-4 in the pseudorapidity range |η|<1. The directed flow in Cu+Au collisions is compared with the rapidity-odd and, for the first time, the rapidity-even components of charged particle directed flow in Au+Au collisions at sNN=200 GeV. The slope of the directed flow pseudorapidity dependence in Cu+Au collisions is found to be similar to that in Au+Au collisions, with the intercept shifted toward positive pseudorapidity values, i.e., the Cu-going direction. The mean transverse momentum projected onto the spectator plane (px) in Cu+Au collision also exhibits approximately linear dependence on pseudorapidity with the intercept at about η≈-0.4 (shifted from zero in the Au-going direction), closer to the rapidity of the Cu+Au system center of mass. The observed dependencies find a natural explanation in a picture of the directed flow originating partly due the "tilted source" and partly due to the asymmetry in the initial density distribution. A charge dependence of (px) was also observed in Cu+Au collisions, consistent with an effect of the initial electric field created by charge difference of the spectator protons in two colliding nuclei. The rapidity-even component of directed flow in Au+Au collisions is close to that in Pb+Pb collisions at sNN=2.76 TeV, indicating a similar magnitude of dipolelike fluctuations in the initial-state density distribution. Higher harmonic flow in Cu+Au collisions exhibits similar trends to those observed in Au+Au and Pb+Pb collisions and is qualitatively reproduced by a viscous hydrodynamic model and a multiphase transport model. For all harmonics with n≥2 we observe an approximate scaling of vn with the number of constituent quarks; this scaling works as well in Cu+Au collisions as it does in Au+Au collisions. © 2018 American Physical Society.
22 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Global polarization of Λ hyperons in Au + Au collisions at sNN =200 GeV - STAR Collaboration (Physical Review C, 2018)
Global polarization of Λ hyperons has been measured to be of the order of a few tenths of a percentage in Au+Au collisions at sNN = 200 GeV, with no significant difference between Λ and Λ. These new results reveal the collision energy dependence of the global polarization together with the results previously observed at sNN = 7.7-62.4 GeV and indicate noticeable vorticity of the medium created in noncentral heavy-ion collisions at the highest Relativistic Heavy Ion Collider collision energy. The signal is in rough quantitative agreement with the theoretical predictions from a hydrodynamic model and from a multi-phase transport model. The polarization is larger in more peripheral collisions, and depends weakly on the hyperon's transverse momentum and pseudorapidity ηH within |ηH|<1. An indication of the polarization dependence on the event-by-event charge asymmetry is observed at the 2σ level, suggesting a possible contribution to the polarization from the axial current induced by the initial magnetic field. © 2018 American Physical Society.
181 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Improved measurement of the longitudinal spin transfer to Λ and Λ hyperons in polarized proton-proton collisions at s =200 GeV - STAR Collaboration (Physical Review D, 2018)
The longitudinal spin transfer DLL to Λ and Λ hyperons produced in high-energy polarized proton-proton collisions is expected to be sensitive to the helicity distribution functions of strange quarks and antiquarks of the proton, and to longitudinally polarized fragmentation functions. We report an improved measurement of DLL from data obtained at a center-of-mass energy of s=200 GeV with the STAR detector at RHIC. The data have an approximately twelve times larger figure of merit than prior results and cover |η|<1.2 in pseudorapidity with transverse momenta pT up to 6 GeV/c. In the forward scattering hemisphere at largest pT, the longitudinal spin transfer is found to be DLL=-0.036±0.048(stat)±0.013(sys) for Λ hyperons and DLL=0.032±0.043(stat)±0.013(sys) for Λ antihyperons. The dependences on η and pT are presented and compared with model evaluations. © 2018 authors. Published by the American Physical Society.
6 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Low- pT e+e- Pair Production in Au +Au Collisions at sNN =200 GeV and U + U Collisions at sNN =193 GeV at STAR - STAR Collaboration (Physical Review Letters, 2018)
We report first measurements of e+e- pair production in the mass region 0.4<Mee<2.6 GeV/c2 at low transverse momentum (pT<0.15 GeV/c) in noncentral Au+Au collisions at sNN=200 GeV and U+U collisions at sNN=193 GeV. Significant enhancement factors, expressed as ratios of data over known hadronic contributions, are observed in the 40%-80% centrality of these collisions. The excess yields peak distinctly at low pT with a width (âpT2â ©) between 40 and 60 MeV/c. The absolute cross section of the excess depends weakly on centrality, while those from a theoretical model calculation incorporating an in-medium broadened ρ spectral function and radiation from a quark gluon plasma or hadronic cocktail contributions increase dramatically with an increasing number of participant nucleons. Model calculations of photon-photon interactions generated by the initial projectile and target nuclei describe the observed excess yields but fail to reproduce the pT2 distributions. © 2018 authors. Published by the American Physical Society. Published by the American Physical Society under the terms of the »https://creativecommons.org/licenses/by/4.0/» Creative Commons Attribution 4.0 International license. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI. Funded by SCOAP3.
52 citations (Crossref) [2023-10-31]
Keywords: Au+Au collisions; Colliding beam accelerators; Enhancement factor; Germanium compounds; Gold; Mass regions; Measurements of; Pair production; Photons; Transverse momenta; dept.phy; peer-reviewed

Transverse spin transfer to Λ and Λ hyperons in polarized proton-proton collisions at s =200 GeV - STAR Collaboration (Physical Review D, 2018)
The transverse spin transfer from polarized protons to Λ and Λ hyperons is expected to provide sensitivity to the transversity distribution of the nucleon and to the transversely polarized fragmentation functions. We report the first measurement of the transverse spin transfer to Λ and Λ along the polarization direction of the fragmenting quark, DTT, in transversely polarized proton-proton collisions at s=200 GeV with the STAR detector at RHIC. The data correspond to an integrated luminosity of 18 pb-1 and cover the pseudorapidity range |η|<1.2 and transverse momenta pT up to 8 GeV/c. The dependence on pT and η are presented. The DTT results are found to be comparable with a model prediction and are also consistent with zero within uncertainties. © 2018 authors. Published by the American Physical Society.
11 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Speckle imaging of KOI binary stars with the WIYN telescope - Hess, N.M.; Thayer, P.R.; Horch, E.P.; Davidson, Jr., J.W.; Baptista, B.J.; Everett, M.E.; Howell, S.B. (Proc SPIE Int Soc Opt Eng, 2018)
Binary star systems where one of the stars is an exoplanet host appear to be more common than expected prior to the Kepler mission. The Kepler mission and subsequent ground-based follow-up work have revealed a number of Kepler Objects of Interest (KOIs) that have nearby stellar companions (within ∼1 arcsec). KOIs with stellar companions and at least one suspected exoplanet were selected for this work. Recent work on these stars has mainly focused on placing the companions on the H-R diagram and inferring if they are likely to be gravitationally bound based on whether their locations are consistent with a common isochrone. However, we have been observing these KOI double stars with speckle imaging over several years and are now in a position to assess whether these systems have components with a common proper motion, and can be seen as physically associated on that basis. We will give sample results of KOI double stars that are in fact common proper motion pairs. We compare our results with estimates of the multiplicity rate of exoplanet hosts from other methods and comment on the use of our data for constraining orbital parameters at this point, particularly the inclination angle. For transit observations, the inclination of the planetary orbit is already known, and the relationship between planetary and stellar orbital planes could have implications for star and planet formation. © 2018 SPIE.
2 citations (Crossref) [2023-10-31] Journal Abbreviation: Proc SPIE Int Soc Opt Eng
Keywords: Binary star; Binary star system; Extrasolar planets; Host-stars; Inclination angles; Interferometry; Multiplicity rate; Orbital parameters; Orbits; Speckle; Speckle imaging; Stars; astrometry; binary stars; dept.phy; exoplanet host stars

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Tang, H.; Gherasimova, M. (International Journal of High Speed Electronics and Systems, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.C.; Broadbridge, C.; Tang, H.; Gherasimova, M. (High Performance Materials and Devices for High-Speed Electronic Systems, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: Materials; dept.phy

Machine learning based analysis of human prostate cancer cell lines at different metastatic ability using native fluorescence spectroscopy with selective excitation wavelength - Xue, J.; Pu, Y.; Smith, J.; Gao, X.; Wu, B. (Progr. Biomed. Opt. Imaging Proc. SPIE, 2018)
Native fluorescence spectra play important roles in cancer detection. It is widely acknowledged that the emission spectrum of a tissue is a superposition of spectra of various salient fluorophores. However, component quantification is essentially an ill-posed problem. To address this problem, the native fluorescence spectra of normal human very low (LNCap), moderately metastatic (DU-145), and advanced metastatic (PC-3) cell lines were studied by the selected wavelength of 300 nm to investigate the key fluorescent molecules such as tryptophan, collagen and NADH. The native fluorescence spectra of cancer cell lines at different risk levels were analyzed using various machine learning algorithms for feature detection and develop criteria to separate the three types of cells. Principal component analysis (PCA), nonnegative matrix factorization (NMF), and partial least squares fitting were used separately to reduce dimension, extract features and detect biomolecular alterations reflected in the spectra. The scores corresponding to the basis spectra were used for classification. A linear support vector machine (SVM) was used to classify the spectra of the cells with different metastatic ability. In detection of signals coming from tryptophan and NADH with observed data corrupted by noise and inference, a sufficient statistic can be obtained based on the basis spectra retrieved using nonnegative matrix factorization. This work shows changes of relative contents of tryptophan and NADH obtained from native fluorescence spectroscopy may present potential criteria for detecting cancer cell lines of different metastatic ability. © 2018 SPIE.
1 citations (Crossref) [2023-10-31] Journal Abbreviation: Progr. Biomed. Opt. Imaging Proc. SPIE
Keywords: Amino acids; Artificial intelligence; Cell culture; Cells; Diseases; Emission spectroscopy; Factorization; Feature extraction; Fluorescence; Fluorescence spectroscopy; Image retrieval; Learning algorithms; Least squares approximations; Matrix algebra; NADH; Native fluorescence; Native fluorescence (NFL) spectra; Nonnegative matrix factorization; Photonics; Principal component analysis; Spectrum analysis; Support vector machines; advanced metastatic (PC-3); dept.phy; low metastatic (LNCap); moderately metastatic (DU-145); nonnegative matrix factorization; principal component analysis; support vector machine (SVM) classifier; tryptophan

The optomechanical design of the Quad-camera Wavefront-sensing Six-channel Speckle Interferometer (QWSSI) - Clark, C.A.; Van Belle, G.T.; Horch, E.P.; Trilling, D.E.; Hartman, Z.D.; Collins, M.; Von Braun, K.; Gehring, J. (Proc SPIE Int Soc Opt Eng, 2020)
The Quad-camera Wavefront-sensing Six-channel Speckle Interferometer (QWSSI) is a new speckle imaging instrument available on the 4.3-m Lowell Discovery Telescope (LDT). QWSSI is built to efficiently make use of collected photons and available detector area. The instrument images on a single Electron Multiplying CCD (EMCCD) at four wavelengths in the optical (577, 658, 808, and 880nm) with 40nm bandpasses. Longward of 1μm, two imaging wavelengths in the NIR are collected at 1150 and 1570nm on two InGaAs cameras with 50nm bandpasses. All remaining non-imaging visible light is then sent into a wavefront EMCCD. All cameras are operated synchronously via concurrent triggering from a timing module. With the simultaneous wavefront sensing, QWSSI characterizes atmospheric aberrations in the wavefront for each speckle frame. This results in additional data that can be utilized during post-processing, enabling advanced techniques such as Multi-Frame Blind Deconvolution. The design philosophy was optimized for an inexpensive, rapid build; virtually all parts were commercial-off-the-shelf (COTS), and custom parts were fabricated or 3D printed on-site. QWSSI's unique build and capabilities represent a new frontier in civilian high-resolution speckle imaging. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.
2 citations (Crossref) [2023-10-31] Journal Abbreviation: Proc SPIE Int Soc Opt Eng
Keywords: 3D printers; Aberrations; Additional datum; Atmospheric aberration; Cameras; Commercial off-the-shelf; Convolution; Design philosophy; Diffraction-limited imaging; Gallium alloys; Gallium compounds; Indium alloys; Instrument design; Interferometers; Interferometry; Light; Multi-frame blind deconvolution; Opto-mechanical design; Optomechanics; Semiconducting indium gallium arsenide; Semiconductor alloys; Speckle; Speckle imaging; Speckle interferometer; Stellar proper- ties; Wave-front sensing; Wavefront-sensing; Wavefronts; dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Toward an imaging capability with the Southern Connecticut Stellar Interferometer - Klaucke, P.M.; Pellegrino, R.A.; Weiss, S.A.; Horch, E.P. (Proc SPIE Int Soc Opt Eng, 2020)
The Southern Connecticut Stellar Interferometer (SCSI) is an intensity interferometer that is designed to use correlated photon arrival times to determine the geometry of stars. Originally a low-cost, two-telescope instrument that used a 1-pixel single-photon avalanche diode (SPAD) detector at the focal plane of each telescope to record photon events, it is now being upgraded to include a third telescope. This will allow for the simultaneous detection of the photon correlation at three baselines, and thus the ability to map out the two-dimensional geometry of the source much more efficiently than with the two-telescope arrangement. Recent papers in the literature suggest that it may be possible to derive phase information in the Fourier domain from such triple correlations for the brightest stars, potentially giving SCSI an imaging capability. Prior to investigating this possibility, steps must be taken to maximize the observing efficiency of the SCSI. We present here our latest efforts in achieving better pointing, tracking, and collimation with our telescopes, and we discuss our first modeling results of the three-telescope situation in order to understand under what conditions the upgraded SCSI could retrieve imaging information. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.
1 citations (Crossref) [2023-10-31] Journal Abbreviation: Proc SPIE Int Soc Opt Eng
Keywords: Avalanche diodes; Correlation interferometry; Hanbury Brown and Twiss Effect; Image reconstruction; Imaging capabilities; Imaging information; Interferometers; Interferometry; Observing efficiency; Optical intensity interferometry; Particle beams; Phase recovery; Photons; Simultaneous detection; Single photon avalanche diode; Stars; Stellar interferometers; Telescope instruments; Telescopes; Two-dimensional geometry; dept.phy

Characterization of iron doped zinc oxide nanoparticles using fluorescence spectroscopy - Fernando, M.; Singhal, R.; LeMaire, P.K.; Wu, B. (Front. Opt. - Proc. Front. Opt. Laser Sci. APS/DLS, 2019)
ZnO and Fe-doped ZnO nanoparticles were analyzed in ethanol solution and dry powder form using fluorescence spectroscopy. Near-band-edge emission (NBE) and defect emission (DE) peaks were studied. A blue-shift was observed with the NBE emission peak. © OSA 2019. The Author(s).
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Front. Opt. - Proc. Front. Opt. Laser Sci. APS/DLS
Keywords: Blue shift; Defect emission; Dry powders; Emission peaks; Ethanol solutions; Fe-doped; Fluorescence; Fluorescence spectroscopy; II-VI semiconductors; Iron oxides; Iron-doped; Nanoparticles; Near band edge emissions; Oxide minerals; Zinc oxide; ZnO nanoparticles; dept.phy

Thin Film Deposition and Carbon Nanotube Synthesis - Frey, J.; Schwendemann, T.C. (International Journal of High Speed Electronics and Systems, 2019)
Carbon nanotubes (CNTs) are a viable product for many different markets. One specific area of promise is the use of CNTs in supercapacitors. The CNT synthesis is a two-step process with the first being the formation of a thin film layer. The thin film substrate is created by means of the Thermal Evaporation Physical Vapor Deposition (TPVD) process. After the thin film substrate is deposited, the CNTs are grown in a Chemical Vapor Deposition (CVD) growth chamber. Analysis of the thin film substrate and CNTs is performed primarily using Scanning Electron Microscopy (SEM). The results show the inclusion of ultrapure water in the CVD process contributed to the success of CNT growth. Multiple prong CNT grow is seen for CVDs trails of silver thin film layer deposited on silicon substrates. The silver nanoparticle had a large diameter with an acute contact angle. The single prong growth indicates the iron nanoparticles formed an obtuse contact angle due to the amorphic surface of alumina substrate. The focus of this project is to explore and investigate different materials and conditions for optimal CNT synthesis in the hopes of creating a uniform forest of vertically aligned carbon nanotubes. © 2019 World Scientific Publishing Company.
0 citations (Crossref) [2023-10-31]
Keywords: Alumina; Alumina substrates; Aluminum oxide; Carbon nanotube synthesis; Carbon nanotubes; Chemical vapor deposition; Chemical vapor depositions (CVD); Contact angle; Iron nanoparticles; Nanoparticles; Physical vapor deposition; Scanning electron microscopy; Silicon substrates; Silver nanoparticles; Substrates; Thermal evaporation; Thin film substrate; Thin films; Thin-film depositions; Vertically aligned carbon nanotube; dept.phy; peer-reviewed

Breast cancer diagnosis using fluorescence spectroscopy with dualwavelength excitation and machine learning - Gaoa, X.; Wu, B. (Progr. Biomed. Opt. Imaging Proc. SPIE, 2019)
Intrinsic fluorescence spectra of fresh normal and cancerous human breast tissues were measured using two selective excitation wavelengths including 290nm and 340nm. Dual-wavelength excitation may reveal more molecular information than single-wavelength excitation. In the meantime, it is significantly faster than the acquisition of excitation-emission (EEM) matrix. Unsupervised machine learning algorithms principal component analysis (PCA) and non-negative matrix factorization (NMF) were used to reduce the dimensionality of the spectral data. The relative concentrations of the basis spectra retrieved by PCA and NMF were considered features of the samples and used to distinguish normal and malignant tissues. The performances of classification using support vector machine (SVM) based on PCA and NMF features were compared. The classification using spectral data with dual-wavelength excitation was compared with single-wavelength excitation. Classification based on NMF-retrieved components from spectral data with dual-wavelength excitation yielded the best performance. © 2019 SPIE.
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Progr. Biomed. Opt. Imaging Proc. SPIE
Keywords: Biopsy; Breast Cancer; Breast cancer; Cancer diagnosis; Classification (of information); Diseases; Dual wavelength; Dual-wavelength excitation; Factorization; Fluorescence; Fluorescence spectroscopy; Histology; Learning algorithms; Machine learning; Matrix algebra; Nonnegative matrix factorization; Optical biopsies; Optical biopsy; Principal component analysis; Support vector machine; Support vector machines; Tissue; dept.phy

Centrality and transverse momentum dependence of D0 -meson production at mid-rapidity in Au + Au collisions at s NN =200 GeV - STAR Collaboration (Physical Review C, 2019)
We report a new measurement of D0-meson production at mid-rapidity (|y|<1) in Au + Au collisions at sNN=200GeV utilizing the heavy flavor tracker, a high resolution silicon detector at the STAR experiment. Invariant yields of D0 mesons with transverse momentum pT9GeV/c are reported in various centrality bins (0-10%, 10-20%, 20-40%, 40-60%, and 60-80%). Blast-wave thermal models are used to fit the D0-meson pT spectra to study D0 hadron kinetic freeze-out properties. The average radial flow velocity extracted from the fit is considerably smaller than that of light hadrons (π,K, and p), but comparable to that of hadrons containing multiple strange quarks (φ,Ξ-), indicating that D0 mesons kinetically decouple from the system earlier than light hadrons. The calculated D0 nuclear modification factors reaffirm that charm quarks suffer a large amount of energy loss in the medium, similar to those of light quarks for pT>4GeV/c in central 0-10% Au + Au collisions. At low pT, the nuclear modification factors show a characteristic structure qualitatively consistent with the expectation from model predictions that charm quarks gain sizable collective motion during the medium evolution. The improved measurements are expected to offer new constraints to model calculations and help gain further insights into the hot and dense medium created in these collisions. © 2019 American Physical Society.
44 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Longitudinal double-spin asymmetry for inclusive jet and dijet production in pp collisions at s =510 GeV - STAR Collaboration (Physical Review D, 2019)
We report the first measurement of the inclusive jet and the dijet longitudinal double-spin asymmetries, ALL, at midrapidity in polarized pp collisions at a center-of-mass energy s=510 GeV. The inclusive jet ALL measurement is sensitive to the gluon helicity distribution down to a gluon momentum fraction of x≈0.015, while the dijet measurements, separated into four jet-pair topologies, provide constraints on the x dependence of the gluon polarization. Both results are consistent with previous measurements made at s=200 GeV in the overlapping kinematic region, x>0.05, and show good agreement with predictions from recent next-to-leading order global analyses. © 2019 authors. Published by the American Physical Society.
26 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Measurement of inclusive J/ψ suppression in Au+Au collisions at sNN=200 GeV through the dimuon channel at STAR - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2019)
J/ψ suppression has long been considered a sensitive signature of the formation of the Quark-Gluon Plasma (QGP) in relativistic heavy-ion collisions. In this letter, we present the first measurement of inclusive J/ψ production at mid-rapidity through the dimuon decay channel in Au+Au collisions at sNN=200 GeV with the STAR experiment. These measurements became possible after the installation of the Muon Telescope Detector was completed in 2014. The J/ψ yields are measured in a wide transverse momentum (pT) range of 0.15 GeV/c to 12 GeV/c from central to peripheral collisions. They extend the kinematic reach of previous measurements at RHIC with improved precision. In the 0-10% most central collisions, the J/ψ yield is suppressed by a factor of approximately 3 for pT>5 GeV/c relative to that in p+p collisions scaled by the number of binary nucleon-nucleon collisions. The J/ψ nuclear modification factor displays little dependence on pT in all centrality bins. Model calculations can qualitatively describe the data, providing further evidence for the color-screening effect experienced by J/ψ mesons in the QGP. © 2019 The Author(s)
18 citations (Crossref) [2023-10-31]
Keywords: Color-screening; J/ψ suppression; Quark-gluon plasma; dept.phy; peer-reviewed

Measurement of the longitudinal spin asymmetries for weak boson production in proton-proton collisions at s =510 GeV - STAR Collaboration (Physical Review D, 2019)
We report new STAR measurements of the single-spin asymmetries AL for W+ and W- bosons produced in polarized proton-proton collisions at s=510 GeV as a function of the decay-positron and decay-electron pseudorapidity. The data were obtained in 2013 and correspond to an integrated luminosity of 250 pb-1. The results are combined with previous results obtained with 86 pb-1. A comparison with theoretical expectations based on polarized lepton-nucleon deep-inelastic scattering and prior polarized proton-proton data suggests a difference between the ū and d quark helicity distributions for 0.05<x<0.25. In addition, we report new results for the double-spin asymmetries ALL for W±, as well as AL for Z/γ∗ production and subsequent decay into electron-positron pairs. © 2019 authors. Published by the American Physical Society.
20 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Measurements of the transverse-momentum-dependent cross sections of J /ψ production at mid-rapidity in proton+proton collisions at s =510 and 500 GeV with the STAR detector - STAR Collaboration (Physical Review D, 2019)
We present measurements of the differential cross sections of inclusive J/ψ meson production as a function of transverse momentum (pTJ/ψ) using the μ+μ- and e+e- decay channels in proton+proton collisions at center-of-mass energies of 510 and 500 GeV, respectively, recorded by the STAR detector at the Relativistic Heavy Ion Collider. The measurement from the μ+μ- channel is for 0<pTJ/ψ<9 GeV/c and rapidity range |yJ/ψ|<0.4, and that from the e+e- channel is for 4<pTJ/ψ<20 GeV/c and |yJ/ψ|<1.0. The ψ(2S) to J/ψ ratio is also measured for 4<pTmeson<12 GeV/c through the e+e- decay channel. Model calculations, which incorporate different approaches toward the J/ψ production mechanism, are compared with experimental results and show reasonable agreement within uncertainties. © 2019 authors. Published by the American Physical Society.
8 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

STAR Collaboration - STAR Collaboration (Nuclear Physics A, 2019)
1 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2019)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (High Performance Logic and Circuits for High-Speed Electronic Systems, 2019)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Three Red Suns in the Sky: A Transiting, Terrestrial Planet in a Triple M-dwarf System at 6.9 pc - Winters, J.G.; Medina, A.A.; Irwin, J.M.; Charbonneau, D.; Astudillo-Defru, N.; Horch, E.P.; Eastman, J.D.; Vrijmoet, E.H.; Henry, T.J.; Diamond-Lowe, H.; Winston, E.; Barclay, T.; et al. (Astronomical Journal, 2019)
We present the discovery from Transiting Exoplanet Survey Satellite (TESS) data of LTT 1445Ab. At a distance of 6.9 pc, it is the second nearest transiting exoplanet system found to date, and the closest one known for which the primary is an M dwarf. The host stellar system consists of three mid-to-late M dwarfs in a hierarchical configuration, which are blended in one TESS pixel. We use MEarth data and results from the Science Processing Operations Center data validation report to determine that the planet transits the primary star in the system. The planet has a radius of, an orbital period of days, and an equilibrium temperature of K. With radial velocities from the High Accuracy Radial Velocity Planet Searcher, we place a 3σ upper mass limit of 8.4 on the planet. LTT 1445Ab provides one of the best opportunities to date for the spectroscopic study of the atmosphere of a terrestrial world. We also present a detailed characterization of the host stellar system. We use high-resolution spectroscopy and imaging to rule out the presence of any other close stellar or brown dwarf companions. Nineteen years of photometric monitoring of A and BC indicate a moderate amount of variability, in agreement with that observed in the TESS light-curve data. We derive a preliminary astrometric orbit for the BC pair that reveals an edge-on and eccentric configuration. The presence of a transiting planet in this system hints that the entire system may be co-planar, implying that the system may have formed from the early fragmentation of an individual protostellar core. © 2019. The American Astronomical Society. All rights reserved..
55 citations (Crossref) [2023-10-31]
Keywords: binaries: close; dept.phy; peer-reviewed; planets and satellites: detection; stars: individual (LTT 1445); stars: low-mass

Human brain glioma grading using label free laser-induced fluorescence spectroscopy - Zhou, Y.; Liu, C.-H.; Zhu, K.; Wu, B.; Yu, X.; Cheng, G.; Zhao, M.; Zong, R.; Zhang, C.; Chen, H.; Li, S.; Liang, Q.; et al. (Progr. Biomed. Opt. Imaging Proc. SPIE, 2019)
Laser-induced fluorescence (LIF) technique was used to generate spectral signatures of endogenous fluorophores relevant to the tissue molecular composition changes in human brain glioma tumors. The goal is to study the changes of fluorescence emission spectra from endogenous fluorophores in human brain glioma of different grades, and to find new biomarkers for prognostic optical molecular pathological diagnosis. Two hundred and thirty-seven (237) native fluorescence spectra from 61 subjects were measured using LabRAM HR Evolution micro photoluminescence (PL) system for four grades of glioma tumors in ex-vivo. The differences of four grades of glioma tumors were identified by the characteristic fluorophores fingerprints under the excitation laser wavelength at UV 325nm. To our best knowledge, this is the first report for human brain study using this technique. The fluorescence peaks of biomarkers with major contribution were found, including tryptophan, collagen, elastin, reduced nicotinamide adenine dinucleotide (NADH), flavin adenine dinucleotide (FAD) and phospholipids that play important roles in the cellular energy metabolism and glycolysis pathway. The ratios of peak intensities and the peak positions in fluorescence spectra of may be used to diagnose human brain diseases or to guide biopsy during surgical resection. © 2019 SPIE.
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Progr. Biomed. Opt. Imaging Proc. SPIE
Keywords: Amino acids; Biomarkers; Biopsy; Brain; Cellular energy; Cellular energy metabolism; Emission spectroscopy; FAD; Fluorescence; Fluorescence microscopy; Fluorescence spectroscopy; Fluorophores; Grading; Human brain; Human brain glioma tissues; Laser excitation; Laser induced fluorescence spectroscopy; Laser optics; Laser produced plasmas; Metabolism; NADH; Native fluorescence; Native laser-induced fluorescence spectroscopy; Native-fluorescence; Nucleotides; Optical molecular pathology; Pathology; Phospholipids; Tryptophan; Tumors; dept.phy

A portable visible resonance Raman analyzer with a handheld optical fiber probe for in vivo diagnosis of brain glioblastoma multiforme in an animal model - Zhou, Y.; Zhang, S.; Wu, B.; Yu, X.; Cheng, G.; Zhu, K.; Zhao, M.; Zheng, J.; Zhang, M.; Liang, Q.; Liu, C.-H.; Alfano, R.R. (Front. Opt. - Proc. Front. Opt. Laser Sci. APS/DLS, 2019)
A VRR-LRR analyzer with handheld fiber‐optic probe is reported for the first time for diagnosis of brain GBM in vivo. The sensitivity for identification is 80% compared with histopathology examination. © OSA 2019. The Author(s).
2 citations (Crossref) [2023-10-31] Journal Abbreviation: Front. Opt. - Proc. Front. Opt. Laser Sci. APS/DLS
Keywords: Animal model; Fiberoptic probes; Glioblastoma multiforme; Handhelds; In-vivo; Optical fiber probe; Optical fibers; Probes; Resonance Raman; dept.phy

Global Λ-hyperon polarization in Au+Au collisions at √sNN = 3 GeV - STAR Collaboration (Physical Review C, 2021)
Global hyperon polarization, P¯H, in Au+Au collisions over a large range of collision energy, sNN, was recently measured and successfully reproduced by hydrodynamic and transport models with intense fluid vorticity of the quark-gluon plasma. While naïve extrapolation of data trends suggests a large P¯H as the collision energy is reduced, the behavior of P¯H at small sNN¡7.7 GeV is unknown. Operating the STAR experiment in fixed-target mode, we measured the polarization of Λ hyperons along the direction of global angular momentum in Au+Au collisions at sNN=3 GeV. The observation of substantial polarization of 4.91±0.81(stat.)±0.15(syst.)% in these collisions may require a reexamination of the viscosity of any fluid created in the collision, of the thermalization timescale of rotational modes, and of hadronic mechanisms to produce global polarization. © 2021 American Physical Society.
39 citations (Crossref) [2023-10-31] tex.art_number: L061901 tex.document_type: Article tex.source: Scopus
Keywords: dept.phy; peer-reviewed

Measurement of the sixth-order cumulant of net-proton multiplicity distributions in au+au collisions at s NN =27, 54.4, and 200 GeV at RHIC - STAR Collaboration (Physical Review Letters, 2021)
According to first-principle lattice QCD calculations, the transition from quark-gluon plasma to hadronic matter is a smooth crossover in the region μB≤Tc. In this range the ratio, C6/C2, of net-baryon distributions are predicted to be negative. In this Letter, we report the first measurement of the midrapidity net-proton C6/C2 from 27, 54.4, and 200 GeV Au+Au collisions at the Relativistic Heavy Ion Collider (RHIC). The dependence on collision centrality and kinematic acceptance in (pT, y) are analyzed. While for 27 and 54.4 GeV collisions the C6/C2 values are close to zero within uncertainties, it is observed that for 200 GeV collisions, the C6/C2 ratio becomes progressively negative from peripheral to central collisions. Transport model calculations without critical dynamics predict mostly positive values except for the most central collisions within uncertainties. These observations seem to favor a smooth crossover in the high-energy nuclear collisions at top RHIC energy. © 2021 American Physical Society.
18 citations (Crossref) [2023-10-31] tex.art_number: 262301 tex.coden: PRLTA tex.document_type: Article tex.pubmed_id: 35029466 tex.source: Scopus
Keywords: Au+Au collisions; Colliding beam accelerators; Cumulants; First principles; Germanium alloys; Germanium compounds; Gold compounds; Hadronic matters; Heavy ions; Lattice QCD calculations; Measurements of; Mid-rapidity; Multiplicity distributions; Quantum theory; Quark-gluon plasma; Uncertainty; dept.phy; peer-reviewed

Understanding reentrance in frustrated magnets: The case of the Er2Sn2 O7 pyrochlore - Yahne, D.R.; Pereira, D.; Jaubert, L.D.C.; Sanjeewa, L.D.; Powell, M.; Kolis, J.W.; Xu, G.; Enjalran, M.; Gingras, M.J.P.; Ross, K.A. (Physical Review Letters, 2021)
Reentrance, the return of a system from an ordered phase to a previously encountered less-ordered one as a controlled parameter is continuously varied, is a recurring theme found in disparate physical systems, yet its microscopic cause is often not investigated thoroughly. Here, through detailed characterization and theoretical modeling, we uncover the microscopic mechanism behind reentrance in the strongly frustrated pyrochlore antiferromagnet Er2Sn2O7. We use single crystal heat capacity measurements to expose that Er2Sn2O7 exhibits multiple instances of reentrance in its magnetic field B vs temperature T phase diagram for magnetic fields along three cubic high symmetry directions. Through classical Monte Carlo simulations, mean field theory, and classical linear spin-wave expansions, we argue that the origins of the multiple occurrences of reentrance observed in Er2Sn2O7 are linked to soft modes. These soft modes arise from phase competition and enhance thermal fluctuations that entropically stabilize a specific ordered phase, resulting in an increased transition temperature for certain field values and thus the reentrant behavior. Our work represents a detailed examination into the mechanisms responsible for reentrance in a frustrated magnet and may serve as a template for the interpretation of reentrant phenomena in other physical systems. © 2021 American Physical Society.
6 citations (Crossref) [2023-10-31] tex.art_number: 277206 tex.coden: PRLTA tex.document_type: Article tex.pubmed_id: 35061439 tex.source: Scopus
Keywords: Antiferromagnets; Binary alloys; Controlled parameter; Crystal symmetry; Frustrated magnet; Intelligent systems; Magnetic fields; Magnetic-field; Magnetization; Magnets; Mean field theory; Microscopic mechanisms; Monte Carlo methods; Ordered phasis; Physical systems; Pyrochlores; Single crystals; Soft modes; Specific heat; Spin waves; Theoretical modeling; dept.phy

A new absolute proper motion determination of leo i using HST/WFPC2 images and gaia EDR3 - Casetti-Dinescu, D.I.; Hansen, C.K.; Girard, T.M.; Kozhurina-Platais, V.; Platais, I.; Horch, E.P. (Astronomical Journal, 2022)
We measure the absolute proper motion of Leo I using a WFPC2/HST data set that spans up to 10 yr to date the longest time baseline utilized for this satellite. The measurement relies on ∼2300 Leo I stars located near the center of light of the galaxy; the correction to absolute proper motion is based on 174 Gaia EDR3 stars and 10 galaxies. Having generated highly precise, relative proper motions for all Gaia EDR3 stars in our WFPC2 field of study, our correction to the absolute EDR3 system does not rely on these Gaia stars being Leo I members. This new determination also benefits from a recently improved astrometric calibration of WFPC2. The resulting proper-motion value, (μ α , μ δ ) = (-0.007 0.035, - 0.119 0.026) mas yr-1 is in agreement with recent, large-area, Gaia EDR3-based determinations. We discuss all the recent measurements of Leo I's proper motion and adopt a combined, multistudy average of (μ α 3 meas,μ δ 3 meas)=(-0.036±0.016,-0.130±0.010) mas yr-1. This value of absolute proper motion for Leo I indicates its orbital pole is well aligned with that of the vast polar structure, defined by the majority of the brightest dwarf spheroidal satellites of the Milky Way. © 2021. The Author(s). Published by the American Astronomical Society.
3 citations (Crossref) [2023-10-31] tex.art_number: 1 tex.document_type: Article tex.source: Scopus
Keywords: dept.phy; peer-reviewed

Validation of 13 hot and potentially terrestrial TESS planets - Giacalone, S.; Dressing, C.D.; Hedges, C.; Kostov, V.B.; Collins, K.A.; Jensen, E.L.N.; Yahalomi, D.A.; Bieryla, A.; Ciardi, D.R.; Howell, S.B.; Lillo-Box, J.; Barkaoui, K.; et al. (Astronomical Journal, 2022)
The James Webb Space Telescope will be able to probe the atmospheres and surface properties of hot, terrestrial planets via emission spectroscopy. We identify 18 potentially terrestrial planet candidates detected by the Transiting Exoplanet Survey Satellite (TESS) that would make ideal targets for these observations. These planet candidates cover a broad range of planet radii (R p ∼0.6-2.0R ) and orbit stars of various magnitudes (K s = 5.78-10.78, V = 8.4-15.69) and effective temperatures (T eff ∼3000-6000 K). We use ground-based observations collected through the TESS Follow-up Observing Program (TFOP) and two vetting tools - DAVE and TRICERATOPS - to assess the reliabilities of these candidates as planets. We validate 13 planets: TOI-206 b, TOI-500 b, TOI-544 b, TOI-833 b, TOI-1075 b, TOI-1411 b, TOI-1442 b, TOI-1693 b, TOI-1860 b, TOI-2260 b, TOI-2411 b, TOI-2427 b, and TOI-2445 b. Seven of these planets (TOI-206 b, TOI-500 b, TOI-1075 b, TOI-1442 b, TOI-2260 b, TOI-2411 b, and TOI-2445 b) are ultra-short-period planets. TOI-1860 is the youngest (133 ± 26 Myr) solar twin with a known planet to date. TOI-2260 is a young (321 ± 96 Myr) G dwarf that is among the most metal-rich ([Fe/H] = 0.22 ± 0.06 dex) stars to host an ultra-short-period planet. With an estimated equilibrium temperature of 1/42600 K, TOI-2260 b is also the fourth hottest known planet with R p ¡ 2 R . © 2022. The Author(s). Published by the American Astronomical Society.
tex.art_number: 99 tex.document_type: Article tex.source: Scopus
Keywords: dept.phy; peer-reviewed

Observations with the Southern Connecticut Stellar Interferometer. I. Instrument Description and First Results - Horch, E.P.; Weiss, S.A.; Klaucke, P.M.; Pellegrino, R.A.; Rupert, J.D. (Astronomical Journal, 2022)
We discuss the design, construction, and operation of a new intensity interferometer, based on the campus of Southern Connecticut State University in New Haven, Connecticut. While this paper will focus on observations taken with an original two-telescope configuration, the current instrumentation consists of three portable 0.6 m Dobsonian telescopes with single-photon avalanche diode detectors located at the Newtonian focus of each telescope. Photons detected at each station are time stamped and read out with timing correlators that can give cross-correlations in timing to a precision of 48 ps. We detail our observations to date with the system, which has now been successfully used at our university in 16 nights of observing. Components of the instrument were also deployed on one occasion at Lowell Observatory, where the Perkins and Hall telescopes were made to function as an intensity interferometer. We characterize the performance of the instrument in detail. In total, the observations indicate the detection of a correlation peak at the level of 6.76σ when observing unresolved stars, and consistency with partial or no detection when observing at a baseline sufficient to resolve the star. Using these measurements, we conclude that the angular diameter of Arcturus is larger than 15 mas and that of Vega is between 0.8 and 17 mas. While the uncertainties are large at this point, both results are consistent with measures from amplitude-based long baseline optical interferometers. © 2022. The American Astronomical Society. All rights reserved.
4 citations (Crossref) [2023-10-31] tex.art_number: 92 tex.document_type: Article tex.source: Scopus
Keywords: dept.phy; peer-reviewed

Disappearance of partonic collectivity in sNN=3 GeV au+au collisions at RHIC - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2022)
We report on the measurements of directed flow v1 and elliptic flow v2 for hadrons (π±, K±, KS0, p, ϕ, Λ and Ξ−) from Au+Au collisions at sNN=3 GeV and v2 for (π±, K±, p and p‾) at 27 and 54.4 GeV with the STAR experiment. While at the two higher energy midcentral collisions the number-of-constituent-quark (NCQ) scaling holds, at 3 GeV the v2 at midrapidity is negative for all hadrons and the NCQ scaling is absent. In addition, the v1 slopes at midrapidity for almost all observed hadrons are found to be positive, implying dominant repulsive baryonic interactions. The features of negative v2 and positive v1 slope at 3 GeV can be reproduced with a baryonic mean-field in transport model calculations. These results imply that the medium in such collisions is likely characterized by baryonic interactions. © 2022 The Author(s)
22 citations (Crossref) [2023-10-31] tex.art_number: 137003 tex.coden: PYLBA tex.document_type: Article tex.source: Scopus
Keywords: dept.phy; peer-reviewed

Light nuclei collectivity from sNN=3 GeV au+au collisions at RHIC - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2022)
In high-energy heavy-ion collisions, partonic collectivity is evidenced by the constituent quark number scaling of elliptic flow anisotropy for identified hadrons. A breaking of this scaling and dominance of baryonic interactions is found for identified hadron collective flow measurements in sNN = 3 GeV Au+Au collisions. In this paper, we report measurements of the first- and second-order azimuthal anisotropic parameters, v1 and v2, of light nuclei (d, t, 3He, 4He) produced in sNN = 3 GeV Au+Au collisions at the STAR experiment. An atomic mass number scaling is found in the measured v1 slopes of light nuclei at mid-rapidity. For the measured v2 magnitude, a strong rapidity dependence is observed. Unlike v2 at higher collision energies, the v2 values at mid-rapidity for all light nuclei are negative and no scaling is observed with the atomic mass number. Calculations by the Jet AA Microscopic Transport Model (JAM), with baryonic mean-field plus nucleon coalescence, are in good agreement with our observations, implying baryonic interactions dominate the collective dynamics in 3 GeV Au+Au collisions at RHIC. © 2022 The Author
13 citations (Crossref) [2023-10-31] tex.art_number: 136941 tex.coden: PYLBA tex.document_type: Article tex.source: Scopus
Keywords: dept.phy; peer-reviewed

Measurement of cold nuclear matter effects for inclusive J/ψ in p+Au collisions at sNN=200 GeV - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2022)
Measurement by the STAR experiment at RHIC of the cold nuclear matter (CNM) effects experienced by inclusive J/ψ at mid-rapidity in 0-100% p+Au collisions at sNN = 200 GeV is presented. Such effects are quantified utilizing the nuclear modification factor, RpAu, obtained by taking a ratio of J/ψ yield in p+Au collisions to that in p+p collisions scaled by the number of binary nucleon-nucleon collisions. The differential J/ψ yield in both p+p and p+Au collisions is measured through the dimuon decay channel, taking advantage of the trigger capability provided by the Muon Telescope Detector in the RHIC 2015 run. Consequently, the J/ψ RpAu is derived within the transverse momentum (pT) range of 0 to 10 GeV/c. A suppression of approximately 30% is observed for pT<2 GeV/c, while J/ψ RpAu becomes compatible with unity for pT greater than 3 GeV/c, indicating the J/ψ yield is minimally affected by the CNM effects at high pT. Comparison to a similar measurement from 0-20% central Au+Au collisions reveals that the observed strong J/ψ suppression above 3 GeV/c is mostly due to the hot medium effects, providing strong evidence for the formation of the quark-gluon plasma in these collisions. Several model calculations show qualitative agreement with the measured J/ψ RpAu, while their agreement with the J/ψ yields in p+p and p+Au collisions is worse. © 2022 The Author(s)
5 citations (Crossref) [2023-10-31] tex.art_number: 136865 tex.author_keywords: Cold nuclear matter effects; J/ψ suppression; RHIC tex.coden: PYLBA tex.document_type: Article tex.source: Scopus
Keywords: dept.phy; peer-reviewed

Measurement of inclusive electrons from open heavy-flavor hadron decays in p+p collisions at s =200 GeV with the STAR detector - STAR Collaboration (Physical Review D, 2022)
We report a new measurement of the production cross section for inclusive electrons from open heavy-flavor hadron decays as a function of transverse momentum (pT) at midrapidity (|y|¡0.7) in p+p collisions at s=200 GeV. The result is presented for 2.5¡pT¡10 GeV/c with an improved precision above 6 GeV/c with respect to the previous measurements, providing more constraints on perturbative QCD calculations. Moreover, this measurement also provides a high-precision reference for measurements of nuclear modification factors for inclusive electrons from open-charm and -bottom hadron decays in heavy-ion collisions. © 2022 American Physical Society.
2 citations (Crossref) [2023-10-31] tex.art_number: 032007 tex.document_type: Article tex.source: Scopus
Keywords: dept.phy; peer-reviewed

Longitudinal double-spin asymmetry for inclusive jet and dijet production in polarized proton collisions at s =200 GeV - STAR Collaboration (Physical Review D, 2021)
We report high-precision measurements of the longitudinal double-spin asymmetry, ALL, for midrapidity inclusive jet and dijet production in polarized pp collisions at a center-of-mass energy of √s=200 GeV. The new inclusive jet data are sensitive to the gluon helicity distribution, Δg(x,Q2), for gluon momentum fractions in the range from x≃0.05 to x≃0.5, while the new dijet data provide further constraints on the x dependence of Δg(x,Q2). The results are in good agreement with previous measurements at √s=200 GeV and with recent theoretical evaluations of prior world data. Our new results have better precision and thus strengthen the evidence that Δg(x,Q2) is positive for x>0.05.
14 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Invariant jet mass measurements in pp collisions at s =200 GeV at RHIC - STAR Collaboration (Physical Review D, 2021)
We present the first inclusive measurements of the invariant and softdrop jet mass in proton-proton collisions at √s=200 GeV at STAR. The measurements are fully corrected for detector effects, and reported differentially in both the jet transverse momentum and jet radius parameter. We compare the measurements to established leading-order Monte Carlo event generators and find that STAR-tuned pythia-6 reproduces the data, while LHC tunes of pythia-8 and herwig-7 do not agree with the data, providing further constraints on parameter tuning. Finally, we observe that softdrop grooming, for which the contribution of wide-angle nonperturbative radiation is suppressed, shifts the jet mass distributions into closer agreement with the partonic jet mass as determined by both pythia-8 and a next-to-leading-logarithmic accuracy perturbative QCD calculation. These measurements complement recent LHC measurements in a different kinematic region, as well as establish a baseline for future jet mass measurements in heavy-ion collisions at RHIC.
2 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Flow and interferometry results from Au+Au collisions at sNN =4.5 GeV - STAR Collaboration (Physical Review C, 2021)
The beam energy scan (BES) program at the BNL Relativistic Heavy Ion Collider (RHIC) was extended to energies below √sNN=7.7 GeV in 2015 by successful implementation of the fixed-target mode of operation in the STAR (Solenoidal Tracker At RHIC) experiment. In this mode, ions circulate in one ring of the collider and interact with a stationary target at the entrance of the STAR time projection chamber. The first results for Au+Au collisions at √sNN=4.5 GeV are presented, demonstrating good performance of all the relevant detector subsystems in fixed-target mode. Results presented here include directed and elliptic flow of identified hadrons, and radii from pion femtoscopy. The latter, together with recent HADES results, reveal a long-sought peak structure that may be caused by the system evolving through a first-order phase transition from quark-gluon plasma to the hadronic phase. Directed and elliptic flow for pions are presented for the first time at this beam energy. Pion and proton elliptic flow show behavior which hints at constituent quark scaling, and demonstrate that a definitive conclusion will be achievable using the full statistics of the ongoing second phase of BES (BES-II). In particular, BES-II to date has recorded fixed-target data sets with two orders of magnitude more events at each of nine energies between √sNN=3.0 and 7.7 GeV.
26 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Cumulants and correlation functions of net-proton, proton, and antiproton multiplicity distributions in Au + Au collisions at energies available at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2021)
We report a systematic measurement of cumulants, Cn, for net-proton, proton, and antiproton multiplicity distributions, and correlation functions, κn, for proton and antiproton multiplicity distributions up to the fourth order in Au+Au collisions at √sNN=7.7, 11.5, 14.5, 19.6, 27, 39, 54.4, 62.4, and 200 GeV. The Cn and κn are presented as a function of collision energy, centrality and kinematic acceptance in rapidity, y, and transverse momentum, pT. The data were taken during the first phase of the Beam Energy Scan (BES) program (2010–2017) at the BNL Relativistic Heavy Ion Collider (RHIC) facility. The measurements are carried out at midrapidity (|y|< 0.5) and transverse momentum 0.4<pT<2.0GeV/c, using the STAR detector at RHIC. We observe a nonmonotonic energy dependence (√sNN = 7.7–62.4 GeV) of the net-proton C4/C2 with the significance of 3.1σ for the 0–5% central Au+Au collisions. This is consistent with the expectations of critical fluctuations in a QCD-inspired model. Thermal and transport model calculations show a monotonic variation with √sNN. For the multiparticle correlation functions, we observe significant negative values for a two-particle correlation function, κ2, of protons and antiprotons, which are mainly due to the effects of baryon number conservation. Furthermore, it is found that the four-particle correlation function, κ4, of protons plays a role in determining the energy dependence of proton C4/C1 below 19.6 GeV, which cannot be understood by the effect of baryon number conservation.
63 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Azimuthal anisotropy measurements of strange and multistrange hadrons in U+ U collisions at sNN =193 GeV at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2021)
We present systematic measurements of azimuthal anisotropy for strange and multistrange hadrons (K0s, Λ, Ξ, and Ω) and ϕ mesons at midrapidity (|y|< 1.0) in collisions of U+U nuclei at √sNN=193 GeV, recorded by the STAR detector at the Relativistic Heavy Ion Collider. Transverse momentum (pT) dependence of flow coefficients (v2, v3, and v4) is presented for minimum bias collisions and three different centrality intervals. Number of constituent quark scaling of the measured flow coefficients in U+U collisions is discussed. We also present the ratio of vn scaled by the participant eccentricity (ɛn{2}) to explore system size dependence and collectivity in U+U collisions. The magnitude of v2/ɛ2 is found to be smaller in U+U collisions than that in central Au+Au collisions contradicting naive eccentricity scaling. Furthermore, the ratios between various flow harmonics (v3/v3/22, v4/v4/22) are studied and compared with hydrodynamic and transport model calculations.
8 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Twin High-Resolution, High-Speed Imagers for the Gemini Telescopes: Instrument Description and Science Verification Results - Scott, Nicholas J.; Howell, Steve B.; Gnilka, Crystal L.; Stephens, Andrew W.; Salinas, Ricardo; Matson, Rachel A.; Furlan, Elise; Horch, Elliott P.; Everett, Mark E.; Ciardi, David R.; Mills, Dave; Quigley, Emmett A. (Frontiers in Astronomy and Space Sciences, 2021)
Two new imaging instruments, ‘Alopeke and Zorro, were designed, built, and commissioned at the Gemini-North and Gemini-South telescopes in 2018 and 2019, respectively. Here we describe them and present the results from over a year of operation. The two identical instruments are based on the legacy of the DSSI (Differential Speckle Survey Instrument) instrument, successfully used for years at the WIYN and the Gemini telescopes in Hawaii and Chile. ‘Alopeke and Zorro are dual-channel imagers having both speckle (6.7″) and “wide-field” (∼1 arcminute) field-of-view options. They were built to primarily perform speckle interferometry providing diffraction-limited imagery at optical wavebands, yielding pixel scale uncertainties of ±0.21 mas, position angle uncertainties of ±0.7◦, and photometric uncertainties of Δm ± 0.02–0.04 magnitudes (for the blue and red channels, respectively) when run through the standard data reduction pipeline. One of their main scientific roles is the validation and characterization of exoplanets and their host stars as discovered by transit surveys such as the NASA Kepler, K2, and TESS missions. The limiting magnitude for speckle observations at Gemini can be quite faint (r ∼18 in good observing conditions) but typically the observed targets are brighter. The instruments can also function as conventional CCD imagers providing a 1 arc-minute field of view and allowing simultaneous two-color, high-speed time-series operation. These resident visitor instruments are remotely operable and are available for use by the community via the peer-reviewed proposal process.
50 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

A Comprehensive Astrometric Calibration of HST's WFPC2. I. Distortion Mapping - Casetti-Dinescu, Dana I.; Girard, Terrence M.; Kozhurina-Platais, Vera; Platais, Imants; Anderson, Jay; Horch, Elliott P. (Publications of the Astronomical Society of the Pacific, 2021)
Wide field planetary camera 2 (WFPC2) exposures are already some 20 years older than Gaia epoch observations, or future James Webb Space Telescope observations. As such, they offer an unprecedented time baseline for high-precision proper-motion studies, provided the full astrometric potential of these exposures is reached. We have started such a project with the work presented here being its first step. We explore geometric distortions beyond the well-known ones published in the early 2000 s. This task is accomplished by using the entire database of WFPC2 exposures in filters F555W, F606W and F814W and three standard astrometric catalogs: Gaia EDR3, 47 Tuc and ωCen. The latter two were constructed using Hubble Space Telescope observations made with cameras other than WFPC2. We explore a suite of centering algorithms, and various distortion maps in order to understand and quantify their performance. We find no high-frequency systematics beyond the 34th-row correction, down to a resolution of 10 pixels. Low-frequency systematics starting at a resolution of 50 pixels are present at a level of 30–50 millipix (1.4–2.3 mas) for the PC and 20–30 millipix (2–3 mas) for the WF chips. We characterize these low-frequency systematics by providing correction maps and updated cubic-distortion coefficients for each filter.
3 citations (Crossref) [2023-10-31]
Keywords: dept.mat; dept.phy; peer-reviewed

Dissecting the Quadruple Binary Hyad vA 351 Masses for Three M Dwarfs and a White Dwarf\ast - Benedict, G. Fritz; Franz, Otto G.; Horch, Elliott P.; Prato, L.; Torres, Guillermo; McArthur, Barbara E.; Wasserman, Lawrence H.; Latham, David W.; Stefanik, Robert P.; Latham, Christian; Skiff, Brian A. (The Astronomical Journal, 2021)
We extend results first announced by Franz et al., that identified vA 351 = H346 in the Hyades as a multiple star system containing a white dwarf. With Hubble Space Telescope Fine Guidance Sensor fringe tracking and scanning, and more recent speckle observations, all spanning 20.7 years, we establish a parallax, relative orbit, and mass fraction for two components, with a period, and total mass 2.1 . With ground-based radial velocities from the McDonald Observatory Otto Struve 2.1 m Telescope Sandiford Spectrograph, and Center for Astrophysics Digital Speedometers, spanning 37 years, we find that component B consists of BC, two M dwarf stars orbiting with a very short period ( days), having a mass ratio / = 0.95. We confirm that the total mass of the system can only be reconciled with the distance and component photometry by including a fainter, higher-mass component. The quadruple system consists of three M dwarfs (A, B, C) and one white dwarf (D). We determine individual M dwarf masses = 0.53 ± 0.10 , = 0.43 ± 0.04 , and = 0.41 ± 0.04 . The white dwarf mass, 0.54 ± 0.04 , comes from cooling models, an assumed Hyades age of 670 Myr, and consistency with all previous and derived astrometric, photometric, and radial velocity results. Velocities from Hα and He i emission lines confirm the BC period derived from absorption lines, with similar (He i) and higher (Hα) velocity amplitudes. We ascribe the larger Hα amplitude to emission from a region each component shadows from the other, depending on the line of sight.
1 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Measurement of transverse single-spin asymmetries of π 0 and electromagnetic jets at forward rapidity in 200 and 500 GeV transversely polarized proton-proton collisions - STAR Collaboration (Physical Review D, 2021)
The STAR Collaboration reports measurements of the transverse single-spin asymmetry (TSSA) of inclusive π0 at center-of-mass energies (√s) of 200 GeV and 500 GeV in transversely polarized proton-proton collisions in the pseudo-rapidity region 2.7 to 4.0. The results at the two different energies show a continuous increase of the TSSA with Feynman-x, and, when compared to previous measurements, no dependence on √s from 19.4 GeV to 500 GeV is found. To investigate the underlying physics leading to this large TSSA, different topologies have been studied. π0 with no nearby particles tend to have a higher TSSA than inclusive π0. The TSSA for inclusive electromagnetic jets, sensitive to the Sivers effect in the initial state, is substantially smaller, but shows the same behavior as the inclusive π0 asymmetry as a function of Feynman-x. To investigate final-state effects, the Collins asymmetry of π0 inside electromagnetic jets has been measured. The Collins asymmetry is analyzed for its dependence on the π0 momentum transverse to the jet thrust axis and its dependence on the fraction of jet energy carried by the π0. The asymmetry was found to be small in each case for both center-of-mass energies. All the measurements are compared to QCD-based theoretical calculations for transverse-momentum-dependent parton distribution functions and fragmentation functions. Some discrepancies are found, which indicates new mechanisms might be involved.
14 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Comparison of transverse single-spin asymmetries for forward π0 production in polarized pp, pAl and pAu collisions at nucleon pair c.m. energy sNN =200 GeV - STAR Collaboration (Physical Review D, 2021)
The STAR collaboration reports a measurement of the transverse single-spin asymmetries, AN, for neutral pions produced in polarized proton collisions with protons (pp), with aluminum nuclei (pAl) and with gold nuclei (pAu) at a nucleon-nucleon center-of-mass energy of 200 GeV. Neutral pions are observed in the forward direction relative to the transversely polarized proton beam, in the pseudorapidity region 2.7<η<3.8. Results are presented for π0s observed in the STAR forward meson spectrometer electromagnetic calorimeter in narrow Feynman x (xF) and transverse momentum (pT) bins, spanning the range 0.17<xF<0.81 and 1.7<pT<6.0 GeV/c. For fixed xF<0.47, the asymmetries are found to rise with increasing transverse momentum. For larger xF, the asymmetry flattens or falls as pT increases. Parametrizing the ratio r(A)≡AN(pA)/AN(pp)=AP over the kinematic range, the ratio r(A) is found to depend only weakly on A, with ⟨P⟩=−0.027±0.005. No significant difference in P is observed between the low-pT region, pT<2.5 GeV/c, where gluon saturation effects may play a role, and the high-pT region, pT>2.5 GeV/c. It is further observed that the value of AN is significantly larger for events with a large-pT isolated π0 than for events with a nonisolated π0 accompanied by additional jetlike fragments. The nuclear dependence r(A) is similar for isolated and nonisolated π0 events.
8 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Intraoperative detection of human meningioma using a handheld visible resonance Raman analyzer. - Zhang, Liang; Zhou, Yan; Wu, Binlin; Zhang, Shengjia; Zhu, Ke; Liu, Cheng-hui; Yu, Xinguang; Alfano, Robert R. (Lasers in medical science, 2021)
8 citations (Crossref) [2023-10-31] https://pubmed.ncbi.nlm.nih.gov/34365551/
Keywords: dept.phy; peer-reviewed

Classifying breast cancer cell lines of different metastasis potentials using visible resonance raman spectroscopy and machine learning - Wu, Binlin; Zhang, Lin; Jimenez, Kenneth; Boydston-White, Susie; Wang, Eric; Liu, Cheng-hui; Alfano, Robert R. (Conference on lasers and electro-optics, 2021)
0 citations (Crossref) [2023-10-31]
Keywords: Breast cancer cells; Cancer cell lines; Cell culture; Cells; Classification accuracy; Classifieds; Diseases; Machine-learning; Metastatic potential; Principal component analysis; Principal-component analysis; Raman spectroscopy; Resonance Raman spectroscopy; Support vector machines; Support vectors machine; dept.phy

Investigation of experimental observables in search of the chiral magnetic effect in heavy-ion collisions in the STAR experiment - Choudhury, S.; Dong, X.; Drachenberg, J. L.; Dunlop, J. C.; Esumi, ShinIchi; Feng, Yicheng; Finch, E.; Hu, Yu; Jia, Jiangyong; Lauret, Jerome; Li, Wei; Liao, Jinfeng; et al. (Chinese Physics C, 2022)
The chiral magnetic effect (CME) is a novel transport phenomenon, arising from the interplay between quantum anomalies and strong magnetic fields in chiral systems. In high-energy nuclear collisions, the CME may survive the expansion of the quark-gluon plasma fireball and be detected in experiments. Over the past two decades, experimental searches for the CME have attracted extensive interest at the Relativistic Heavy Ion Collider (RHIC) and the Large Hadron Collider (LHC). The main goal of this study is to investigate three pertinent experimental approaches: the correlator, the R correlator, and the signed balance functions. We exploit simple Monte Carlo simulations and a realistic event generator (EBE-AVFD) to verify the equivalence of the core components among these methods and to ascertain their sensitivities to the CME signal and the background contributions for the isobar collisions at the RHIC. © 2022 Chinese Physical Society and the Institute of High Energy Physics of the Chinese Academy of Sciences and the Institute of Modern Physics of the Chinese Academy of Sciences and IOP Publishing Ltd.
11 citations (Crossref) [2023-10-31] https://iopscience.iop.org/article/10.1088/1674-1137/ac2a1f ; http://hepnp.ihep.ac.cn/article/id/55afc331-6758-45b3-97ce-444828b72c70 ; http://cpc.ihep.ac.cn/article/doi/10.1088/1674-1137/ac2a1f ; http://csnsdoc.ihep.ac.cn/article/doi/10.1088/1674-1137/ac2a1f ; https://inspirehep.net/literature/1863127
Keywords: dept.phy; peer-reviewed

Selected topics in electronics and systems - nanotechnology for electronics, biosensors, additive manufacturing and emerging systems applications - Jain, F; Broadbridge, Christine; Gherasimova, M; Tang, H (WORLD SCIENTIFIC, 2021)
Keywords: dept.phy

HAT-P-58b – HAT-P-64b: Seven planets transiting bright stars - Bakos, G. Á.; Hartman, Joel D.; Bhatti, Waqas; Csubry, Z.; Penev, Kaloyan; Bieryla, Allyson; Latham, D. W.; Quinn, S. N.; Buchhave, Lars A.; Kovács, Gábor L.; Torres, Guillermo; Noyes, R. W.; et al. (The Astronomical Journal, 2021)
We report the discovery and characterization of seven transiting exoplanets from the HATNet survey. The planets, which are hot Jupiters and Saturns transiting bright Sun-like stars, include: HAT-P-58b (with mass M p = 0.37 M J, radius R p = 1.33 R J, and orbital period P = 4.0138 days), HAT-P-59b (M p = 1.54 M J, R p = 1.12 R J, P = 4.1420 days), HAT-P-60b (M p = 0.57 M J, R p = 1.63 R J, P = 4.7948 days), HAT-P-61b (M p = 1.06 M J, R p = 0.90 R J, P = 1.9023 days), HAT-P-62b (M p = 0.76 M J, R p = 1.07 R J, P = 2.6453 days), HAT-P-63b (M p = 0.61 M J, R p = 1.12 R J, P = 3.3777 days), and HAT-P-64b (M p = 0.58 M J, R p = 1.70 R J, P = 4.0072 days). The typical errors on these quantities are 0.06 M J, 0.03 R J, and 0.2 s, respectively. We also provide accurate stellar parameters for each of the host stars. With V = 9.710 0.050 mag, HAT-P-60 is an especially bright transiting planet host, and an excellent target for additional follow-up observations. With R p = 1.703 0.070 R J, HAT-P-64b is a highly inflated hot Jupiter around a star nearing the end of its main-sequence lifetime, and is among the largest known planets. Five of the seven systems have long-cadence observations by TESS which are included in the analysis. Of particular note is HAT-P-59 (TOI-1826.01) which is within the northern continuous viewing zone of the TESS mission, and HAT-P-60, which is the TESS candidate TOI-1580.01. © 2021. The American Astronomical Society. All rights reserved..
5 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Observations with the differential speckle survey instrument. X. Preliminary orbits of k-dwarf binaries and other stars - Horch, Elliott P.; Broderick, Kyle G.; Casetti-Dinescu, Dana I.; Henry, Todd J.; Fekel, Francis C.; Muterspaugh, Matthew W.; Willmarth, Daryl W.; Winters, Jennifer G.; van Belle, Gerard T.; Clark, Catherine; Everett, Mark E. (The Astronomical Journal, 2021)
This paper details speckle observations of binary stars taken at the Lowell Discovery Telescope, the WIYN telescope, and the Gemini telescopes between 2016 January and 2019 September. The observations taken at Gemini and Lowell were done with the Differential Speckle Survey Instrument (DSSI), and those done at WIYN were taken with the successor instrument to DSSI at that site, the NN-EXPLORE Exoplanet Star and Speckle Imager (NESSI). In total, we present 378 observations of 178 systems, and we show that the uncertainty in the measurement precision for the combined data set is ∼2 mas in separation, ∼1°-2° in position angle depending on the separation, and ∼0.1 mag in magnitude difference. Together with data already in the literature, these new results permit 25 visual orbits and one spectroscopic-visual orbit to be calculated for the first time. In the case of the spectroscopic-visual analysis, which is done on the ternary star HD 173093, we calculate masses with a precision of better than 1% for all three stars in that system. Twenty-one of the visual orbits calculated have a K dwarf as the primary star; we add these to the known orbits of K-dwarf primary stars and discuss the basic orbital properties of these stars at this stage. Although incomplete, the data that exist so far indicate that binaries with K-dwarf primaries tend not to have low-eccentricity orbits at separations of one to a few tens of astronomical units, that is, on solar system scales. © 2021 Institute of Physics Publishing. All rights reserved.
6 citations (Crossref) [2023-10-31] https://par.nsf.gov/biblio/10296367-observations-differential-speckle-survey-instrument-preliminary-orbits-dwarf-binaries-other-stars ; https://ui.adsabs.harvard.edu/abs/2021AJ....161..295H/abstract ;
Keywords: dept.phy; peer-reviewed

Methods for a blind analysis of isobar data collected by the STAR collaboration - STAR Collaboration (Nuclear Science and Techniques, 2021)
21 citations (Crossref) [2023-10-31]
Keywords: Au+Au collisions; Calculating efficiencies; Colliding beam accelerators; Data challenges; Germanium compounds; Gold; Magnetic effects; Nitrogen compounds; Quality assurance; Quality control; Ruthenium compounds; Species specifics; Stars; Time dependent; Time-dependent changes; Tuning analysis; Zirconium compounds; dept.phy; peer-reviewed

The same frequency of planets inside and outside open clusters of stars. - Meibom, Soren; Torres, Guillermo; Fressin, Francois; Latham, David; Rowe, Jason; Ciardi, David; Bryson, Steven; Rogers, Leslie; Henze, Christopher; Janes, Kenneth; Barnes, Sydney; Marcy, Geoffrey; et al. (Nature, 2013)
: Most stars and their planets form in open clusters. Over 95 per cent of such clusters have stellar densities too low (less than a hundred stars per cubic parsec) to withstand internal and external dynamical stresses and fall apart within a few hundred million years 1. Older open clusters have survived by virtue of being richer and denser in stars (1,000 to 10,000 per cubic parsec) when they formed. Such clusters represent a stellar environment very different from the birthplace of the Sun and other planet-hosting field stars. So far more than 800 planets have been found around Sun-like stars in the field 2. The field planets are usually the size of Neptune or smaller 3,4,5. In contrast, only four planets have been found orbiting stars in open clusters 6,7,8, all with masses similar to or greater than that of Jupiter. Here we report observations of the transits of two Sun-like stars by planets smaller than Neptune in the billion-year-old open cluster NGC6811. This demonstrates that small planets can form and survive in a dense cluster environment, and implies that the frequency and properties of planets in open clusters are consistent with those of planets around field stars in the Galaxy., (C) 2013 Nature Publishing Group
84 citations (Crossref) [2023-10-31] Place: (C) 2013 Nature Publishing Group
Keywords: Jupiter; Neptune; article; astronomy; cluster analysis; dept.phy; environment; frequency analysis; planet; priority journal; simulation; sun; velocity

Fluctuation-driven selection at criticality in a frustrated magnetic system: the case of multiple-k partial order on the pyrochlore lattice. - Javanparast, Behnam; Hao, Zhihao; Enjalran, Matthew; Gingras, Michel J P (Physical review letters, 2015)
We study the problem of partially ordered phases with periodically arranged disordered (paramagnetic) sites on the pyrochlore lattice, a network of corner-sharing tetrahedra. The periodicity of these phases is characterized by one or more wave vectors k={1/21/21/2}. Starting from a general microscopic Hamiltonian including anisotropic nearest-neighbor exchange, long-range dipolar interactions, and second- and third-nearest neighbor exchange, we use standard mean-field theory (SMFT) to identify an extended range of interaction parameters that support partially ordered phases. We demonstrate that thermal fluctuations ignored in SMFT are responsible for the selection of one particular partially ordered phase, e.g., the "4-k" phase over the "1-k" phase. We suggest that the transition into the 4-k phase is continuous with its critical properties controlled by the cubic fixed point of a Ginzburg-Landau theory with a four-component vector order parameter. By combining an extension of the Thouless-Anderson-Palmer method originally used to study fluctuations in spin glasses with parallel-tempering Monte Carlo simulations, we establish the phase diagram for different types of partially ordered phases. Our results elucidate the long-standing puzzle concerning the origin of the 4-k partially ordered phase observed in the Gd2Ti2O7 dipolar pyrochlore antiferromagnet below its paramagnetic phase transition temperature.
21 citations (Crossref) [2023-10-31] Place: United States Javanparast, Behnam. Department of Physics and Astronomy, University of Waterloo, Waterloo, Ontario N2L 3G1, Canada. Hao, Zhihao. Department of Physics and Astronomy, University of Waterloo, Waterloo, Ontario N2L 3G1, Canada. Enjalran, Matthew. Physics Department, Southern Connecticut State University, 501 Crescent Street, New Haven, Connecticut 06515-1355, USA. Gingras, Michel J P. Department of Physics and Astronomy, University of Waterloo, Waterloo, Ontario N2L 3G1, Canada. Gingras, Michel J P. Canadian Institute for Advanced Research, 180 Dundas Street West, Toronto, Ontario M5G 1Z8, Canada. Gingras, Michel J P. Perimeter Institute for Theoretical Physics, 31 Caroline Street North, Waterloo, Ontario N2L 2Y5, Canada.
Keywords: Corner-sharing tetrahedra; Crystal lattices; Ginzburg Landau theory; Hamiltonians; Intelligent systems; Interaction parameters; Mean field theory; Microscopic hamiltonians; Monte Carlo methods; Parallel tempering Monte Carlo simulations; Paramagnetic phase transitions; Paramagnetism; Phase diagrams; Spin fluctuations; Thermal fluctuations; Vector order parameter; dept.phy

Global [LAMBDA] hyperon polarization in nuclear collisions. - STAR Collaboration (Nature, 2017)
: The measurement of an alignment between the angular momentum of a non-central collision between heavy ions and the spin of emitted particles reveals that the fluid produced in the collision is extremely vortical., The extreme energy densities generated by ultra-relativistic collisions between heavy atomic nuclei produce a state of matter that behaves surprisingly like a fluid, with exceptionally high temperature and low viscosity 1. Non-central collisions have angular momenta of the order of 1,000h, and the resulting fluid may have a strong vortical structure 2,3,4 that must be understood to describe the fluid properly. The vortical structure is also of particular interest because the restoration of fundamental symmetries of quantum chromodynamics is expected to produce novel physical effects in the presence of strong vorticity 5. However, no experimental indications of fluid vorticity in heavy ion collisions have yet been found. Since vorticity represents a local rotational structure of the fluid, spin-orbit coupling can lead to preferential orientation of particle spins along the direction of rotation. Here we present measurements of an alignment between the global angular momentum of a non-central collision and the spin of emitted particles (in this case the collision occurs between gold nuclei and produces [LAMBDA] baryons), revealing that the fluid produced in heavy ion collisions is the most vortical system so far observed. (At high energies, this fluid is a quark-gluon plasma.) We find that [LAMBDA] and Symbol hyperons show a positive polarization of the order of a few per cent, consistent with some hydrodynamic predictions 6. (A hyperon is a particle composed of three quarks, at least one of which is a strange quark; the remainder are up and down quarks, found in protons and neutrons.) A previous measurement 7 that reported a null result, that is, zero polarization, at higher collision energies is seen to be consistent with the trend of our observations, though with larger statistical uncertainties. These data provide experimental access to the vortical structure of the nearly ideal liquid 8 created in a heavy ion collision and should prove valuable in the development of hydrodynamic models that quantitatively connect observations to the theory of the strong force., (C) 2017 Nature Publishing Group
512 citations (Crossref) [2023-10-31] Place: (C) 2017 Nature Publishing Group
Keywords: dept.phy

Combinatorial Strategies for Synthesis and Characterization of Alloy Microstructures over Large Compositional Ranges. - Li, Yanglin; Jensen, Katharine E; Liu, Yanhui; Liu, Jingbei; Gong, Pan; Scanley, B Ellen; Broadbridge, Christine C; Schroers, Jan (ACS combinatorial science, 2016)
The exploration of new alloys with desirable properties has been a long-standing challenge in materials science because of the complex relationship between composition and microstructure. In this Research Article, we demonstrate a combinatorial strategy for the exploration of composition dependence of microstructure. This strategy is comprised of alloy library synthesis followed by high-throughput microstructure characterization. As an example, we synthesized a ternary Au-Cu-Si composition library containing over 1000 individual alloys using combinatorial sputtering. We subsequently melted and resolidified the entire library at controlled cooling rates. We used scanning optical microscopy and X-ray diffraction mapping to explore trends in phase formation and microstructural length scale with composition across the library. The integration of combinatorial synthesis with parallelizable analysis methods provides a efficient method for examining vast compositional ranges. The availability of microstructures from this vast composition space not only facilitates design of new alloys by controlling effects of composition on phase selection, phase sequence, length scale, and overall morphology, but also will be instrumental in understanding the complex process of microstructure formation in alloys.
19 citations (Crossref) [2023-10-31] Place: United States Li, Yanglin. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Li, Yanglin. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States. Jensen, Katharine E. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States. Liu, Yanhui. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Liu, Yanhui. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States. Liu, Jingbei. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Liu, Jingbei. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States. Gong, Pan. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States. Scanley, B Ellen. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Scanley, B Ellen. Department of Physics, Southern Connecticut State University, New Haven, Connecticut 06515, United States. Broadbridge, Christine C. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Broadbridge, Christine C. Department of Physics, Southern Connecticut State University, New Haven, Connecticut 06515, United States. Schroers, Jan. Center for Research on Interface Structures and Phenomena, Yale University, New Haven, Connecticut 06511, United States. Schroers, Jan. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut 06511, United States.
Keywords: *Alloys/ch [Chemistry]; *Combinatorial Chemistry Techniques/mt [Methods]; *Copper/ch [Chemistry]; *Gold/ch [Chemistry]; *Silicon/ch [Chemistry]; Alloys; Combinatorial Chemistry Techniques; Copper; Gold; High-Throughput Screening Assays; Materials Testing; Physical Phenomena; Silicon; alloy; alloy microstructure; chemistry; combinatorial chemistry; combinatorial materials science; copper; dept.phy; gold; high throughput screening; high-throughput; materials testing; phase mapping; physical phenomena; procedures; silicon

Charge-Dependent Directed Flow in Cu+Au Collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2017)
We present the first measurement of charge-dependent directed flow in Cu+Au collisions at sNN=200 GeV. The results are presented as a function of the particle transverse momentum and pseudorapidity for different centralities. A finite difference between the directed flow of positive and negative charged particles is observed that qualitatively agrees with the expectations from the effects of the initial strong electric field between two colliding ions with different nuclear charges. The measured difference in directed flow is much smaller than that obtained from the parton-hadron-string-dynamics model, which suggests that most of the electric charges, i.e., quarks and antiquarks, have not yet been created during the lifetime of the strong electric field, which is of the order of, or less than, 1 fm/c. © 2017 American Physical Society.
17 citations (Crossref) [2023-10-31]
Keywords: Antiquarks; Charged particles; Colliding beam accelerators; Directed flow; Dynamics modeling; Electric fields; Nuclear charges; Pseudorapidities; Strong electric fields; Transverse momenta; dept.phy

Dijet imbalance measurements in Au+Au and pp collisions at sNN =200 GeV at STAR - STAR Collaboration (Physical Review Letters, 2017)
We report the first dijet transverse momentum asymmetry measurements from Au+Au and pp collisions at RHIC. The two highest-energy back-to-back jets reconstructed from fragments with transverse momenta above 2 GeV/c display a significantly higher momentum imbalance in heavy-ion collisions than in the pp reference. When reexamined with correlated soft particles included, we observe that these dijets then exhibit a unique new feature - momentum balance is restored to that observed in pp for a jet resolution parameter of R=0.4, while rebalancing is not attained with a smaller value of R=0.2. © 2017 American Physical Society.
18 citations (Crossref) [2023-10-31]
Keywords: Asymmetry measurements; Colliding beam accelerators; Germanium compounds; Gold compounds; Heavy ion collision; Heavy ions; Momentum; Momentum balances; Pp collisions; Rebalancing; Resolution parameters; Soft particles; Transverse momenta; dept.phy

Beam-Energy Dependence of Directed Flow of Λ, Λ , K±, Ks0, and φ in Au+Au Collisions - STAR Collaboration (Physical Review Letters, 2018)
Rapidity-odd directed-flow measurements at midrapidity are presented for Λ, Λ, K±, Ks0, and φ at sNN=7.7, 11.5, 14.5, 19.6, 27, 39, 62.4, and 200 GeV in Au+Au collisions recorded by the Solenoidal Tracker detector at the Relativistic Heavy Ion Collider. These measurements greatly expand the scope of data available to constrain models with differing prescriptions for the equation of state of quantum chromodynamics. Results show good sensitivity for testing a picture where flow is assumed to be imposed before hadron formation and the observed particles are assumed to form via coalescence of constituent quarks. The pattern of departure from a coalescence-inspired sum rule can be a valuable new tool for probing the collision dynamics. © 2018 authors. Published by the American Physical Society.
62 citations (Crossref) [2023-10-31]
Keywords: Au+Au collisions; Beam energies; Colliding beam accelerators; Collision dynamics; Directed flow; Elementary particles; Equation of state; Equations of state; Germanium compounds; Gold compounds; Heavy ions; High energy physics; Quantum chromodynamics; Quantum theory; Relativistic Heavy Ion Collider; Tracker detector; dept.phy; peer-reviewed

Polarization of Λ (Λ ̄) Hyperons along the Beam Direction in Au+Au Collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2019)
The Λ (Λ̄) hyperon polarization along the beam direction has been measured in Au+Au collisions at sNN=200 GeV, for the first time in heavy-ion collisions. The polarization dependence on the hyperons' emission angle relative to the elliptic flow plane exhibits a second harmonic sine modulation, indicating a quadrupole pattern of the vorticity component along the beam direction, expected due to elliptic flow. The polarization is found to increase in more peripheral collisions, and shows no strong transverse momentum (pT) dependence at pT greater than 1 GeV/c. The magnitude of the signal is about 5 times smaller than those predicted by hydrodynamic and multiphase transport models; the observed phase of the emission angle dependence is also opposite to these model predictions. In contrast, the kinematic vorticity calculations in the blast-wave model tuned to reproduce particle spectra, elliptic flow, and the azimuthal dependence of the Gaussian source radii measured with the Hanbury Brown-Twiss intensity interferometry technique reproduce well the modulation phase measured in the data and capture the centrality and transverse momentum dependence of the polarization signal. © 2019 American Physical Society.
100 citations (Crossref) [2023-10-31]
Keywords: Azimuthal dependence; Colliding beam accelerators; Emission angle dependence; Gaussian beams; Heavy ion collision; Heavy ions; Hyperon polarization; Interferometry; Interferometry technique; Modulation; Multiphase transport; Polarization; Polarization dependence; Polarization signals; Vorticity; dept.phy; peer-reviewed

Low- p T e + e − Pair Production in Au + Au Collisions at √ s N N = 200 GeV and U + U Collisions at √ s N N = 193 GeV at STAR - STAR Collaboration (Physical Review Letters, 2018)
We report first measurements of e{+}e{-} pair production in the mass region 0.4
52 citations (Crossref) [2023-10-31] Place: United States Adam, J. Creighton University, Omaha, Nebraska 68178. Adamczyk, L. AGH University of Science and Technology, FPACS, Cracow 30-059, Poland. Adams, J R. Ohio State University, Columbus, Ohio 43210. Adkins, J K. University of Kentucky, Lexington, Kentucky 40506-0055. Agakishiev, G. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Aggarwal, M M. Panjab University, Chandigarh 160014, India. Ahammed, Z. Variable Energy Cyclotron Centre, Kolkata 700064, India. Ajitanand, N N. State University of New York, Stony Brook, New York 11794. Alekseev, I. Alikhanov Institute for Theoretical and Experimental Physics, Moscow 117218, Russia. Alekseev, I. National Research Nuclear University MEPhI, Moscow 115409, Russia. Anderson, D M. Texas A&M University, College Station, Texas 77843. Aoyama, R. University of Tsukuba, Tsukuba, Ibaraki 305-8571, Japan. Aparin, A. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Arkhipkin, D. Brookhaven National Laboratory, Upton, New York 11973. Aschenauer, E C. Brookhaven National Laboratory, Upton, New York 11973. Ashraf, M U. Tsinghua University, Beijing 100084. Atetalla, F. Kent State University, Kent, Ohio 44242. Attri, A. Panjab University, Chandigarh 160014, India. Averichev, G S. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Bai, X. Central China Normal University, Wuhan, Hubei 430079. Bairathi, V. National Institute of Science Education and Research, HBNI, Jatni 752050, India. Barish, K. University of California, Riverside, California 92521. Bassill, A J. University of California, Riverside, California 92521. Behera, A. State University of New York, Stony Brook, New York 11794. Bellwied, R. University of Houston, Houston, Texas 77204. Bhasin, A. University of Jammu, Jammu 180001, India. Bhati, A K. Panjab University, Chandigarh 160014, India. Bielcik, J. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Bielcikova, J. Nuclear Physics Institute AS CR, Prague 250 68, Czech Republic. Bland, L C. Brookhaven National Laboratory, Upton, New York 11973. Bordyuzhin, I G. Alikhanov Institute for Theoretical and Experimental Physics, Moscow 117218, Russia. Brandenburg, J D. Rice University, Houston, Texas 77251. Brandin, A V. National Research Nuclear University MEPhI, Moscow 115409, Russia. Brown, D. Lehigh University, Bethlehem, Pennsylvania 18015. Bryslawskyj, J. University of California, Riverside, California 92521. Bunzarov, I. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Butterworth, J. Rice University, Houston, Texas 77251. Caines, H. Yale University, New Haven, Connecticut 06520. Calderon de la Barca Sanchez, M. University of California, Davis, California 95616. Campbell, J M. Ohio State University, Columbus, Ohio 43210. Cebra, D. University of California, Davis, California 95616. Chakaberia, I. Brookhaven National Laboratory, Upton, New York 11973. Chakaberia, I. Kent State University, Kent, Ohio 44242. Chakaberia, I. Shandong University, Jinan, Shandong 250100. Chaloupka, P. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Chang, F-H. National Cheng Kung University, Tainan 70101. Chang, Z. Brookhaven National Laboratory, Upton, New York 11973. Chankova-Bunzarova, N. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Chatterjee, A. Variable Energy Cyclotron Centre, Kolkata 700064, India. Chattopadhyay, S. Variable Energy Cyclotron Centre, Kolkata 700064, India. Chen, J H. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Chen, X. University of Science and Technology of China, Hefei, Anhui 230026. Chen, X. Institute of Modern Physics, Chinese Academy of Sciences, Lanzhou, Gansu 730000. Cheng, J. Tsinghua University, Beijing 100084. Cherney, M. Creighton University, Omaha, Nebraska 68178. Christie, W. Brookhaven National Laboratory, Upton, New York 11973. Contin, G. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Crawford, H J. University of California, Berkeley, California 94720. Das, S. Central China Normal University, Wuhan, Hubei 430079. Dedovich, T G. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Deppner, I M. University of Heidelberg, Heidelberg 69120, Germany. Derevschikov, A A. Institute of High Energy Physics, Protvino 142281, Russia. Didenko, L. Brookhaven National Laboratory, Upton, New York 11973. Dilks, C. Pennsylvania State University, University Park, Pennsylvania 16802. Dong, X. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Drachenberg, J L. Lamar University, Beaumont, Texas 77710. Dunlop, J C. Brookhaven National Laboratory, Upton, New York 11973. Efimov, L G. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Elsey, N. Wayne State University, Detroit, Michigan 48201. Engelage, J. University of California, Berkeley, California 94720. Eppley, G. Rice University, Houston, Texas 77251. Esha, R. University of California, Los Angeles, California 90095. Esumi, S. University of Tsukuba, Tsukuba, Ibaraki 305-8571, Japan. Evdokimov, O. University of Illinois at Chicago, Chicago, Illinois 60607. Ewigleben, J. Lehigh University, Bethlehem, Pennsylvania 18015. Eyser, O. Brookhaven National Laboratory, Upton, New York 11973. Fatemi, R. University of Kentucky, Lexington, Kentucky 40506-0055. Fazio, S. Brookhaven National Laboratory, Upton, New York 11973. Federic, P. Nuclear Physics Institute AS CR, Prague 250 68, Czech Republic. Federicova, P. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Fedorisin, J. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Filip, P. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Finch, E. Southern Connecticut State University, New Haven, Connecticut 06515. Fisyak, Y. Brookhaven National Laboratory, Upton, New York 11973. Flores, C E. University of California, Davis, California 95616. Fulek, L. AGH University of Science and Technology, FPACS, Cracow 30-059, Poland. Gagliardi, C A. Texas A&M University, College Station, Texas 77843. Galatyuk, T. Technische Universitat Darmstadt, Darmstadt 64289, Germany. Geurts, F. Rice University, Houston, Texas 77251. Gibson, A. Valparaiso University, Valparaiso, Indiana 46383. Grosnick, D. Valparaiso University, Valparaiso, Indiana 46383. Gunarathne, D S. Temple University, Philadelphia, Pennsylvania 19122. Guo, Y. Kent State University, Kent, Ohio 44242. Gupta, A. University of Jammu, Jammu 180001, India. Guryn, W. Brookhaven National Laboratory, Upton, New York 11973. Hamad, A I. Kent State University, Kent, Ohio 44242. Hamed, A. Texas A&M University, College Station, Texas 77843. Harlenderova, A. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Harris, J W. Yale University, New Haven, Connecticut 06520. He, L. Purdue University, West Lafayette, Indiana 47907. Heppelmann, S. Pennsylvania State University, University Park, Pennsylvania 16802. Heppelmann, S. University of California, Davis, California 95616. Herrmann, N. University of Heidelberg, Heidelberg 69120, Germany. Hirsch, A. Purdue University, West Lafayette, Indiana 47907. Holub, L. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Horvat, S. Yale University, New Haven, Connecticut 06520. Huang, X. Tsinghua University, Beijing 100084. Huang, B. University of Illinois at Chicago, Chicago, Illinois 60607. Huang, S L. State University of New York, Stony Brook, New York 11794. Huang, H Z. University of California, Los Angeles, California 90095. Huang, T. National Cheng Kung University, Tainan 70101. Humanic, T J. Ohio State University, Columbus, Ohio 43210. Huo, P. State University of New York, Stony Brook, New York 11794. Igo, G. University of California, Los Angeles, California 90095. Jacobs, W W. Indiana University, Bloomington, Indiana 47408. Jentsch, A. University of Texas, Austin, Texas 78712. Jia, J. Brookhaven National Laboratory, Upton, New York 11973. Jia, J. State University of New York, Stony Brook, New York 11794. Jiang, K. University of Science and Technology of China, Hefei, Anhui 230026. Jowzaee, S. Wayne State University, Detroit, Michigan 48201. Judd, E G. University of California, Berkeley, California 94720. Kabana, S. Kent State University, Kent, Ohio 44242. Kalinkin, D. Indiana University, Bloomington, Indiana 47408. Kang, K. Tsinghua University, Beijing 100084. Kapukchyan, D. University of California, Riverside, California 92521. Kauder, K. Wayne State University, Detroit, Michigan 48201. Ke, H W. Brookhaven National Laboratory, Upton, New York 11973. Keane, D. Kent State University, Kent, Ohio 44242. Kechechyan, A. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Kikola, D P. Warsaw University of Technology, Warsaw 00-661, Poland. Kim, C. University of California, Riverside, California 92521. Kinghorn, T A. University of California, Davis, California 95616. Kisel, I. Frankfurt Institute for Advanced Studies FIAS, Frankfurt 60438, Germany. Kisiel, A. Warsaw University of Technology, Warsaw 00-661, Poland. Klein, S R. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Kochenda, L. National Research Nuclear University MEPhI, Moscow 115409, Russia. Kosarzewski, L K. Warsaw University of Technology, Warsaw 00-661, Poland. Kraishan, A F. Temple University, Philadelphia, Pennsylvania 19122. Kramarik, L. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Krauth, L. University of California, Riverside, California 92521. Kravtsov, P. National Research Nuclear University MEPhI, Moscow 115409, Russia. Krueger, K. Argonne National Laboratory, Argonne, Illinois 60439. Kulathunga, N. University of Houston, Houston, Texas 77204. Kumar, S. Panjab University, Chandigarh 160014, India. Kumar, L. Panjab University, Chandigarh 160014, India. Kvapil, J. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Kwasizur, J H. Indiana University, Bloomington, Indiana 47408. Lacey, R. State University of New York, Stony Brook, New York 11794. Landgraf, J M. Brookhaven National Laboratory, Upton, New York 11973. Lauret, J. Brookhaven National Laboratory, Upton, New York 11973. Lebedev, A. Brookhaven National Laboratory, Upton, New York 11973. Lednicky, R. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Lee, J H. Brookhaven National Laboratory, Upton, New York 11973. Li, X. University of Science and Technology of China, Hefei, Anhui 230026. Li, C. University of Science and Technology of China, Hefei, Anhui 230026. Li, W. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Li, Y. Tsinghua University, Beijing 100084. Liang, Y. Kent State University, Kent, Ohio 44242. Lidrych, J. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Lin, T. Texas A&M University, College Station, Texas 77843. Lipiec, A. Warsaw University of Technology, Warsaw 00-661, Poland. Lisa, M A. Ohio State University, Columbus, Ohio 43210. Liu, F. Central China Normal University, Wuhan, Hubei 430079. Liu, P. State University of New York, Stony Brook, New York 11794. Liu, H. Indiana University, Bloomington, Indiana 47408. Liu, Y. Texas A&M University, College Station, Texas 77843. Ljubicic, T. Brookhaven National Laboratory, Upton, New York 11973. Llope, W J. Wayne State University, Detroit, Michigan 48201. Lomnitz, M. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Longacre, R S. Brookhaven National Laboratory, Upton, New York 11973. Luo, X. Central China Normal University, Wuhan, Hubei 430079. Luo, S. University of Illinois at Chicago, Chicago, Illinois 60607. Ma, G L. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Ma, Y G. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Ma, L. Fudan University, Shanghai 200433. Ma, R. Brookhaven National Laboratory, Upton, New York 11973. Magdy, N. State University of New York, Stony Brook, New York 11794. Majka, R. Yale University, New Haven, Connecticut 06520. Mallick, D. National Institute of Science Education and Research, HBNI, Jatni 752050, India. Margetis, S. Kent State University, Kent, Ohio 44242. Markert, C. University of Texas, Austin, Texas 78712. Matis, H S. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Matonoha, O. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Mayes, D. University of California, Riverside, California 92521. Mazer, J A. Rutgers University, Piscataway, New Jersey 08854. Meehan, K. University of California, Davis, California 95616. Mei, J C. Shandong University, Jinan, Shandong 250100. Minaev, N G. Institute of High Energy Physics, Protvino 142281, Russia. Mioduszewski, S. Texas A&M University, College Station, Texas 77843. Mishra, D. National Institute of Science Education and Research, HBNI, Jatni 752050, India. Mohanty, B. National Institute of Science Education and Research, HBNI, Jatni 752050, India. Mondal, M M. Institute of Physics, Bhubaneswar 751005, India. Mooney, I. Wayne State University, Detroit, Michigan 48201. Morozov, D A. Institute of High Energy Physics, Protvino 142281, Russia. Nasim, Md. University of California, Los Angeles, California 90095. Negrete, J D. University of California, Riverside, California 92521. Nelson, J M. University of California, Berkeley, California 94720. Nemes, D B. Yale University, New Haven, Connecticut 06520. Nie, M. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Nigmatkulov, G. National Research Nuclear University MEPhI, Moscow 115409, Russia. Niida, T. Wayne State University, Detroit, Michigan 48201. Nogach, L V. Institute of High Energy Physics, Protvino 142281, Russia. Nonaka, T. University of Tsukuba, Tsukuba, Ibaraki 305-8571, Japan. Nurushev, S B. Institute of High Energy Physics, Protvino 142281, Russia. Odyniec, G. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Ogawa, A. Brookhaven National Laboratory, Upton, New York 11973. Oh, K. Pusan National University, Pusan 46241, Korea. Oh, S. Yale University, New Haven, Connecticut 06520. Okorokov, V A. National Research Nuclear University MEPhI, Moscow 115409, Russia. Olvitt, D. Temple University, Philadelphia, Pennsylvania 19122. Page, B S. Brookhaven National Laboratory, Upton, New York 11973. Pak, R. Brookhaven National Laboratory, Upton, New York 11973. Panebratsev, Y. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Pawlik, B. Institute of Nuclear Physics PAN, Cracow 31-342, Poland. Pei, H. Central China Normal University, Wuhan, Hubei 430079. Perkins, C. University of California, Berkeley, California 94720. Pluta, J. Warsaw University of Technology, Warsaw 00-661, Poland. Porter, J. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Posik, M. Temple University, Philadelphia, Pennsylvania 19122. Pruthi, N K. Panjab University, Chandigarh 160014, India. Przybycien, M. AGH University of Science and Technology, FPACS, Cracow 30-059, Poland. Putschke, J. Wayne State University, Detroit, Michigan 48201. Quintero, A. Temple University, Philadelphia, Pennsylvania 19122. Radhakrishnan, S K. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Ramachandran, S. University of Kentucky, Lexington, Kentucky 40506-0055. Ray, R L. University of Texas, Austin, Texas 78712. Reed, R. Lehigh University, Bethlehem, Pennsylvania 18015. Ritter, H G. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Roberts, J B. Rice University, Houston, Texas 77251. Rogachevskiy, O V. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Romero, J L. University of California, Davis, California 95616. Ruan, L. Brookhaven National Laboratory, Upton, New York 11973. Rusnak, J. Nuclear Physics Institute AS CR, Prague 250 68, Czech Republic. Rusnakova, O. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Sahoo, N R. Texas A&M University, College Station, Texas 77843. Sahu, P K. Institute of Physics, Bhubaneswar 751005, India. Salur, S. Rutgers University, Piscataway, New Jersey 08854. Sandweiss, J. Yale University, New Haven, Connecticut 06520. Schambach, J. University of Texas, Austin, Texas 78712. Schmah, A M. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Schmidke, W B. Brookhaven National Laboratory, Upton, New York 11973. Schmitz, N. Max-Planck-Institut fur Physik, Munich 80805, Germany. Schweid, B R. State University of New York, Stony Brook, New York 11794. Seck, F. Technische Universitat Darmstadt, Darmstadt 64289, Germany. Seger, J. Creighton University, Omaha, Nebraska 68178. Sergeeva, M. University of California, Los Angeles, California 90095. Seto, R. University of California, Riverside, California 92521. Seyboth, P. Max-Planck-Institut fur Physik, Munich 80805, Germany. Shah, N. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Shahaliev, E. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Shanmuganathan, P V. Lehigh University, Bethlehem, Pennsylvania 18015. Shao, M. University of Science and Technology of China, Hefei, Anhui 230026. Shen, W Q. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Shen, F. Shandong University, Jinan, Shandong 250100. Shi, S S. Central China Normal University, Wuhan, Hubei 430079. Shou, Q Y. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Sichtermann, E P. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Siejka, S. Warsaw University of Technology, Warsaw 00-661, Poland. Sikora, R. AGH University of Science and Technology, FPACS, Cracow 30-059, Poland. Simko, M. Nuclear Physics Institute AS CR, Prague 250 68, Czech Republic. Singha, S. Kent State University, Kent, Ohio 44242. Smirnov, N. Yale University, New Haven, Connecticut 06520. Smirnov, D. Brookhaven National Laboratory, Upton, New York 11973. Solyst, W. Indiana University, Bloomington, Indiana 47408. Sorensen, P. Brookhaven National Laboratory, Upton, New York 11973. Spinka, H M. Argonne National Laboratory, Argonne, Illinois 60439. Srivastava, B. Purdue University, West Lafayette, Indiana 47907. Stanislaus, T D S. Valparaiso University, Valparaiso, Indiana 46383. Stewart, D J. Yale University, New Haven, Connecticut 06520. Strikhanov, M. National Research Nuclear University MEPhI, Moscow 115409, Russia. Stringfellow, B. Purdue University, West Lafayette, Indiana 47907. Suaide, A A P. Universidade de Sao Paulo, Sao Paulo 05314-970, Brazil. Sugiura, T. University of Tsukuba, Tsukuba, Ibaraki 305-8571, Japan. Sumbera, M. Nuclear Physics Institute AS CR, Prague 250 68, Czech Republic. Summa, B. Pennsylvania State University, University Park, Pennsylvania 16802. Sun, Y. University of Science and Technology of China, Hefei, Anhui 230026. Sun, X. Central China Normal University, Wuhan, Hubei 430079. Sun, X M. Central China Normal University, Wuhan, Hubei 430079. Surrow, B. Temple University, Philadelphia, Pennsylvania 19122. Svirida, D N. Alikhanov Institute for Theoretical and Experimental Physics, Moscow 117218, Russia. Szymanski, P. Warsaw University of Technology, Warsaw 00-661, Poland. Tang, Z. University of Science and Technology of China, Hefei, Anhui 230026. Tang, A H. Brookhaven National Laboratory, Upton, New York 11973. Taranenko, A. National Research Nuclear University MEPhI, Moscow 115409, Russia. Tarnowsky, T. Michigan State University, East Lansing, Michigan 48824. Thomas, J H. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Timmins, A R. University of Houston, Houston, Texas 77204. Tlusty, D. Rice University, Houston, Texas 77251. Todoroki, T. Brookhaven National Laboratory, Upton, New York 11973. Tokarev, M. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Tomkiel, C A. Lehigh University, Bethlehem, Pennsylvania 18015. Trentalange, S. University of California, Los Angeles, California 90095. Tribble, R E. Texas A&M University, College Station, Texas 77843. Tribedy, P. Brookhaven National Laboratory, Upton, New York 11973. Tripathy, S K. Institute of Physics, Bhubaneswar 751005, India. Tsai, O D. University of California, Los Angeles, California 90095. Tu, B. Central China Normal University, Wuhan, Hubei 430079. Ullrich, T. Brookhaven National Laboratory, Upton, New York 11973. Underwood, D G. Argonne National Laboratory, Argonne, Illinois 60439. Upsal, I. Ohio State University, Columbus, Ohio 43210. Van Buren, G. Brookhaven National Laboratory, Upton, New York 11973. Vanek, J. Nuclear Physics Institute AS CR, Prague 250 68, Czech Republic. Vasiliev, A N. Institute of High Energy Physics, Protvino 142281, Russia. Vassiliev, I. Frankfurt Institute for Advanced Studies FIAS, Frankfurt 60438, Germany. Videbaek, F. Brookhaven National Laboratory, Upton, New York 11973. Vokal, S. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Voloshin, S A. Wayne State University, Detroit, Michigan 48201. Vossen, A. Indiana University, Bloomington, Indiana 47408. Wang, G. University of California, Los Angeles, California 90095. Wang, Y. Central China Normal University, Wuhan, Hubei 430079. Wang, F. Purdue University, West Lafayette, Indiana 47907. Wang, Y. Tsinghua University, Beijing 100084. Webb, J C. Brookhaven National Laboratory, Upton, New York 11973. Wen, L. University of California, Los Angeles, California 90095. Westfall, G D. Michigan State University, East Lansing, Michigan 48824. Wieman, H. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Wissink, S W. Indiana University, Bloomington, Indiana 47408. Witt, R. United States Naval Academy, Annapolis, Maryland 21402. Wu, Y. Kent State University, Kent, Ohio 44242. Xiao, Z G. Tsinghua University, Beijing 100084. Xie, G. University of Illinois at Chicago, Chicago, Illinois 60607. Xie, W. Purdue University, West Lafayette, Indiana 47907. Xu, Q H. Shandong University, Jinan, Shandong 250100. Xu, Z. Brookhaven National Laboratory, Upton, New York 11973. Xu, J. Central China Normal University, Wuhan, Hubei 430079. Xu, Y F. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Xu, N. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Yang, S. Brookhaven National Laboratory, Upton, New York 11973. Yang, C. Shandong University, Jinan, Shandong 250100. Yang, Q. Shandong University, Jinan, Shandong 250100. Yang, Y. National Cheng Kung University, Tainan 70101. Ye, Z. University of Illinois at Chicago, Chicago, Illinois 60607. Ye, Z. University of Illinois at Chicago, Chicago, Illinois 60607. Yi, L. Shandong University, Jinan, Shandong 250100. Yip, K. Brookhaven National Laboratory, Upton, New York 11973. Yoo, I-K. Pusan National University, Pusan 46241, Korea. Yu, N. Central China Normal University, Wuhan, Hubei 430079. Zbroszczyk, H. Warsaw University of Technology, Warsaw 00-661, Poland. Zha, W. University of Science and Technology of China, Hefei, Anhui 230026. Zhang, Z. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Zhang, L. Central China Normal University, Wuhan, Hubei 430079. Zhang, Y. University of Science and Technology of China, Hefei, Anhui 230026. Zhang, X P. Tsinghua University, Beijing 100084. Zhang, J. Institute of Modern Physics, Chinese Academy of Sciences, Lanzhou, Gansu 730000. Zhang, S. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Zhang, S. University of Science and Technology of China, Hefei, Anhui 230026. Zhang, J. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Zhao, J. Purdue University, West Lafayette, Indiana 47907. Zhong, C. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Zhou, C. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Zhou, L. University of Science and Technology of China, Hefei, Anhui 230026. Zhu, Z. Shandong University, Jinan, Shandong 250100. Zhu, X. Tsinghua University, Beijing 100084. Zyzak, M. Frankfurt Institute for Advanced Studies FIAS, Frankfurt 60438, Germany.
Keywords: dept.phy; peer-reviewed

First Observation of the Directed Flow of D0 and D0 ̄ in Au+Au Collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2019)
We report the first measurement of rapidity-odd directed flow (v1) for D0 and D0̄ mesons at midrapidity (|y|<0.8) in Au+Au collisions at sNN=200 GeV using the STAR detector at the Relativistic Heavy Ion Collider. In 10-80% Au+Au collisions, the slope of the v1 rapidity dependence (dv1/dy), averaged over D0 and D0̄ mesons, is -0.080±0.017(stat)±0.016(syst) for transverse momentum pT above 1.5 GeV/c. The absolute value of D0 meson dv1/dy is about 25 times larger than that for charged kaons, with 3.4σ significance. These data give a unique insight into the initial tilt of the produced matter, and offer constraints on the geometric and transport parameters of the hot QCD medium created in relativistic heavy-ion collisions. © 2019 American Physical Society.
47 citations (Crossref) [2023-10-31]
Keywords: Absolute values; Au+Au collisions; Bosons; Colliding beam accelerators; Directed flow; Germanium compounds; Gold compounds; Hadrons; Heavy ions; Mid-rapidity; Relativistic Heavy Ion Collider; Relativistic heavy ion collision; Transport parameters; Transverse momenta; dept.phy; peer-reviewed

Observation of Excess J /ψ Yield at Very Low Transverse Momenta in Au+Au Collisions at sNN =200 GeV and U+ U Collisions at sNN =193 GeV - STAR Collaboration (Physical Review Letters, 2019)
We report on the first measurements of J/ψ production at very low transverse momentum (pT<0.2 GeV/c) in hadronic Au+Au collisions at sNN=200 GeV and U+U collisions at sNN=193 GeV. Remarkably, the inferred nuclear modification factor of J/ψ at midrapidity in Au+Au (U+U) collisions reaches about 24 (52) for pT<0.05 GeV/c in the 60%-80% collision centrality class. This noteworthy enhancement cannot be explained by hadronic production accompanied by cold and hot medium effects. In addition, the dN/dt distribution of J/ψ for the very low pT range is presented for the first time. The distribution is consistent with that expected from the Au nucleus and shows a hint of interference. Comparison of the measurements to theoretical calculations of coherent production shows that the excess yield can be described reasonably well and reveals a partial disruption of coherent production in semicentral collisions, perhaps due to the violent hadronic interactions. Incorporating theoretical calculations, the results strongly suggest that the dramatic enhancement of J/ψ yield observed at extremely low pT originates from coherent photon-nucleus interactions. In particular, coherently produced J/ψ's in violent hadronic collisions may provide a novel probe of the quark-gluon plasma. © 2019 authors. Published by the American Physical Society.
19 citations (Crossref) [2023-10-31]
Keywords: Au+Au collisions; Colliding beam accelerators; Germanium compounds; Gold compounds; Hadronic collisions; Hadronic interactions; Isomers; Nitrogen compounds; Nuclear modification factors; Quark-gluon plasma; Semicentral collisions; Theoretical calculations; Transverse momenta; dept.phy; peer-reviewed

Global polarization of ξ and ω hyperons in au+au collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2021)
Global polarization of Ξ and ω hyperons has been measured for the first time in Au+Au collisions at sNN=200 GeV. The measurements of the Ξ- and Ξ¯+ hyperon polarization have been performed by two independent methods, via analysis of the angular distribution of the daughter particles in the parity violating weak decay Ξ→Λ+π, as well as by measuring the polarization of the daughter Λ hyperon, polarized via polarization transfer from its parent. The polarization, obtained by combining the results from the two methods and averaged over Ξ- and Ξ¯+, is measured to be ⟨PΞ ©=0.47±0.10(stat)±0.23(syst)% for the collision centrality 20%-80%. The ⟨PΞ. © 2021 American Physical Society. All rights reserved.
37 citations (Crossref) [2023-10-31] tex.art_number: 162301 tex.coden: PRLTA tex.document_type: Article tex.pubmed_id: 33961449 tex.source: Scopus
Keywords: Angular distribution; Au+Au collisions; Colliding beam accelerators; Global polarizations; Hyperon polarization; Measurements of; Polarization; Polarization transfer; dept.phy; peer-reviewed

Measurement of e+e- momentum and angular distributions from linearly polarized photon collisions - STAR Collaboration (Physical Review Letters, 2021)
The Breit-Wheeler process which produces matter and antimatter from photon collisions is experimentally investigated through the observation of 6085 exclusive electron-positron pairs in ultraperipheral Au+Au collisions at sqrt[s_{NN}]=200 GeV. The measurements reveal a large fourth-order angular modulation of cos4DELTAphi=(16.8+/-2.5)% and smooth invariant mass distribution absent of vector mesons (phi, omega, and rho) at the experimental limit of <=0.2% of the observed yields. The differential cross section as a function of e{+}e{-} pair transverse momentum P_{} peaks at low value with sqrt[ ]=38.1+/-0.9 MeV and displays a significant centrality dependence. These features are consistent with QED calculations for the collision of linearly polarized photons quantized from the extremely strong electromagnetic fields generated by the highly charged Au nuclei at ultrarelativistic speed. The experimental results have implications for vacuum birefringence and for mapping the magnetic field which is important for emergent QCD phenomena.
54 citations (Crossref) [2023-10-31] Place: United States Adam, J. Brookhaven National Laboratory, Upton, New York 11973. Adamczyk, L. AGH University of Science and Technology, FPACS, Cracow 30-059, Poland. Adams, J R. Ohio State University, Columbus, Ohio 43210. Adkins, J K. University of Kentucky, Lexington, Kentucky 40506-0055. Agakishiev, G. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Aggarwal, M M. Panjab University, Chandigarh 160014, India. Ahammed, Z. Variable Energy Cyclotron Centre, Kolkata 700064, India. Alekseev, I. Alikhanov Institute for Theoretical and Experimental Physics NRC "Kurchatov Institute," Moscow 117218, Russia. Alekseev, I. National Research Nuclear University MEPhI, Moscow 115409, Russia. Anderson, D M. Texas A&M University, College Station, Texas 77843. Aparin, A. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Aschenauer, E C. Brookhaven National Laboratory, Upton, New York 11973. Ashraf, M U. Central China Normal University, Wuhan, Hubei 430079. Atetalla, F G. Kent State University, Kent, Ohio 44242. Attri, A. Panjab University, Chandigarh 160014, India. Averichev, G S. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Bairathi, V. Indian Institute of Science Education and Research (IISER), Berhampur 760010, India. Barish, K. University of California, Riverside, California 92521. Behera, A. State University of New York, Stony Brook, New York 11794. Bellwied, R. University of Houston, Houston, Texas 77204. Bhasin, A. University of Jammu, Jammu 180001, India. Bielcik, J. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Bielcikova, J. Nuclear Physics Institute of the CAS, Rez 250 68, Czech Republic. Bland, L C. Brookhaven National Laboratory, Upton, New York 11973. Bordyuzhin, I G. Alikhanov Institute for Theoretical and Experimental Physics NRC "Kurchatov Institute," Moscow 117218, Russia. Brandenburg, J D. Brookhaven National Laboratory, Upton, New York 11973. Brandenburg, J D. Shandong University, Qingdao, Shandong 266237. Brandin, A V. National Research Nuclear University MEPhI, Moscow 115409, Russia. Butterworth, J. Rice University, Houston, Texas 77251. Caines, H. Yale University, New Haven, Connecticut 06520. Calderon de la Barca Sanchez, M. University of California, Davis, California 95616. Cebra, D. University of California, Davis, California 95616. Chakaberia, I. Brookhaven National Laboratory, Upton, New York 11973. Chakaberia, I. Kent State University, Kent, Ohio 44242. Chaloupka, P. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Chan, B K. University of California, Los Angeles, California 90095. Chang, F-H. National Cheng Kung University, Tainan 70101. Chang, Z. Brookhaven National Laboratory, Upton, New York 11973. Chankova-Bunzarova, N. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Chatterjee, A. Central China Normal University, Wuhan, Hubei 430079. Chen, D. University of California, Riverside, California 92521. Chen, J H. Fudan University, Shanghai 200433. Chen, X. University of Science and Technology of China, Hefei, Anhui 230026. Chen, Z. Shandong University, Qingdao, Shandong 266237. Cheng, J. Tsinghua University, Beijing 100084. Cherney, M. Creighton University, Omaha, Nebraska 68178. Chevalier, M. University of California, Riverside, California 92521. Choudhury, S. Fudan University, Shanghai 200433. Christie, W. Brookhaven National Laboratory, Upton, New York 11973. Crawford, H J. University of California, Berkeley, California 94720. Csanad, M. ELTE Eotvos Lorand University, Budapest H-1117, Hungary. Daugherity, M. Abilene Christian University, Abilene, Texas 79699. Dedovich, T G. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Deppner, I M. University of Heidelberg, Heidelberg 69120, Germany. Derevschikov, A A. NRC "Kurchatov Institute", Institute of High Energy Physics, Protvino 142281, Russia. Didenko, L. Brookhaven National Laboratory, Upton, New York 11973. Dong, X. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Drachenberg, J L. Abilene Christian University, Abilene, Texas 79699. Dunlop, J C. Brookhaven National Laboratory, Upton, New York 11973. Edmonds, T. Purdue University, West Lafayette, Indiana 47907. Elsey, N. Wayne State University, Detroit, Michigan 48201. Engelage, J. University of California, Berkeley, California 94720. Eppley, G. Rice University, Houston, Texas 77251. Esha, R. State University of New York, Stony Brook, New York 11794. Esumi, S. University of Tsukuba, Tsukuba, Ibaraki 305-8571, Japan. Evdokimov, O. University of Illinois at Chicago, Chicago, Illinois 60607. Ewigleben, A. Lehigh University, Bethlehem, Pennsylvania 18015. Eyser, O. Brookhaven National Laboratory, Upton, New York 11973. Fatemi, R. University of Kentucky, Lexington, Kentucky 40506-0055. Fazio, S. Brookhaven National Laboratory, Upton, New York 11973. Federic, P. Nuclear Physics Institute of the CAS, Rez 250 68, Czech Republic. Fedorisin, J. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Feng, C J. National Cheng Kung University, Tainan 70101. Feng, Y. Purdue University, West Lafayette, Indiana 47907. Filip, P. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Finch, E. Southern Connecticut State University, New Haven, Connecticut 06515. Fisyak, Y. Brookhaven National Laboratory, Upton, New York 11973. Francisco, A. Yale University, New Haven, Connecticut 06520. Fulek, L. AGH University of Science and Technology, FPACS, Cracow 30-059, Poland. Gagliardi, C A. Texas A&M University, College Station, Texas 77843. Galatyuk, T. Technische Universitat Darmstadt, Darmstadt 64289, Germany. Geurts, F. Rice University, Houston, Texas 77251. Gibson, A. Valparaiso University, Valparaiso, Indiana 46383. Gopal, K. Indian Institute of Science Education and Research (IISER) Tirupati, Tirupati 517507, India. Grosnick, D. Valparaiso University, Valparaiso, Indiana 46383. Hamad, A I. Kent State University, Kent, Ohio 44242. Hamed, A. American University of Cairo, New Cairo, New Cairo 11835, Egypt. Harris, J W. Yale University, New Haven, Connecticut 06520. He, S. Central China Normal University, Wuhan, Hubei 430079. He, W. Fudan University, Shanghai 200433. He, X. Institute of Modern Physics, Chinese Academy of Sciences, Lanzhou, Gansu 730000. Heppelmann, S. University of California, Davis, California 95616. Heppelmann, S. Pennsylvania State University, University Park, Pennsylvania 16802. Herrmann, N. University of Heidelberg, Heidelberg 69120, Germany. Hoffman, E. University of Houston, Houston, Texas 77204. Holub, L. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Hong, Y. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Horvat, S. Yale University, New Haven, Connecticut 06520. Hu, Y. Fudan University, Shanghai 200433. Huang, H Z. University of California, Los Angeles, California 90095. Huang, S L. State University of New York, Stony Brook, New York 11794. Huang, T. National Cheng Kung University, Tainan 70101. Huang, X. Tsinghua University, Beijing 100084. Humanic, T J. Ohio State University, Columbus, Ohio 43210. Huo, P. State University of New York, Stony Brook, New York 11794. Igo, G. University of California, Los Angeles, California 90095. Isenhower, D. Abilene Christian University, Abilene, Texas 79699. Jacobs, W W. Indiana University, Bloomington, Indiana 47408. Jena, C. Indian Institute of Science Education and Research (IISER) Tirupati, Tirupati 517507, India. Jentsch, A. Brookhaven National Laboratory, Upton, New York 11973. Ji, Y. University of Science and Technology of China, Hefei, Anhui 230026. Jia, J. Brookhaven National Laboratory, Upton, New York 11973. Jia, J. State University of New York, Stony Brook, New York 11794. Jiang, K. University of Science and Technology of China, Hefei, Anhui 230026. Jowzaee, S. Wayne State University, Detroit, Michigan 48201. Ju, X. University of Science and Technology of China, Hefei, Anhui 230026. Judd, E G. University of California, Berkeley, California 94720. Kabana, S. Kent State University, Kent, Ohio 44242. Kabir, M L. University of California, Riverside, California 92521. Kagamaster, S. Lehigh University, Bethlehem, Pennsylvania 18015. Kalinkin, D. Indiana University, Bloomington, Indiana 47408. Kang, K. Tsinghua University, Beijing 100084. Kapukchyan, D. University of California, Riverside, California 92521. Kauder, K. Brookhaven National Laboratory, Upton, New York 11973. Ke, H W. Brookhaven National Laboratory, Upton, New York 11973. Keane, D. Kent State University, Kent, Ohio 44242. Kechechyan, A. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Kelsey, M. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Khyzhniak, Y V. National Research Nuclear University MEPhI, Moscow 115409, Russia. Kikola, D P. Warsaw University of Technology, Warsaw 00-661, Poland. Kim, C. University of California, Riverside, California 92521. Kimelman, B. University of California, Davis, California 95616. Kincses, D. ELTE Eotvos Lorand University, Budapest H-1117, Hungary. Kinghorn, T A. University of California, Davis, California 95616. Kisel, I. Frankfurt Institute for Advanced Studies FIAS, Frankfurt 60438, Germany. Kiselev, A. Brookhaven National Laboratory, Upton, New York 11973. Kisiel, A. Warsaw University of Technology, Warsaw 00-661, Poland. Klein, S R. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Kocan, M. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Kochenda, L. National Research Nuclear University MEPhI, Moscow 115409, Russia. Kosarzewski, L K. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Kramarik, L. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Kravtsov, P. National Research Nuclear University MEPhI, Moscow 115409, Russia. Krueger, K. Argonne National Laboratory, Argonne, Illinois 60439. Kulathunga Mudiyanselage, N. University of Houston, Houston, Texas 77204. Kumar, L. Panjab University, Chandigarh 160014, India. Kunnawalkam Elayavalli, R. Wayne State University, Detroit, Michigan 48201. Kwasizur, J H. Indiana University, Bloomington, Indiana 47408. Lacey, R. State University of New York, Stony Brook, New York 11794. Lan, S. Central China Normal University, Wuhan, Hubei 430079. Landgraf, J M. Brookhaven National Laboratory, Upton, New York 11973. Lauret, J. Brookhaven National Laboratory, Upton, New York 11973. Lebedev, A. Brookhaven National Laboratory, Upton, New York 11973. Lednicky, R. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Lee, J H. Brookhaven National Laboratory, Upton, New York 11973. Leung, Y H. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Li, C. University of Science and Technology of China, Hefei, Anhui 230026. Li, W. Rice University, Houston, Texas 77251. Li, W. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Li, X. University of Science and Technology of China, Hefei, Anhui 230026. Li, Y. Tsinghua University, Beijing 100084. Liang, Y. Kent State University, Kent, Ohio 44242. Licenik, R. Nuclear Physics Institute of the CAS, Rez 250 68, Czech Republic. Lin, T. Texas A&M University, College Station, Texas 77843. Lin, Y. Central China Normal University, Wuhan, Hubei 430079. Lisa, M A. Ohio State University, Columbus, Ohio 43210. Liu, F. Central China Normal University, Wuhan, Hubei 430079. Liu, H. Indiana University, Bloomington, Indiana 47408. Liu, P. State University of New York, Stony Brook, New York 11794. Liu, P. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Liu, T. Yale University, New Haven, Connecticut 06520. Liu, X. Ohio State University, Columbus, Ohio 43210. Liu, Y. Texas A&M University, College Station, Texas 77843. Liu, Z. University of Science and Technology of China, Hefei, Anhui 230026. Ljubicic, T. Brookhaven National Laboratory, Upton, New York 11973. Llope, W J. Wayne State University, Detroit, Michigan 48201. Longacre, R S. Brookhaven National Laboratory, Upton, New York 11973. Lukow, N S. Temple University, Philadelphia, Pennsylvania 19122. Luo, S. University of Illinois at Chicago, Chicago, Illinois 60607. Luo, X. Central China Normal University, Wuhan, Hubei 430079. Ma, G L. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Ma, L. Fudan University, Shanghai 200433. Ma, R. Brookhaven National Laboratory, Upton, New York 11973. Ma, Y G. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Magdy, N. University of Illinois at Chicago, Chicago, Illinois 60607. Majka, R. Yale University, New Haven, Connecticut 06520. Mallick, D. National Institute of Science Education and Research, HBNI, Jatni 752050, India. Margetis, S. Kent State University, Kent, Ohio 44242. Markert, C. University of Texas, Austin, Texas 78712. Matis, H S. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Mazer, J A. Rutgers University, Piscataway, New Jersey 08854. Minaev, N G. NRC "Kurchatov Institute", Institute of High Energy Physics, Protvino 142281, Russia. Mioduszewski, S. Texas A&M University, College Station, Texas 77843. Mohanty, B. National Institute of Science Education and Research, HBNI, Jatni 752050, India. Mooney, I. Wayne State University, Detroit, Michigan 48201. Moravcova, Z. Czech Technical University in Prague, FNSPE, Prague 115 19, Czech Republic. Morozov, D A. NRC "Kurchatov Institute", Institute of High Energy Physics, Protvino 142281, Russia. Nagy, M. ELTE Eotvos Lorand University, Budapest H-1117, Hungary. Nam, J D. Temple University, Philadelphia, Pennsylvania 19122. Nasim, Md. Indian Institute of Science Education and Research (IISER), Berhampur 760010, India. Nayak, K. Central China Normal University, Wuhan, Hubei 430079. Neff, D. University of California, Los Angeles, California 90095. Nelson, J M. University of California, Berkeley, California 94720. Nemes, D B. Yale University, New Haven, Connecticut 06520. Nie, M. Shandong University, Qingdao, Shandong 266237. Nigmatkulov, G. National Research Nuclear University MEPhI, Moscow 115409, Russia. Niida, T. University of Tsukuba, Tsukuba, Ibaraki 305-8571, Japan. Nogach, L V. NRC "Kurchatov Institute", Institute of High Energy Physics, Protvino 142281, Russia. Nonaka, T. Central China Normal University, Wuhan, Hubei 430079. Odyniec, G. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Ogawa, A. Brookhaven National Laboratory, Upton, New York 11973. Oh, S. Yale University, New Haven, Connecticut 06520. Okorokov, V A. National Research Nuclear University MEPhI, Moscow 115409, Russia. Page, B S. Brookhaven National Laboratory, Upton, New York 11973. Pak, R. Brookhaven National Laboratory, Upton, New York 11973. Pandav, A. National Institute of Science Education and Research, HBNI, Jatni 752050, India. Panebratsev, Y. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Pawlik, B. AGH University of Science and Technology, FPACS, Cracow 30-059, Poland. Pawlik, B. Institute of Nuclear Physics PAN, Cracow 31-342, Poland. Pawlowska, D. Warsaw University of Technology, Warsaw 00-661, Poland. Pei, H. Central China Normal University, Wuhan, Hubei 430079. Perkins, C. University of California, Berkeley, California 94720. Pinsky, L. University of Houston, Houston, Texas 77204. Pinter, R L. ELTE Eotvos Lorand University, Budapest H-1117, Hungary. Pluta, J. Warsaw University of Technology, Warsaw 00-661, Poland. Porter, J. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Posik, M. Temple University, Philadelphia, Pennsylvania 19122. Pruthi, N K. Panjab University, Chandigarh 160014, India. Przybycien, M. AGH University of Science and Technology, FPACS, Cracow 30-059, Poland. Putschke, J. Wayne State University, Detroit, Michigan 48201. Qiu, H. Institute of Modern Physics, Chinese Academy of Sciences, Lanzhou, Gansu 730000. Quintero, A. Temple University, Philadelphia, Pennsylvania 19122. Radhakrishnan, S K. Kent State University, Kent, Ohio 44242. Ramachandran, S. University of Kentucky, Lexington, Kentucky 40506-0055. Ray, R L. University of Texas, Austin, Texas 78712. Reed, R. Lehigh University, Bethlehem, Pennsylvania 18015. Ritter, H G. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Roberts, J B. Rice University, Houston, Texas 77251. Rogachevskiy, O V. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Romero, J L. University of California, Davis, California 95616. Ruan, L. Brookhaven National Laboratory, Upton, New York 11973. Rusnak, J. Nuclear Physics Institute of the CAS, Rez 250 68, Czech Republic. Sahoo, N R. Shandong University, Qingdao, Shandong 266237. Sako, H. University of Tsukuba, Tsukuba, Ibaraki 305-8571, Japan. Salur, S. Rutgers University, Piscataway, New Jersey 08854. Sandweiss, J. Yale University, New Haven, Connecticut 06520. Sato, S. University of Tsukuba, Tsukuba, Ibaraki 305-8571, Japan. Schmidke, W B. Brookhaven National Laboratory, Upton, New York 11973. Schmitz, N. Max-Planck-Institut fur Physik, Munich 80805, Germany. Schweid, B R. State University of New York, Stony Brook, New York 11794. Seck, F. Technische Universitat Darmstadt, Darmstadt 64289, Germany. Seger, J. Creighton University, Omaha, Nebraska 68178. Sergeeva, M. University of California, Los Angeles, California 90095. Seto, R. University of California, Riverside, California 92521. Seyboth, P. Max-Planck-Institut fur Physik, Munich 80805, Germany. Shah, N. Indian Institute Technology, Patna, Bihar 801106, India. Shahaliev, E. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Shanmuganathan, P V. Brookhaven National Laboratory, Upton, New York 11973. Shao, M. University of Science and Technology of China, Hefei, Anhui 230026. Shen, F. Shandong University, Qingdao, Shandong 266237. Shen, W Q. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Shi, S S. Central China Normal University, Wuhan, Hubei 430079. Shou, Q Y. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Sichtermann, E P. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Sikora, R. AGH University of Science and Technology, FPACS, Cracow 30-059, Poland. Simko, M. Nuclear Physics Institute of the CAS, Rez 250 68, Czech Republic. Singh, J. Panjab University, Chandigarh 160014, India. Singha, S. Institute of Modern Physics, Chinese Academy of Sciences, Lanzhou, Gansu 730000. Smirnov, N. Yale University, New Haven, Connecticut 06520. Solyst, W. Indiana University, Bloomington, Indiana 47408. Sorensen, P. Brookhaven National Laboratory, Upton, New York 11973. Spinka, H M. Argonne National Laboratory, Argonne, Illinois 60439. Srivastava, B. Purdue University, West Lafayette, Indiana 47907. Stanislaus, T D S. Valparaiso University, Valparaiso, Indiana 46383. Stefaniak, M. Warsaw University of Technology, Warsaw 00-661, Poland. Stewart, D J. Yale University, New Haven, Connecticut 06520. Strikhanov, M. National Research Nuclear University MEPhI, Moscow 115409, Russia. Stringfellow, B. Purdue University, West Lafayette, Indiana 47907. Suaide, A A P. Universidade de Sao Paulo, Sao Paulo 05314-970, Brazil. Sumbera, M. Nuclear Physics Institute of the CAS, Rez 250 68, Czech Republic. Summa, B. Pennsylvania State University, University Park, Pennsylvania 16802. Sun, X M. Central China Normal University, Wuhan, Hubei 430079. Sun, Y. University of Science and Technology of China, Hefei, Anhui 230026. Sun, Y. Huzhou University, Huzhou, Zhejiang 313000. Surrow, B. Temple University, Philadelphia, Pennsylvania 19122. Svirida, D N. Alikhanov Institute for Theoretical and Experimental Physics NRC "Kurchatov Institute," Moscow 117218, Russia. Szymanski, P. Warsaw University of Technology, Warsaw 00-661, Poland. Tang, A H. Brookhaven National Laboratory, Upton, New York 11973. Tang, Z. University of Science and Technology of China, Hefei, Anhui 230026. Taranenko, A. National Research Nuclear University MEPhI, Moscow 115409, Russia. Tarnowsky, T. Michigan State University, East Lansing, Michigan 48824. Thomas, J H. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Timmins, A R. University of Houston, Houston, Texas 77204. Tlusty, D. Creighton University, Omaha, Nebraska 68178. Tokarev, M. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Tomkiel, C A. Lehigh University, Bethlehem, Pennsylvania 18015. Trentalange, S. University of California, Los Angeles, California 90095. Tribble, R E. Texas A&M University, College Station, Texas 77843. Tribedy, P. Brookhaven National Laboratory, Upton, New York 11973. Tripathy, S K. ELTE Eotvos Lorand University, Budapest H-1117, Hungary. Tsai, O D. University of California, Los Angeles, California 90095. Tu, Z. Brookhaven National Laboratory, Upton, New York 11973. Ullrich, T. Brookhaven National Laboratory, Upton, New York 11973. Underwood, D G. Argonne National Laboratory, Argonne, Illinois 60439. Upsal, I. Brookhaven National Laboratory, Upton, New York 11973. Upsal, I. Shandong University, Qingdao, Shandong 266237. Van Buren, G. Brookhaven National Laboratory, Upton, New York 11973. Vanek, J. Nuclear Physics Institute of the CAS, Rez 250 68, Czech Republic. Vasiliev, A N. NRC "Kurchatov Institute", Institute of High Energy Physics, Protvino 142281, Russia. Vassiliev, I. Frankfurt Institute for Advanced Studies FIAS, Frankfurt 60438, Germany. Videbaek, F. Brookhaven National Laboratory, Upton, New York 11973. Vokal, S. Joint Institute for Nuclear Research, Dubna 141 980, Russia. Voloshin, S A. Wayne State University, Detroit, Michigan 48201. Wang, F. Purdue University, West Lafayette, Indiana 47907. Wang, G. University of California, Los Angeles, California 90095. Wang, J S. Huzhou University, Huzhou, Zhejiang 313000. Wang, P. University of Science and Technology of China, Hefei, Anhui 230026. Wang, Y. Central China Normal University, Wuhan, Hubei 430079. Wang, Y. Tsinghua University, Beijing 100084. Wang, Z. Shandong University, Qingdao, Shandong 266237. Webb, J C. Brookhaven National Laboratory, Upton, New York 11973. Weidenkaff, P C. University of Heidelberg, Heidelberg 69120, Germany. Wen, L. University of California, Los Angeles, California 90095. Westfall, G D. Michigan State University, East Lansing, Michigan 48824. Wieman, H. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Wissink, S W. Indiana University, Bloomington, Indiana 47408. Witt, R. United States Naval Academy, Annapolis, Maryland 21402. Wu, Y. University of California, Riverside, California 92521. Xiao, Z G. Tsinghua University, Beijing 100084. Xie, G. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Xie, W. Purdue University, West Lafayette, Indiana 47907. Xu, H. Huzhou University, Huzhou, Zhejiang 313000. Xu, N. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Xu, Q H. Shandong University, Qingdao, Shandong 266237. Xu, Y F. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Xu, Y. Shandong University, Qingdao, Shandong 266237. Xu, Z. Brookhaven National Laboratory, Upton, New York 11973. Xu, Z. University of California, Los Angeles, California 90095. Yang, C. Shandong University, Qingdao, Shandong 266237. Yang, Q. Shandong University, Qingdao, Shandong 266237. Yang, S. Brookhaven National Laboratory, Upton, New York 11973. Yang, Y. National Cheng Kung University, Tainan 70101. Yang, Z. Central China Normal University, Wuhan, Hubei 430079. Ye, Z. Rice University, Houston, Texas 77251. Ye, Z. University of Illinois at Chicago, Chicago, Illinois 60607. Yi, L. Shandong University, Qingdao, Shandong 266237. Yip, K. Brookhaven National Laboratory, Upton, New York 11973. Zbroszczyk, H. Warsaw University of Technology, Warsaw 00-661, Poland. Zha, W. University of Science and Technology of China, Hefei, Anhui 230026. Zhang, D. Central China Normal University, Wuhan, Hubei 430079. Zhang, S. University of Science and Technology of China, Hefei, Anhui 230026. Zhang, S. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Zhang, X P. Tsinghua University, Beijing 100084. Zhang, Y. University of Science and Technology of China, Hefei, Anhui 230026. Zhang, Y. Central China Normal University, Wuhan, Hubei 430079. Zhang, Z J. National Cheng Kung University, Tainan 70101. Zhang, Z. Brookhaven National Laboratory, Upton, New York 11973. Zhao, J. Purdue University, West Lafayette, Indiana 47907. Zhong, C. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Zhou, C. Shanghai Institute of Applied Physics, Chinese Academy of Sciences, Shanghai 201800. Zhu, X. Tsinghua University, Beijing 100084. Zhu, Z. Shandong University, Qingdao, Shandong 266237. Zurek, M. Lawrence Berkeley National Laboratory, Berkeley, California 94720. Zyzak, M. Frankfurt Institute for Advanced Studies FIAS, Frankfurt 60438, Germany.
Keywords: Angular distribution; Angular-modulation; Au+Au collisions; Colliding beam accelerators; Differential cross section; Electron-positron pairs; Invariant mass distribution; Linearly polarized; Matter and antimatters; Photons; Transverse momenta; dept.phy; peer-reviewed

Observation of Ds± /D0 enhancement in au+au collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2021)
We report on the first measurement of charm-strange meson Ds± production at midrapidity in Au+Au collisions at sNN=200 GeV from the STAR experiment. The yield ratio between strange (Ds±) and nonstrange (D0) open-charm mesons is presented and compared to model calculations. A significant enhancement, relative to a pythia simulation of p+p collisions, is observed in the Ds±/D0 yield ratio in Au+Au collisions over a large range of collision centralities. Model calculations incorporating abundant strange-quark production in the quark-gluon plasma and coalescence hadronization qualitatively reproduce the data. The transverse-momentum integrated yield ratio of Ds±/D0 at midrapidity is consistent with a prediction from a statistical hadronization model with the parameters constrained by the yields of light and strange hadrons measured at the same collision energy. These results suggest that the coalescence of charm quarks with strange quarks in the quark-gluon plasma plays an important role in Ds±-meson production in heavy-ion collisions. © 2021 authors. Published by the American Physical Society. Funded by SCOAP3.
11 citations (Crossref) [2023-10-31] tex.art_number: 092301 tex.coden: PRLTA tex.document_type: Article tex.pubmed_id: 34506181 tex.source: Scopus
Keywords: Au+Au collisions; Bosons; Coalescence; Colliding beam accelerators; Collision energies; Collisional plasmas; Germanium compounds; Gold compounds; Hadrons; Heavy ion collision; Heavy ions; Meson production; Model calculations; Quantum theory; Quark production; Quark-gluon plasma; Transverse momenta; dept.phy; peer-reviewed

Unexpectedly Large Electron Correlation Measured in Auger Spectra of Ferromagnetic Iron Thin Films: Orbital-Selected Coulomb and Exchange Contributions - Gotter, R.; Verna, A.; Sbroscia, M.; Moroni, R.; Bisio, F.; Iacobucci, S.; Offi, F.; Vaidya, S. R.; Ruocco, A.; Stefani, G. (Physical Review Letters, 2020)
4 citations (Crossref) [2023-10-31] WOS:000556273400010
Keywords: dept.phy

Beam-energy dependence of identified two-particle angular correlations ins root s(NN)=7.7-200 GeV Au + Au collisions - STAR Collaboration (Physical Review C, 2020)
4 citations (Crossref) [2023-10-31] WOS:000510148200002
Keywords: dept.phy; peer-reviewed

Measurements of W and Z /γ∗ cross sections and their ratios in p+p collisions at RHIC - STAR Collaboration (Physical Review D, 2021)
We report on the W and Z/γ∗ differential and total cross sections as well as the W+/W− and (W++W−)/(Z/γ∗) cross section ratios measured by the STAR experiment at RHIC in p+p collisions at √s=500 GeV and 510 GeV. The cross sections and their ratios are sensitive to quark and antiquark parton distribution functions. In particular, at leading order, the W cross section ratio is sensitive to the ¯d/¯u ratio. These measurements were taken at high Q2∼M2W,M2Z and can serve as input into global analyses to provide constraints on the sea quark distributions. The results presented here combine three STAR datasets from 2011, 2012, and 2013, accumulating an integrated luminosity of 350 pb−1. We also assess the expected impact that our W+/W− cross section ratios will have on various quark distributions, and find sensitivity to the ¯u−¯d and ¯d/¯u distributions.
11 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Nonmonotonic energy dependence of net-proton number fluctuations - STAR Collaboration (Physical Review Letters, 2021)
Nonmonotonic variation with collision energy (sNN) of the moments of the net-baryon number distribution in heavy-ion collisions, related to the correlation length and the susceptibilities of the system, is suggested as a signature for the quantum chromodynamics critical point. We report the first evidence of a nonmonotonic variation in the kurtosis times variance of the net-proton number (proxy for net-baryon number) distribution as a function of sNN with 3.1 σ significance for head-on (central) gold-on-gold (Au+Au) collisions measured solenoidal tracker at Relativistic Heavy Ion Collider. Data in noncentral Au+Au collisions and models of heavy-ion collisions without a critical point show a monotonic variation as a function of sNN. © 2021 American Physical Society.
101 citations (Crossref) [2023-10-31] tex.art_number: 092301 tex.coden: PRLTA tex.document_type: Article tex.pubmed_id: 33750161 tex.source: Scopus
Keywords: Colliding beam accelerators; Collision energies; Correlation lengths; Gold; Hadrons; Heavy ion collision; Heavy ions; Ion sources; Monotonic variations; Non-monotonic variation; Number fluctuations; Quantum chromodynamics; Quantum theory; Relativistic Heavy Ion Collider; dept.phy; peer-reviewed

Human brain meningioma tumor detection using visible resonance Raman spectroscopy - Zhang, Liang; Zhou, Yan; Zhang, Shengjia; Wu, Binlin; Zhu, Ke; Liu, Cheng-hui; Yu, Xinguang; Alfano, Robert R. (Advanced biomedical and clinical diagnostic and surgical guidance systems XIX, 2021)
0 citations (Crossref) [2023-10-31]
Keywords: Brain; Brain neoplasms; Detection and diagnosis; Diagnosis; Healthy tissues; Margin status; Remote control; Resonance Raman; Resonance Raman spectroscopy; Surgery; Tumor boundary; Tumor detection; Tumors; dept.phy

Analysis of Stokes shift spectra for distinguishing human prostate cancerous and normal tissues using machine learning methods - Mo, Haiding; Wang, Eric; Tian, Yuke; Pu, Yang; Wu, Binlin; Alfano, Robert R. (Photonic diagnosis, monitoring, prevention, and treatment of infections and inflammatory diseases 2021, 2021)
Early detection of prostate cancer is critical for the success of cancer therapy. It is believed that the biochemical changes that cause the optical spectra changes would appear earlier than the histological aberration. The aim of this ex vivo study was to evaluate the ability of Stokes Shift Spectra (S3) to identify human prostate cancerous tissues from the normal. Fifteen (15) pairs of with pathologically confirmed human prostate cancerous and normal tissues underwent Stokes Shift Spectra measurements with selective wavelength interval of 40 nm. The spectra were then analyzed using machine learning (ML) algorithms to classify the two types of tissues. The ML algorithms including principal component analysis (PCA) and nonnegative matrix factorization (NMF) were used for dimension reduction and feature detection. The characteristic component spectra were used to identify the key fluorophores related to carcinogenesis. The results show that these key fluorophores within tissue, e.g., tryptophan, collagen, and NADH, have different relative concentrations between cancerous and normal tissues. A multi-class classification was performed using support vector machines (SVMs). A leave-one-out cross validation was used to evaluate the performance of the classification with the gold standard histopathological results as the ground truth. The results with high sensitivity and specificity indicate that the S3 method is effective for detecting changes of fluorophore composition in human prostate tissues due to the development of cancer. © 2021 SPIE.
0 citations (Crossref) [2023-10-31]
Keywords: Amino acids; Diagnosis; Dimension reduction; Diseases; Factorization; Fluorophores; Histology; Learning systems; Leave-one-out cross validations; Machine learning methods; Matrix algebra; Multi-class classification; Nonnegative matrix factorization; Relative concentration; Spectra measurements; Statistical methods; Support vector machine (SVMs); Support vector machines; Tissue; Tissue engineering; Urology; dept.phy

Human blood biomarkers for glioma and meningioma detection by a portable visible resonance Raman analyzer - Zhang, Liang; Zhou, Yan; Zhang, Shengjia; Wu, Binlin; Zhu, Ke; Zhang, Chunyuan; Liu, Cheng-hui; Yu, Xinguang; Alfano, Robert R. (Optical biopsy XIX: Toward real-time spectroscopic imaging and diagnosis, 2021)
Recent reports pointed out that the application of optical spectroscopy in the field of liquid biopsy has aroused great interest among researchers and demonstrated the potential of its clinical application. We report a preliminary investigation on the visible resonance Raman (VRR) spectra of human brain blood liquid collected from the scalp and around the meningeal tumor during surgery and a set of venous blood samples from healthy people and glioma grade III patients using a portable VRR-LRRTM, HR800, HR-Evolution and WITec300 Raman systems in vivo and ex vivo. The biochemical fingerprints and molecular biomarkers were found. These findings indicate that if VRR spectroscopy technology is combined with polymerase chain reaction (PCR) or genetic molecular biomarker methods (VRR-PCR), it will greatly increase the possibility for its clinical application. © 2021 SPIE.
1 citations (Crossref) [2023-10-31]
Keywords: Biomarkers; Biopsy; Blood; Clinical application; Healthy people; Molecular biomarker; Optical spectroscopy; Polymerase chain reaction; Raman systems; Resonance Raman; Spectroscopy; Spectroscopy technology; Tumors; Venous bloods; dept.phy

Identifying metastatic ability of prostate cancer cell lines using native fluorescence spectroscopy and machine learning methods - Xue, Jianpeng; Pu, Yang; Smith, Jason T.; Gao, Xin; Wang, Chun; Wu, Binlin (Scientific Reports, 2021)
Metastasis is the leading cause of mortalities in cancer patients due to the spreading of cancer cells to various organs. Detecting cancer and identifying its metastatic potential at the early stage is important. This may be achieved based on the quantification of the key biomolecular components within tissues and cells using recent optical spectroscopic techniques. The aim of this study was to develop a noninvasive label-free optical biopsy technique to retrieve the characteristic molecular information for detecting different metastatic potentials of prostate cancer cells. Herein we report using native fluorescence (NFL) spectroscopy along with machine learning (ML) to differentiate prostate cancer cells with different metastatic abilities. The ML algorithms including principal component analysis (PCA) and nonnegative matrix factorization (NMF) were used for dimension reduction and feature detection. The characteristic component spectra were used to identify the key biomolecules that are correlated with metastatic potentials. The relative concentrations of the molecular spectral components were retrieved and used to classify the cancer cells with different metastatic potentials. A multi-class classification was performed using support vector machines (SVMs). The NFL spectral data were collected from three prostate cancer cell lines with different levels of metastatic potentials. The key biomolecules in the prostate cancer cells were identified to be tryptophan, reduced nicotinamide adenine dinucleotide (NADH) and hypothetically lactate as well. The cancer cells with different metastatic potentials were classified with high accuracy using the relative concentrations of the key molecular components. The results suggest that the changes in the relative concentrations of these key fluorophores retrieved from NFL spectra may present potential criteria for detecting prostate cancer cells of different metastatic abilities.
7 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85099803629
Keywords: Cell Line; Fluorescence; Humans; Lactic Acid; Machine Learning; Male; NAD; Neoplasm Metastasis; Principal Component Analysis; Prostatic Neoplasms; ROC Curve; Reproducibility of Results; Spectrometry; Support Vector Machine; Tryptophan; Tumor; dept.phy; diagnostic imaging; human; lactic acid; machine learning; male; metabolism; metastasis; nicotinamide adenine dinucleotide; pathology; principal component analysis; prostate tumor; receiver operating characteristic; reproducibility; spectrofluorometry; support vector machine; tryptophan; tumor cell line

Speckle imaging characterization of radial velocity exoplanet systems - Dalba, Paul A.; Kane, Stephen R.; Howell, Steve B; Horch, Elliott P; Li, Zhexing; Hirsch, Lea A.; Burt, Jennifer; Brandt, Timothy D.; Močnik, Teo; Henry, Gregory W. (Astronomical Journal, 2021)
We conducted speckle imaging observations of 53 stellar systems that were members of long-term radial velocity (RV) monitoring campaigns and exhibited substantial accelerations indicative of planetary or stellar companions in wide orbits. Our observations were made with blue and red filters using the Differential Speckle Survey Instrument at Gemini-South and the NN-Explore Exoplanet Stellar Speckle Imager at the WIYN telescope. The speckle imaging identifies eight luminous companions within 2" of the primary stars. In three of these systems-HD 1388, HD 87359, and HD 104304-the properties of the imaged companion are consistent with the RV measurements, suggesting that these companions may be associated with the primary and the cause of the RV variation. For all 53 stellar systems, we derive differential magnitude limits (i.e., contrast curves) from the imaging. We extend this analysis to include upper limits on companion mass in systems without imaging detections. In 25 systems, we rule out companions with masses greater than 0.2 M⊙, suggesting that the observed RV signals are caused by late-M dwarfs or substellar (potentially planetary) objects. On the other hand, the joint RV and imaging analysis almost entirely rules out planetary explanations of the RV signal for HD 19522 and suggests that the companion must have an angular separation below a few tenths of an arcsecond. This work highlights the importance of combined RV and imaging observations for characterizing the outer regions of nearby planetary systems. © 2021 Institute of Physics Publishing. All rights reserved.
5 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85101618449
Keywords: dept.phy; peer-reviewed

Speckle observations of TESS exoplanet host stars: Understanding the binary exoplanet host star orbital period distribution - Howell, Steve B; Matson, Rachel A.; Ciardi, David R; Everett, Mark E; Livingston, John H.; Scott, Nicholas J; Horch, Elliott P; Winn, Joshua N (Astronomical Journal, 2021)
We present high-resolution speckle interferometric imaging observations of TESS exoplanet host stars using the NN-EXPLORE Exoplanet and Stellar Speckle Imager instrument at the 3.5 m WIYN telescope. Eight TESS objects of interest that were originally discovered by Kepler were previously observed using the Differential Speckle Survey Instrument. Speckle observations of 186 TESS stars were carried out, and 45 (24%) likely bound companions were detected. This is approximately the number of companions we would expect to observe given the established 46% binarity rate in exoplanet host stars. For the detected binaries, the distribution of stellar mass ratio is consistent with that of the standard Raghavan distribution and may show a decrease in high-q systems as the binary separation increases. The distribution of binary orbital periods, however, is not consistent with the standard Ragahavan model, and our observations support the premise that exoplanet-hosting stars with binary companions have, in general, wider orbital separations than field binaries. We find that exoplanet-hosting binary star systems show a distribution peaking near 100 au, higher than the 40–50 au peak that is observed for field binaries. This fact led to earlier suggestions that planet formation is suppressed in close binaries.
24 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85102449269
Keywords: dept.phy; peer-reviewed

Visual Orbits of Spectroscopic Binaries with the CHARA Array. III. HD 8374 and HD 24546 - Lester, Kathryn V.; Fekel, Francis C.; Muterspaugh, Matthew; Gies, Douglas R.; Schaefer, Gail H.; Farrington, Christopher D.; Guo, Zhao; Matson, Rachel A.; Monnier, John D.; Brummelaar, Theo ten; Sturmann, Judit; Weiss, Samuel A. (The Astronomical Journal, 2020)
We present the visual orbits of two long-period spectroscopic binary stars, HD 8374 and HD 24546, using interferometric observations acquired with the CHARA Array and the Palomar Testbed Interferometer. We also obtained new radial velocities from echelle spectra using the APO 3.5 m and Fairborn 2.0 m telescopes. By combining the visual and spectroscopic observations, we solve for the full, three-dimensional orbits and determine the stellar masses and distances to within 3% uncertainty. We then estimate the effective temperature and radius of each component star through Doppler tomography and spectral energy distribution analyses, in order to compare the observed stellar parameters to the predictions of stellar evolution models. For HD 8374, we find masses of M 1 = 1.636 ± 0.050M ⊙ and M 2 = 1.587 ± 0.049M ⊙, radii of R 1 = 1.84 ± 0.05R ⊙ and R 2 = 1.66 ± 0.12R ⊙, temperatures of K and K, and an estimated age of 1.0 Gyr. For HD 24546, we find masses of M 1 = 1.434 ± 0.014M ⊙ and M 2 = 1.409 ± 0.014M ⊙, radii of R 1 = 1.67 ± 0.06R ⊙ and R 2 = 1.60 ± 0.10R ⊙, temperatures of K and K, and an estimated age of 1.4 Gyr. HD 24546 is therefore too old to be a member of the Hyades cluster, despite its physical proximity to the group.
5 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Measurement of the mass difference and the binding energy of the hypertriton and antihypertriton - STAR Collaboration (Nature Physics, 2020)
According to the CPT theorem, which states that the combined operation of charge conjugation, parity transformation and time reversal must be conserved, particles and their antiparticles should have the same mass and lifetime but opposite charge and magnetic moment. Here, we test CPT symmetry in a nucleus containing a strange quark, more specifically in the hypertriton. This hypernucleus is the lightest one yet discovered and consists of a proton, a neutron and a Λ hyperon. With data recorded by the STAR detector1–3 at the Relativistic Heavy Ion Collider, we measure the Λ hyperon binding energy BΛ for the hypertriton, and find that it differs from the widely used value4 and from predictions5–8, where the hypertriton is treated as a weakly bound system. Our results place stringent constraints on the hyperon–nucleon interaction9,10 and have implications for understanding neutron star interiors, where strange matter may be present11. A precise comparison of the masses of the hypertriton and the antihypertriton allows us to test CPT symmetry in a nucleus with strangeness, and we observe no deviation from the expected exact symmetry.
66 citations (Crossref) [2023-10-31] Number: 4
Keywords: Binding energy; Charge conjugation; Colliding beam accelerators; Combined operations; Cpt symmetries; Heavy ions; Magnetic moments; Mass difference; Opposite charge; Relativistic Heavy Ion Collider; Stars; Stringent constraints; Time reversal; dept.phy; peer-reviewed

Human glioma tumors detection by a portable visible resonance Raman analyzer with a hand-held optical fiber probe - Zhou, Yan; Zhang, Shengjia; Wu, Binlin; Yu, Xinguang; Cheng, Gangge; Zhu, Ke; Zhao, Mingyue; Zheng, Jichun; Zhang, Liang; Zhang, Mingqian; Liang, Qijun; Go, Yun Ii; et al. (Biomedical Vibrational Spectroscopy 2020: Advances in Research and Industry, 2020)
Based on Visible Resonance Raman (VRR) method, we have developed a novel label-free portable VRR LRR2000 Raman analyzer with a portable fiber-optic probe and used it for the classification of human gliomas ex vivo and for the analysis of changes in tumor chemical compositions in molecular level. The purpose of this study was to examine the performance of the LRR2000 Raman analyzer as an optical biopsy tool for detecting human brain tumors compared to the commercial laboratory HR800 and WITec300 micro confocal Raman spectroscopy instruments. As of 2018, a total 1,938 VRR spectra were collected using LRR2000, HR800 and WITec300 Raman system, ex vivo. Identification of the four grades of glioma tumors and control tissues was performed based on the characteristic native molecular fingerprints. LRR2000 demonstrated consistent diagnostic results with HR800 and WITec300 Raman systems. LRR2000 showed the advantages of high speed, convenience and low cost compared to the two confocal micro Raman systems. Using artificial intelligence (AI)-based analysis of part of the data, the cross-validated accuracy for identifying glioma tumors is ~90% compared with gold standard histopathology examination.
3 citations (Crossref) [2023-10-31]
Keywords: Biopsy; Brain; Chemical analysis; Handhelds; Histology; Human brain; Industrial research; Molecular biology; Optical biopsies; Optical fibers; Optical molecular Pathology; Palmprint recognition; Principal component analysis; Principle component analysis; Probes; Resonance; Resonance Raman; Spectroscopy; Spectrum analysis; Support vector machines; Tissue engineering; Tumors; Vibrational spectroscopy; dept.phy; glioma tumor; handheld LRR2000 analyzer; human brain tissues; optical biopsy; principle component analysis(PCA); support vector machine (SVM); visible resonance Raman (VRR)

Measurement of inclusive charged-particle jet production in Au + Au collisions at sNN =200 GeV - STAR Collaboration (Physical Review C, 2020)
The STAR Collaboration at the Relativistic Heavy Ion Collider reports the first measurement of inclusive jet production in peripheral and central Au+Au collisions at √sNN=200 GeV. Jets are reconstructed with the anti-kT algorithm using charged tracks with pseudorapidity |η|<1.0 and transverse momentum 0.2<pchT,jet<30 GeV/c, with jet resolution parameter R=0.2, 0.3, and 0.4. The large background yield uncorrelated with the jet signal is observed to be dominated by statistical phase space, consistent with a previous coincidence measurement. This background is suppressed by requiring a high-transverse-momentum (high-pT) leading hadron in accepted jet candidates. The bias imposed by this requirement is assessed, and the pT region in which the bias is small is identified. Inclusive charged-particle jet distributions are reported in peripheral and central Au+Au collisions for 5<pchT,jet<25 GeV/c and 5<pchT,jet<30 GeV/c, respectively. The charged-particle jet inclusive yield is suppressed for central Au+Au collisions, compared to both the peripheral Au+Au yield from this measurement and to the pp yield calculated using the PYTHIA event generator. The magnitude of the suppression is consistent with that of inclusive hadron production at high pT and that of semi-inclusive recoil jet yield when expressed in terms of energy loss due to medium-induced energy transport. Comparison of inclusive charged-particle jet yields for different values of R exhibits no significant evidence for medium-induced broadening of the transverse jet profile for R <0.4 in central Au+Au collisions. The measured distributions are consistent with theoretical model calculations that incorporate jet quenching.
13 citations (Crossref) [2023-10-31] tex.ids: adamMeasurementInclusiveChargedparticle2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85097626551 type: Article
Keywords: dept.phy; peer-reviewed

Measurement of inclusive J/ψ polarization in p+p collisions at s =200 GeV by the STAR experiment - STAR Collaboration (Physical Review D, 2020)
We report on new measurements of inclusive J/ψ polarization at midrapidity in p+p collisions at √s=200 GeV by the STAR experiment at the Relativistic Heavy Ion Collider. The polarization parameters, λθ, λϕ, and λθϕ, are measured as a function of transverse momentum (pT) in both the helicity and Collins-Soper (CS) reference frames within pT<10 GeV/c. Except for λθ in the CS frame at the highest measured pT, all three polarization parameters are consistent with 0 in both reference frames without any strong pT dependence. Several model calculations are compared with data, and the one using the Color Glass Condensate effective field theory coupled with nonrelativistic QCD gives the best overall description of the experimental results, even though other models cannot be ruled out due to experimental uncertainties.
7 citations (Crossref) [2023-10-31] tex.ids: adamMeasurementInclusivePs2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85097129164 type: Article
Keywords: dept.phy; peer-reviewed

Beam-energy dependence of the directed flow of deuterons in Au+Au collisions - STAR Collaboration (Physical Review C, 2020)
We present a measurement of the first-order azimuthal anisotropy v1 of deuterons from Au+Au collisions at √sNN=7.7, 11.5, 14.5, 19.6, 27, and 39 GeV recorded with the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The energy dependence of the v1(y) slope, dv1/dy|y=0, for deuterons, where y is the rapidity, is extracted for semicentral collisions (10%–40% centrality) and compared with that of protons. While the v1(y) slopes of protons are generally negative for √sNN>10GeV, those for deuterons are consistent with zero, a strong enhancement of the v1(y) slope of deuterons is seen at the lowest collision energy (the largest baryon density) at √sNN=7.7GeV. In addition, we report the transverse momentum dependence of v1 for protons and deuterons. The experimental results are compared with transport and coalescence models.
8 citations (Crossref) [2023-10-31] tex.ids: adamBeamenergyDependenceDirected2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85094100808 type: Article
Keywords: dept.phy; peer-reviewed

Strange hadron production in Au+Au collisions at sNN =7.7, 11.5, 19.6, 27, and 39 GeV - STAR Collaboration (Physical Review C, 2020)
We present STAR measurements of strange hadron (K0S, Λ, ¯¯¯Λ, Ξ−, ¯¯¯Ξ+, Ω−, ¯¯¯Ω+, and ϕ) production at midrapidity (|y|<0.5) in Au+Au collisions at √sNN = 7.7–39 GeV from the Beam Energy Scan Program at the Relativistic Heavy Ion Collider (RHIC). Transverse-momentum spectra, averaged transverse mass, and the overall integrated yields of these strange hadrons are presented versus the centrality and collision energy. Antibaryon-to-baryon ratios (¯¯¯Λ/Λ, ¯¯¯Ξ+/Ξ−, ¯¯¯Ω+/Ω−) are presented as well and used to test a thermal statistical model and to extract the temperature normalized strangeness and baryon chemical potentials at hadronic freeze-out (μB/Tch and μS/Tch) in central collisions. Strange baryon-to-pion ratios are compared to various model predictions in central collisions for all energies. The nuclear modification factors (RCP) and antibaryon-to-meson ratios as a function of transverse momentum are presented for all collision energies. The K0S RCP shows no suppression for pT up to 3.5 GeV/c at energies of 7.7 and 11.5 GeV. The ¯¯¯Λ/K0S ratio also shows baryon-to-meson enhancement at intermediate pT (≈2.5 GeV/c) in central collisions at energies above 19.6 GeV. Both observations suggest that there is likely a change of the underlying strange quark dynamics at collision energies below 19.6 GeV.
52 citations (Crossref) [2023-10-31] tex.ids: adamStrangeHadronProduction2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85092797509 type: Article
Keywords: dept.phy; peer-reviewed

Beam energy dependence of net- Λ fluctuations measured by the STAR experiment at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2020)
The measurements of particle multiplicity distributions have generated considerable interest in understanding the fluctuations of conserved quantum numbers in the quantum chromodynamics (QCD) hadronization regime, in particular near a possible critical point and near the chemical freeze-out. Net-protons and net-kaons have been used as proxies for the net-baryon number and net-strangeness, respectively. We report the measurement of efficiency- and centrality-bin width-corrected cumulant ratios (C2/C1, C3/C2) of net-Λ distributions, in the context of both strangeness and baryon number conservation, as a function of collision energy, centrality, and rapidity. The results are for Au+Au collisions at five beam energies (√sNN=19.6, 27, 39, 62.4, and 200 GeV) recorded with the Solenoidal Tracker at RHIC (STAR). We compare our results to the Poisson and negative binomial (NBD) expectations, as well as to ultrarelativistic quantum molecular dynamics (UrQMD) and hadron resonance gas (HRG) model predictions. Both NBD and Poisson baselines agree with data within the statistical and systematic uncertainties. UrQMD describes the measured net-ΛC1 and C3 at 200 GeV reasonably well but deviates from C2, and the deviation increases as a function of collision energy. The ratios of the measured cumulants show no features of critical fluctuations. The chemical freeze-out temperatures extracted from a recent HRG calculation, which was successfully used to describe the net-proton, net-kaon, and net-charge data, indicate Λ freeze-out conditions similar to those of kaons. However, large deviations are found when comparing with temperatures obtained from net-proton fluctuations. The net-Λ cumulants show a weak but finite dependence on the rapidity coverage in the acceptance of the detector, which can be attributed to quantum number conservation.
10 citations (Crossref) [2023-10-31] tex.ids: adamBeamEnergyDependence2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85092548370 type: Article
Keywords: dept.phy; peer-reviewed

Underlying event measurements in p+p collisions at s =200 GeV at RHIC - STAR Collaboration (Physical Review D, 2020)
Particle production sensitive to nonfactorizable and nonperturbative processes that contribute to the underlying event associated with a high transverse momentum (pT) jet in proton+proton collisions at √s=200 GeV is studied with the STAR detector. Each event is divided into three regions based on the azimuthal angle with respect to the highest-pT jet direction: in the leading jet direction (“Toward”), opposite to the leading jet (“Away”), and perpendicular to the leading jet (“Transverse”). In the Transverse region, the average charged particle density is found to be between 0.4 and 0.6 and the mean transverse momentum, ⟨pT⟩, between 0.5 and 0.7 GeV/c for particles with pT>0.2 GeV/c at mid-pseudorapidity (|η|<1) and jet pT>15 GeV/c. Both average particle density and ⟨pT⟩ depend weakly on the leading jet pT. Closer inspection of the Transverse region hints that contributions to the underlying event from initial- and final-state radiation are significantly smaller in these collisions than at the higher energies, up to 13 TeV, recorded at the LHC. Underlying event measurements associated with a high-pT jet will contribute to our understanding of QCD processes at hard and soft scales at RHIC energies, as well as provide constraints to modeling of underlying event dynamics.
11 citations (Crossref) [2023-10-31] tex.ids: adamUnderlyingEventMeasurements2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85083517688 type: Article
Keywords: dept.phy; peer-reviewed

Bulk properties of the system formed in Au+Au collisions at sNN =14.5 GeV at the BNL STAR detector - STAR Collaboration (Physical Review C, 2020)
We report systematic measurements of bulk properties of the system created in Au+Au collisions at √sNN=14.5 GeV recorded by the STAR detector at the Relativistic Heavy Ion Collider (RHIC). The transverse momentum spectra of π±, K±, and p(¯p) are studied at midrapidity (|y|<0.1) for nine centrality intervals. The centrality, transverse momentum (pT), and pseudorapidity (η) dependence of inclusive charged particle elliptic flow (v2), and rapidity-odd charged particles directed flow (v1) results near midrapidity are also presented. These measurements are compared with the published results from Au+Au collisions at other energies, and from Pb+Pb collisions at √sNN=2.76 TeV. The results at √sNN=14.5 GeV show similar behavior as established at other energies and fit well in the energy dependence trend. These results are important as the 14.5-GeV energy fills the gap in μB, which is of the order of 100 MeV, between √sNN=11.5 and 19.6 GeV. Comparisons of the data with UrQMD and AMPT models show poor agreement in general.
16 citations (Crossref) [2023-10-31] tex.ids: adamBulkPropertiesSystem2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85082714606 type: Article
Keywords: dept.phy; peer-reviewed

Measurement of groomed jet substructure observables in p+p collisions at s=200 GeV with STAR - STAR Collaboration (Physics Letters B, 2020)
In this letter, measurements of the shared momentum fraction (zg) and the groomed jet radius (Rg), as defined in the SoftDrop algorithm, are reported in p+p collisions at s=200 GeV collected by the STAR experiment. These substructure observables are differentially measured for jets of varying resolution parameters from R=0.2−0.6 in the transverse momentum range 15<pT,jet<60 GeV/c. These studies show that, in the pT,jet range accessible at s=200 GeV and with increasing jet resolution parameter and jet transverse momentum, the zg distribution asymptotically converges to the DGLAP splitting kernel for a quark radiating a gluon. The groomed jet radius measurements reflect a momentum-dependent narrowing of the jet structure for jets of a given resolution parameter, i.e., the larger the pT,jet, the narrower the first splitting. For the first time, these fully corrected measurements are compared to Monte Carlo generators with leading order QCD matrix elements and leading log in the parton shower, and to state-of-the-art theoretical calculations at next-to-leading-log accuracy. We observe that PYTHIA 6 with parameters tuned to reproduce RHIC measurements is able to quantitatively describe data, whereas PYTHIA 8 and HERWIG 7, tuned to reproduce LHC data, are unable to provide a simultaneous description of both zg and Rg, resulting in opportunities for fine parameter tuning of these models for p+p collisions at RHIC energies. We also find that the theoretical calculations without non-perturbative corrections are able to qualitatively describe the trend in data for jets of large resolution parameters at high pT,jet, but fail at small jet resolution parameters and low jet transverse momenta.
16 citations (Crossref) [2023-10-31] tex.ids: adamMeasurementGroomedJet2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85095685198 type: Article
Keywords: Groomed jet radius; Jet substructure; SoftDrop; Splitting function; dept.phy; peer-reviewed

Investigation of the linear and mode-coupled flow harmonics in Au+Au collisions at sNN = 200 GeV - STAR Collaboration (Physics Letters B, 2020)
Flow harmonics (vn) of the Fourier expansion for the azimuthal distributions of hadrons are commonly employed to quantify the azimuthal anisotropy of particle production relative to the collision symmetry planes. While lower order Fourier coefficients (v2 and v3) are more directly related to the corresponding eccentricities of the initial state, the higher-order flow harmonics (vn>3) can be induced by a mode-coupled response to the lower-order anisotropies, in addition to a linear response to the same-order anisotropies. These higher-order flow harmonics and their linear and mode-coupled contributions can be used to more precisely constrain the initial conditions and the transport properties of the medium in theoretical models. The multiparticle azimuthal cumulant method is used to measure the linear and mode-coupled contributions in the higher-order anisotropic flow, the mode-coupled response coefficients, and the correlations of the event plane angles for charged particles as functions of centrality and transverse momentum in Au+Au collisions at nucleon-nucleon center-of-mass energy sNN= 200 GeV. The results are compared to similar LHC measurements as well as to several viscous hydrodynamic calculations with varying initial conditions.
10 citations (Crossref) [2023-10-31] tex.ids: adamInvestigationLinearModecoupled2020, adamInvestigationLinearModecoupled2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85090403270 type: Article
Keywords: Collectivity; Correlation; Shear viscosity; dept.phy; peer-reviewed

Results on total and elastic cross sections in proton–proton collisions at s=200 GeV - STAR Collaboration (Physics Letters B, 2020)
We report results on the total and elastic cross sections in proton-proton collisions at s=200 GeV obtained with the Roman Pot setup of the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The elastic differential cross section was measured in the squared four-momentum transfer range 0.045≤−t≤0.135 GeV2. The value of the exponential slope parameter B of the elastic differential cross section dσ/dt∼e−Bt in the measured −t range was found to be B=14.32±0.09(stat.)−0.28+0.13(syst.) GeV−2. The total cross section σtot, obtained from extrapolation of the dσ/dt to the optical point at −t=0, is σtot=54.67±0.21(stat.)−1.38+1.28(syst.) mb. We also present the values of the elastic cross section σel=10.85±0.03(stat.)−0.41+0.49(syst.) mb, the elastic cross section integrated within the STAR t-range σeldet=4.05±0.01(stat.)−0.17+0.18(syst.) mb, and the inelastic cross section σinel=43.82±0.21(stat.)−1.44+1.37(syst.) mb. The results are compared with the world data.
5 citations (Crossref) [2023-10-31] tex.ids: adamResultsTotalElastic2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85089410330 type: Article
Keywords: Diffraction; Elastic scattering; Proton-proton collisions; dept.phy; peer-reviewed

Identifying bound stellar companions to kepler exoplanet host stars using speckle imaging - Colton, Nicole M.; Horch, Elliott P; Everett, Mark E; Howell, Steve B; Davidson, James W., Jr.; Baptista, Brian J.; Casetti-Dinescu, Dana I (Astronomical Journal, 2021)
The Kepler mission and subsequent ground-based follow-up observations have revealed a number of exoplanet host stars with nearby stellar companions. This study presents speckle observations of 57 Kepler objects of interest (KOIs) that are also double stars, each observed over a 3-8 yr period, which has allowed us to track their relative motions with high precision. Measuring the position angle and separation of the companion with respect to the primary can help determine if the pair exhibits common proper motion, indicating it is likely to be a bound binary system. We report on the motions of 34 KOIs that have close stellar companions, three of which are triple stars, for a total of 37 companions studied. Eighteen of the 34 systems are confirmed exoplanet hosts, including one triple star, while four other systems have been subsequently judged to be false positives and twelve are yet to be confirmed as planet hosts. We find that 21 are most likely to be common proper motion pairs, 4 are line-of-sight companions, and 12 are of an uncertain disposition at present. The fraction of the confirmed exoplanet host systems that are common proper motion pairs is approximately 86% in this sample. In this subsample, the planets are exclusively found with periods of less than 110 days, so that in all cases the stellar companion is found at a much larger separation from the planet host star than the planet itself. A preliminary period-radius relation for the confirmed planets in our sample suggests no obvious differences at this stage with the full sample of known exoplanets. © 2020. The American Astronomical Society. All rights reserved.
10 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85098523712
Keywords: dept.phy; peer-reviewed

HAT-P-68b: A transiting hot jupiter around a K5 dwarf star - Lindor, Bethlee M.; Hartman, Joel D.; Bakos, Gáspár Á.; Bhatti, Waqas; Csubry, Zoltan; Penev, Kaloyan; Bieryla, Allyson; Lathman, David W; Torres, Guillermo; Buchhave, Lars A; de Val-Borro, Miguel; Howard, Andrew W; et al. (Astronomical Journal, 2021)
We report the discovery by the ground-based Hungarian-made Automated Telescope Network (HATNet) survey of the transiting exoplanet HAT-P-68b, which has a mass of 0.724 ± 0.043 MJ, and radius of 1.072 ± 0.012 RJ. The planet is in a circular P = 2.2984 day orbit around a moderately bright V = 13.937 ± 0.030 magnitude K-dwarf star of mass ${0.673}_{-0.014}{+0.020}$ M⊙, and radius 0.6726 ± 0.0069 R⊙. The planetary nature of this system is confirmed through follow-up transit photometry obtained with the Fred L. Whipple Observatory (FLWO) 1.2 m telescope, high-precision radial velocities measured using Keck I/High Resolution Echelle Spectrometer (HIRES), FLWO 1.5 m/Tillinghast Reflector Echelle Spectrograph (TRES), and Observatoire de Haute-Provence (OHP) 1.9 m/Sophie, and high-spatial-resolution speckle imaging from WIYN 3.5 m/DSSI. HAT-P-68 is at an ecliptic latitude of +3° and outside the field of view of both the NASA Transiting Exoplanet Survey Satellite primary mission and the K2 mission. The large transit depth of 0.036 mag (r band) makes HAT-P-68b a promising target for atmospheric characterization via transmission spectroscopy.
2 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85101652867
Keywords: dept.phy; peer-reviewed

Glioma tumors classified using visible resonance raman spectroscopy and machine learning - Wu, Binlin; Zhou, Yan; Zhang, Liang; Zhang, Shengjia; Yu, Xinguang; Wang, Eric; Zhu, Ke; Liu, Cheng-hui; Alfano, Robert R. (Frontiers in Optics, 2020)
Machine learning algorithms were used to classify and analyze spectral data collected by visible resonance Raman spectroscopy to distinguish normal human brain tissue and glioma tumor tissues at different grades and show promising results. © OSA 2020 © 2020 The Author(s)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy; ⛔ No DOI found

Measurement of away-side broadening with self-subtraction of flow in Au+Au collisions at √sNN = 200 GeV - STAR Collaboration (Chinese Physics C, 2020)
High transverse momentum ( ) particle production is suppressed owing to the parton (jet) energy loss in the hot dense medium created in relativistic heavy-ion collisions. Redistribution of energy at low-to-modest has been difficult to measure, owing to large anisotropic backgrounds. We report a data-driven method for background evaluation and subtraction, exploiting the away-side pseudorapidity gaps, to measure the jetlike correlation shape in Au+Au collisions at GeV in the STAR experiment. The correlation shapes, for trigger particles and various associated particle ranges within , are consistent with Gaussians, and their widths increase with centrality. The results indicate jet broadening in the medium created in central heavy-ion collisions.
1 citations (Crossref) [2023-10-31] tex.ids: adamMeasurementAwaysideBroadening2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85092055995 type: Article
Keywords: dept.phy; di-hadron correlations; heavy-ion; jet; peer-reviewed

Selected topics in electronics and systems - nanotechnology for electronics, photonics, biosensors, and emerging technologies - Jain, F; Broadbridge, Christine; Gherasimova, M; Tang, H (WORLD SCIENTIFIC, 2020)
Keywords: dept.phy

Measurement of the central exclusive production of charged particle pairs in proton-proton collisions at √s = 200 GeV with the STAR detector at RHIC - STAR Collaboration (Journal of High Energy Physics, 2020)
We report on the measurement of the Central Exclusive Production of charged particle pairs h+h− (h = π, K, p) with the STAR detector at RHIC in proton-proton collisions at s$$ \sqrt{s} $$= 200 GeV. The charged particle pairs produced in the reaction pp → p′ + h+h− + p′ are reconstructed from the tracks in the central detector and identified using the specific energy loss and the time of flight method, while the forward-scattered protons are measured in the Roman Pot system. Exclusivity of the event is guaranteed by requiring the transverse momentum balance of all four final-state particles. Differential cross sections are measured as functions of observables related to the central hadronic final state and to the forward-scattered protons. They are measured in a fiducial region corresponding to the acceptance of the STAR detector and determined by the central particles’ transverse momenta and pseudorapidities as well as by the forward-scattered protons’ momenta. This fiducial region roughly corresponds to the square of the four-momentum transfers at the proton vertices in the range 0.04 GeV2 < −t1, −t2 < 0.2 GeV2, invariant masses of the charged particle pairs up to a few GeV and pseudorapidities of the centrally-produced hadrons in the range |η| < 0.7. The measured cross sections are compared to phenomenological predictions based on the Double Pomeron Exchange (DPE) model. Structures observed in the mass spectra of π+π− and K+K− pairs are consistent with the DPE model, while angular distributions of pions suggest a dominant spin-0 contribution to π+π− production. For π+π− production, the fiducial cross section is extrapolated to the Lorentz-invariant region, which allows decomposition of the invariant mass spectrum into continuum and resonant contributions. The extrapolated cross section is well described by the continuum production and at least three resonances, the f0(980), f2(1270) and f0(1500), with a possible small contribution from the f0(1370). Fits to the extrapolated differential cross section as a function of t1 and t2 enable extraction of the exponential slope parameters in several bins of the invariant mass of π+π− pairs. These parameters are sensitive to the size of the interaction region.
6 citations (Crossref) [2023-10-31] tex.ids: adamMeasurementCentralExclusive2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85089773182 type: Article
Keywords: Diffraction; Forward physics; Hadron-Hadron scattering (experiments); dept.phy; peer-reviewed

Measurement of D0 -meson + hadron two-dimensional angular correlations in Au+ Au collisions at sNN =200 GeV - STAR Collaboration (Physical Review C, 2020)
Open heavy-flavor hadrons provide unique probes of the medium produced in ultrarelativistic heavy-ion collisions. Due to their increased mass relative to light-flavor hadrons, long lifetime, and early production in hard-scattering interactions, they provide access to the full evolution of the partonic medium formed in heavy-ion collisions. This paper reports two-dimensional (2D) angular correlations between neutral D mesons and unidentified charged particles produced in minimum-bias Au+Au collisions at √sNN=200GeV. D0 and ¯¯¯D0 mesons are reconstructed via their weak decay to K∓π± using the Heavy Flavor Tracker in the Solenoidal Tracker at RHIC experiment. Correlations on relative pseudorapidity and azimuth (Δη,Δϕ) are presented for peripheral, midcentral, and central collisions with D0 transverse momentum from 2–10GeV/c. Attention is focused on the 2D peaked correlation structure near the triggered D0 meson, the near-side (NS) peak, which serves as a proxy for a charm-quark-containing jet. The correlated NS yield of charged particles per D0 meson and the 2D widths of the NS peak increase significantly from peripheral to central collisions. These results are compared with similar correlations using unidentified charged particles, consisting primarily of light-flavor hadrons, at similar trigger particle momenta. Similar per-trigger yields and widths of the NS correlation peak are observed. The present results provide additional evidence that D0 mesons undergo significant interactions with the medium formed in heavy-ion collision and show, for the first time, significant centrality evolution of the NS 2D peak in the correlations of particles associated with a heavy-flavor hadron produced in these collisions.
6 citations (Crossref) [2023-10-31] tex.ids: adamMeasurementD0Meson2020, adamMeasurementD0Meson2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85089306320 type: Article
Keywords: dept.phy; peer-reviewed

First measurement of λc baryon production in au+au collisions at sNN=200 GeV - STAR Collaboration (Physical Review Letters, 2020)
We report on the first measurement of the charmed baryon Λ±c production at midrapidity (|y|<1) in Au+Au collisions at √sNN=200 GeV collected by the STAR experiment at the Relativistic Heavy Ion Collider. The Λc/D0 [denoting (Λ+c+Λ−c)/(D0+¯D0)] yield ratio is measured to be 1.08±0.16 (stat)±0.26 (sys) in the 0%–20% most central Au+Au collisions for the transverse momentum (pT) range 3<pT<6 GeV/c. This is significantly larger than the pythia model calculations for p+p collisions. The measured Λc/D0 ratio, as a function of pT and collision centrality, is comparable to the baryon-to-meson ratios for light and strange hadrons in Au+Au collisions. Model calculations including coalescence hadronization for charmed baryon and meson formation reproduce the features of our measured Λc/D0 ratio.
38 citations (Crossref) [2023-10-31] tex.ids: adamFirstMeasurementLc2020, adamFirstMeasurementLc2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85084355470 type: Article
Keywords: Au+Au collisions; Bosons; Colliding beam accelerators; Germanium compounds; Gold compounds; Hadronization; Hadrons; Heavy ions; Mid-rapidity; Model calculations; Particle detectors; Relativistic Heavy Ion Collider; STAR experiment; Transverse momenta; Yield ratios; dept.phy; peer-reviewed

Ultra-violet argon dayglow lines in the atmosphere of mercury - Zeelik, Michael; Dalgarno, Alexander (Planetary and Space Science, 1973)
We investigate the response of an atmosphere of argon to solar ultra-violet radiation. With the assumption that Mercury has an argon atmosphere that is optically thick to ionizing radiation the intensities of the ultra-violet dayglow lines resulting from photoelectron impact are calculated. For most of the model atmospheres, the predicted intensities are above the detection threshold of the 1973 Venus-Mercury ultra-violet spectrometer of Broadfoot, McElroy and Belton. © 1973.
1 citations (Crossref) [2023-10-31] Citation Key Alias: pop00099 tex.type: [object Object]
Keywords: dept.phy

A technique for measuring the 3-dimensional to 2-dimensional conductivity change of YBCO superconductors at the normal-to-superconducting phase change - Hmurcik, Lawrence V; Bidarian, A; Ibarra, B; Matthews, L D (Journal of Materials Science, 1998)
It is well known that conduction in YBa2Cu3O7 (YBCO) is by means of copper "planes" and "chains," where planes and chains describe the degree of bonding between copper and oxygen. Changes of conductivity versus temperature have been used to show that conduction in YBCO in the normal state is 3-dimensional, while conduction approaching the onset of the superconducting state is first 2-dimensional and then 3-dimensional. We have found another method to monitor this 2-to-3 transition. Using square samples, and measuring the voltage at each corner caused by a current applied to the opposite corners, one can find the conductivities along the x-axis and the y-axis. The ratio of these conductivities is unity for homogeneous samples in the normal state. However, in transition to the superconducting state, the ratio of conductivities changes. We examine this change as a function of sample purity, sample history, and exposure to an external magnetic field. Our data are consistent with data reported in the literature, and they suggest the existence of another state change deep in the superconducting state, which is only observable with the application of a magnetic field., Measurements were also carried out to correlate the anisotropy with sample porosity. Measurements of normal state resistivity, critical temperature, and critical current characterize the sample's porosity, and these data affect the anisotropy in the superconducting state in a manner directly proportional to the porosity., (C)1998 Kluwer Academic Publishers
1 citations (Crossref) [2023-10-31] Place: (C)1998 Kluwer Academic Publishers Publisher: (1)Science and Engineering, University of Bridgeport, Bridgeport, CT 06601, USA APS #MHM741373; E-mail: hmurcik@cse.bridgeport.edu
Keywords: Anisotropy; Critical temperature; Electric conductivity measurement; Electric current measurement; High temperature superconductors; Magnetic field effects; Oxide superconductors; Phase transitions; Porosity; Temperature measurement; Voltage measurement; Yttrium barium copper oxides; dept.phy

Pressure-dependent photoluminescence spectroscopy of a chromium doped chloride elpasolite crystal - Rinzler, A G; Kappers, L A; Bartram, R H; Dolan, J F (International Quantum Electronics Conference, 1990)
tex.type: Proceedings paper
Keywords: dept.phy; ⛔ No DOI found

Speckle interferometry at SOAR in 2019 - Tokovinin, Andrei; Mason, Brian D.; Mendez, Rene A.; Costa, Edgardo; Horch, Elliott P. (The Astronomical Journal, 2020)
The results of speckle-interferometric observations at the 4.1 m Southern Astrophysical Research Telescope in 2019 are given, totaling 2555 measurements of 1972 resolved pairs with separations from 15 mas (median 0.″21) and magnitude difference up to 6 mag, and non-resolutions of 684 targets. We resolved for the first time 90 new pairs or subsystems in known binaries. This work continues our long-term speckle program. Its main goal is to monitor orbital motion of close binaries, including members of high-order hierarchies and Hipparcos pairs in the solar neighborhood. We give a list of 127 orbits computed using our latest measurements. Their quality varies from excellent (25 orbits of grades 1 and 2) to provisional (47 orbits of grades 4 and 5). © 2020 The American Astronomical Society. All rights reserved.
20 citations (Crossref) [2023-10-31] tex.ids: tokovininSpeckleInterferometrySOAR2020, tokovininSpeckleInterferometrySoar2020 tex.adsnote: Provided by the SAO/NASA Astrophysics Data System tex.adsurl: https://ui.adsabs.harvard.edu/abs/2020AJ....160....7T arXiv: 2005.05305 [astro-ph.SR] tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85087554458 tex.eid: 7 type: Article
Keywords: 1081; 154; 1777; Astrophysics - Solar and Stellar Astrophysics; Binary stars; Multiple stars; Visual binary stars; dept.phy; peer-reviewed

Observations of binary stars with the differential speckle survey instrument. IX. Observations of known and suspected binaries, and a partial survey of be stars - Horch, Elliott P.; van Belle, Gerard T.; Davidson, James W., Jr.; Willmarth, Daryl; Fekel, Francis C.; Muterspaugh, Matthew; Casetti-Dinescu, Dana I.; Hahne, Frederick W.; Granucci, Nicole M.; Clark, Catherine; Winters, Jennifer G.; Rupert, Justin D.; et al. (The Astronomical Journal, 2020)
We report 370 measures of 170 components of binary and multiple-star systems, obtained from speckle imaging observations made with the Differential Speckle Survey Instrument at Lowell Observatory's Discovery Channel Telescope in 2015 through 2017. Of the systems studied, 147 are binary stars, 10 are seen as triple systems, and 1 quadruple system is measured. Seventy-six high-quality nondetections and 15 newly resolved components are presented in our observations. The uncertainty in relative astrometry appears to be similar to our previous work at Lowell, namely, linear measurement uncertainties of approximately 2 mas, and the relative photometry appears to be uncertain at the 0.1-0.15 mag level. Using these measures and those in the literature, we calculate six new visual orbits, including one for the Be star 66 Oph and two combined spectroscopic-visual orbits. The latter two orbits, which are for HD 22451 (YSC 127) and HD 185501 (YSC 135), yield individual masses of the components at the level of 2% or better, and independent distance measures that in one case agrees with the value found in the Gaia DR2 and in the other disagrees at the 2σ level. We find that HD 22451 consists of an F6V+F7V pair with orbital period of 2401.1 ± 3.2 days and masses of 1.342 ± 0.029 and 1.236 ± 0.026M⊙. For HD 185501, both stars are G5 dwarfs that orbit one another with a period of 433.94 ± 0.15 days, and the masses are 0.898 ± 0.012 and 0.876 ± 0.012M⊙ . We discuss the details of both the new discoveries and the orbit objects. © 2020. The American Astronomical Society. All rights reserved..
17 citations (Crossref) [2023-10-31] tex.ids: horchObservationsBinaryStars2020a tex.adsnote: Provided by the SAO/NASA Astrophysics Data System tex.adsurl: https://ui.adsabs.harvard.edu/abs/2020AJ....159..233H arXiv: 2004.03065 [astro-ph.SR] tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85086596087 tex.eid: 233 type: Article
Keywords: Astrophysics - Earth and Planetary Astrophysics; Astrophysics - Instrumentation and Methods for Astrophysics; Astrophysics - Solar and Stellar Astrophysics; dept.phy; peer-reviewed

A hot terrestrial planet orbiting the bright M dwarf L 168-9 unveiled by TESS - Astudillo-Defru, N.; Cloutier, R.; Wang, S. X.; Teske, J.; Brahm, R.; Hellier, C.; Ricker, G.; Vand erspek, R.; Latham, D.; Seager, S.; Winn, J. N.; Jenkins, J. M.; et al. (Astronomy & Astrophysics, 2020)
We report the detection of a transiting super-Earth-sized planet (R = 1.39 ± 0.09 R⊕ ) in a 1.4-day orbit around L 168-9 (TOI-134), a bright M1V dwarf (V = 11, K = 7.1) located at 25.15 ± 0.02 pc. The host star was observed in the first sector of the Transiting Exoplanet Survey Satellite (TESS) mission. For confirmation and planet mass measurement purposes, this was followed up with ground-based photometry, seeing-limited and high-resolution imaging, and precise radial velocity (PRV) observations using the HARPS and Magellan/PFS spectrographs. By combining the TESS data and PRV observations, we find the mass of L 168-9 b to be 4.60 ± 0.56 M⊕ and thus the bulk density to be 1.74-0.33+0.44 times higher than that of the Earth. The orbital eccentricity is smaller than 0.21 (95% confidence). This planet is a level one candidate for the TESS mission's scientific objective of measuring the masses of 50 small planets, and it is one of the most observationally accessible terrestrial planets for future atmospheric characterization. © ESO 2020.
32 citations (Crossref) [2023-10-31] tex.ids: astudillo-defruHotTerrestrialPlanet2020a tex.adsnote: Provided by the SAO/NASA Astrophysics Data System tex.adsurl: https://ui.adsabs.harvard.edu/abs/2020A&A...636A..58A arXiv: 2001.09175 [astro-ph.EP] tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85084144642 tex.eid: A58 type: Article
Keywords: Astrophysics - Earth and Planetary Astrophysics; Astrophysics - Solar and Stellar Astrophysics; Atmospheric characterization; Earth (planet); High-resolution imaging; Mass measurements; Orbital eccentricity; Orbits; Planetary systems; Planets; Radial velocity; Scientific objectives; Seeing limited; Stars: individual: L 168-9; Stars: late-type; Techniques: photometric; Techniques: radial velocities; Terrestrial planets; dept.phy; peer-reviewed; planetary systems; stars: individual: L 168-9; stars: late-type; techniques: photometric; techniques: radial velocities

Growth of AlGaN nanowires by metalorganic chemical vapor deposition - Su, J.; Gherasimova, M.; Cui, G.; Tsukamoto, Hironori; Han, J.; Onuma, T.; Kurimoto, M.; Chichibu, Shigefusa F.; Broadbridge, Christine; He, Y.; Nurmikko, Arto V. (Applied Physics Letters, 2005)
Growth of ternary AlGaN nanowires using metalorganic chemical vapor deposition is investigated. Structural, chemical, and optical characterization at nanoscopic scale is carried out by high resolution transmission electron microscopy, x-ray energy dispersive spectroscopy, and spatially resolved cathodoluminescence. Spontaneous formation of Al (Ga) NGaN coaxial nanowires with distinct emission at 370 nm is observed. It is identified that the interplay between surface kinetics and thermodynamics facilitates the catalytic growth of GaN core while a limited surface diffusion of Al adatoms leads to nonselective, vapor-solid growth of Al(Ga)N sheath. The observation points to a fundamental difference in nanosynthesis using near-equilibrium and nonequilibrium techniques. © 2005 American Institute of Physics.
37 citations (Crossref) [2023-10-31] Citation Key Alias: pop00071 tex.type: [object Object]
Keywords: Aluminum compounds; Cathodoluminescence; Coaxial nanowires; Energy dispersive spectroscopy; Metallorganic chemical vapor deposition; Nanoscopic scale; Nanostructured materials; Optical properties; Reaction kinetics; Surface kinetics; Synthesis (chemical); Transmission electron microscopy; X-ray energy dispersive spectroscopy; dept.phy

Comparison of extended x-ray absorption fine structure and Scherrer analysis of x-ray diffraction as methods for determining mean sizes of polydisperse nanoparticles - Calvin, Scott; Luo, Shuixiang; Caragianisbroadbridge, C; Mcguinness, J K; Anderson, Eric; Lehman, A; Wee, K H; Morrison, Shannon A; Kurihara, L K (Applied Physics Letters, 2005)
Curve fitting of extended x-ray absorption fine structure (EXAFS) spectra, transmission electron microscopy (TEM) imaging, and Scherrer analysis of x-ray diffraction (XRD) are compared as methods for determining the mean crystallite size in polydisperse samples of platinum nanoparticles. By applying the techniques to mixtures of pure samples, it is found that EXAFS correctly determines the relative mean sizes of these polydisperse samples, while XRD tends to be weighted more toward the largest crystallites in the sample. Results for TEM are not clear cut, due to polycrystallinity and aggregation, but are consistent with the other results. © 2005 American Institute of Physics.
68 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/112-863-384-595-634 tex.type: [object Object]
Keywords: Curve fitting; Diffraction; EXAFS; Imaging techniques; Nanostructured materials; Platinum; Platinum nanoparticles; Polydisperse samples; Transmission electron microscopy; X ray diffraction; dept.phy

Conceptual Underpinnings of Students’ Ability to Understand Reflections from a Plane Mirror - Cummings, Karen (AIP Conference Proceedings, 2005)
In this paper we explore students' pre-instruction knowledge of several conceptual and procedural pieces of knowledge that we believe are prerequisite to one's ability to generate correct light ray diagrams and understand image formation by a plane mirror. The research population is an algebra-based, introductory physics class of about 50 students at a medium-sized, urban, public university. Both individual interviews and written free response questions were used to gather data. © 2005 American Institute of Physics.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/096-094-774-595-400, pop00418 tex.number: [object Object]
Keywords: dept.phy

An exploration of microscopy for educational applications in the high school classroom - Fitzsimmons, Ryan; Koekkoek, Robert; Caragianis-Broadbridge, Christine; Lehman, Ann; Cummings, Karen (MRS Proceedings, 2005)
This project was initiated with an undergraduate student's exploration of two advanced research tools: the scanning electron microscope (SEM) and the atomic force microscope (AFM). A research project was developed to study the application of microscopy to introductory physics instruction, Nine modules covering various aspects of introductory physics were created. Module components included discussions, laboratory experiments and assessments. Four of the nine modules were implemented in various high school classes. Assessments were used to compare student learning with the modules versus standard textbook/lecture techniques, Preliminary results of this study are presented along with recently developed methods created to facilitate implementation of these modules within the high school classroom. © 2006 Materials Research Society.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/060-305-083-686-777 tex.type: [object Object]
Keywords: Atomic force microscopy; Education; Project management; Scanning electron microscopy; School buildings; School classroom; Student learning; dept.phy

A preliminary investigation of the efficacy of oral motor exercises for children with mild articulation disorders - Guisti Braislin, M.A.; Cascella, P.W. (International Journal of Rehabilitation Research, 2005)
Although oral motor therapy is sometimes used to treat articulation disorders in school-age children, several reports question its efficacy. In this case study, four first-grade students, two boys and two girls, received 15 half-hour sessions of oral motor treatment based on Easy Does it for Articulation: An Oral Motor Approach (). Pre- and post-test measures of the children's articulation indicated no real differences in speech production. These results question the efficacy of general and discrete oral motor exercises because they did not enhance the children's speech production. © 2005 Lippincott Williams & Wilkins.
19 citations (Crossref) [2023-10-31]
Keywords: *Articulation Disorders/th [Therapy]; *Exercise Therapy/mt [Methods]; *Mouth; Articulation; Articulation Disorders; Articulation disorders; Child; Efficacy; Exercise Therapy; Exercise equipment; Female; Humans; Male; Mouth; Oral motor exercises; Patient monitoring; Patient rehabilitation; Speech; Speech production; Treatment Outcome; article; case report; child; consonant; dept.phy; efficacy; female; human; interrater reliability; kinesiotherapy; male; methodology; mouth; oral motor exercises; preschool child; priority journal; speech articulation; speech disorder; speech therapy; standardization; treatment indication; treatment outcome

Catalytic growth of group III-nitride nanowires and nanostructures by metalorganic chemical vapor deposition - Su, J; Cui, G; Gherasimova, M; Tsukamoto, Hironori; Han, J; Ciuparu, Dragos; Lim, Sangyun; Pfefferle, Lisa D; He, Y; Nurmikko, A V; Broadbridge, Christine; Lehman, Ann Hein (Applied Physics Letters, 2005)
We report flexible synthesis of group III-nitride nanowires and nanostructures by metalorganic chemical vapor deposition (MOCVD) via a catalytic vapor-liquid-solid (VLS) growth mechanism. Supersaturation and surface stoichiometry strongly influence the stability of liquid droplets and growth selectivity. To facilitate and sustain the VLS growth, indium catalyst is introduced based on thermodynamic consideration. The employment of mesoporous molecular sieves (MCM-41) helps to prevent the coalescence of catalyst droplets and to promote nucleation statistics. Both GaN and AlN nanowires have been synthesized using MOCVD. Three-dimensional AlNGaN trunk-branch nanostructures are reported to illustrate the versatility of incorporating the VLS mechanism into MOCVD process. © 2005 American Institute of Physics.
55 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/046-539-752-343-072 tex.type: [object Object]
Keywords: Catalysis; Catalysts; Growth kinetics; Indium; Metallorganic chemical vapor deposition; Molecular sieves; Nanostructured materials; Nanowires; Nitrides; Nucleation; Scanning electron microscopy; Stoichiometry; Supersaturation; Synthesis (chemical); Thermodynamics; Transmission electron microscopy; Trimethyl-gallium (TMGa); Trimethylaluminum (TMAl); Vapor-solid-liquid (VLS) growth mechanism; dept.phy

A hybrid epitaxy method for InAs on GaP - Chen, A; Yulius, Aristo; Woodall, J M; Broadbridge, Christine (Applied Physics Letters, 2004)
The interface formation mechanism during the molecular-beam epitaxy (MBE) of InAs/GaP has been studied with the aid of the In-Ga-P phase diagram. It is discovered that an initial dissolution and crystallization process similar to liquid phase epitaxy (LPE) may happen at sufficiently high temperature, resulting in a graded composition at the interface. Consequently, "parasitic LPE/MBE" is the name for this hybrid form of MBE. High-resolution TEM images confirm the existence of the interfacial layer in the sample grown at high temperature. The graded interface smears out the band offset and leads to a nonrectifying heterojunction. Low-temperature (LT) MBE growth can turn off the LPE component, enabling the growth of an abrupt interface. Based on this "LPE/MBE" model, a LT MBE technique is developed to grow an abrupt InAs/InGaP interface for heterojunction power Schottky rectifiers. The LT InAs/InGaP heterojunction demonstrates nearly ideal Schottky rectifier characteristics, while the sample grown at high temperature shows resistive ohmic characteristics. The LT InAs/InGaP Schottky diode also demonstrates good stability with respect to anneal temperature, similar to the InAs/GaP heterojunctions. © 2004 American Institute of Physics.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-537-776-623-144 tex.type: [object Object]
Keywords: Baliga figure of merit (BFOM); Current voltage characteristics; Liquid phase epitaxy; Metal-semiconductor (MS) diodes; Molecular beam epitaxy; Phase diagrams; Rapid thermal annealer (RTA); Rapid thermal annealing; Schottkey rectifiers; Schottky barrier diodes; Semiconducting gallium compounds; Semiconducting indium compounds; Transmission electron microscopy; dept.phy

Attitudes Toward Problem Solving as Predictors of Student Success - Cummings, Karen (AIP Conference Proceedings, 2004)
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/147-561-918-415-471, pop00071 tex.number: [object Object]
Keywords: dept.phy

Vapor-liquid-solid growth of III-Nitride nanowires and heterostructures by metal-organic chemical vapor deposition - Su, J; Gherasimova, M; Cui, G; Han, J; Lim, Sangyun; Ciuparu, Dragos; Pfefferle, Lisa D; He, Y; Nurmikko, A V; Broadbridge, Christine; Lehman, Ann Hein; Onuma, T; et al. (MRS Proceedings, 2004)
We report flexible synthesis of III-Nitride nanowires and heterostructures by metal-organic chemical vapor deposition (MOCVD) via a catalytic vapor-liquid-solid (VLS) growth mechanism. Indium is used as an in-situ catalyst to facilitate and sustain the stability of liquid phase droplet for VLS growth based on thermodynamic consideration. The employment of mesoporous molecular sieves (MCM-41) helps to prevent the coalescence of catalyst droplets and to promote nucleation statistics. Cathodoluminescence (CL) of GaN nanowires shows near band-edge emission at 370nm, and strong E 2 phonon peak is observed at room temperature in Raman scattering spectra. Both binary GaN and AlN nanowires have been synthesized by MOCVD. Three-dimensional AlN/GaN trunk-branch nanostructures are reported to illustrate the versatility of incorporating the VLS mechanism into MOCVD process. © 2005 Materials Research Society.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-591-869-918-808 tex.type: [object Object]
Keywords: Catalysis; Heterojunctions; Metallorganic chemical vapor deposition; Molecular beam epitaxy; Nanoelectronics; Nanostructured materials; Nanowires; Nucleation; Optical characterization; Synthesis (chemical); Thermodynamics; Vapor-liquid-solid (VLS) growth; dept.phy

Understanding paramagnetic spin correlations in the spin-liquid pyrochlore Tb 2 Ti 2 O 7 - Kao, Ying-Jer; Enjalran, Matthew; Maestro, Adrian Del; Molavian, Hamid R.; Gingras, Michel J. P. (Physical Review B, 2003)
Recent elastic and inelastic neutron scattering studies of the highly frustrated pyrochlore antiferromagnet Tb2Ti2O7 have shown some very intriguing features that cannot be modeled by the local 〈111〉 classical Ising model, naively expected to describe this system at low temperatures. By including single-ion excitations from the ground state doublet to higher crystal field levels, we successfully describe the elastic neutron scattering pattern and dispersion relations in Tb2Ti2O7, quantitatively consistent with experimental observations. © 2003 The American Physical Society.
72 citations (Crossref) [2023-10-31] Citation Key Alias: pop00050 tex.type: [object Object]
Keywords: article; complex formation; correlation analysis; dept.phy; low temperature; molecular model; neutron scattering; oxygen; quantitative analysis; terbium; titanium

Thin film thickness and grain structure determination of ferroelectric SrBi2Ta2O9 with cross-sectional atomic force microscopy - Pechkis, Daniel L.; Caragianis-Broadbridge, Christine; Lehman, Ann Hein; Klein, Kate; Han, Jin-ping; Ma, Tso-Ping (Microscopy and Microanalysis, 2002)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00148 tex.type: [object Object]
Keywords: dept.phy

Alloy formation in nanostructured silicon - Gao, Bo; Sinha, Saion K.; Fleming, Les; Zhou, Otto (Advanced Materials, 2001)
250 citations (Crossref) [2023-10-31] Citation Key Alias: pop00001 tex.type: [object Object]
Keywords: dept.phy

Microstructure and physical properties of ferroelectric-gate memory capacitors with various buffer layers - Caragianis-Broadbridge, Christine; Han, J; Ma, T P; Lehman, Ann Hein; Zhu, Wenjuan; Luo, Zhijiong; Pechkis, Daniel; Laube, Bruce L (MRS Proceedings, 2001)
This paper reports the microstructure and physical properties of ferroelectric capacitors formed from SrBi2Ta2O9 (SBT) layers on Si with various buffer layers including jet-vapor deposited silicon nitride, zirconium oxide, hafnium oxide and thermally grown silicon oxide. Results from cross-sectional transmission electron microscopy (X-TEM), energy dispersive spectroscopy (EDS), X-Ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and non-contact atomic force microscopy (nc-AFM) data coupled with capacitance-voltage (C-V) and current-voltage (I-V) data indicate that both the microstructure and physical properties of SBT films deposited on silicon are dependent on the buffer layer material employed.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-822-098-712-167 tex.type: [object Object]
Keywords: Atomic force microscopy; Buffer layers; Capacitance; Capacitors; Electric currents; Electric potential; Energy dispersive spectroscopy; Ferroelectric devices; Ferroelectric-gate memory capacitors; Gates (transistor); Microstructure; Silica; Silicon nitride; Thin films; Transmission electron microscopy; X ray diffraction analysis; X ray photoelectron spectroscopy; dept.phy

Synthesis of silicon nano-dendrites - Sinha, Saion K; Gao, Bo; Zhou, Otto (MRS Proceedings, 2001)
A new branched silicon nanostructure called Silicon Nano-Dendrite (SiND) was prepared by Laser ablation. During the Laser ablation process, the Argon flow was switched on and off very fast and simultaneously decreasing the flow rate, to create a non-steady-state flow. The resulting structure will open up new avenues in molecular electronics as the FeSi2 nano-particle at the end can be used to grow nanotube-nanowire junctions.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-722-833-203-829 tex.type: [object Object]
Keywords: Carbon nanotubes; Electron diffraction; Fullerenes; Laser ablation; Molecular electronic applications; Nanostructured materials; Semiconducting silicon; Semiconductor quantum dots; Silicon nano-dendrites; Synthesis (chemical); Transmission electron microscopy; dept.phy

Ccd speckle observations of binary stars with the wiyn telescope. vi. measures during 2007-2008 - Horch, Elliott P.; Falta, David; Anderson, Lisa M.; DeSousa, Michael D.; Miniter, Craig M.; Ahmed, Tasmia; van Altena, William F. (The Astronomical Journal, 2009)
Results of 974 speckle observations of 546 binary stars are presented. Observations were obtained at the WIYN 3.5 m Telescope at Kitt Peak National Observatory during the time interval from 2007 January to 2008 June. In all cases, the relative separation and position angle of the components are measured, and the magnitude difference is determined in 809 cases. The precision of the results as judged from repeat observations and objects with very well-determined orbits is similar to previous papers in this series, namely ∼ 3 mas in separation and <1° in position angle in most cases. Similarly, the photometric precision remains consistent with previous WIYN speckle data, on average ∼ 0.1 mag per observation. Six systems of special interest are discussed. © 2010. The American Astronomical Society. All rights reserved.
58 citations (Crossref) [2023-10-31] Citation Key Alias: pop00066 tex.type: [object Object]
Keywords: Binaries: visual; Techniques: high angular resolution; Techniques: interferometric; Techniques:Photometric; dept.phy; peer-reviewed

Low loss EELS study of the ultrathin SrTiO3 film grown on the si single crystal - Su, Dong; Couillard, Martin; Sawicki, M; Broadbridge, Christine; Zhu, Y. (Microscopy and Microanalysis, 2009)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00259 tex.type: [object Object]
Keywords: dept.phy

Comparing the force and motion conceptual evaluation and the force concept inventory - Thornton, Ronald K.; Kuhl, Dennis; Cummings, Karen; Marx, Jeffrey (Physical Review Special Topics-Physics Education Research, 2009)
In this paper we compare and contrast student's pretest/post-test performance on the Halloun-Hestenes force concept inventory (FCI) to the Thornton-Sokoloff force and motion conceptual evaluation (FMCE). Both tests are multiple-choice assessment instruments whose results are used to characterize how well a first term, introductory physics course promotes conceptual understanding. However, the two exams have slightly different content domains, as well as different representational formats; hence, one exam or the other might better fit the interests of a given instructor or researcher. To begin the comparison, we outline how to determine a single-number score for the FMCE and present ranges of normalized gains on this exam. We then compare scores on the FCI and the FMCE for approximately 2000 students enrolled in the Studio Physics course at Rensselaer Polytechnic Institute over a period of eight years (1998-2006) that encompassed significant evolution of the course and many different instructors. We found that the mean score on the FCI is significantly higher than the mean score on the FMCE, however there is a very strong relationship between scores on the two exams. The slope of a best fit line drawn through FCI versus FMCE data is approximately 0.54, and the correlation coefficient is approximately r=0.78, for preinstructional and postinstructional testings combined. In spite of this strong relationship, the assessments measure different normalized gains under identical circumstances. Additionally, students who scored well on one exam did not necessarily score well on the other. We use this discrepancy to uncover some subtle, but important, differences between the exams. We also present ranges of normalized gains for the FMCE in a variety of instructional settings.
55 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/013-428-484-414-954 tex.article-number: [object Object] tex.unique-id: [object Object]
Keywords: dept.phy

Observations of binary stars with the differential speckle survey instrument. i. instrument description and first results - Horch, Elliott P.; Veillette, Daniel R.; Gallé, Roberto Baena; Shah, Sagar C.; O'Rielly, Grant; van Altena, William F. (The Astronomical Journal, 2009)
First results of a new speckle imaging system, the Differential Speckle Survey Instrument, are reported. The instrument is designed to take speckle data in two filters simultaneously with two independent CCD imagers. This feature results in three advantages over other speckle cameras: (1) twice as many frames can be obtained in the same observation time which can increase the signal-to-noise ratio for astrometric measurements, (2) component colors can be derived from a single observation, and (3) the two colors give substantial leverage over atmospheric dispersion, allowing for subdiffraction-limited separations to be measured reliably. Fifty-four observations are reported from the first use of the instrument at the Wisconsin-Indiana-Yale-NOAO 3.5 m Telescope9The WIYN Observatory is a joint facility of the University of Wisconsin-Madison, Indiana University, Yale University, and the National Optical Astronomy Observatories. in 2008 September, including seven components resolved for the first time. These observations are used to judge the basic capabilities of the instrument. © 2009. The American Astronomical Society. All rights reserved.
99 citations (Crossref) [2023-10-31] Citation Key Alias: pop00033 tex.type: [object Object]
Keywords: astrometry; binaries: close; binaries: visual; dept.phy; instrumentation: high angular resolution; instrumentation: interferometers; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Research grade instrumentation for nanotechnology and MSE education - Broadbridge, Christine; Garofano, Jacquelynn; Altman, Eric I; Khalil, Yehia F; Henrich, Victor E; Segal, Y; Padmore, Myrtlerose; Michael, Philip; Walker, Fred (MRS Proceedings, 2009)
The Center for Research on Interface Structures and Phenomena (CRISP) is a National Science Foundation (NSF) Materials Research Science and Engineering Center (MRSEC). CRISP is a partnership between Yale University, Southern Connecticut State University (SCSU) and Brookhaven National Laboratory. A main focus of CRISP research is complex oxide interfaces that are prepared using epitaxial techniques, including molecular beam epitaxy (MBE). Complex oxides exhibit a wealth of electronic, magnetic and chemical behaviors, and the surfaces and interfaces of complex oxides can have properties that differ substantially from those of the corresponding bulk materials. CRISP employs this research program in a concerted way to educate students at all levels. CRISP has constructed a robust MBE apparatus specifically designed for safe and productive use by undergraduates. Students can grow their own samples and then characterize them with facilities at both Yale and SCSU, providing a complete research and educational experience. This paper will focus on the implementation of the CRISP Teaching MBE facility and its use in the study of the synthesis and properties of the crystalline oxide-silicon interface. C 2010 Materials Research Society.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/018-591-860-685-232 tex.type: [object Object]
Keywords: Brookhaven national laboratory; Bulk materials; Chemical behavior; Complex oxides; Crystal growth; Crystalline materials; Crystalline oxides; Educational experiences; Epitaxial techniques; Interface structures; Materials research; Materials research societies; Materials science; Molecular beam epitaxy; Molecular beams; National Science Foundations; Research; Research programs; Science and engineering; Silicon interface; Students; Surfaces and interfaces; Yale University; dept.phy

Authentic science research and the utilization of nanoscience in the non-traditional classroom setting - Day, Deborah A; Yu, Zizi; Wang, Zelun; Dalecki, Jennifer; Jadbabaie, Arian; Feng, Emily Z; Mattessich, Thomas J; Caragianis-Broadbridge, Christine; Reed, Mark A; Munden, Ryan (MRS Proceedings, 2009)
Applications of nanoscience in the non-traditional classroom have successfully exposed students to various methods of research with applications to micro- and nano-electronics. Activities obtained from the NanoSense website associated with current global energy and water concerns are solid examples 1. In this regard, all 36 students in the 2008-2009 Science Research Program (SRP) prepared and delivered individual and group lesson plans in addition to their authentic, year-long research projects. Two out of 36 students selected nanoscience based projects in preparation for science fair competition in 2009. Additionally, preliminary research was conducted while participating in the Center for Research on Interface Structures and Phenomena (CRISP) Research Experience for Teachers (RET) Program in summer 2008 which supported the idea of developing a photolithography kit. This kit is intended to introduce high school students to the fundamentals of photolithography. In this paper, the design, implementation and feasibility of this kit in the high school classroom is described as well as details involving individual and group nanoscience based projects. Supporting educational models include self-regulated learning (SRL) concepts: situated cognition; social constructivism; Renzulli's (1977) enrichment triad and Types I - III inquiry enrichment activities 2,3. © 2009 Materials Research Society.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/030-237-245-323-128 tex.type: [object Object]
Keywords: Classroom settings; Education computing; Educational models; Global energy; High school; High school students; Interface structures; Lesson plans; Micro- and nano-electronics; Nanoscience; Non-traditional; Photolithography; Research; Research experience; School buildings; Science fairs; Science research; Self-regulated learning; Situated cognition; Social constructivism; Students; Teaching; dept.phy

A Study of Peer Instruction Methods with High School Physics Students - Cummings, Karen; Roberts, Stephen G. (AIP conference proceedings, 2008)
This paper reports on the results of an experiment to test the use of a Peer Instruction (PI) pedagogical model in a small class, high school environment. The study reports findings based on a population of 213 high school students attending algebra based physics courses, both Honors and A level, taught by 5 different instructors. The results show a correlation between use of Peer Instruction and improved student conceptual understanding, as demonstrated by gains on a pre-/post- assessment instrument (FCI). However, there also appears to be a number of other factors that strongly influence the resulting gains. In addition to instructor differences, the data seem to indicate that students who are more "physics-inclined" and can answer questions correctly prior to instruction and prior to any Peer Instruction discussion subsequently achieve higher gains as measured by the FCI. While this is to be expected, the use of normalized gains is intended to mitigate this result, but it appears to be prevalent nonetheless. This raises questions as to what degree the FCI gains can be attributed to the use of Peer Instruction, to teacher differences, to student ability level or to simply increased familiarity with the question types presented on the FCI.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/109-121-084-717-635, pop00223 tex.number: [object Object]
Keywords: Audio and visual aids; Conceptual learning; Curricula and evaluation; High school; Peer-instruction; Physics; Research in physics education; Teacher training; Teaching methods and strategies; Variations; dept.phy

Charge-coupled device speckle observations of binary stars with the WIYN telescope. v. measures during 2001-2006 - Horch, Elliott P.; van Altena, William F.; Cyr, William M.; Kinsman-Smith, Lori; Srivastava, Amit; Zhou, Jing (The Astronomical Journal, 2008)
A total of 1067 speckle observations of 345 binary stars are presented. Of these, 161 are double stars first resolved by Hipparcos, 17 are resolved for the first time in the observations presented here, and 21 are stars previously discovered by our program and reported in earlier papers in the series. In 947 cases, a magnitude difference is reported along with the relative astrometry. When comparing to systems with very well-known orbits, we find that the root mean square (rms) deviation in separation residuals is 2.81 0.28 mas, and the rms deviation in position angle residuals is 0.88 0.07°. The magnitude difference measures show no significant deviation from Hipparcos photometry, and have average standard deviation of approximately 0.10 mag as judged from repeat observations. Five important systems discovered by Hipparcos are discussed. © 2008. The American Astronomical Society. All rights reserved..
56 citations (Crossref) [2023-10-31] Citation Key Alias: pop00069 tex.type: [object Object]
Keywords: Astrometry; Binaries: visual; Techniques: interferometric; Techniques: photometric; dept.phy; peer-reviewed

Sign change of the extended s -wave pairing vertex in the dynamic Hubbard model: A quantum Monte Carlo study - Bouadim, K.; Enjalran, Matthew; Hébert, F.; Batrouni, G. George; Scalettar, Richard T. (Physical Review B, 2008)
The "dynamic" Hubbard Hamiltonian describes interacting fermions on a lattice whose on-site repulsion is modulated by a coupling to a fluctuating bosonic field. We investigate one such model, introduced by Hirsch, using the determinant quantum Monte Carlo method. Our key result is that the extended s -wave pairing vertex, repulsive in the usual static Hubbard model, becomes attractive as the coupling to the fluctuating Bose field increases. The sign problem prevents us from exploring a low enough temperature to see if a superconducting transition occurs. We also observe a stabilization of antiferromagnetic correlations and the Mott gap near half-filling, and a near linear behavior of the energy as a function of particle density which indicates a tendency toward phase separation. © 2008 The American Physical Society.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00117 tex.type: [object Object]
Keywords: dept.phy

Ill-behaved convergence of a model of the Gd3Ga5O12 garnet antiferromagnet with truncated magnetic dipole?dipole interactions - Yavors'kii, T.; Gingras, Michel J. P.; Enjalran, Matthew (Journal of Physics: Condensed Matter, 2007)
Previous studies have found that calculations which consider long-range magnetic dipolar interactions truncated at a finite cut-off distance R c predict spurious (unphysical) long-range ordered phases for Ising and Heisenberg systems on the pyrochlore lattice. In this paper we show that, similar to these two cases, calculations that use truncated dipolar interactions to model the Gd3Ga5O12 garnet antiferromagnet also predict unphysical phases with incommensurate ordering wavevector q ord that is very sensitive to the dipolar cut-off distance R c. © IOP Publishing Ltd.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00283 tex.type: [object Object]
Keywords: Antiferromagnetic materials; Crystal lattices; Finite cut off distance; Gadolinium compounds; Garnets; Heisenberg systems; Magnetic dipolar interactions; Magnetic moments; Numerical methods; Wavevector; dept.phy

A partnership inspiring interest in MSE careers: the center for research on interface structures and phenomena (CRISP) - Caragianis-Broadbridge, Christine; Edgecumbe, Heather; Osenko, Greg; Lehman, Ann; Alter, Lisa; Tully, John C (MRS Proceedings, 2007)
The intent of the CRISP education and outreach effort is to use materials science as a vehicle for enhancing the scientific literacy and knowledge of kindergarten through postgraduate level students. A challenging part of our mission has been inspiring students to take the next step and consider further study (or a career) in the field of Materials Science and Engineering (MSE). The CRISP educational programs were developed through a partnership between Yale University, Southern Connecticut State University and the urban school district of New Haven, CT. An overview of the methods and results of both formal and informal educational program components is included for years one and two of the CRISP MRSEC. This paper will focus on two CRISP programs: 1) MRSEC Initiative for Multidisciplinary Education & Research (MIMER) and 2) "Exploring Materials Science" mobile kits. The evaluation data indicates that the approach used in developing these educational programs is important. Specifically, the impact of these programs is influenced by the students' ability to relate the acquired knowledge to real life applications and technologies. In particular, emphasizing career opportunities rather than just presenting content-based programs is a key element to increasing interest towards further study in Materials Science and Engineering. © 2008 Materials Research Society.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/131-870-031-945-517 tex.type: [object Object]
Keywords: Career opportunities; Connecticut; Content-based; Educational program; Engineering education; Interface structures; Key elements; Materials; Materials science and engineering; Multidisciplinary education; Post-graduate levels; Professional aspects; Real-life applications; Scientific literacy; Students; Teaching; Urban schools; Yale University; dept.phy

The effectiveness of incorporating conceptual writing assignments into physics instruction - Cummings, Karen; Murphy, Michael (AIP Conference Proceedings, 2007)
This preliminary study examines the impact of conceptual writing assignments on student understanding of two physics concepts. Writing assignments covered the concepts of Newton's Third Law and the impulse-momentum relationship and were given to students in both high school and college level introductory physics classes. The students in these classes along with students in classes taught in an identical fashion by the same instructors without the addition of writing assignments were tested on their conceptual understanding of the two content areas. The results of this initial study indicate that the efficacy of this approach varied with topic. This study further indicates that students' benefit from the writing assignments was independent of their writing ability. © 2007 American Institute of Physics.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/168-392-262-279-442, pop00249 tex.number: [object Object]
Keywords: College; Conceptual learning; High school; Writing; dept.phy

Publishing and refereeing papers in physics education research - Hsu, Leon; Beichner, Robert J; Cummings, Karen; Kolodner, Janet L; Mccullough, Laura (Conference Cognitive Science, 2007)
At the 2007 Physics Education Research Conference, a workshop on publishing and refereeing was held with a panel of editors from four different publishing venues: the physics education research section of the American Journal of Physics, the Journal of the Learning Sciences, Physical Review Special Topics - Physics Education Research, and the Physics Education Research Conference Proceedings. These editors answered questions from participants regarding publishing in their respective venues, as well as writing referee reports that would be useful to both journal editors and authors. This paper summarizes the discussion. © 2007 American Institute of Physics.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Conference proceedings; Journals; Publishing; Referee reports; dept.phy

What factors really influence shifts in students’ attitudes and expectations in an introductory physics course? - Marx, Jeffrey; Cummings, Karen (2006 Physics Education Research Conference, 2007)
To gauge the impact of instruction on students' general expectations about physics and their attitudes about problem solving, we administered two different, but related, survey instruments to students in the first semester of introductory, calculus-based physics at McDaniel College. The surveys we used were the Maryland Physics Expectation Survey (MPEX) and the Attitudes about Problem Solving Survey (APSS). We found that the McDaniel College students' overall responses were more "expert-like" post-instruction: on the MPEX, the students' Overall agree/disagree score started at 59/18 and ended at 63/17, and on the APSS, the students' agreement-score went from 63 to 79. (All scores are out of 100%.) All of the students to whom we administered the MPEX and a significant sub-group to whom we administered the APSS realized these improvements without experiencing any explicit instructional intervention in this course aimed toward improving attitudes and expectations. These results contrast much of the previously reported findings in this area. © 2007 American Institute of Physics.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-519-377-568-644 tex.number: [object Object]
Keywords: dept.phy

Dynamic Hubbard model: a Monte Carlo study - Hébert, F.; Bouadim, K; Enjalran, M; Scalettar, R. T. (AIP Conference Proceedings, 2006)
Dynamic Hubbard models describe relaxation of atomic orbitals when electrons are added to already occupied orbitals, a phenomenon that is not present in the conventional Hubbard model and that may play a role in superconductivity. We use the determinant algorithm to study the properties of a particular dynamic Hubbard model on a two-dimensional square lattice. We report preliminary results for a set of correlation functions, and our data are compared to results from the standard Hubbard model. We find that a dynamic interaction enhances the pair-field susceptibility, signaling the possible on-set of a superconducting phase. © 2006 American Institute of Physics.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/054-798-190-566-827, pop00239 tex.number: [object Object]
Keywords: Hubbard model; Quantum Monte Carlo; Superconductivity; dept.phy

Comparison of common segmentation techniques applied to transmission electron microscopy images - Sadowski, Thomas; Broadbridge, Christine; Daponte, John S (MRS Proceedings, 2006)
Nanoparticles are of interest in many applications since their decreased size may give them properties that are very different from bulk material. Often nanoparticle properties such as size (diameter) and size distribution are evaluated using transmission electron microscopy (TEM). These parameters, size and size distribution, can be more easily obtained from digitized TEM images by mapping particle signal to black and background pixel to white in a process known as thresholding then performing an algorithm known as a particle analysis. The goal of this study was to compare the ability of several popular thresholding algorithms to segment TEM images. Performance of the thresholding algorithms was evaluated through qualitative and quantitative measures. Results show that the choice of a thresholding algorithm will strongly affect the results obtained from particle analysis. © 2007 Materials Research Society.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/062-589-551-901-205 tex.type: [object Object]
Keywords: Algorithms; Bulk material; Image segmentation; Nanoparticles; Parameter estimation; Particle analysis; Size distribution; Thresholding algorithms; Transmission electron microscopy; dept.phy

Computer assisted analysis of microscopy images - Sawicki, M; Munhutu, P; Daponte, John S; Caragianisbroadbridge, Christine; Lehman, Ann; Sadowski, Thomas; Garcia, E; Heyden, C; Mirabelle, L; Benjamin, P (Visualization and Data Analysis, 2009)
The use of Transmission Electron Microscopy (TEM) to characterize the microstructure of a material continues to grow in importance as technological advancements become increasingly more dependent on nanotechnology 1. Since nanoparticle properties such as size (diameter) and size distribution are often important in determining potential applications, a particle analysis is often performed on TEM images. Traditionally done manually, this has the potential to be labor intensive, time consuming, and subjective 2. To resolve these issues, automated particle analysis routines are becoming more widely accepted within the community 3. When using such programs, it is important to compare their performance, in terms of functionality and cost. The primary goal of this study was to apply one such software package, ImageJ to grayscale TEM images of nanoparticles with known size. A secondary goal was to compare this popular open-source general purpose image processing program to two commercial software packages. After a brief investigation of performance and price, ImageJ was identified as the software best suited for the particle analysis conducted in the study. While many ImageJ functions were used, the ability to break agglomerations that occur in specimen preparation into separate particles using a watershed algorithm was particularly helpful 4. © 2009 SPIE-IS&T.
1 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Agglomeration; Commercial softwares; Computer aided analysis; Computer-assisted analysis; Data visualization; Electron microscopes; General purpose; Gray-scale; Image processing; Imaging systems; Labor intensives; Microscopy; Microscopy images; Nanoparticles; Open sources; Particle analysis; Particle size analysis; Potential applications; Semiconductor quantum wires; Software packages; Specimen preparation; TEM images; Technological advancements; Tem; Thresholding; Transmission Electron Microscope (TEM); Transmission electron microscopy; Visualization; Water-shed algorithms; dept.csc; dept.phy

Characterization of nanoparticles by computer imaging particle analysis - DaPonte, J.; Sadowski, T.; Broadbridge, C. C.; Munhutu, P.; Lehman, A.; Krishnamoorthy, D.; Garcia, E. C.; Sawicki, M. S.; Heyden, C.; Mirabelle, L.; Benjamin, P. (Nanomaterials Synthesis, Interfacing, and Integrating in Devices, Circuits, and Systems II, 2007)
Nanoparticles, particles with a diameter of 1-100 nanometers (nm), are of interest in many applications including device fabrication, quantum computing, and sensing because their decreased size may give rise to certain properties that are very different from those exhibited by bulk materials. Further advancement of nanotechnology cannot be realized without an increased understanding of nanoparticle properties such as size (diameter) and size distribution. Frequently, these parameters are evaluated using numerous imaging modalities including transmission electron microscopy (TEM) and atomic force microscopy (AFM). In the past, these parameters have been obtained from digitized images by manually measuring and counting many of these nanoparticles, a task that is highly subjective and labor intensive. Recently, computer imaging particle analysis routines that count and measure objects in a binary image^1 have emerged as an objective and rapid alternative to manual techniques. In this paper a procedure is described that can be used to preprocess a set of gray scale images so that they are correctly thresholded into binary images prior to a particle analysis ultimately resulting in a more accurate assessment of the size and frequency (size distribution) of nanoparticles. Particle analysis was performed on two types of calibration samples imaged using AFM and TEM. Additionally, results of particle analysis can be used for identifying and removing small noise particles from the image. This filtering technique is based on identifying the location of small particles in the binary image, assessing their size, and removing them without affecting the size of other larger particles.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/032-875-618-829-762, pop00276
Keywords: Atomic force microscopy; Bulk materials; Computer imaging; Device fabrication; Imaging techniques; Nanoparticles; Particle analysis; Quantum computers; Size distribution; Thresholding; Transmission electron microscopy; dept.csc; dept.phy

Application of particle analysis to transmission electron microscopy (TEM) - Daponte, John S; Sadowski, Thomas; Broadbridge, Christine; Day, D; Lehman, A; Krishna, D; Marinella, L; Munhutu, P; Sawicki, M (Visual Information Processing Conference, 2007)
Nanoparticles, particles with a diameter of 1-100 nanometers (nm), are of interest in many applications including device fabrication, quantum computing, and sensing because their size may give them properties that are very different from bulk materials. Further advancement of nanotechnology cannot be obtained without an increased understanding of nanoparticle properties such as size (diameter) and size distribution frequently evaluated using transmission electron microscopy (TEM). In the past, these parameters have been obtained from digitized TEM images by manually measuring and counting many of these nanoparticles, a task that is highly subjective and labor intensive. More recently, computer imaging particle analysis has emerged as an objective alternative by counting and measuring objects in a binary image. This paper will describe the procedures used to preprocess a set of gray scale TEM images so that they could be correctly thresholded into binary images. This allows for a more accurate assessment of the size and frequency (size distribution) of nanoparticles. Several preprocessing methods including pseudo flat field correction and rolling ball background correction were investigated with the rolling ball algorithm yielding the best results. Examples of particle analysis will be presented for different types of materials and different magnifications. In addition, a method based on the results of particle analysis for identifying and removing small noise particles will be discussed. This filtering technique is based on identifying the location of small particles in the binary image and removing them without affecting the size of other larger particles.
1 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Computer imaging; Flat field correction; Flat field correction and rolling ball background correction; Imaging particle analysis; Imaging systems; Magnification; Microfabrication; Nanoparticles; Nanotechnology; Quantum computers; Rolling ball background correction; Size distribution; Transmission electron microscopy; dept.csc; dept.phy

Comparison of thresholding techniques on nanoparticle images - Daponte, John S; Sadowski, Thomas; Broadbridge, Christine; Day, D; Lehman, A; Krishna, D; Marinella, L; Munhutu, P; Sawicki, M (Visual Information Processing Conference, 2007)
Thresholding is an image processing procedure used to convert an image consisting of gray level pixels into a black and white binary image. One application of thresholding is particle analysis. Once foreground objects are separated from the background, a quantitative analysis that characterizes the number, size and shape of particles is obtained which can then be used to evaluate a series of nanoparticle samples. Numerous thresholding techniques exist differing primarily in how they deal with variations in noise, illumination and contrast. In this paper, several popular thresholding algorithms are qualitatively and quantitatively evaluated on transmission electron microscopy (TEM) and atomic force microscopy (AFM) images. Initially, six thresholding algorithms were investigated: Otsu, Riddler-Calvard, Kittler, Entropy, Tsai and Maximum Likelihood. The Riddler-Calvard algorithm was not included in the quantitative analysis because it did not produce acceptable qualitative results for the images in the series. Two quantitative measures were used to evaluate these algorithms. One is based on comparing object area the other on diameter before and after thresholding. For AFM images the Kittler algorithm yielded the best results followed by the Entropy and Maximum Likelihood techniques. The Tsai algorithm yielded the top results for TEM images followed by the Entropy and Kittler methods.
2 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Algorithms; Atomic force microscopy; Binary images; Maximum likelihood; Nanoparticle; Nanoparticle samples; Nanoparticles; Pixels; Riddler-Calvard algorithm; Thresholding; Transmission electron microscopy; Tsai algorithm; dept.csc; dept.phy

Quantitative confirmation of visual improvements to micro-CT bone density images - Daponte, John S; Clark, Michael R; Nelson, Paul; Sadowski, Thomas; Wood, Elizabeth (Visual Information Processing Conference, 2006)
The primary goal of this research was to investigate the ability of quantitative variables to confirm qualitative improvements of the deconvolution algorithm as a preprocessing step in evaluating micro CT bone density images. The analysis of these types of images is important because they are necessary to evaluate various countermeasures used to reduce or potentially reverse bone loss experienced by some astronauts when exposed to extended weightlessness during space travel. Nine low resolution (17.5 microns) CT bone density image sequences, ranging from between 85 to 88 images per sequence, were processed with three preprocessing treatment groups consisting of no preprocessing, preprocessing with a deconvolution algorithm and preprocessing with a Gaussian filter. The quantitative parameters investigated consisted of Bone Volume to Total Volume Ratio, the Structured Model Index, Fractal Dimension, Bone Area Ratio, Bone Thickness Ratio, Euler's Number and the Measure of Enhancement. Trends found in these quantitative variables appear to corroborate the visual improvements observed in the past and suggest which quantitative parameters may be capable of distinguishing between groups that experience bone loss and others that do not.
1 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Algorithms; Bone Thickness Ratio; Computerized tomography; Digital filters; Euler's Number; Gaussian filters; Image enhancement; Image sequences; Medical imaging; Optical resolving power; dept.csc; dept.phy

Animating climate model data - Daponte, John S; Sadowski, Thomas; Thomas, Paul (Visual Information Processing Conference, 2006)
This paper describes a collaborative project conducted by the Computer Science Department at Southern Connecticut State University and NASA's Goddard Institute for Space Science (GISS). Animations of output from a climate simulation math model used at GISS to predict rainfall and circulation have been produced for West Africa from June to September 2002. These early results have assisted scientists at GISS in evaluating the accuracy of the RM3 climate model when compared to similar results obtained from satellite imagery. The results presented below will be refined to better meet the needs of GISS scientists and will be expanded to cover other geographic regions for a variety of time frames.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Animation; Climate model data; Computer simulation; Data reduction; Geographical regions; Imaging systems; Mathematical models; Satellite imagery; Satellites; Simulation math model; dept.csc; dept.phy

Kinematics of stars in the outskirts of the clouds - Casetti, Dana (2019)
I will review recent observations of the kinematics of stars in the outskirts of the Magellanic Clouds and in the Magellanic Stream, and discuss these observations in the context of the interaction of the Clouds with the Galaxy and with each other.
Publisher: Zenodo, DOI: 10.5281/ZENODO.3472510
Keywords: dept.phy

Distinguishing metastatic triple-negative breast cancer from nonmetastatic breast cancer using second harmonic generation imaging and resonance Raman spectroscopy - Bendau, Ethan; Smith, Jason; Zhang, Lin; Ackerstaff, Ellen; Kruchevsky, Natalia; Wu, Binlin; Koutcher, Jason A.; Alfano, Robert; Shi, Lingyan (Journal of Biophotonics, 2020)
Triple-negative breast cancer (TNBC) is an aggressive subset of breast cancer that is more common in African-American and Hispanic women. Early detection followed by intensive treatment is critical to improving poor survival rates. The current standard to diagnose TNBC from histopathology of biopsy samples is invasive and time-consuming. Imaging methods such as mammography and magnetic resonance (MR) imaging, while covering the entire breast, lack the spatial resolution and specificity to capture the molecular features that identify TNBC. Two nonlinear optical modalities of second harmonic generation (SHG) imaging of collagen, and resonance Raman spectroscopy (RRS) potentially offer novel rapid, label-free detection of molecular and morphological features that characterize cancerous breast tissue at subcellular resolution. In this study, we first applied MR methods to measure the whole-tumor characteristics of metastatic TNBC (4T1) and nonmetastatic estrogen receptor positive breast cancer (67NR) models, including tumor lactate concentration and vascularity. Subsequently, we employed for the first time in vivo SHG imaging of collagen and ex vivo RRS of biomolecules to detect different microenvironmental features of these two tumor models. We achieved high sensitivity and accuracy for discrimination between these two cancer types by quantitative morphometric analysis and nonnegative matrix factorization along with support vector machine. Our study proposes a new method to combine SHG and RRS together as a promising novel photonic and optical method for early detection of TNBC.
22 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/jbio.202000005
Keywords: Breast; Breast Neoplasms; Collagen; Diseases; Factorization; Feature extraction; Female; Harmonic generation; Humans; Label-free detection; Lactate concentration; Magnetic resonance; Mammography; Matrix algebra; Molecular imaging; Morphological features; Morphometric analysis; Nonlinear optics; Nonnegative matrix factorization; Raman spectrometry; Raman spectroscopy; Resonance Raman spectroscopy; Second Harmonic Generation Microscopy; Spectrum Analysis; Raman; Subcellular resolution; Support vector machines; Triple Negative Breast Neoplasms; Triple-negative breast cancers; Tumors; breast; breast tumor; dept.phy; diagnostic imaging; female; human; mammography; peer-reviewed; second harmonic generation microscopy; triple negative breast cancer

Synthesis and characterization of CuS, CuS/graphene oxide nanocomposite for supercapacitor applications - Singhal, Rahul; Thorne, David; LeMaire, Peter K.; Martinez, Xavier; Zhao, Chen; Gupta, Ram K.; Uhl, David; Scanley, Ellen; Broadbridge, Christine C.; Sharma, Rakesh K. (AIP Advances, 2020)
Supercapacitors or electrochemical capacitors are receiving greater interest because of their high-power density, long life, and low maintenance. We have synthesized CuS nanoparticles and graphene oxide (CuS-GO) nanocomposites for supercapacitor applications because of their low cost and excellent electrochemical properties. The phase purity of each material was determined using powder XRD studies. The bandgap was determined by UV-visible spectrophotometric studies. Scanning electron microscope and transmission electron microscope images revealed the nano-scale morphology of the synthesized particles. All the electrochemical measurements were conducted in a standard three-electrode configuration, using a platinum wire as the counter electrode and Hg/HgO as the reference electrode. CuS and its composites with graphene oxide on nickel foam were used as working electrodes. All the electrochemical measurements were performed in 3M KOH solution. The CuS-GO nanocomposite electrode showed a specific capacitance of 250 F/g, 225 F/g, 182 F/g, 166 F/g, 161 F/g, and 158 F/g at a current density of 0.5 A/g, 1 A/g, 5 A/g, 10 A/g, 15 A/g, and 20 A/g, respectively. CuS-GO electrodes showed a specific capacitance retention of 70% after 5000 charge-discharge cycles at a current density of 5 A/g. © 2020 Author(s).
19 citations (Crossref) [2023-10-31] WOS:000519123100001
Keywords: Capacitance; Charge-discharge cycle; Copper compounds; Electric discharges; Electrochemical capacitor; Electrochemical electrodes; Electrochemical measurements; Foams; Graphene; Mercury compounds; Nanocomposite electrodes; Nanocomposites; Potassium hydroxide; Scanning electron microscopy; Spectrophotometric study; Supercapacitor; Supercapacitor application; Synthesis (chemical); Synthesis and characterizations; Transmission electron; Transmission electron microscopy; dept.phy; peer-reviewed

Local RR Lyrae stars: native and alien - Zinn, R; Chen, X; Layden, A C; Casetti-Dinescu, D I (Monthly Notices of the Royal Astronomical Society, 2020)
Measurements of [Fe/H] and radial velocity are presented for 89 RR Lyrae (RRL) candidates within 6 kpc of the Sun. After the removal of two suspected non-RRLs, these stars were added to an existing data base, which yielded 464 RRLs with [Fe/H] on a homogeneous scale. Using data from the Gaia satellite (Data Release 2), we calculated the positions and space velocities for this sample. These data confirm the existence of a thin disc of RRL with [α/Fe] ∼ solar. The majority of the halo RRLs with large total energies have near-zero angular momenta about the Z-axis. Kinematically, these stars closely resemble the Gaia-Sausage/Gaia-Enceladus stars that others have proposed are debris from the merger of a large galaxy with the Milky Way. The metallicity and period distributions of the RRLs and their positions in the period-amplitude diagram suggest that this disrupted galaxy was as massive as the Large Magellanic Cloud and possibly greater. © 2019 The Author(s)
10 citations (Crossref) [2023-10-31] tex.ids: zinnLocalRRLyrae2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85082725399 type: Article
Keywords: Dynamics; Galaxy: formation; Galaxy: kinematics; Stars: variables: RR Lyrae; dept.phy; peer-reviewed

Erratum: “understanding the effects of stellar multiplicity on the derived planet radii from transit surveys: implications for kepler, k2, and tess” (2015, apj, 805, 16) - Ciardi, David R; Beichman, Charles A; Horch, Elliott P; Howell, Steve B (The Astrophysical Journal, 2017)
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/020-178-620-022-037 tex.type: [object Object]
Keywords: dept.phy

Author Correction: Determination of critical cooling rates in metallic glass forming alloy libraries through laser spike annealing. - Bordeenithikasem, Punnathat; Liu, Jingbei; Kube, Sebastian A; Li, Yanglin; Ma, Tianxing; Scanley, B Ellen; Broadbridge, Christine C; Vlassak, Joost J; Singer, Jonathan P; Schroers, Jan (Scientific reports, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.
1 citations (Crossref) [2023-10-31] Place: England Bordeenithikasem, Punnathat. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Liu, Jingbei. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Kube, Sebastian A. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Li, Yanglin. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Ma, Tianxing. Department of Mechanical and Aerospace Engineering, Rutgers University, Piscataway, New Jersey, 08854, USA. Scanley, B Ellen. Department of Physics, Southern Connecticut State University, New Haven, Connecticut, 06515, USA. Broadbridge, Christine C. Department of Physics, Southern Connecticut State University, New Haven, Connecticut, 06515, USA. Vlassak, Joost J. School of Engineering and Applied Science, Harvard University, Cambridge, Massachusetts, 02138, USA. Singer, Jonathan P. Department of Mechanical and Aerospace Engineering, Rutgers University, Piscataway, New Jersey, 08854, USA. Schroers, Jan. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. jan.schroers@yale.edu. Erratum for (EFR)
Keywords: dept.phy; peer-reviewed

K2 discovers a busy bee: an unusual transiting neptune found in the beehive cluster - Obermeier, Christian; Henning, Thomas; Schlieder, Joshua E.; Crossfield, Ian J. M.; Petigura, Erik A.; Howard, Andrew W.; Sinukoff, Evan; Isaacson, Howard; Ciardi, David R.; David, Trevor J.; Hillenbrand, Lynne A.; Beichman, Charles A.; et al. (The Astronomical Journal, 2016)
Open clusters have been the focus of several exoplanet surveys, but only a few planets have so far been discovered. The Kepler spacecraft revealed an abundance of small planets around small cool stars, therefore, such cluster members are prime targets for exoplanet transit searches. Kepler's new mission, K2, is targeting several open clusters and star-forming regions around the ecliptic to search for transiting planets around their low-mass constituents. Here, we report the discovery of the first transiting planet in the intermediate-age (800 Myr) Beehive cluster (Praesepe). K2-95 is a faint (Kp = 15.5 mag) dwarf from K2's Campaign 5 with an effective temperature of 3471 ±124 K, approximately solar metallicity and a radius of 0.402± 0.050.R⊕ We detected a transiting planet with a radius of3.47+0.78 -0.53R⊕ and an orbital period of 10.134 days. We combined photometry, medium/high-resolution spectroscopy, adaptive optics/speckle imaging, and archival survey images to rule out any false-positive detection scenarios, validate the planet, and further characterize the system. The planet's radius is very unusual as M-dwarf field stars rarely have Neptune-sized transiting planets. The comparatively large radius of K2-95b is consistent with the other recently discovered cluster planets K2-25b (Hyades) and K2-33b (Upper Scorpius), indicating systematic differences in their evolutionary states or formation. These discoveries from K2 provide a snapshot of planet formation and evolution in cluster environments and thus make excellent laboratories to test differences between field-star and cluster planet populations. © 2016. The American Astronomical Society. All rights reserved..
62 citations (Crossref) [2023-10-31] Citation Key Alias: pop00057 tex.type: [object Object]
Keywords: dept.phy; eclipses; peer-reviewed; stars: individual (K2-95); stars: low-mass; techniques: photometric; techniques: spectroscopic

ϒ production in U + U collisions at sNN =193 GeV measured with the STAR experiment ϒ PRODUCTION in U + U COLLISIONS at ⋯ L. ADAMCZYK et al. - Adamczyk, Leszek; Adkins, J. K.; Agakishiev, G.; Aggarwal, M. M.; Ahammed, Zubayer; Alekseev, I. G.; Anderson, Derek; Aoyama, Ryo; Aparin, A.; Arkhipkin, D.; Aschenauer, E. C.; Ashraf, Muhammad Usman; et al. (Physical Review C, 2016)
18 citations (Crossref) [2023-10-31] Citation Key Alias: pop00056 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed

Proper motion of the Draco dwarf galaxy from Subaru Suprime-Cam data - Casetti-Dinescu, Dana I.; Girard, Terrence M. (Monthly Notices of the Royal Astronomical Society, 2016)
We have measured the absolute proper motion of the Draco dwarf spheroidal galaxy using Subaru Suprime-Cam images taken at three epochs, with time baselines of 4.4 and 7 yr. The magnitude limit of the proper-motion study is i = 25, thus allowing for thousands of background galaxies and Draco stars to be used to perform extensive astrometric tests and to derive the correction to an inertial reference frame. The derived proper motion is (μα, μδ) = (-0.284 ± 0.047, -0.289 ± 0.041) mas yr-1. This motion implies an orbit that takes Draco to a pericentre of ~20 kpc; a somewhat disruptive orbit suggesting that tides might account for the rising velocity-dispersion profile of Draco seen in line-of-sight velocity studies. The orbit is only marginally consistent with Draco's membership to the vast polar structure of Galactic satellites, in contrast to a recent Hubble Space Telescope proper-motion measurement that finds alignment very likely. Our study is a test case to demonstrate that deep imaging with mosaic cameras of appropriate resolution can be used for high-accuracy, ground-based proper-motion measurement. As a useful by-product of the study, we also identify two faint brown-dwarf candidates in the foreground field. © 2016 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
14 citations (Crossref) [2023-10-31] Citation Key Alias: pop00087 tex.type: [object Object]
Keywords: Astrometry; Brown dwarfs; Galaxies: dwarf; Galaxies: individual: Draco; Proper motions; dept.phy; peer-reviewed

Time reversal optical tomography: Detecting and locating tumors in an ex vivo model human breast - Wu, Binlin; Alrubaiee, M.; Gayen, S. K. (Optics and Laser Technology, 2016)
Time reversal optical tomography (TROT), a recently introduced diffuse optical imaging approach, is used to detect, locate, and obtain cross-section images of tumors inside a "model human breast." The model cancerous breast is assembled as a semi-cylindrical slab of uniform thickness using ex vivo human breast tissues with two pieces of tumors embedded in it. The experimental arrangement used a 750-nm light beam from a Ti:sapphire laser to illuminate an end face (source plane) of the sample in a multi-source probing scheme. A multi-detector signal acquisition scheme measured transmitted light intensity distribution on the other end face (detector plane). The perturbations in light intensity distribution in the detector plane were analyzed using TROT to obtain locations of the tumor pieces in three dimensions and estimate their cross sections. The estimated locations and dimensions of targets are in good agreement with the results of a corroborating magnetic resonance imaging experiment. © 2015 Elsevier Ltd. All rights reserved.
3 citations (Crossref) [2023-10-31] Citation Key Alias: pop00228 tex.type: [object Object]
Keywords: Biological tissues; Breast Cancer; Breast cancer; Histology; Image reconstruction; Infrared devices; Infrared imaging; Inverse image reconstruction; Light propagation; Light propagation in biological tissues; Location; Magnetic resonance imaging; Medical imaging; Near-infrared imaging; Optical tomography; Sapphire; Signal processing; Thermography (imaging); Time reversal; Tissue; Tumors; dept.phy

Two new long-period giant planets from the McDonald observatory planet search and two stars with long-period radial velocity signals related to stellar activity cycles - Endl, Michael; Brugamyer, Erik; Cochran, William D.; MacQueen, Phillip J.; Robertson, Paul; Meschiari, Stefano; Ramirez, Ivan; Shetrone, Matthew D.; Gullikson, Kevin; Johnson, Marshall C.; Wittenmyer, Robert A.; Horner, Jonathan; et al. (The Astrophysical Journal, 2016)
We report the detection of two new long-period giant planets orbiting the stars HD 95872 and HD 162004 (φ1 Dra B) by the McDonald Observatory planet search. The planet HD 95872b has a minimum mass of 4.6 MJup and an orbital semimajor axis of 5.2 AU. The giant planet φ1 Dra Bb has a minimum mass of 1.5 MJup and an orbital semimajor axis of 4.4 AU. Both of these planets qualify as Jupiter analogs. These results are based on over one and a half decades of precise radial velocity (RV) measurements collected by our program using the McDonald Observatory Tull Coude spectrograph at the 2.7 m Harlan J. Smith Telescope. In the case of φ1 Dra B we also detect a long-term nonlinear trend in our data that indicates the presence of an additional giant planet, similar to the Jupiter-Saturn pair. The primary of the binary star system, φ1 Dra A, exhibits a very large amplitude RV variation due to another stellar companion. We detect this additional member using speckle imaging. We also report two cases - HD 10086 and HD 102870 (β Virginis) - of significant RV variation consistent with the presence of a planet, but that are probably caused by stellar activity, rather than reflexive Keplerian motion. These two cases stress the importance of monitoring the magnetic activity level of a target star, as long-term activity cycles can mimic the presence of a Jupiter-analog planet. © 2016. The American Astronomical Society. All rights reserved.
30 citations (Crossref) [2023-10-31] Citation Key Alias: pop00073 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: activity; techniques: radial velocities

Refrustration and competing orders in the prototypical Dy2Ti2O7 spin ice material - Henelius, Patrik; Lin, T.; Enjalran, Matthew; Hao, Zhihao; Rau, Jeffrey G.; Altosaar, Jaan; Flicker, Felix; Yavors'kii, T.; Gingras, Michel J. P. (Physical Review B, 2016)
Spin ices, frustrated magnetic materials analogous to common water ice, have emerged over the past 15 years as exemplars of high frustration in three dimensions. Recent experimental developments aimed at interrogating anew the low-temperature properties of these systems, in particular whether the predicted transition to long-range order occurs, behoove researchers to scrutinize our current dipolar spin ice model description of these materials. In this work, we do so by combining extensive Monte Carlo simulations and mean-field theory calculations to analyze data from previous magnetization, diffuse neutron scattering, and specific-heat measurements on the paradigmatic Dy2Ti2O7 spin ice material. In this work, we also reconsider the possible importance of the nuclear specific heat Cnuc in Dy2Ti2O7. We find that Cnuc is not entirely negligible below a temperature ∼0.5 K and must therefore be taken into account in a quantitative analysis of the calorimetric data of this compound below that temperature. We find that in this material, small effective spin-spin exchange interactions compete with the magnetostatic dipolar interaction responsible for the main spin ice phenomenology. This causes an unexpected "refrustration" of the long-range order that would be expected from the incompletely self-screened dipolar interaction and which positions the material at the boundary between two competing classical long-range-ordered ground states. This allows for the manifestation of new physical low-temperature phenomena in Dy2Ti2O7, as exposed by recent specific-heat measurements. We show that among the four most likely causes for the observed upturn of the specific heat at low temperature [an exchange-induced transition to long-range order, quantum non-Ising (transverse) terms in the effective spin Hamiltonian, the nuclear hyperfine contribution, and random disorder], only the last appears to be reasonably able to explain the calorimetric data. © 2016 American Physical Society.
47 citations (Crossref) [2023-10-31] Citation Key Alias: pop00040 tex.type: [object Object]
Keywords: CattaneoChristov heat flux; Oldroyd-B fluid; dept.phy; nonlinear analysis

197 candidates and 104 validated planets in k2's first five fields - Crossfield, Ian J M; Ciardi, David R; Petigura, Erik A; Sinukoff, Evan; Schlieder, Joshua E; Schlieder, Joshua E; Howard, Andrew W; Beichman, Charles A; Isaacson, Howard; Dressing, Courtney D; Christiansen, Jessie L; Fulton, Benjamin J; et al. (Astrophysical Journal Supplement Series, 2016)
We present 197 planet candidates discovered using data from the first year of the NASA K2 mission (Campaigns 0-4), along with the results of an intensive program of photometric analyses, stellar spectroscopy, high-resolution imaging, and statistical validation. We distill these candidates into sets of 104 validated planets (57 in multi-planet systems), false positives, and 63 remaining candidates. Our validated systems span a range of properties, with median values of RP= 2.3 R⊕, P = 8.6 days, Teff = 5300 K, and Kp = 12.7mag. Stellar spectroscopy provides precise stellar and planetary parameters for most of these systems. We show that K2 has increased by 30% the number of small planets known to orbit moderately bright stars (1-4 R R⊕, Kp = 9-13 mag). Of particular interest are planets smaller than 2 R⊕, orbiting stars brighter than Kp = 11.5 mag, 5 receiving Earth-like irradiation levels, and several multi-planet systems - including 4 planets orbiting the M dwarf K2-72 near mean-motion resonances. By quantifying the likelihood that each candidate is a planet we demonstrate that our candidate sample has an overall false positive rate of 15%-30%, with rates substantially lower for small candidates (<2R⊕) and larger for candidates with radii >8 R⊕ and/or with P<3 days. Extrapolation of the current planetary yield suggests that K2 will discover between 500 and 1000 planets in its planned four-year mission, assuming sufficient follow-up resources are available. Efficient observing and analysis, together with an organized and coherent follow-up strategy, are essential for maximizing the efficacy of planet-validation efforts for K2, TESS, and future large-scale surveys. © 2016. The American Astronomical Society. All rights reserved.
150 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-053-995-602-624 tex.type: [object Object]
Keywords: catalogs; dept.phy; planets and satellites: fundamental parameters; planets and satellites: general; techniques: high angular resolution; techniques: photometric; techniques: spectroscopic

Three temperate neptunes orbiting nearby stars - Fulton, Benjamin J; Howard, Andrew W; Weiss, Lauren M; Sinukoff, Evan; Petigura, Erik A; Isaacson, Howard; Hirsch, Lea A; Marcy, Geoffrey W; Henry, Gregory W; Grunblatt, Samuel K; Huber, Daniel; Huber, Daniel; et al. (The Astrophysical Journal, 2016)
We present the discovery of three modestly irradiated, roughly Neptune-mass planets orbiting three nearby Solartype stars. HD 42618 b has a minimum mass of 15.4±2.4 M⊕, a semimajor axis of 0.55 au, an equilibrium temperature of 337 K, and is the first planet discovered to orbit the solar analogue host star, HD 42618. We also discover new planets orbiting the known exoplanet host stars HD 164922 and HD 143761 (p CrB). The new planet orbiting HD 164922 has a minimum mass of 12.9±1.6 M⊕ and orbits interior to the previously known Jovian mass planet orbiting at 2.1 au. HD 164922 c has a semimajor axis of 0.34 au and an equilibrium temperature of 418 K. HD 143761 c orbits with a semimajor axis of 0.44 au, has a minimum mass of 25±2 M⊕, and is the warmest of the three new planets with an equilibrium temperature of 445 K. It orbits exterior to the previously known warm Jupiter in the system. A transit search using space-based CoRoT data and ground-based photometry from the Automated Photometric Telescopes (APTs) at Fairborn Observatory failed to detect any transits, but the precise, high-cadence APT photometry helped to disentangle planetary-reflex motion from stellar activity. These planets were discovered as part of an ongoing radial velocity survey of bright, nearby, chromospherically inactive stars using the Automated Planet Finder (APF) telescope at Lick Observatory. The high-cadence APF data combined with nearly two decades of radial velocity data from Keck Observatory and gives unprecedented sensitivity to both short-period low-mass, and long-period intermediate-mass planets. © 2016. The American Astronomical Society. All rights reserved..
23 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/015-506-416-922-520 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (HD 42618; HD 164922; HD 143761)

Speckle imaging at large telescopes: current results and future prospects - Horch, Elliott P (Proceedings of SPIE, 2016)
In recent years, speckle imaging has proven very useful for certain problems in single-Aperture high-resolution imaging, including searching for faint stellar companions near exoplanet host stars and for satellite imaging. These developments have largely been the result of the availability of electron-multiplying CCD cameras, which allow for greater sensitivity and better photometric linearity when compared with other detectors that have comparable speed. This in turn has led to an increased use for speckle imaging at mid-sized and large telescopes. Some results of these efforts will be discussed, and the outlook for the future of speckle will be given. © 2016 SPIE.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/043-284-682-979-188 tex.type: [object Object]
Keywords: CCD cameras; Electron multiplying ccds; Faint Companion Detection; Future prospects; High resolution; High-Resolution Astronomy; High-resolution imaging; Image Reconstruction; Image reconstruction; Interferometry; Large telescopes; Satellite imaging; Single aperture; Speckle; Speckle Imaging; Speckle imaging; Telescopes; dept.phy

SCSI: the southern connecticut stellar interferometer - Horch, Elliott P; Weiss, Samuel A; Rupert, Justin D; Dimaio, Alex J; Nusdeo, Daniel A; Peronio, Pietro; Rech, Ivan; Gulinatti, Angelo; Giudice, Andrea (Proceedings of SPIE, 2016)
The construction of a new prototype visible-light intensity interferometer for use in stellar astronomy is described. The instrument is located in New Haven, Connecticut, at Southern Connecticut State University, but key components of the system are also portable and have been taken to existing research-class telescopes to maximize sensitivity and baseline. The interferometer is currently a two-station instrument, but it is easily expandable to several stations for simultaneous measurement using multiple baselines. The design features single photon avalanche diode (SPAD) arrays, which increase the throughput and signal-To-noise ratio of the instrument. Predicted system performance and preliminary observations will be discussed. © 2016 SPIE.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/071-922-688-145-060 tex.type: [object Object]
Keywords: Avalanche diodes; Design features; Intensity Interferometry; Interferometers; Interferometry; Particle beams; Photon Counting; Photon counting; Photons; Signal to noise ratio; Simultaneous measurement; Single Photon Avalanche Diode Arrays; Single photon avalanche diode; Single-photon avalanche diode arrays; Stars; Stellar interferometers; Timing Correlation; Ultra-High-Resolution Astronomy; Ultrahigh resolution; Visible light; dept.phy

Speckle imaging excludes low-mass companions orbiting the exoplanet host star trappist-1 - Howell, Steve B; Everett, Mark E; Horch, Elliott P; Winters, Jennifer G; Hirsch, Lea A; Nusdeo, Dan; Scott, Nicholas J (The Astrophysical Journal, 2016)
We have obtained the highest-resolution images available of TRAPPIST-1 using the Gemini-South telescope and our speckle imaging camera. Observing at 692 and 883 nm, we reached the diffraction limit of the telescope providing a best resolution of 27 mas or, at the distance of TRAPPIST-1, a spatial resolution of 0.32 au. Our imaging of the star extends from 0.32 to 14.5 au. We show that to a high confidence level, we can exclude all possible stellar and brown dwarf companions, indicating that TRAPPIST-1 is a single star. © 2016. The American Astronomical Society. All rights reserved.
45 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/135-678-895-243-534 tex.type: [object Object]
Keywords: dept.phy; stars: imaging; stars: individual (TRAPPIST-1; 2MASS J23062928-0502285)

Combinatorial development of antibacterial Zr-Cu-Al-Ag thin film metallic glasses. - Liu, Yanhui; Padmanabhan, Jagannath; Cheung, Bettina; Liu, Jingbei; Chen, Zheng; Scanley, B Ellen; Wesolowski, Donna; Pressley, Mariyah; Broadbridge, Christine C; Altman, Sidney; Schwarz, Udo D; Kyriakides, Themis R; et al. (Scientific Reports, 2016)
Metallic alloys are normally composed of multiple constituent elements in order to achieve integration of a plurality of properties required in technological applications. However, conventional alloy development paradigm, by sequential trial-and-error approach, requires completely unrelated strategies to optimize compositions out of a vast phase space, making alloy development time consuming and labor intensive. Here, we challenge the conventional paradigm by proposing a combinatorial strategy that enables parallel screening of a multitude of alloys. Utilizing a typical metallic glass forming alloy system Zr-Cu-Al-Ag as an example, we demonstrate how glass formation and antibacterial activity, two unrelated properties, can be simultaneously characterized and the optimal composition can be efficiently identified. We found that in the Zr-Cu-Al-Ag alloy system fully glassy phase can be obtained in a wide compositional range by co-sputtering, and antibacterial activity is strongly dependent on alloy compositions. Our results indicate that antibacterial activity is sensitive to Cu and Ag while essentially remains unchanged within a wide range of Zr and Al. The proposed strategy not only facilitates development of high-performing alloys, but also provides a tool to unveil the composition dependence of properties in a highly parallel fashion, which helps the development of new materials by design.
51 citations (Crossref) [2023-10-31] Place: England Liu, Yanhui. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Liu, Yanhui. Department of Mechanical Engineering and Materials Science, Yale University, New Haven CT 06511, USA. Padmanabhan, Jagannath. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Padmanabhan, Jagannath. Department of Biomedical Engineering, Yale University, New Haven CT 06511, USA. Cheung, Bettina. Department of Biomedical Engineering, Yale University, New Haven CT 06511, USA. Liu, Jingbei. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Liu, Jingbei. Department of Mechanical Engineering and Materials Science, Yale University, New Haven CT 06511, USA. Chen, Zheng. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Chen, Zheng. Department of Mechanical Engineering and Materials Science, Yale University, New Haven CT 06511, USA. Scanley, B Ellen. Department of Physics, Southern Connecticut State University, New Haven, Connecticut 06515, USA. Wesolowski, Donna. Department of Molecular, Cellular and Developmental Biology, Yale University, New Haven CT 06520, USA. Pressley, Mariyah. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Broadbridge, Christine C. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Broadbridge, Christine C. Department of Physics, Southern Connecticut State University, New Haven, Connecticut 06515, USA. Altman, Sidney. Department of Molecular, Cellular and Developmental Biology, Yale University, New Haven CT 06520, USA. Schwarz, Udo D. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Schwarz, Udo D. Department of Mechanical Engineering and Materials Science, Yale University, New Haven CT 06511, USA. Schwarz, Udo D. Department of Chemical and Environmental Engineering, Yale University, New Haven CT 06520, USA. Kyriakides, Themis R. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Kyriakides, Themis R. Department of Biomedical Engineering, Yale University, New Haven CT 06511, USA. Kyriakides, Themis R. Department of Pathology, Yale University, New Haven CT 06520, USA. Schroers, Jan. Center for Research on Interface Structures and Phenomena, Yale University, New Haven CT 06511, USA. Schroers, Jan. Department of Mechanical Engineering and Materials Science, Yale University, New Haven CT 06511, USA.
Keywords: *Alloys/ch [Chemistry]; *Aluminum/ch [Chemistry]; *Anti-Bacterial Agents/ch [Chemistry]; *Combinatorial Chemistry Techniques; *Silver/ch [Chemistry]; Alloys; Alloys/pd [Pharmacology]; Aluminum; Anti-Bacterial Agents; Anti-Bacterial Agents/pd [Pharmacology]; Combinatorial Chemistry Techniques; Copper; Copper/ch [Chemistry]; Escherichia coli; Escherichia coli/de [Drug Effects]; Escherichia coli/gd [Growth & Development]; Escherichia coli/ul [Ultrastructure]; Glass; Glass/ch [Chemistry]; Microscopy; Atomic Force; Silver; Structure-Activity Relationship; Zirconium; Zirconium/ch [Chemistry]; alloy; aluminum; antiinfective agent; atomic force microscopy; chemistry; combinatorial chemistry; copper; dept.phy; drug effect; glass; growth; development and aging; peer-reviewed; silver; structure activity relation; ultrastructure; zirconium

A quintuple star system containing two eclipsing binaries - Rappaport, S; Lehmann, H; Kalomeni, B; Borkovits, T; Latham, D W; Bieryla, Allyson; Ngo, Henry; Mawet, Dimitri; Howell, Steve B; Horch, Elliott P; Jacobs, T L; Lacourse, D; et al. (Monthly Notices of the Royal Astronomical Society, 2016)
We present a quintuple star system that contains two eclipsing binaries. The unusual architecture includes two stellar images separated by 11 arcsec on the sky: EPIC 212651213 and EPIC 212651234. The more easterly image (212651213) actually hosts both eclipsing binaries which are resolved within that image at 0.09 arcsec, while the westerly image (212651234) appears to be single in adaptive optics (AO), speckle imaging, and radial velocity (RV) studies. The 'A' binary is circular with a 5.1-d period, while the 'B' binary is eccentric with a 13.1-d period. The γ velocities of the A and B binaries are different by ~10 km s-1. That, coupled with their resolved projected separation of 0.09 arcsec, indicates that the orbital period and separation of the 'C' binary (consisting of A orbiting B) are ≃65 yr and ≃25 au, respectively, under the simplifying assumption of a circular orbit. Motion within the C orbit should be discernible via future RV, AO, and speckle imaging studies within a couple of years. The C system (i.e. 212651213) has an RV and proper motion that differ from that of 212651234 by only ~1.4 kms-1 and ~3 mas yr-1. This set of similar space velocities in three dimensions strongly implies that these two objects are also physically bound, making this at least a quintuple star system. © 2016 The Authors.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/126-257-541-980-666 tex.type: [object Object]
Keywords: Binaries: close; Binaries: eclipsing; Binaries: general; Binaries: spectroscopic; Binaries: visual; dept.phy; peer-reviewed

Differential speckle and wide-field imaging for the Gemini-North and WIYN telescopes - Scott, Nicholas J; Howell, Steve B; Horch, Elliott P (Proceedings of SPIE, 2016)
Two new instruments are currently being built for the Gemini-North and WIYN telescopes. They are based on the existing DSSI (Differential Speckle Survey Instrument), but the new dual-channel instruments will have both speckle and "wide-field" imaging capabilities. Nearly identical copies of the instrument will be installed as a public access permanent loan at the Gemini-N and WIYN telescopes. Many exoplanet targets will come from the NASA K2 and TESS missions. The faint limiting magnitude, for speckle observations, will remain around 16 to 17th magnitude depending on observing conditions, while wide-field, high speed imaging should be able to go to 21+. For Gemini, the instrument will be remotely operable from either the mid-level facility at Hale Pohaku or the remote operations base in Hilo. © 2016 SPIE.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/030-410-801-313-630 tex.type: [object Object]
Keywords: High resolution imaging; High speed imaging; High-resolution imaging; Image reconstruction; Imaging capabilities; Instrumentation; Interferometry; NASA; Remote operation; Speckle; Speckle interferometry; Survey instruments; Telescopes; Wide field imaging; dept.phy

Speckle interferometry of secondary components in nearby visual binaries - Tokovinin, Andrei; Horch, Elliott P (The Astronomical Journal, 2016)
Statistical characterization of secondary subsystems in binaries helps to distinguish between various scenarios of multiple-star formation. The Differential Speckle Survey Instrument was used at the Gemini-N telescope for several hours in 2015 July to probe the binarity of 25 secondary components in nearby solar-type binaries. Six new subsystems were resolved, with meaningful detection limits for the remaining targets. The large incidence of secondary subsystems agrees with other similar studies. The newly resolved subsystem HIP 115417 Ba,Bb causes deviations in the observed motion of the outer binary from which an astrometric orbit of Ba,Bb with a period of 117 years is deduced. © 2016. The American Astronomical Society. All rights reserved.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/112-209-617-018-947 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; stars: low-mass

Speckle interferometry at SOAR in 2015 - Tokovinin, Andrei; Mason, Brian D; Hartkopf, William I; Mendez, Rene A; Horch, Elliott P (The Astronomical Journal, 2016)
The results of speckle interferometric observations at the Southern Astrophysical Research Telescope in 2015 are provided, totaling 1303 measurements of 924 resolved binary and multiple stars, and non-resolutions of 260 targets. The separations range from 12 mas to 3.″37 (median 0.″17); the maximum measured magnitude difference is 6.7 mag. We resolved 27 pairs for the first time, including 10 as inner or outer subsystems in previously known binaries, e.g., the 50 mas pair in Cha. Newly resolved pairs are commented upon. We discuss three apparently non-hierarchical systems that have been discovered in this series, arguing that their unusual configurations are the result of projection. The resolved quadruple system HIP 71510 is also studied. © 2016. The American Astronomical Society. All rights reserved..
38 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-730-326-407-996 tex.type: [object Object]
Keywords: binaries: general; dept.phy; peer-reviewed

Stellar companions to the exoplanet host stars HD 2638 and HD 164509 - Wittrock, Justin M; Kane, Stephen R; Horch, Elliott P; Hirsch, Lea A; Howell, Steve B; Ciardi, David R; Everett, Mark E; Teske, Johanna K (The Astronomical Journal, 2016)
An important aspect of searching for exoplanets is understanding the binarity of the host stars. It is particularly important, because nearly half of the solar-like stars within our own Milky Way are part of binary or multiple systems. Moreover, the presence of two or more stars within a system can place further constraints on planetary formation, evolution, and orbital dynamics. As part of our survey of almost a hundred host stars, we obtained images at 692 and 880 nm bands using the Differential Speckle Survey Instrument (DSSI) at the Gemini-North Observatory. From our survey, we detect stellar companions to HD-2638 and HD-164509. The stellar companion to HD-2638 has been previously detected, but the companion to HD-164509 is a newly discovered companion. The angular separation for HD-2638 is 0.512±0 002 and for HD-164509 is 0.697 0. 00 ' 2. This corresponds to a projected separation of 25.6±1.9 au and 36.5±1.9 au, respectively. By employing stellar isochrone models, we estimate the mass of the stellar companions of HD-2638 and HD-164509 to be 0.483±0.007-Me and 0.416 0.007 M, respectively, and their effective temperatures to be 3570±8K and 3450±7K, respectively. These results are consistent with the detected companions being late-type M dwarfs. © 2016. The American Astronomical Society. All rights reserved.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-023-747-811-953 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planetary systems; stars: individual (HD 2638; HD 164509); techniques: high angular resolution

Measurement of muscle food spoilage using fluorescence imaging - Wu, Binlin; Dahlberg, Kevin (Proceedings of SPIE, 2016)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/090-654-960-089-370 tex.type: [object Object]
Keywords: dept.phy

A new method using multiphoton imaging and morphometric analysis for differentiating chromophobe renal cell carcinoma and oncocytoma kidney tumors - Wu, Binlin; Mukherjee, Sushmita; Jain, Manu (Proceedings of SPIE, 2016)
Distinguishing chromophobe renal cell carcinoma (chRCC) from oncocytoma on hematoxylin and eosin images may be difficult and require time-consuming ancillary procedures. Multiphoton microscopy (MPM), an optical imaging modality, was used to rapidly generate sub-cellular histological resolution images from formalin-fixed unstained tissue sections from chRCC and oncocytoma. Tissues were excited using 780nm wavelength and emission signals (including second harmonic generation and autofluorescence) were collected in different channels between 390 nm and 650 nm. Granular structure in the cell cytoplasm was observed in both chRCC and oncocytoma. Quantitative morphometric analysis was conducted to distinguish chRCC and oncocytoma. To perform the analysis, cytoplasm and granules in tumor cells were segmented from the images. Their area and fluorescence intensity were found in different channels. Multiple features were measured to quantify the morphological and fluorescence properties. Linear support vector machine (SVM) was used for classification. Re-substitution validation, cross validation and receiver operating characteristic (ROC) curve were implemented to evaluate the efficacy of the SVM classifier. A wrapper feature algorithm was used to select the optimal features which provided the best predictive performance in separating the two tissue types (classes). Statistical measures such as sensitivity, specificity, accuracy and area under curve (AUC) of ROC were calculated to evaluate the efficacy of the classification. Over 80% accuracy was achieved as the predictive performance. This method, if validated on a larger and more diverse sample set, may serve as an automated rapid diagnostic tool to differentiate between chRCC and oncocytoma. An advantage of such automated methods are that they are free from investigator bias and variability. Copyright © 2016 SPIE.
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/048-047-970-666-605 tex.type: [object Object]
Keywords: Artificial intelligence; Autofluorescence; Cancer diagnosis; Cells; Classification (of information); Computer aided diagnosis; Cytology; Diagnosis; Diseases; Fluorescence; Harmonic generation; Imaging techniques; Kidney cancer; Learning algorithms; Learning systems; Morphometric analysis; Multi-photon microscopy; Multiphoton microscopy; Nonlinear optics; Support vector machines; Tissue; Tumors; autofluorescence; cancer diagnosis; classification; dept.phy; imaging; kidney cancer; machine learning; morphometric analysis

Observations of binary stars with the differential speckle survey instrument. VI. Measures during 2014 at the Discovery Channel Telescope - Horch, Elliott P.; van Belle, Gerard T.; Davidson, James W.; Ciastko, Lindsay A.; Everett, Mark E.; Bjorkman, Karen S. (The Astronomical Journal, 2015)
We present the results of 938 speckle measures of double stars and suspected double stars drawn mainly from the Hipparcos Catalog, as well as 208 observations where no companion was noted. One hundred fourteen pairs have been resolved for the first time. The data were obtained during four observing runs in 2014 using the Differential Speckle Survey Instrument at Lowell Observatory's Discovery Channel Telescope. The measurement precision obtained when comparing to ephemeris positions of binaries with very well-known orbits is generally less than 2 mas in separation and 0.°5 in position angle. Differential photometry is found to have internal precision of approximately 0.1 mag and to be in very good agreement with Hipparcos measures in cases where the comparison is most relevant. We also estimate the detection limit in the cases where no companion was found. Visual orbital elements are derived for six systems. © 2015. The American Astronomical Society. All rights reserved.
53 citations (Crossref) [2023-10-31] Citation Key Alias: pop00059 tex.type: [object Object]
Keywords: astrometry; binaries: visual; dept.phy; peer-reviewed; techniques: interferometric; techniques: photometric

Computational nanocharacterization for combinatorially developed bulk metallic glass - Gossett, Eric; Scanley, Ellen; Liu, Yanhui; Li, Yanglin; Liu, Ze; Sohn, Sungwoo; Schroers, Jan; Broadbridge, Christine; Schwendemann, Todd C. (International Journal of High Speed Electronics and Systems, 2015)
Bulk metallic glasses synthesized at specialized facilities at Yale using magnetron cosputtering are sent to Southern Connecticut State University for elemental characterization. Characterization is done using a Zeiss Sigma VP SEM coupled with an Oxford EDS. Characterization is automated using control software provided by Oxford. Collected data is processed and visualized using computational methods developed internally. Processed data is then organized into a database suitable for web retrieval. This technique allows for the rapid characterization of a combinatorial wafer to be carried out in ~11 hours for a single wafer containing ~600 unique compounds. © 2015 World Scientific Publishing Company.
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00134 tex.type: [object Object]
Keywords: Bulk metallic glass; Combinatorial synthesis; Computational methods; Control software; Glass; Magnetron co-sputtering; Magnetron sputtering; Metallic glass; Nano-characterization; Single wafer; Spectrography; Web retrieval; combinatorial synthesis; computational methods; dept.phy; energy dispersive X-ray spectrography; magnetron sputtering; nano-characterization; peer-reviewed

Combinatorial exploration of color in gold-based alloys - Liu, Jingbei; Liu, Yanhui; Gong, Pan; Li, Yanglin; Moore, Kimberly M.; Scanley, Ellen; Walker, Fred; Broadbridge, Christine; Schroers, Jan (Gold Bulletin, 2015)
Combinatorial approaches comprised of combinatorial magnetron co-sputtering deposition and fast screening methods are introduced to study color as a function of composition in Au-based alloys. The microstructures of the thin films and bulk alloys are identified by X-ray diffraction, and their colors of the alloys are characterized by optical reflectivity. The results reveal that when comparing microstructures and reflectivity, thin films are similar to bulk alloys. In Au-Ag-Cu solid solutions, the color of the ternary alloy follows the rule of mixture. For colors resulting from AuAl2 intermetallic, the color of an alloy scales with the percentage of the intermetallic phase and the deviation from its ideal binary composition. In the Au-Al-Cu library, we found a ∼90 % AuAl2 area fraction compositional window where copper addition can be tuned to improve mechanical properties while keeping purple color, even though Al and CuAl2 phases exist. Moreover, when comparing the color in Au-Cu-Si-Ag amorphous and crystalline state solid solution for the same composition, the colors are essentially identical. © 2015 The Author(s).
32 citations (Crossref) [2023-10-31] Citation Key Alias: pop00036 tex.type: [object Object]
Keywords: Aluminum; Amorphous alloys; Amorphous silicon; Amorphousalloys; Binary composition; Color; Combinatorial approach; Crystalline materials; Crystalline state; Decorative thin film coating; Decorative thin films; Gold; Gold alloys; Gold based alloys; Gold coatings; Intermetallic phase; Intermetallics; Magnetron co-sputtering; Magnetrons; Microstructure; Optical reflectivity; Reflection; Silver; Silver alloys; Solid solution; Solid solutions; Thin films; X ray diffraction; dept.phy

Influence of stellar multiplicity on planet formation. III. adaptive optics imaging of kepler stars with gas giant planets - Wang, Ji; Fischer, Debra A.; Horch, Elliott P.; Xie, Ji-Wei (The Astrophysical Journal, 2015)
As hundreds of gas giant planets have been discovered, we study how these planets form and evolve in different stellar environments, specifically in multiple stellar systems. In such systems, stellar companions may have a profound influence on gas giant planet formation and evolution via several dynamical effects such as truncation and perturbation. We select 84 Kepler Objects of Interest (KOIs) with gas giant planet candidates. We obtain high-angular resolution images using telescopes with adaptive optics (AO) systems. Together with the AO data, we use archival radial velocity data and dynamical analysis to constrain the presence of stellar companions. We detect 59 stellar companions around 40 KOIs for which we develop methods of testing their physical association. These methods are based on color information and galactic stellar population statistics. We find evidence of suppressive planet formation within 20 AU by comparing stellar multiplicity. The stellar multiplicity rate (MR) for planet host stars is 0+5-0% within 20 AU. In comparison, the stellar MR is 18% ± 2% for the control sample, i.e., field stars in the solar neighborhood. The stellar MR for planet host stars is 34% ± 8% for separations between 20 and 200 AU, which is higher than the control sample at 12% ± 2%. Beyond 200 AU, stellar MRs are comparable between planet host stars and the control sample. We discuss the implications of the results on gas giant planet formation and evolution. © 2015. The American Astronomical Society. All rights reserved.
59 citations (Crossref) [2023-10-31] Citation Key Alias: pop00037 tex.type: [object Object]
Keywords: dept.phy; methods: observational; methods: statistical; planet-star interactions; planetary systems; planets and satellites: formation; techniques: high angular resolution

Oxide 2D electron gases as a route for high carrier densities on (001) Si - Kornblum, Lior; Jin, Eric N.; Kumah, Divine; Ernst, Alexis T.; Broadbridge, Christine; Ahn, Chong H.; Walker, Fred (Applied Physics Letters, 2015)
Two dimensional electron gases (2DEGs) formed at the interfaces of oxide heterostructures draw considerable interest owing to their unique physics and potential applications. Growing such heterostructures on conventional semiconductors has the potential to integrate their functionality with semiconductor device technology. We demonstrate 2DEGs on a conventional semiconductor by growing GdTiO3-SrTiO3 on silicon. Structural analysis confirms the epitaxial growth of heterostructures with abrupt interfaces and a high degree of crystallinity. Transport measurements show the conduction to be an interface effect, ∼9 × 1013 cm-2 electrons per interface. Good agreement is demonstrated between the electronic behavior of structures grown on Si and on an oxide substrate, validating the robustness of this approach to bridge between lab-scale samples to a scalable, technologically relevant materials system. © 2015 AIP Publishing LLC.
16 citations (Crossref) [2023-10-31] Citation Key Alias: pop00055 tex.type: [object Object]
Keywords: D electrons; Degree of crystallinity; Electron gas; Electronic behaviors; Heterojunctions; Interface effect; Materials systems; Oxide heterostructures; Oxide substrates; Semiconducting silicon; Semiconductor devices; Silicon; Transport measurements; Two dimensional electron gas; dept.phy

A seismic and gravitationally bound double star observed by Kepler - Appourchaux, T; Antia, H M; Ball, Warrick H; Creevey, O; Lebreton, Y; Verma, Kuldeep; Vorontsov, Sergei V; Campante, T L; Campante, T L; Davies, G R; Davies, G R; Gaulme, Patrick; et al. (Astronomy and Astrophysics, 2015)
Context. Solar-like oscillations have been observed by Kepler and CoRoT in many solar-type stars, thereby providing a way to probe stars using asteroseismology. Aims. The derivation of stellar parameters has usually been done with single stars. The aim of the paper is to derive the stellar parameters of a double-star system (HIP93511), for which an interferometric orbit has been observed along with asteroseismic measurements. Methods. We used a time series of nearly two years of data for the double star to detect the two oscillation-mode envelopes that appear in the power spectrum. Using a new scaling relation based on luminosity, we derived the radius and mass of each star. We derived the age of each star using two proxies: one based upon the large frequency separation and a new one based upon the small frequency separation. Using stellar modelling, the mode frequencies allowed us to derive the radius, the mass, and the age of each component. In addition, speckle interferometry performed since 2006 has enabled us to recover the orbit of the system and the total mass of the system. Results. From the determination of the orbit, the total mass of the system is 2.34-0.33 +0.45 M⊙. The total seismic mass using scaling relations is 2.47 ± 0.07 M⊙. The seismic age derived using the new proxy based upon the small frequency separation is 3.5 ± 0.3 Gyr. Based on stellar modelling, the mean common age of the system is 2.7-3.9 Gyr. The mean total seismic mass of the system is 2.34-2.53 M⊙ consistent with what we determined independently with the orbit. The stellar models provide the mean radius, mass, and age of the stars as RA = 1.82-1.87R⊙, MA = 1.25-1.39 M⊙, AgeA = 2.6-3.5 Gyr; RB = 1.22-1.25 R⊙, MB = 1.08-1.14 M⊙, AgeB = 3.35-4.21 Gyr. The models provide two sets of values for Star A: [1.25-1.27] M⊙ and [1.34-1.39] M⊙. We detect a convective core in Star A, while Star B does not have any. For the metallicity of the binary system of Z ≈ 0.02, we set the limit between stars having a convective core in the range [1.14-1.25] M⊙. © ESO, 2015.
42 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-480-656-795-885 tex.type: [object Object]
Keywords: Asteroseismology; Binaries: general; Interferometry; Orbits; Seismology; Separation; Speckle; Stars; Stars: evolution; Stars: solar types; asteroseismology; astrometry; binaries: general; dept.phy; stars: evolution; stars: solar-type

A kinematically-distinct RR-Lyrae overdensity in the inner regions of the milky way - Casetti-Dinescu, Dana I; Nusdeo, Daniel A; Girard, Terrence M; Korchagin, V I; Altena, William F Van (The Astrophysical Journal, 2015)
We combine the Siding Spring Survey of RR Lyrae stars with the Southern Proper Motion Catalog 4, in order to detect and kinematically characterize overdensities in the inner halo of the Milky Way. We identify one such overdensity above the Galactic plane, in quadrant 4 of the Galaxy. The overdensity extends at least 20° in longitude, has an average heliocentric distance of 8 kpc with a depth of 4 kpc, and is confined within 4 kpc of the Galactic plane. Its metallicity distribution is distinct from that of the field population having a peak at -1.3 and a pronounced tail to -2.0. Proper motions indicate a net vertical motion away from the plane, and a low orbital angular momentum. Qualitatively, these orbit properties suggest a possible association with ω Centauri's parent satellite. However, comparison to a specific ω Cen N-body disruption model does not give a good match with observations. Line of sight velocities, and more extensive N-body modeling will help clarify the nature of this overdensity. © 2015. The American Astronomical Society. All rights reserved.
Citation Key Alias: lens.org/124-540-032-308-91X tex.type: [object Object]
Keywords: Galaxy: halo; Galaxy: kinematics and dynamics; dept.phy; stars: variables: RR Lyrae; ⚠️ Invalid DOI

Understanding the effects of stellar multiplicity on the derived planet radii from transit surveys: implications for kepler, k2, and TESS - Ciardi, David R; Beichman, Charles A; Horch, Elliott P; Howell, Steve B (The Astrophysical Journal, 2015)
We present a study on the effect of undetected stellar companions on the derived planetary radii for Kepler Objects of Interest (KOIs). The current production of the KOI list assumes that each KOI is a single star. Not accounting for stellar multiplicity statistically biases the planets toward smaller radii. The bias toward smaller radii depends on the properties of the companion stars and whether the planets orbit the primary or the companion stars. Defining a planetary radius correction factor, XR, we find that if the KOIs are assumed to be single, then, on average, the planetary radii may be underestimated by a factor of 〈XR〉 ≈ 1.5. If typical radial velocity and high-resolution imaging observations are performed and no companions are detected, then this factor reduces to 〈XR〉 ≈ 1.2. The correction factor 〈XR〉 is dependent on the primary star properties and ranges from 〈XR〉 ≈ 1.6 for A and F stars to 〈XR〉 ≈ 1.2 for K and M stars. For missions like K2 and TESS where the stars may be closer than the stars in the Kepler target sample, observational vetting (primary imaging) reduces the radius correction factor to 〈XR〉 ≈ 1.1. Finally, we show that if the stellar multiplicity rates are not accounted for correctly, then occurrence rate calculations for Earth-sized planets may overestimate the frequency of small planets by as much as 15%-20%. © 2015. The American Astronomical Society. All rights reserved.
182 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/088-016-640-995-341 tex.type: [object Object]
Keywords: binaries: general; dept.phy; planetary systems

Patterned deposition of nanoparticles using dip pen nanolithography for synthesis of carbon nanotubes - Dahlberg, Kevin; Woods, Kelly; Jenkins, Carol; Broadbridge, Christine; Schwendemann, Todd C (MRS Proceedings, 2015)
Ordered carbon nanotube (CNT) growth by deposition of nanoparticle catalysts using dip pen nanolithography (DPN) is presented. DPN is a direct write, tip based lithography technique capable of multi-component deposition of a wide range of materials with nanometer precision. A Nanolnk NLP 2000 is used to pattern different catalytic nanoparticle solutions on various substrates. To generate a uniform pattern of nanoparticle clusters, various conditions need to be considered. These parameters include: the humidity in the vessel, temperature, and tip-surface dwell time. By patterning different nanoparticle solutions next to each other, identical growth conditions can be compared for different catalysts in a streamlined analysis process. Fe, Ni, and Co nanoparticle solutions patterned on silicon, mica, and graphite substrates serve as nucleation sites for CNT growth. The CNTs were synthesized by a chemical vapor deposition (CVD) reaction. Each nanoparticle patterned substrate is placed in a tube furnace held at 725°C during CNT growth. The carbon source used in the growth chamber is toluene. The toluene is injected at a rate of 5 mL/hr. Growth is observed for Fe and Ni nanoparticle patterns, but is lacking for the Co patterns. The results of these reactions provide important information regarding efficient and highly reproducible mechanisms for CNT growth. © 2015 Materials Research Society.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/070-622-015-549-684 tex.type: [object Object]
Keywords: Carbon nanotubes; Catalysts; Catalytic nanoparticle; Chemical vapor deposition; Chemical vapor depositions (CVD); Deposition; Dip-pen nanolithography; Lithography; Mica; Nanolithography; Nanoparticle catalysts; Nanoparticle clusters; Nanoparticle solutions; Nanoparticles; Nanotubes; Nickel; Patterned deposition; Patterned substrates; Silicate minerals; Substrates; Synthesis (chemical); Toluene; Vapor deposition; Yarn; dept.phy

High-resolution multi-band imaging for validation and characterization of small kepler planets - Everett, Mark E.; Barclay, Thomas; Ciardi, David R.; Horch, Elliott P.; Howell, Steve B.; Crepp, Justin R.; Silva, David R. (The Astronomical Journal, 2015)
High-resolution ground-based optical speckle and near-infrared adaptive optics images are taken to search for stars in close angular proximity to host stars of candidate planets identi fied by the NASA Kepler Mission. Neighboring stars are a potential source of false positive signals. These stars also blend into Kepler light curves, affecting estimated planet properties, and are important for an understanding of planets in multiple star systems. Deep images with high angular resolution help to validate candidate planets by excluding potential background eclipsing binaries as the source of the transit signals. A study of 18 Kepler Object of Interest stars hosting a total of 28 candidate and validated planets is presented. Validation levels are determined for 18 planets against the likelihood of a false positive from a background eclipsing binary. Most of these are validated at the 99% level or higher, including five newly validated planets in two systems: Kepler-430 and Kepler-431. The stellar properties of the candidate host stars are determined by supplementing existing literature values with new spectroscopic characterizations. Close neighbors of seven of these stars are examined using multi-wavelength photometry to determine their nature and influence on the candidate planet properties. Most of the close neighbors appear to be gravitationally bound secondaries, while a few are best explained as closely co-aligned field stars. Revised planet properties are derived for each candidate and validated planet, including cases where the close neighbors are the potential host stars. © 2015. The American Astronomical Society. All rights reserved.
46 citations (Crossref) [2023-10-31] Citation Key Alias: pop00061 tex.type: [object Object]
Keywords: Binaries: visual; Planetary systems; Planets and satellites: detection; Planets and satellites: fundamental parameters; Surveys; Techniques: high angular resolution; dept.phy; peer-reviewed

Research Experiences for Students: Interdisciplinary skill development to prepare the future workforce for success - Ferrari, Nicole; Jenkins, Carol; Garofano, Jacquelynn; Day, Deborah A; Schwendemann, Todd C; Broadbridge, Christine (MRS Proceedings, 2015)
Research Experiences for Undergraduates (REU) programs traditionally function as a recruitment vehicle to encourage students to pursue further studies in STEM (Science, Technology, Engineering and Math) and as an opportunity for STEM majors to delve deeper into their chosen fields of study. Based on a critical examination of REU student feedback, evaluators at CRISP (Center for Research on Interface Structures and Phenomena) have found that in addition to these conventional benefits of research-based experiences, the value of interdisciplinary skill development is integral to the REU experience and these contributions may warrant a more formal evaluative definition. Using the emerging 21st Century Skills Framework, CRISP has begun conducting a series of small-scale studies in an effort to define the contribution of student research experiences in cross-disciplinary skill development and the positive effects that exposure to real-world science practices have on refinement of career decisions and vocational success. Using Likert-type survey methods, this study directly examines current and former REU students' perceptions of the importance of interdisciplinary 21st century skills such as creativity, collaboration, communication, information literacy, and problem-solving in their REU experience and their perceived value of these skills in their future and/or current careers. Through better understanding the role these "soft skills" play in student research experiences, CRISP hopes to maximize these interdisciplinary benefits within its REU program to best prepare students for the complex demands of the 21st century workplace. © 2015 Materials Research Society.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/096-003-001-017-805 tex.type: [object Object]
Keywords: Amphibious vehicles; Cross-disciplinary; Education; Engineering research; Functions; Information literacy; Interdisciplinary skills; Interface structures; Problem solving; Research Experiences for Undergraduates programs; Research experiences for students; Research-based experiences; Skill development; Students; dept.phy

Cutting the cord: toward wireless optical intensity interferometry - Horch, Elliott P (Proceedings of SPIE, 2015)
Intensity interferometry, which was first used for obtaining ultra-high-resolution image information in astronomy in the 1960's and 1970's, is now being revived using modern detectors and electronics. This paper explores the possibility of wireless optical interferometry made possible by technological advancements in timing correlation, signal processing, and detector technology. If this can be achieved, then baselines of one to several kilometers may be possible in optical interferometry in the coming years. This would improve the resolution over the current generation of amplitude-based optical interferometers by a factor of at least ten. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only. © 2015 SPIE.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/068-868-231-716-094 tex.type: [object Object]
Keywords: Avalanche diodes; Correlation detectors; Current generation; Detector technology; Interferometry; Optical correlation; Optical interferometer; Optical interferometry; Particle beams; Photon counting; Photons; Signal processing; Single photon avalanche diode; Single photon avalanche diodes; Technological advancement; Timing correlation; Ultra-high-resolution astronomy; Ultrahigh resolution; dept.phy

Observations of binary stars with the differential speckle survey instrument. V. toward an empirical metal-poor mass–luminosity relation - Horch, Elliott P; Altena, William F Van; Demarque, Pierre; Howell, Steve B; Everett, Mark E; Ciardi, David R; Teske, Johanna K; Henry, Todd J; Winters, Jennifer G (The Astronomical Journal, 2015)
In an effort to better understand the details of the stellar structure and evolution of metal-poor stars, the Gemini North telescope was used on two occasions to take speckle imaging data of a sample of known spectroscopic binary stars and other nearby stars in order to search for and resolve close companions. The observations were obtained using the Differential Speckle Survey Instrument, which takes data in two filters simultaneously. The results presented here are of 90 observations of 23 systems in which one or more companions was detected, and six stars where no companion was detected to the limit of the camera capabilities at Gemini. In the case of the binary and multiple stars, these results are then further analyzed to make first orbit determinations in five cases, and orbit refinements in four other cases. The mass information is derived, and since the systems span a range in metallicity, a study is presented that compares our results with the expected trend in total mass as derived from the most recent Yale isochrones as a function of metal abundance. These data suggest that metal-poor main-sequence stars are less massive at a given color than their solar-metallicity analogues in a manner consistent with that predicted from the theory. © 2015. The American Astronomical Society. All rights reserved..
25 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-359-698-007-676 tex.type: [object Object]
Keywords: astrometry; binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Dynamical masses of young M dwarfs: masses and orbital parameters of gj 3305 ab, the wide binary companion to the imaged exoplanet host 51 eri - Montet, Benjamin T; Bowler, Brendan P; Shkolnik, Evgenya L; Deck, Katherine M; Wang, Ji; Horch, Elliott P; Liu, Michael C; Hillenbrand, Lynne A; Kraus, Adam L; Charbonneau, David; Hillenbrand, Lynne A; Kraus, Adam L; et al. (The Astrophysical Journal, 2015)
We combine new high resolution imaging and spectroscopy from Keck/NIRC2, Discovery Channel Telescope/DSSI, and Keck/HIRES with published astrometry and radial velocities to measure individual masses and orbital elements of the GJ 3305 AB system, a young (∼20 Myr) M+M binary (unresolved spectral type M0) member of the β Pictoris moving group comoving with the imaged exoplanet host 51 Eri. We measure a total system mass of 1.11 ± 0.04 , a period of 29.03 ± 0.50 year, a semimajor axis of 9.78 ± 0.14 AU, and an eccentricity of 0.19 ± 0.02. The primary component has a dynamical mass of 0.67 ± 0.05 and the secondary has a mass of 0.44 ± 0.05 . The recently updated BHAC15 models are consistent with the masses of both stars to within Given the observed masses the models predict an age of the GJ 3305 AB system of 37 ± 9 Myr. Based on the observed system architecture and our dynamical mass measurement, it is unlikely that the orbit of 51 Eri b has been significantly altered by the Kozai-Lidov mechanism. © 2015. The American Astronomical Society. All rights reserved..
42 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/082-123-910-981-94X tex.type: [object Object]
Keywords: astrometry; binaries: close; dept.phy; stars: fundamental parameters; stars: individual (GJ 3305 AB)

A comparison of spectroscopic versus imaging techniques for detecting close companions to kepler objects of interest - Teske, Johanna K; Everett, Mark E; Hirsch, Lea A; Furlan, Elise; Horch, Elliott P; Horch, Elliott P; Howell, Steve B; Ciardi, David R; Gonzales, Erica J; Crepp, Justin R (The Astronomical Journal, 2015)
Kepler planet candidates require both spectroscopic and imaging follow-up observations to rule out false positives and detect blended stars. Traditionally, spectroscopy and high-resolution imaging have probed different host star companion parameter spaces, the former detecting tight binaries and the latter detecting wider bound companions as well as chance background stars. In this paper, we examine a sample of 11 Kepler host stars with companions detected by two techniques - near-infrared adaptive optics and/or optical speckle interferometry imaging, and a new spectroscopic deblending method. We compare the companion effective temperatures (Teff) and flux ratios (FB/FA, where A is the primary and B is the companion) derived from each technique and find no cases where both companion parameters agree within 1σ errors. In 3/11 cases the companion Teff values agree within 1σ errors, and in 2/11 cases the companion FB/FA values agree within 1σ errors. Examining each Kepler system individually considering multiple avenues (isochrone mapping, contrast curves, probability of being bound), we suggest two cases for which the techniques most likely agree in their companion detections (detect the same companion star). Overall, our results support the advantage that the spectroscopic deblending technique has for finding very close-in companions (θ ≲ 0.″02-0.″05) that are not easily detectable with imaging. However, we also specifically show how high-contrast AO and speckle imaging observations detect companions at larger separations (θ ≥ 0.″02-0.″05) that are missed by the spectroscopic technique, provide additional information for characterizing the companion and its potential contamination (e.g., position angle, separation, magnitude differences), and cover a wider range of primary star effective temperatures. The investigation presented here illustrates the utility of combining the two techniques to reveal higher-order multiples in known planet-hosting systems. © 2015. The American Astronomical Society. All rights reserved.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/163-960-215-288-558 tex.type: [object Object]
Keywords: binaries: general; dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution; techniques: interferometric; techniques: photometric; techniques: spectroscopic

Speckle interferometry at soar in 2014 - Tokovinin, Andrei; Mason, Brian D; Hartkopf, William I; Mendez, Rene A; Horch, Elliott P (The Astronomical Journal, 2015)
The results of speckle interferometric observations at the Southern Astrophysical Research Telescope (SOAR) telescope in 2014 are given. A total of 1641 observations were taken, yielding 1636 measurements of 1218 resolved binary and multiple stars and 577 non-resolutions of 441 targets. We resolved for the first time 56 pairs, including some nearby astrometric or spectroscopic binaries and ten new subsystems in previously known visual binaries. The calibration of the data is checked by linear fits to the positions of 41 wide binaries observed at SOAR over several seasons. The typical calibration accuracy is 0.°1 in angle and 0.3% in pixel scale, while the measurement errors are on the order of 3 mas. The new data are used here to compute 194 binary star orbits, 148 of which are improvements on previous orbital solutions and 46 are first-time orbits. © 2015. The American Astronomical Society. All rights reserved..
81 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-545-424-948-585 tex.type: [object Object]
Keywords: binaries: general; dept.phy; peer-reviewed

Validation of 12 small kepler transiting planets in the habitable zone - Torres, Guillermo; Kipping, David M; Fressin, Francois; Caldwell, Douglas A; Twicken, Joseph D; Ballard, Sarah; Batalha, Natalie M; Bryson, Stephen T; Ciardi, David R; Henze, Christopher E; Howell, Steve B; Isaacson, Howard; et al. (The Astrophysical Journal, 2015)
We present an investigation of 12 candidate transiting planets from Kepler with orbital periods ranging from 34 to 207 days, selected from initial indications that they are small and potentially in the habitable zone (HZ) of their parent stars. Few of these objects are known. The expected Doppler signals are too small to confirm them by demonstrating that their masses are in the planetary regime. Here we verify their planetary nature by validating them statistically using the BLENDER technique, which simulates large numbers of false positives and compares the resulting light curves with the Kepler photometry. This analysis was supplemented with new follow-up observations (high-resolution optical and near-infrared spectroscopy, adaptive optics imaging, and speckle interferometry), as well as an analysis of the flux centroids. For 11 of them (KOI-0571.05, 1422.04, 1422.05, 2529.02, 3255.01, 3284.01, 4005.01, 4087.01, 4622.01, 4742.01, and 4745.01) we show that the likelihood they are true planets is far greater than that of a false positive, to a confidence level of 99.73% (3σ) or higher. For KOI-4427.01 the confidence level is about 99.2% (2.6σ). With our accurate characterization of the GKM host stars, the derived planetary radii range from 1.1 to 2.7 R ⊕. All 12 objects are confirmed to be in the HZ, and nine are small enough to be rocky. Excluding three of them that have been previously validated by others, our study doubles the number of known rocky planets in the HZ. KOI-3284.01 (Kepler-438b) and KOI-4742.01 (Kepler-442b) are the planets most similar to the Earth discovered to date when considering their size and incident flux jointly. © 2015. The American Astronomical Society. All rights reserved..
94 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/036-512-292-095-617 tex.type: [object Object]
Keywords: dept.phy; methods: statistical; planetary systems; stars: individual (KOI-3284 (Kepler-438); KOI-4742 (Kepler-442)); techniques: photometric

On the occurrence rate of hot jupiters in different stellar environments - Wang, Ji; Fischer, Debra A; Horch, Elliott P; Huang, Xu (The Astrophysical Journal, 2015)
Many hot Jupiters (HJs) are detected by the Doppler and transit techniques. From surveys using these two techniques, however, the measured HJ occurrence rates differ by a factor of two or more. Using the California Planet Survey sample and the Kepler sample, we investigate the causes for this difference in the HJ occurrence rate. First, we find that 12.8% ± 0.24% of HJs are misidentified in the Kepler mission because of photometric dilution and subgiant contamination. Second, we explore the differences between the Doppler sample and the Kepler sample that can account for the different HJ occurrence rate. Third, we discuss how to measure the fundamental HJ occurrence rates by synthesizing the results from the Doppler and Kepler surveys. The fundamental HJ occurrence rates are measures of the HJ occurrence rate as a function of stellar multiplicity and evolutionary stage, e.g., the HJ occurrence rate for single and multiple stars or for main-sequence and subgiant stars. While we find qualitative evidence that HJs occur less frequently in subgiants and multiple stellar systems, we conclude that our current knowledge of stellar properties and the stellar multiplicity rate is too limited for us to reach any quantitative result for the fundamental HJ occurrence rates. This concern extends to ηEarth, the occurrence rate of Earth-like planets. © 2015. The American Astronomical Society. All rights reserved.
54 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/156-890-481-368-476 tex.type: [object Object]
Keywords: Fundamental parameters stars; Methods; Photometric techniques; Radial velocities; Solar-type stars; Statistical planets and satellites; Statistics techniques; dept.phy

Microscopy and team-based interdisciplinary materials research to achieve 21st century skills - Broadbridge, Christine; Sadowski, Thomas; Garofano, Jacquelynn; DaPonte, John S. (Microscopy and Microanalysis, 2014)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00363 tex.type: [object Object]
Keywords: dept.phy

Recent star formation in the leading arm of the Magellanic Stream - Casetti-Dinescu, Dana I.; Bidin, Christian Moni; Girard, Terrence M.; Méndez, Réne A.; Vieira, Katherine; Korchagin, Vladimir I.; Altena, William F. van (The Astrophysical Journal, 2014)
Strongly interacting galaxies undergo a short-lived but dramatic phase of evolution characterized by enhanced star formation, tidal tails, bridges, and other morphological peculiarities. The nearest example of a pair of interacting galaxies is the Magellanic Clouds, whose dynamical interaction produced the gaseous features known as the Magellanic Stream trailing the pair's orbit about the Galaxy, the bridge between the Clouds, and the leading arm (LA), a wide and irregular feature leading the orbit. Young, newly formed stars in the bridge are known to exist, giving witness to the recent interaction between the Clouds. However, the interaction of the Clouds with the Milky Way (MW) is less well understood. In particular, the LA must have a tidal origin; however, no purely gravitational model is able to reproduce its morphology and kinematics. A hydrodynamical interaction with the gaseous hot halo and disk of the Galaxy is plausible as suggested by some models and supporting neutral hydrogen (H I) observations. Here we show for the first time that young, recently formed stars exist in the LA, indicating that the interaction between the Clouds and our Galaxy is strong enough to trigger star formation in certain regions of the LA—regions in the outskirts of the MW disk (R ∼ 18 kpc), far away from the Clouds and the bridge.
25 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/084-595-728-951-339, pop00078 tex.type: [object Object]
Keywords: Galaxy: general; Magellanic Clouds; dept.phy; galaxies: interactions; stars: early-type

An analytic algorithm to calculate the inclination, ascending node, and semimajor axis of spectroscopic binary orbits using a single speckle measurement and the parallax - Docobo, Jose Angel; Campo, P P; Andrade, Manuel; Horch, Elliott P (Astrophysical Bulletin, 2014)
It is well known that in spectroscopic binary orbits, the inclination, the ascending node, and the semimajor axis remain undetermined, therefore the principal objective of this research is to establish an analytic methodology for the calculation of these parameters for spectroscopic binaries, both single-lined (SB1) and double-lined (SB2). In other words, the goal is to determine their “three-dimensional” orbits using a single speckle measurement (ρ, θ, t) and the parallax (π). Moreover, estimates of the individual masses of each system can also be obtained. The proposed algorithm was successfully applied to SB1 systems: YSC 148 (HD 37393) and CHR 225 (HD 34318), and SB2 systems: LSC 1 Aa1,2 (HD 200077) and Mkt 11 Aa, Ab (HD 358). In this late case, previously determined spectroscopic and visual orbits have been used to compare and contrast the results obtained from them with our results. The methodology presented is especially interesting for those cases in which it is only possible to resolve the spectroscopic binary in the zones of maximum angular separation by optical means thereby making it impossible to avail of sufficient observations in order to calculate the visual orbit. © Pleiades Publishing, Ltd. 2014.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/094-814-675-311-054 tex.type: [object Object]
Keywords: dept.phy; general; high angular resolution—techniques; interferometric—binaries; techniques

The three-dimensional orbit and physical properties of the binary COU 2031 (WDS 04464+4221, HIP 22196, HD 30090) - Docobo, Jose Angel; Griffin, R F; Tamazian, V S; Horch, Elliott P; Campo, P P (Monthly Notices of the Royal Astronomical Society, 2014)
We report a comprehensive study of the binary system COU 2031, based on simultaneous and independent astrometric visual and speckle observations and on radial-velocity measurements. The similarity of the two orbital solutions allows us to obtain not only a consistent 3D orbit and a precise value of the parallax of the system but also to determine the physical properties of the components. © 2014 The Authors.
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/132-132-335-733-638 tex.type: [object Object]
Keywords: Binaries: spectroscopic; Binaries: visual; Stars: individual: COU 2031; dept.phy; peer-reviewed

Characterization of carbon nanotube growth via CVD synthesis from a liquid precursor - Jenkins, Carol; Cruz, Melissa; Depalma, Jen; Conroy, Michael; Benardo, Barbara; Horbachuk, Michael; Sadowski, Tom; Broadbridge, Christine; Schwendemann, Todd C (International Journal of High Speed Electronics and Systems, 2014)
As novel theories and uses of carbon nanotubes (CNT) advance, it becomes increasingly important to characterize the methods of production. One such method of CNT production uses a liquid phase precursor (hydrocarbon with nanoparticle catalyst mix) that is injected into a tube furnace with a flowing carrier gas. The CNTs are grown in high purity and are collected on the surface of the quartz tube. The system allows for a number of variables to be tested such as growth temperatures, flow rate of the carrier gas, precursor injection rates and variations of precursor mix however, here only thermal effects are considered. Under thermal conditions ranging from 500 to 850°C, multi-walled carbon nanotubes (MWCNTs) are synthesized and characterized to determine inner and outer diameter as well as tube thickness. © 2014 World Scientific Publishing Company.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-611-840-548-398 tex.type: [object Object]
Keywords: Carbon nanotube growth; Carbon nanotubes; Carbon nanotubes (CNT); Chemical vapor deposition; Chemical vapor deposition (CVD); Chemical vapor depositions (CVD); Liquid precursors; Liquid-phase precursors; Liquids; Nanoparticle catalysts; Outer diameters; Precursor injection; Thermal condition; Transmission electron microscopy; Transmission electron microscopy (TEM); Tubes (components); dept.phy; peer-reviewed

A high density two-dimensional electron gas in an oxide heterostructure on Si (001) - Jin, Eric N; Kornblum, Lior; Kumah, Divine; Zou, Ke; Broadbridge, Christine; Ngai, J H; Ahn, C H; Walker, Fred (APL Materials, 2014)
We present the growth and characterization of layered heterostructures comprised of LaTiO3 and SrTiO3 epitaxially grown on Si (001). Magnetotransport measurements show that the sheet carrier densities of the heterostructures scale with the number of LaTiO3/SrTiO3 interfaces, consistent with the presence of an interfacial 2-dimensional electron gas (2DEG) at each interface. Sheet carrier densities of 8.9 × 1014 cm-2 per interface are observed. Integration of such high density oxide 2DEGs on silicon provides a bridge between the exceptional properties and functionalities of oxide 2DEGs and microelectronic technologies. © 2014 Author(s).
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/087-040-511-772-110 tex.type: [object Object]
Keywords: dept.phy

Limits on stellar companions to exoplanet host stars with eccentric planets - Kane, Stephen R; Howell, Steve B; Horch, Elliott P; Feng, Ying; Hinkel, Natalie R; Ciardi, David R; Everett, Mark E; Howard, Andrew W; Wright, Jason T (The Astrophysical Journal, 2014)
Though there are now many hundreds of confirmed exoplanets known, the binarity of exoplanet host stars is not well understood. This is particularly true of host stars that harbor a giant planet in a highly eccentric orbit since these are more likely to have had a dramatic dynamical history that transferred angular momentum to the planet. Here we present observations of four exoplanet host stars that utilize the excellent resolving power of the Differential Speckle Survey Instrument on the Gemini North telescope. Two of the stars are giants and two are dwarfs. Each star is host to a giant planet with an orbital eccentricity >0.5 and whose radial velocity (RV) data contain a trend in the residuals to the Keplerian orbit fit. These observations rule out stellar companions 4-8 mag fainter than the host star at passbands of 692 nm and 880 nm. The resolution and field of view of the instrument result in exclusion radii of 0.″05-1.″4, which excludes stellar companions within several AU of the host star in most cases. We further provide new RVs for the HD 4203 system that confirm that the linear trend previously observed in the residuals is due to an additional planet. These results place dynamical constraints on the source of the planet's eccentricities, place constraints on additional planetary companions, and inform the known distribution of multiplicity amongst exoplanet host stars. © 2014. The American Astronomical Society. All rights reserved..
24 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-289-457-778-141 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (HD 4203; HD 168443; HD 1690; HD 137759); techniques: Radial velocities; techniques: high angular resolution

High proper motion x-ray binaries from the yale southern proper motion survey - Maccarone, Thomas J.; Girard, Terrence M.; Casetti-Dinescu, Dana I. (Monthly Notices of the Royal Astronomical Society, 2014)
We discuss the results of cross-correlating catalogues of bright X-ray binaries with the Yale Southern Proper Motion Catalog (version 4.0). Several objects already known to have large proper motions from Hipparcos are recovered. Two additional objects are found which show substantial proper motions, both of which are unusual in their X-ray properties. One is IGR J17544-2619, one of the supergiant fast X-ray transients. Assuming the quoted distances in the literature for this source of about 3 kpc are correct, this system has a peculiar velocity of about 275 km s-1-greater than the velocity of a Keplerian orbit at its location of the Galaxy and in line with the expectations formed from suggestions that the supergiant fast X-ray transients should be highly eccentric. We discuss the possibility that these objects may help explain the existence of short gamma-ray bursts outside the central regions of galaxies. The other is the source 2A 1822-371, which is a member of the small class of objects which are low-mass X-ray binaries and long (i.e. >100 ms) X-ray pulsars. This system also shows both an anomalously high X-ray luminosity and a large orbital period derivative for a system with its orbital period, and some possible indications of an eccentric orbit. A coherent picture can be developed by adding in the proper motion information in which this system formed in the Perseus spiral arm of the Galaxy about 3 Myr ago and retains a slightly eccentric orbit which leads to enhanced mass transfer. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
9 citations (Crossref) [2023-10-31] Citation Key Alias: pop00122 tex.type: [object Object]
Keywords: Proper motions; X-rays: binaries; dept.phy; peer-reviewed

An Earth-Sized Planet in the Habitable Zone of a Cool Star. - Quintana, Elisa; Barclay, Thomas; Raymond, Sean; Rowe, Jason; Bolmont, Emeline; Caldwell, Douglas; Howell, Steve; Kane, Stephen; Huber, Daniel; Crepp, Justin; Lissauer, Jack; Ciardi, David; et al. (Science, 2014)
The quest for Earth-like planets is a major focus of current exoplanet research. Although planets that are Earth-sized and smaller have been detected, these planets reside in orbits that are too close to their host star to allow liquid water on their surfaces. We present the detection of Kepler-186f, a 1.11 ± 0.14 Earth-radius planet that is the outermost of five planets, all roughly Earth-sized, that transit a 0.47 ± 0.05 solar-radius star. The intensity and spectrum of the star's radiation place Kepler-186f in the stellar habitable zone, implying that if Kepler-186f has an Earth-like atmosphere and water at its surface, then some of this water is likely to be in liquid form.
189 citations (Crossref) [2023-10-31] Place: Copyright (C) 2014 by the American Association for the Advancement of Science
Keywords: Earth; Earth (Planet); Exobiology; Extraterrestrial Environment; Planets; Stars; Celestial; Water; astrobiology; astronomy; atmosphere; cosmic radiation; dept.phy; habitat use; microclimate; priority journal; review; solar system; surface property; water

Use of the gabor filter for edge detection in the analysis of zinc oxide nanowire images - Scanley, B E; Sadowski, Thomas; Pelligra, Candice; Kreider, M E; Osuji, Chinedum O; Broadbridge, Christine (Microscopy and Microanalysis, 2014)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/150-087-209-672-777 tex.type: [object Object]
Keywords: dept.phy

Intensity interferometry for the 21st century - Horch, Elliott P.; van Belle, G. T.; Genet, R. M.; Holenstein, B. D. (Journal of Astronomical Instrumentation, 2013)
Advances in detector technology and electronic timing capabilities in recent years have resulted in a new opportunity for ultra-high resolution in astronomy using intensity interferometry. We have been working with this technology and describe here the potential as we see it. Two separate opportunities exist at present: The use of Single Photon Avalanche Diode (SPAD) detectors with existing research-grade telescopes and photomultipliers coupled with light bucket telescopes. In the future, there may also be potential for space-based intensity interferometry. While intensity interferometry is not likely to replace amplitude-based interferometry, it does have certain advantages in terms of portability, use of large baselines, narrow-band imaging, and imaging in the blue. We see a new possibility for its use particularly in stellar astrophysics for these reasons. © 2013 World Scientific Publishing Company.
9 citations (Crossref) [2023-10-31] Citation Key Alias: pop00124
Keywords: Instrumentation: Interferometers; dept.phy; high angular resolution; techniques: Interferometric

Kepler-63b: A giant planet in a polar orbit around a young sun-like star - Sanchis-Ojeda, Roberto; Winn, Joshua N.; Marcy, Geoffrey W.; Howard, Andrew W.; Isaacson, Howard; Johnson, John Asher; Torres, Guillermo; Albrecht, Simon; Campante, Tiago L.; Chaplin, William J.; Davies, Guy R.; Lund, Mikkel N.; et al. (The Astrophysical Journal, 2013)
We present the discovery and characterization of a giant planet orbiting the young Sun-like star Kepler-63 (KOI-63, M⊙Kp = 11.6, T eff = 5576 K, M⊙ = 0.98 M⊙). The planet transits every 9.43 days, with apparent depth variations and brightening anomalies caused by large starspots. The planet's radius is 6.1 ± 0.2 R ⊕, based on the transit light curve and the estimated stellar parameters. The planet's mass could not be measured with the existing radial-velocity data, due to the high level of stellar activity, but if we assume a circular orbit, then we can place a rough upper bound of 120 M ⊙⊕ (3σ). The host star has a high obliquity (ψ = 104°), based on the Rossiter-McLaughlin effect and an analysis of starspot-crossing events. This result is valuable because almost all previous obliquity measurements are for stars with more massive planets and shorter-period orbits. In addition, the polar orbit of the planet combined with an analysis of spot-crossing events reveals a large and persistent polar starspot. Such spots have previously been inferred using Doppler tomography, and predicted in simulations of magnetic activity of young Sun-like stars. © 2013. The American Astronomical Society. All rights reserved..
98 citations (Crossref) [2023-10-31] Citation Key Alias: pop00012 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: activity; stars: individual (Kepler-63); stars: rotation; starspots

Exoplanet characterization by proxy: A transiting 2.15 r ⊕ planet near the habitable zone of the late K dwarf Kepler-61 - Ballard, Sarah; Charbonneau, David; Fressin, Francois; Torres, Guillermo; Irwin, Jonathan; Desert, Jean-Michel; Newton, Elisabeth; Mann, Andrew W.; Ciardi, David R.; Crepp, Justin R.; Henze, Christopher E.; Bryson, Stephen T.; et al. (The Astrophysical Journal, 2013)
We present the validation and characterization of Kepler-61b: a 2.15 R ⊕ planet orbiting near the inner edge of the habitable zone of a low-mass star. Our characterization of the host star Kepler-61 is based upon a comparison with a set of spectroscopically similar stars with directly measured radii and temperatures. We apply a stellar prior drawn from the weighted mean of these properties, in tandem with the Kepler photometry, to infer a planetary radius for Kepler-61b of 2.15 ± 0.13 R ⊕ and an equilibrium temperature of 273 ± 13 K (given its period of 59.87756 ± 0.00020 days and assuming a planetary albedo of 0.3). The technique of leveraging the physical properties of nearby “proxy” stars allows for an independent check on stellar characterization via the traditional measurements with stellar spectra and evolutionary models. In this case, such a check had implications for the putative habitability of Kepler-61b: the planet is 10% warmer and larger than inferred from K-band spectral characterization. From the Kepler photometry, we estimate a stellar rotation period of 36 days, which implies a stellar age of >1 Gyr. We summarize the evidence for the planetary nature of the Kepler-61 transit signal, which we conclude is 30,000 times more likely to be due to a planet than a blend scenario. Finally, we discuss possible compositions for Kepler-61b with a comparison to theoretical models as well as to known exoplanets with similar radii and dynamically measured masses.
33 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/071-947-168-650-048, pop00052 tex.type: [object Object]
Keywords: dept.phy; eclipses; planetary systems; stars: individual (Kepler-61; KOI 1361; KIC 6960913)

Spitzer observations of gj 3470 b: a very low-density neptune-size planet orbiting a metal-rich m dwarf* - Demory, Brice-Olivier; Torres, Guillermo; Neves, V.; Rogers, Leslie A.; Gillon, Michaël; Horch, Elliott P.; Sullivan, Peter W.; Bonfils, Xavier; Delfosse, Xavier; Forveille, Thierry; Lovis, Christophe; Mayor, Michel; et al. (The Astrophysical Journal, 2013)
We present Spitzer/IRAC 4.5 μm transit photometry of GJ 3470 b, a Neptune-size planet orbiting an M1.5 dwarf star with a 3.3 day period recently discovered in the course of the HARPS M-dwarf survey. We refine the stellar parameters by employing purely empirical mass-luminosity and surface brightness relations constrained by our updated value for the mean stellar density, and additional information from new near-infrared spectroscopic observations. We derive a stellar mass of and a radius of of M* = 0.539 +0.047-0.043 M⊙ and a radius of R* = 0.568+0.037-0.031 R⊙. We determine the host star of GJ 3470 b to be metal-rich, with a metallicity of [Fe/H] = +0.20 ± 0.10 and an effective temperature of Teff = 3600 ± 100 K. The revised stellar parameters yield a planetary radius Rp= 4.83+0.22-0.21 R⊕that is 13% larger than the value previously reported in the literature. We find a planetary mass M p= 13.9+1.5-1.4 M⊕ that translates to a very low planetary density, ρp = 0.72+0.13 -0.12 g cm-3, which is 33% smaller than the original value. With a mean density half of that of GJ 436 b, GJ 3470 b is an example of a very low-density low-mass planet, similar to Kepler-11 d, Kepler-11 e, and Kepler-18 c, but orbiting a much brighter nearby star that is more conducive to follow-up studies. © 2013. The American Astronomical Society. All rights reserved.
29 citations (Crossref) [2023-10-31] Citation Key Alias: pop00035 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (GJ 3470); techniques: photometric; techniques: spectroscopic

The mass of KOI-94d and a relation for planet radius, mass, and incident flux - Weiss, Lauren M.; Marcy, Geoffrey W.; Rowe, Jason F.; Howard, Andrew W.; Isaacson, Howard; Fortney, Jonathan J.; Miller, Neil; Demory, Brice-Olivier; Fischer, Debra A.; Adams, Elisabeth R.; Dupree, Andrea K.; Howell, Steve B.; et al. (The Astrophysical Journal, 2013)
We measure the mass of a modestly irradiated giant planet, KOI-94d. We wish to determine whether this planet, which is in a 22 day orbit and receives 2700 times as much incident flux as Jupiter, is as dense as Jupiter or rarefied like inflated hot Jupiters. KOI-94 also hosts at least three smaller transiting planets, all of which were detected by the Kepler mission. With 26 radial velocities of KOI-94 from the W. M. Keck Observatory and a simultaneous fit to the Kepler light curve, we measure the mass of the giant planet and determine that it is not inflated. Support for the planetary interpretation of the other three candidates comes from gravitational interactions through transit timing variations, the statistical robustness of multi-planet systems against false positives, and several lines of evidence that no other star resides within the photometric aperture. We report the properties of KOI-94b (M P = 10.5 ± 4.6 M ⊕, R P = 1.71 ± 0.16 R ⊕, P = 3.74 days), KOI-94c (M P = M ⊕, R P = 4.32 ± 0.41 R ⊕, P = 10.4 days), KOI-94d (M P = 106 ± 11 M ⊕, R P = 11.27 ± 1.06 R ⊕, P = 22.3 days), and KOI-94e (M P = M ⊕, R P = 6.56 ± 0.62 R ⊕, P = 54.3 days). The radial velocity analyses of KOI-94b and KOI-94e offer marginal (>2σ) mass detections, whereas the observations of KOI-94c offer only an upper limit to its mass. Using the KOI-94 system and other planets with published values for both mass and radius (138 exoplanets total, including 35 with M P < 150 M ⊕), we establish two fundamental planes for exoplanets that relate their mass, incident flux, and radius from a few Earth masses up to 13 Jupiter masses: (R P/R ⊕) = 1.78(M P/M ⊕)0.53(F/erg s–1 cm–2)–0.03 for M P < 150 M ⊕, and R P/R ⊕ = 2.45(M P/M ⊕)–0.039(F/erg s–1 cm–2)0.094 for M P > 150 M ⊕. These equations can be used to predict the radius or mass of a planet.
223 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/043-207-643-634-196, pop00005 tex.type: [object Object]
Keywords: dept.phy; planets and satellites: composition; techniques: photometric; techniques: spectroscopic

A sub-Mercury-sized exoplanet. - Barclay, Thomas; Rowe, Jason; Lissauer, Jack; Huber, Daniel; Fressin, Francois; Howell, Steve; Bryson, Stephen; Chaplin, William; Desert, Jean-Michel; Lopez, Eric; Marcy, Geoffrey; Mullally, Fergal; et al. (Nature, 2013)
Since the discovery of the first exoplanets, it has been known that other planetary systems can look quite unlike our own. Until fairly recently, we have been able to probe only the upper range of the planet size distribution, and, since last year, to detect planets that are the size of Earth or somewhat smaller. Hitherto, no planets have been found that are smaller than those we see in the Solar System. Here we report a planet significantly smaller than Mercury. This tiny planet is the innermost of three that orbit the Sun-like host star, which we have designated Kepler-37. Owing to its extremely small size, similar to that of the Moon, and highly irradiated surface, the planet, Kepler-37b, is probably rocky with no atmosphere or water, similar to Mercury. © 2013 Macmillan Publishers Limited. All rights reserved.
161 citations (Crossref) [2023-10-31] Place: (C) 2013 Nature Publishing Group
Keywords: Earth; article; astronomy; atmosphere; dept.phy; irradiance; irradiation; moon; orbit determination; planetary surface; priority journal; size structure; solar system; sun; water

Observations of binary stars with the differential speckle survey instrument. iv. observations of kepler, corot, and hipparcos stars from the gemini north telescope - Horch, Elliott P.; Howell, Steve B.; Everett, Mark E.; Ciardi, David R. (The Astronomical Journal, 2012)
We present the results of 71 speckle observations of binary and unresolved stars, most of which were observed with the DSSI speckle camera at the Gemini North Telescope in 2012 July. The main purpose of the run was to obtain diffraction-limited images of high-priority targets for the Kepler and CoRoT missions, but in addition, we observed a number of close binary stars where the resolution limit of Gemini was used to better determine orbital parameters and/or confirm results obtained at or below the diffraction limit of smaller telescopes. Five new binaries and one triple system were discovered, and first orbits are calculated for other two systems. Several systems are discussed in detail. © 2012. The American Astronomical Society. All rights reserved..
79 citations (Crossref) [2023-10-31] Citation Key Alias: pop00016 tex.type: [object Object]
Keywords: astrometry; binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Exploring atomic-scale lateral forces in the attractive regime: a case study on graphite (0001) - Baykara, Mehmet Z.; Schwendemann, Todd C.; Albers, Boris J.; Pilet, N.; Mönig, Harry; Altman, Eric I.; Schwarz, Udo D. (Nanotechnology, 2012)
A non-contact atomic force microscopy-based method has been used to map the static lateral forces exerted on an atomically sharp Pt/Ir probe tip by a graphite surface. With measurements carried out at low temperatures and in the attractive regime, where the atomic sharpness of the tip can be maintained over extended time periods, the method allows the quantification and directional analysis of lateral forces with piconewton and picometer resolution as a function of both the in-plane tip position and the vertical tip-sample distance, without limitations due to a finite contact area or to stick-slip-related sudden jumps of tip apex atoms. After reviewing the measurement principle, the data obtained in this case study are utilized to illustrate the unique insight that the method offers. In particular, the local lateral forces that are expected to determine frictional resistance in the attractive regime are found to depend linearly on the normal force for small tip-sample distances. © 2012 IOP Publishing Ltd.
9 citations (Crossref) [2023-10-31] Citation Key Alias: pop00127 tex.type: [object Object]
Keywords: Atomic force; Atomic force microscopy; Atomic scale; Contact areas; Directional Analysis; Frictional resistance; Graphite; Graphite surfaces; Lateral force; Low temperatures; Measurement principle; Non-contact; Normal forces; Picometer resolution; Probe tips; Slip forming; Time-periods; Tip apex; Tip-sample distance; dept.phy

Transit timing observations from kepler. II. confirmation of two multiplanet systems via a non-parametric correlation analysis - Ford, Eric B.; Fabrycky, Daniel C.; Steffen, Jason H.; Carter, Joshua A.; Fressin, Francois; Holman, Matthew J.; Lissauer, Jack J.; Moorhead, Althea V.; Morehead, Robert C.; Ragozzine, Darin; Rowe, Jason F.; Welsh, William F.; et al. (The Astrophysical Journal, 2012)
We present a new method for confirming transiting planets based on the combination of transit timing variations (TTVs) and dynamical stability. Correlated TTVs provide evidence that the pair of bodies is in the same physical system. Orbital stability provides upper limits for the masses of the transiting companions that are in the planetary regime. This paper describes a non-parametric technique for quantifying the statistical significance of TTVs based on the correlation of two TTV data sets. We apply this method to an analysis of the TTVs of two stars with multiple transiting planet candidates identified by Kepler. We confirm four transiting planets in two multiple-planet systems based on their TTVs and the constraints imposed by dynamical stability. An additional three candidates in these same systems are not confirmed as planets, but are likely to be validated as real planets once further observations and analyses are possible. If all were confirmed, these systems would be near 4:6:9 and 2:4:6:9 period commensurabilities. Our results demonstrate that TTVs provide a powerful tool for confirming transiting planets, including low-mass planets and planets around faint stars for which Doppler follow-up is not practical with existing facilities. Continued Kepler observations will dramatically improve the constraints on the planet masses and orbits and provide sensitivity for detecting additional non-transiting planets. If Kepler observations were extended to eight years, then a similar analysis could likely confirm systems with multiple closely spaced, small transiting planets in or near the habitable zone of solar-type stars. © 2012. The American Astronomical Society. All rights reserved.
73 citations (Crossref) [2023-10-31] Citation Key Alias: pop00013 tex.type: [object Object]
Keywords: dept.phy; planetary systems; planets and satellites: detection; planets and satellites: dynamical evolution and stability; stars: individual (KIC 3231341; 11512246; KOI 168; 1102; Kepler-23; Kepler-24); techniques: miscellaneous

Kepler-20: a sun-like star with three sub-neptune exoplanets and two earth-size candidates - Gautier, Thomas N.; Charbonneau, David; Rowe, Jason F.; Marcy, Geoffrey W.; Isaacson, Howard; Torres, Guillermo; Fressin, Francois; Rogers, Leslie A.; Désert, Jean-Michel; Buchhave, Lars A.; Latham, David W.; Quinn, Samuel N.; et al. (The Astrophysical Journal, 2012)
We present the discovery of the Kepler-20 planetary system, which we initially identified through the detection of five distinct periodic transit signals in the Kepler light curve of the host star 2MASS J19104752+4220194. From high-resolution spectroscopy of the star, we find a stellar effective temperature T eff = 5455 100 K, a metallicity of [Fe/H] = 0.01 0.04, and a surface gravity of log g = 4.4 0.1. We combine these estimates with an estimate of the stellar density derived from the transit light curves to deduce a stellar mass of M = 0.912 0.034 M and a stellar radius of R = 0.944 +0.060 -0.095 R. For three of the transit signals, we demonstrate that our results strongly disfavor the possibility that these result from astrophysical false positives. We accomplish this by first identifying the subset of stellar blends that reproduce the precise shape of the light curve and then using the constraints on the presence of additional stars from high angular resolution imaging, photometric colors, and the absence of a secondary component in our spectroscopic observations. We conclude that the planetary scenario is more likely than that of an astrophysical false positive by a factor of 2 × 105 (Kepler-20b), 1 × 105 (Kepler-20c), and 1.1 × 103 (Kepler-20d), sufficient to validate these objects as planetary companions. For Kepler-20c and Kepler-20d, the blend scenario is independently disfavored by the achromaticity of the transit: from Spitzer data gathered at 4.5 μm, we infer a ratio of the planetary to stellar radii of 0.075 0.015 (Kepler-20c) and 0.065 0.011 (Kepler-20d), consistent with each of the depths measured in the Kepler optical bandpass. We determine the orbital periods and physical radii of the three confirmed planets to be 3.70days and 1.91+0.12 -0.21 R ⊕ for Kepler-20b, 10.85days and 3.07+0.20 -0.31 R ⊕ for Kepler-20c, and 77.61days and 2.75+0.17 -0.30 R ⊕ for Kepler-20d. From multi-epoch radial velocities, we determine the masses of Kepler-20b and Kepler-20c to be 8.7 2.2 M ⊕ and 16.1 3.5 M ⊕, respectively, and we place an upper limit on the mass of Kepler-20d of 20.1 M ⊕ (2σ). © 2012 The American Astronomical Society. All rights reserved.
99 citations (Crossref) [2023-10-31] Citation Key Alias: pop00006 tex.type: [object Object]
Keywords: dept.phy; eclipses; planetary systems

Transit timing observations from kepler: III. confirmation of 4 multiple planet systems by a fourier-domain study of anti-correlated transit timing variations - Steffen, Jason H.; Fabrycky, Daniel C.; Ford, Eric B.; Carter, Joshua A.; Désert, Jean-Michel; Fressin, Francois; Holman, Matthew J.; Lissauer, Jack J.; Moorhead, Althea V.; Rowe, Jason F.; Ragozzine, Darin; Welsh, William F.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
We present a method to confirm the planetary nature of objects in systems with multiple transiting exoplanet candidates. This method involves a Fourier-domain analysis of the deviations in the transit times from a constant period that result from dynamical interactions within the system. The combination of observed anticorrelations in the transit times and mass constraints from dynamical stability allow us to claim the discovery of four planetary systems, Kepler-25, Kepler-26, Kepler-27 and Kepler-28, containing eight planets and one additional planet candidate. © 2012 Fermi Research Alliance LLC, Contractor for the U.S. Dept of Energy Monthly Notices of the Royal Astronomical Society © 2012 RAS.
121 citations (Crossref) [2023-10-31] Citation Key Alias: pop00008 tex.type: [object Object]
Keywords: Celestial mechanics; Methods: data analysis; Stars: individual: KIC 4349452; Stars: individual: KIC 5792202; Stars: individual: KIC 6949607; Stars: individual: KIC 9757613; dept.phy; peer-reviewed

KEPLER-21b: A 1.6 REarth planet transiting the bright oscillating F subgiant star HD179070 - Howell, Steve B.; Rowe, Jason F.; Bryson, Stephen T.; Quinn, Samuel N.; Marcy, Geoffrey W.; Isaacson, Howard; Ciardi, David R.; Chaplin, William J.; Metcalfe, Travis S.; Monteiro, Mário J. P. F. G.; Appourchaux, Thierry; Basu, Sarbani; et al. (The Astrophysical Journal, 2012)
We present Kepler observations of the bright (V = 8.3), oscillating star HD179070. The observations show transit-like events which reveal that the star is orbited every 2.8days by a small, 1.6 R Earth object. Seismic studies of HD179070 using short cadence Kepler observations show that HD179070 has a frequency-power spectrum consistent with solar-like oscillations that are acoustic p-modes. Asteroseismic analysis provides robust values for the mass and radius of HD179070, 1.34 ± 0.06 M ⊙ and 1.86 ± 0.04 R ⊙, respectively, as well as yielding an age of 2.84 ± 0.34Gyr for this F5 subgiant. Together with ground-based follow-up observations, analysis of the Kepler light curves and image data, and blend scenario models, we conservatively show at the >99.7% confidence level (3σ) that the transit event is caused by a 1.64 0.04 R Earth exoplanet in a 2.785755 ± 0.000032day orbit. The exoplanet is only 0.04 AU away from the star and our spectroscopic observations provide an upper limit to its mass of ∼10 M Earth (2σ). HD179070 is the brightest exoplanet host star yet discovered by Kepler. © 2012. The American Astronomical Society. All rights reserved.
101 citations (Crossref) [2023-10-31] Citation Key Alias: pop00009 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: activity; stars: individual (HD 179070: KIC 3632418); stars: interiors; stars: late-type; stars: magnetic field; stars: oscillations (including pulsations); techniques: photometric

Positive attitudinal shifts with the physics by inquiry curriculum across multiple implementations - Lindsey, Beth A; Hsu, Leonardo; Sadaghiani, Homeyra R; Taylor, Jack W; Cummings, Karen (Physical Review Special Topics - Physics Education Research, 2012)
Recent publications have documented positive attitudinal shifts on the Colorado Learning Attitudes about Science Survey (CLASS) among students enrolled in courses with an explicit epistemological focus. We now report positive attitudinal shifts in classes using the Physics by Inquiry (PbI) curriculum, which has only an implicit focus on student epistemologies and nature of science issues. These positive shifts have occurred in several different implementations of the curriculum, across multiple institutions and multiple semesters. In many classes, students experienced significant attitudinal shifts in the problem-solving categories of the CLASS, despite the conceptual focus of most PbI courses.
34 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-830-196-840-815 tex.type: [object Object]
Keywords: dept.phy

Kepler-22b: A 2.4 Earth-radius Planet in the Habitable Zone of a Sun-like Star - Borucki, William J.; Koch, David G.; Batalha, Natalie M.; Bryson, Stephen T.; Rowe, Jason F.; Fressin, Francois; Torres, Guillermo; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Gautier, Thomas N.; et al. (The Astrophysical Journal, 2012)
A search of the time-series photometry from NASA's Kepler spacecraft reveals a transiting planet candidate orbiting the 11th magnitude G5 dwarf KIC 10593626 with a period of 290 days. The characteristics of the host star are well constrained by high-resolution spectroscopy combined with an asteroseismic analysis of the Kepler photometry, leading to an estimated mass and radius of 0.970 0.060 M and 0.979 0.020 R. The depth of 492 10 ppm for the three observed transits yields a radius of 2.38 0.13 Re for the planet. The system passes a battery of tests for false positives, including reconnaissance spectroscopy, high-resolution imaging, and centroid motion. A full BLENDER analysis provides further validation of the planet interpretation by showing that contamination of the target by an eclipsing system would rarely mimic the observed shape of the transits. The final validation of the planet is provided by 16 radial velocities (RVs) obtained with the High Resolution Echelle Spectrometer on Keck I over a one-year span. Although the velocities do not lead to a reliable orbit and mass determination, they are able to constrain the mass to a 3σ upper limit of 124 M ⊕, safely in the regime of planetary masses, thus earning the designation Kepler-22b. The radiative equilibrium temperature is 262 K for a planet in Kepler-22b's orbit. Although there is no evidence that Kepler-22b is a rocky planet, it is the first confirmed planet with a measured radius to orbit in the habitable zone of any star other than the Sun. © 2012. The American Astronomical Society. All rights reserved.
186 citations (Crossref) [2023-10-31] Citation Key Alias: pop00003 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: fundamental parameters; stars: individual (Kepler-22; KIC 10593626)

Portable intensity interferometry - Horch, Elliott P; Camarata, Matthew A (Proceedings of SPIE, 2012)
A limitation of the current generation of long baseline optical interferometers is the need to make the light interfere prior to detection. This is unlike the radio regime where signals can be recorded fast enough to use electronics to accomplish the same result. This paper describes a modern optical intensity interferometer based on electronics with picosecond timing resolution. The instrument will allow for portable optical interferometry with much larger baselines than currently possible by using existing large telescopes. With modern electronics, the limiting magnitude of the technique at a 4-m aperture size becomes competitive with some amplitude-based interferometers. The instrumentation will permit a wireless mode of operation with GPS clocking technology, extending the work to extremely large baselines. We discuss the basic observing strategy, a planned observational program at the Lowell Observatory 1.8-m and 1.0-m telescopes, and the science that can realistically be done with this instrumentation. © 2012 SPIE.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/097-846-651-777-744 tex.type: [object Object]
Keywords: Aperture sizes; Binary star; Binary stars; Current generation; Intensity interferometry; Interferometers; Interferometry; Large telescopes; Long base line; Mode of operations; Optical intensities; Optical interferometer; Optical interferometry; Optical telescopes; Picosecond timing; Single photon avalanche diode; Single photon avalanche diodes; Stars; Stellar disks; Stellar radii; Telescopes; dept.phy

The infrared light curve of SN 2011fe in m101 and the distance to m101 - Matheson, Thomas; Joyce, Richard R; Allen, Lori E; Saha, A; Silva, David R; Woodvasey, W M; Adams, Joshua J; Anderson, R E; Beck, Tracy L; Bentz, Misty C; Bershady, Matthew A; Binkert, W S; et al. (The Astrophysical Journal, 2012)
We present near-infrared light curves of supernova (SN) 2011fe in M101, including 34 epochs in H band starting 14days before maximum brightness in the B band. The light curve data were obtained with the WIYN High-Resolution Infrared Camera. When the data are calibrated using templates of other Type Ia SNe, we derive an apparent H-band magnitude at the epoch of B-band maximum of 10.85 ± 0.04. This implies a distance modulus for M101 that ranges from 28.86 to 29.17mag, depending on which absolute calibration for Type Ia SNe is used. © © 2012. The American Astronomical Society. All rights reserved..
61 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/106-877-142-339-654 tex.type: [object Object]
Keywords: dept.phy; galaxies: distances and redshifts; galaxies: individual (M101); supernovae: individual (SN 2011fe)

Speckle Observations of Binary Stars with the Wiyn Telescope. Vii. Measures During 2008-2009 - Horch, Elliott P.; Bahi, Lizzie Anne P.; Gaulin, Joseph R.; Howell, Steve B.; Sherry, William Henry; Gallé, Roberto Baena; van Altena, William F. (The Astronomical Journal, 2011)
Five hundred thirty-one speckle measures of binary stars are reported. These data were taken mainly during the period 2008 June through 2009 October at the WIYN 3.5m Telescope at Kitt Peak and represent the last data set of single-filter speckle observations taken in the WIYN speckle program prior to the use of the current two-channel speckle camera. The astrometric and photometric precision of these observations is consistent with previous papers in this series: we obtain a typical linear measurement uncertainty of approximately 2.5mas, and the magnitude differences reported have typical uncertainties in the range of 0.1-0.14 mag. In combination with measures already in the literature, the data presented here permit the revision of the orbit of A 1634AB (= HIP 76041) and the first determination of visual orbital elements for HDS 1895 (= HIP 65982).
43 citations (Crossref) [2023-10-31] Citation Key Alias: pop00075 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Kepler-18b, c, and d: a system of three planets confirmed by transit timing variations, light curve validation, warm-spitzer photometry, and radial velocity measurements* - Cochran, William D.; Fabrycky, Daniel C.; Torres, Guillermo; Fressin, Francois; Désert, Jean-Michel; Ragozzine, Darin; Sasselov, Dimitar; Fortney, Jonathan J.; Rowe, Jason F.; Brugamyer, Erik; Bryson, Stephen T.; Carter, Joshua A.; et al. (Astrophysical Journal Supplement Series, 2011)
We report the detection of three transiting planets around a Sun-like star, which we designate Kepler-18. The transit signals were detected in photometric data from the Kepler satellite, and were confirmed to arise from planets using a combination of large transit-timing variations (TTVs), radial velocity variations, Warm-Spitzer observations, and statistical analysis of false-positive probabilities. The Kepler-18 star has a mass of 0.97 M ⊙, a radius of 1.1 R ⊙, an effective temperature of 5345K, and an iron abundance of [Fe/H] = +0.19. The planets have orbital periods of approximately 3.5, 7.6, and 14.9 days. The innermost planet "b" is a "super-Earth" with a mass of 6.9 ± 3.4 M ⊕, a radius of 2.00 ± 0.10 R ⊕, and a mean density of 4.9 ± 2.4gcm3. The two outer planets "c" and "d" are both low-density Neptune-mass planets. Kepler-18c has a mass of 17.3 ± 1.9 M ⊕, a radius of 5.49 ± 0.26 R ⊕, and a mean density of 0.59 0.07gcm 3, while Kepler-18d has a mass of 16.4 ± 1.4 M ⊕, a radius of 6.98 ± 0.33 R ⊕ and a mean density of 0.27 ± 0.03gcm3. Kepler-18c and Kepler-18d have orbital periods near a 2:1 mean-motion resonance, leading to large and readily detected TTVs. © 2011. The American Astronomical Society. All rights reserved.
144 citations (Crossref) [2023-10-31] Citation Key Alias: pop00006 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (Kepler-18; KIC 8644288; 2MASS J19521906+4444467); techniques: photometric; techniques: spectroscopic

Origin of 90° domain wall pinning in Pb(Zr0.2Ti0.8)O3 heteroepitaxial thin films - Su, Dong; Meng, Qingping; Vaz, Carlos A. F.; Han, Myung-Geun; Segal, Y.; Walker, Fred; Sawicki, Monica; Broadbridge, Christine; Ahn, Chong H. (Applied Physics Letters, 2011)
We describe a transmission-electron-microscopy study of the ferroelectric domains in an epitaxial Pb(Zr0.2Ti0.8)O3 (PZT) film grown on La0.7Sr0.3MnO3/SrTiO 3(001). We directly observe the pinning of 90 domain walls by pairs of misfit dislocations, respectively, with Burgers vectors a [100] and a [001]. Model calculations based on the elastic theory confirm our finding that, in addition to the depolarization field surrounding the dislocation, the strain field of misfit dislocation-pairs plays the primary role in the formation and pinning of a domains. © 2011 American Institute of Physics.
48 citations (Crossref) [2023-10-31] Citation Key Alias: pop00042 tex.type: [object Object]
Keywords: Depolarization fields; Domain walls; Domain-wall pinning; Elastic theory; Epitaxial growth; Ferroelectric domains; Ferroelectricity; Heteroepitaxial thin films; Heterojunctions; Lanthanum compounds; Lead; Manganese oxide; Model calculations; PZT; Strain fields; Zirconium; dept.phy

Domain pinning and valence state switching in Pb(Zr0.2Ti0.8)O3/La0.8Sr0.2MnO3 heterostructures - Su, Dong; Vaz, Carlos A. F.; Segal, Y.; Walker, Fred; Ahn, Chong H.; Han, M-G; Sawicki, Monica; Broadbridge, Christine (Microscopy and Microanalysis, 2011)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00142 tex.type: [object Object]
Keywords: dept.phy

Observations of binary stars with the differential speckle survey instrument. III. measures below the diffraction limit of the WIYN telescope - Horch, Elliott P.; van Altena, William F.; Howell, Steve B.; Sherry, William Henry; Ciardi, David R. (The Astronomical Journal, 2011)
In this paper, we study the ability of CCD- and electron-multiplying-CCD- based speckle imaging to obtain reliable astrometry and photometry of binary stars below the diffraction limit of the WIYN 3.5 m Telescope. We present a total of 120 measures of binary stars, 75 of which are below the diffraction limit. The measures are divided into two groups that have different measurement accuracy and precision. The first group is composed of standard speckle observations, that is, a sequence of speckle images taken in a single filter, while the second group consists of paired observations where the two observations are taken on the same observing run and in different filters. The more recent paired observations were taken simultaneously with the Differential Speckle Survey Instrument, which is a two-channel speckle imaging system. In comparing our results to the ephemeris positions of binaries with known orbits, we find that paired observations provide the opportunity to identify cases of systematic error in separation below the diffraction limit and after removing these from consideration, we obtain a linear measurement uncertainty of 3-4 mas. However, if observations are unpaired or if two observations taken in the same filter are paired, it becomes harder to identify cases of systematic error, presumably because the largest source of this error is residual atmospheric dispersion, which is color dependent. When observations are unpaired, we find that it is unwise to report separations below approximately 20 mas, as these are most susceptible to this effect. Using the final results obtained, we are able to update two older orbits in the literature and present preliminary orbits for three systems that were discovered by Hipparcos. © 2011. The American Astronomical Society. All rights reserved..
28 citations (Crossref) [2023-10-31] Citation Key Alias: pop00076 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Observations of Binary Stars with the Differential Speckle Survey Instrument. II. Hipparcos Stars Observed in 2010 January and June - Horch, Elliott P.; Gomez, Shamilia C.; Sherry, William Henry; Howell, Steve B.; Ciardi, David R.; Anderson, Lisa M.; van Altena, William F. (The Astronomical Journal, 2011)
The results of 497 speckle observations of Hipparcos stars and selected other targets are presented. Of these, 367 were resolved into components and 130 were unresolved. The data were obtained using the Differential Speckle Survey Instrument at the WIYN 3.5 m Telescope. (The WIYN Observatory is a joint facility of the University of Wisconsin-Madison, Indiana University, YaleUniversity, and theNational Optical AstronomyObservatories.) Since the first paper in this series, the instrument has been upgraded so that it now uses two electron-multiplying CCD cameras. The measurement precision obtained when comparing to ephemeris positions of binaries with very well known orbits is approximately 1-2 mas in separation and better than 0.̊ 6 in position angle. Differential photometry is found to be in very good agreement with Hipparcos measures in cases where the comparison is most relevant. We derive preliminary orbits for two systems. © 2011. The American Astronomical Society.
88 citations (Crossref) [2023-10-31] Citation Key Alias: pop00029 tex.type: [object Object]
Keywords: Binaries: Visual; Techniques: High angular resolution; Techniques: Interferometric; Techniques: Photometric; dept.phy; peer-reviewed

Team-based interdisciplinary materials research using image processing - Garofano, Jacquelynn; Sadowski, Thomas; DaPonte, John S.; Broadbridge, Christine (MRS Proceedings, 2011)
There is an acute and well-documented need for image processing of microscopy data in materials science regarding, for example, the characterization of the structure/property relationship of a given materials system. In our work, image processing has been used as a framework for conducting interdisciplinary team-based research that effectively integrates programs within the Center for Research on Interface Structures and Phenomena (CRISP) Materials Research Science and Engineering Center (MRSEC), e.g. research experiences for undergraduates (REU), teachers (RET) and high school fellowships. This research resulted from a five-year long collaboration between CRISP and the Physics and Computer Science Departments at Southern Connecticut State University (SCSU). This paper will focus on the implementation of team-based research experiences as a vehicle for interdisciplinary science and education. Representative results of several of the studies are presented and discussed. © 2011 Materials Research Society.
1 citations (Crossref) [2023-10-31] Citation Key Alias: pop00325 tex.type: [object Object]
Keywords: Characterization; Engineering research; High school; Image processing; Interface structures; Interfaces (materials); Materials research; Materials systems; Research experience; Science and engineering; dept.phy

Characteristics of kepler planetary candidates based on the first data set - Borucki, William J.; Koch, David G.; Basri, Gibor; Batalha, Natalie M.; Boss, Alan P.; Brown, Timothy M.; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Dunham, Edward W.; Dupree, Andrea K.; et al. (The Astrophysical Journal, 2011)
In the spring of 2009, the Kepler Mission commenced high-precision photometry on nearly 156,000 stars to determine the frequency and characteristics of small exoplanets, conduct a guest observer program, and obtain asteroseismic data on a wide variety of stars. On 2010 June 15, the Kepler Mission released most of the data from the first quarter of observations. At the time of this data release, 705 stars from this first data set have exoplanet candidates with sizes from as small as that of Earth to larger than that of Jupiter. Here we give the identity and characteristics of 305 released stars with planetary candidates. Data for the remaining 400 stars with planetary candidates will be released in 2011 February. More than half the candidates on the released list have radii less than half that of Jupiter. Five candidates are present in and near the habitable zone; two near super-Earth size, and three bracketing the size of Jupiter. The released stars also include five possible multi-planet systems. One of these has two Neptune-size (2.3 and 2.5 Earth radius) candidates with near-resonant periods. © 2011. The American Astronomical Society.
282 citations (Crossref) [2023-10-31] Citation Key Alias: pop00003 tex.type: [object Object]
Keywords: Planets and satellites: detection; Surveys; dept.phy

Characteristics of planetary candidates observed by Kepler II : Analysis of the first four months of data - Borucki, William J.; Koch, David G.; Basri, Gibor; Batalha, Natalie M.; Brown, Timothy M.; Bryson, Stephen T.; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Dunham, Edward W.; Gautier, Thomas N.; et al. (The Astrophysical Journal, 2011)
On 2011 February 1 the Kepler mission released data for 156,453 stars observed from the beginning of the science observations on 2009 May 2 through September 16. There are 1235 planetary candidates with transit-like signatures detected in this period. These are associated with 997 host stars. Distributions of the characteristics of the planetary candidates are separated into five class sizes: 68 candidates of approximately Earth-size (Rp < 1.25 R⊕), 288 super-Earth-size (1.25 R⊕ ≤ R p < 2 R⊕), 662 Neptune-size (2 R ⊕ ≤ Rp < 6 R⊕), 165 Jupiter-size (6 R⊕ ≤ Rp < 15 R ⊕), and 19 up to twice the size of Jupiter (15 R ⊕ ≤ Rp < 22 R⊕). In the temperature range appropriate for the habitable zone, 54 candidates are found with sizes ranging from Earth-size to larger than that of Jupiter. Six are less than twice the size of the Earth. Over 74% of the planetary candidates are smaller than Neptune. The observed number versus size distribution of planetary candidates increases to a peak at two to three times the Earth-size and then declines inversely proportional to the area of the candidate. Our current best estimates of the intrinsic frequencies of planetary candidates, after correcting for geometric and sensitivity biases, are 5% for Earth-size candidates, 8% for super-Earth-size candidates, 18% for Neptune-size candidates, 2% for Jupiter-size candidates, and 0.1% for very large candidates; a total of 0.34 candidates per star. Multi-candidate, transiting systems are frequent; 17% of the host stars have multi-candidate systems, and 34% of all the candidates are part of multi-candidate systems. © 2011. The American Astronomical Society. All rights reserved.
799 citations (Crossref) [2023-10-31] Citation Key Alias: pop00002 tex.type: [object Object]
Keywords: dept.phy; planetary systems; planets and satellites: detection; stars: statistics; surveys

Kepler-14b: A Massive Hot Jupiter Transiting an F Star in a Close Visual Binary - Buchhave, Lars A; Latham, David W; Carter, Joshua A; Desert, J M; Torres, Guillermo; Adams, Elisabeth R; Bryson, Stephen T; Charbonneau, David; Ciardi, David R; Kulesa, Craig; Dupree, Andrea K; Fischer, Debra A; et al. (Astrophysical Journal Supplement Series, 2011)
We present the discovery of a hot Jupiter transiting an F star in a close visual (03 sky projected angular separation) binary system. The dilution of the host star's light by the nearly equalmagnitude stellar companion (∼0.5mag fainter) significantly affects the derived planetary parameters, and if left uncorrected, leads to an underestimate of the radius and mass of the planet by 10% and 60%, respectively. Other published exoplanets, which have not been observed with high-resolution imaging, could similarly have unresolved stellar companions and thus have incorrectly derived planetary parameters. Kepler-14b (KOI-98) has a period of P = 6.790 days and, correcting for the dilution, has a mass of Mp = 8.40+0.35 -0.34 M J and a radius of Rp = 1.136+0.073-0.054 R J, yielding a mean density of ρp = 7.1 ± 1.1 g cm-3. © 2011. The American Astronomical Society. All rights reserved.
52 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/073-747-569-084-362 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (Kepler-14b; KIC 10264660; 2MASS J19105011+4719589); techniques: photometric; techniques: spectroscopic

Kepler-15b: A hot jupiter enriched in heavy elements and the first kepler mission planet confirmed with the hobby-eberly telescope - Endl, Michael; Macqueen, Phillip J; Cochran, William D; Brugamyer, Erik; Buchhave, Lars A; Rowe, Jason F; Lucas, P W; Isaacson, Howard; Bryson, Steve; Howell, Steve B; Fortney, Jonathan J; Hansen, Terese; et al. (Astrophysical Journal Supplement Series, 2011)
We report the discovery of Kepler-15b (KOI-128), a new transiting exoplanet detected by NASA's Kepler mission. The transit signal with a period of 4.94days was detected in the quarter 1 (Q1) Kepler photometry. For the first time, we have used the High Resolution Spectrograph (HRS) at the Hobby-Eberly Telescope (HET) to determine the mass of a Kepler planet via precise radial velocity (RV) measurements. The 24 HET/HRS RVs and 6 additional measurements from the Fibre-fed chelle Spectrograph spectrograph at the Nordic Optical Telescope reveal a Doppler signal with the same period and phase as the transit ephemeris. We used one HET/HRS spectrum of Kepler-15 taken without the iodine cell to determine accurate stellar parameters. The host star is a metal-rich ([Fe/H]= 0.36 ± 0.07) G-type main-sequence star with Teff = 5515 ± 124 K. The semi-amplitude K of the RV orbit is 78.7+8.5 -9.5ms-1, which yields a planet mass of 0.66 ± 0.1 M Jup. The planet has a radius of 0.96 ± 0.06R Jup and a mean bulk density of 0.9 ± 0.2 gcm-3. The radius of Kepler-15b is smaller than the majority of transiting planets with similar mass and irradiation level. This suggests that the planet is more enriched in heavy elements than most other transiting giant planets. For Kepler-15b we estimate a heavy element mass of 30-40 M ⊕. © 2011. The American Astronomical Society. All rights reserved.
23 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-839-775-387-264 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (Kepler-15; KOI-128; KIC 11359879; 2MASS J19444814+4908244); techniques: image processing; techniques: photometric; techniques: radial Velocities; techniques: spectroscopic

The WIYN Speckle Survey: Toward the Thin and Thick Disk Binary Populations - Horch, Elliott P.; van Altena, William F.; Docobo, J. A.; Tamazian, V. S.; Balega, Y. Y. (International Workshop on Double and Multiple Stars: Dynamics, Physics, and Instrumentation, 2011)
The WIYN Observatory speckle program has been in operation since 1997, taking data mainly with a large-format, low-noise CCD detector. However, new instrumentation, first used in 2008, has created the possibility to use two detectors simultaneously, collecting light in two different filters. The program also now has access to two electron-multiplying CCD cameras, which dramatically improve the limiting magnitude of the diffraction-limited imaging capabilities. The application of this instrumentation to an ongoing survey of the Hipparcos Double Stars and other projects is discussed. © 2011 American Institute of Physics.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/013-059-287-895-92X, pop00174 tex.number: [object Object]
Keywords: binaries: visual; dept.phy; stars: stellar populations; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Speckle camera observations for the NASA kepler mission follow-up program - Howell, Steve B; Everett, Mark E; Sherry, William Henry; Horch, Elliott P; Ciardi, David R (The Astronomical Journal, 2011)
We present the first results from a speckle imaging survey of stars classified as candidate exoplanet host stars discovered by the Kepler mission. We use speckle imaging to search for faint companions or closely aligned background stars that could contribute flux to the Kepler light curves of their brighter neighbors. Background stars are expected to contribute significantly to the pool of false positive candidate transiting exoplanets discovered by the Kepler mission, especially in the case that the faint neighbors are eclipsing binary stars. Here, we describe our Kepler follow-up observing program, the speckle imaging camera used, our data reduction, and astrometric and photometric performance. Kepler stars range from R = 8 to 16 and our observations attempt to provide background non-detection limits 5-6mag fainter and binary separations of ∼0.05-2.0 arcsec. We present data describing the relative brightness, separation, and position angles for secondary sources, as well as relative plate limits for non-detection of faint nearby stars around each of 156 target stars. Faint neighbors were found near 10 of the stars. © 2011. The American Astronomical Society. All rights reserved.
247 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/073-270-251-734-729 tex.type: [object Object]
Keywords: dept.phy; instrumentation: high angular resolution; peer-reviewed; planets and satellites: general; techniques: photometric

The atomic structure and polarization of strained SrTiO3/Si - Kumah, Divine; Reiner, James W.; Segal, Y.; Kolpak, Alexie M.; Zhang, Zhizhi; Su, Dong; Zhu, Yimei; Sawicki, Monica; Broadbridge, Christine; Ahn, Chong H.; Walker, Fred (Applied Physics Letters, 2010)
For thin film devices based on coupling ferroelectric polarization to charge carriers in semiconductors, the role of the interface is critical. To elucidate this role, we use synchrotron x-ray diffraction to determine the interface structure of epitaxial SrTiO3 grown on the (001) surface of Si. The average displacement of the O octahedral sublattice relative to the Sr sublattice determines the film polarization and is measured to be about 0.05 nm toward the Si, with Ti off-center displacements 0.009 nm away from the substrate. Measurements of films with different boundary conditions on the top of the SrTiO3 show that the polarization at the SrTiO3 /Si interface is dominated by oxide-Si chemical interactions. © 2010 American Institute of Physics.
25 citations (Crossref) [2023-10-31] Citation Key Alias: pop00073 tex.type: [object Object]
Keywords: Atomic structure; Chemical interactions; Crystal atomic structure; Different boundary condition; Ferroelectric polarization; Interface structures; Polarization; Semiconducting silicon compounds; Silicon; SrTiO; Strontium alloys; Sub-lattices; Synchrotron x ray diffraction; Thin film devices; X ray diffraction; dept.phy

Kepler observations of three pre-launch exoplanet candidates: discovery of two eclipsing binaries and a new exoplanet - Howell, Steve Bruce; Rowe, Jason F.; Sherry, William; von Braun, Kaspar; Ciardi, David R.; Bryson, Stephen T.; Feldmeier, John J.; Horch, Elliott P.; van Belle, Gerard T. (The Astrophysical Journal, 2010)
Three transiting exoplanet candidate stars were discovered in a ground-based photometric survey prior to the launch of NASA's Kepler mission. Kepler observations of them were obtained during Quarter 1 of the Kepler mission. All three stars are faint by radial velocity follow-up standards, so we have examined these candidates with regard to eliminating false positives and providing high confidence exoplanet selection.We present a first attempt to exclude false positives for this set of faint stars without high-resolution radial velocity analysis. This method of exoplanet confirmation will form a large part of the Kepler mission follow-up for Jupiter-sized exoplanet candidates orbiting faint stars. Using the Kepler light curves and pixel data, as well as medium-resolution reconnaissance spectroscopy and speckle imaging, we find that two of our candidates are binary stars. One consists of a late-F star with an early M companion, while the other is a K0 star plus a late M-dwarf/brown dwarf in a 19 day elliptical orbit. The third candidate (BOKS-1) is an r = 15 G8V star hosting a newly discovered exoplanet with a radius of 1.12 RJupiter in a 3.9 day orbit. © 2010 The American Astronomical Society. All rights reserved.
12 citations (Crossref) [2023-10-31] Citation Key Alias: pop00072 tex.type: [object Object]
Keywords: Binaries: eclipsing; Brown dwarfs; Planetary systems; dept.phy

Visualizing bone porosities using a tabletop scanning electron microscope - Krishnamoorthy, D.; DaPonte, J.; Broadbridge, C. C.; Daniel, D.; Alter, L. (Visual Information Processing XIX, 2010)
Pores are naturally occurring entities in bone. Changes in pore size and number are often associated with diseases such as Osteoporosis and even microgravity during spaceflight. Studying bone perforations may yield great insight into bone's material properties, including bone density and may contribute to identifying therapies to halt or potentially reverse bone loss. Current technologies used in this field include nuclear magnetic resonance, micro-computed tomography and the field emission scanning electron microscope (FE-SEM)^ 2, 5. However, limitations in each method limit further advancement. The objective of this study was to assess the effectiveness of using a new generation of analytical instruments, the TM-1000 tabletop, SEM with back-scatter electron (BSE) detector, to analyze cortical bone porosities. Hind limb unloaded and age-based controlled mouse femurs were extracted and tested in vitro for changes in pores on the periosteal surface. An important advantage of using the tabletop is the simplified sample preparation that excludes extra coatings, dehydration and fixation steps that are otherwise required for conventional SEM. For quantitative data, pores were treated as particles in order to use an analyze particles feature in the NIH ImageJ software. Several image-processing techniques for background smoothing, thresholding and filtering were employed to produce a binary image suitable for particle analysis. It was hypothesized that the unloaded bones would show an increase in pore area, as the lack of mechanical loading would affect bone-remodeling processes taking place in and around pores. Preliminary results suggest only a slight different in frequency but not in size of pores between unloaded and control femurs.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/004-681-726-544-835, pop00157 tex.type: [object Object]
Keywords: Bone; Computerized tomography; Data processing; Electron microscopes; Electrons; Intracortical; Mammals; Particle analysis; Periosteal; Resonance; Scanning; Scanning electron microscope; Scanning electron microscopy; Threshold; Tomography; dept.phy

Kepler Planet-Detection Mission: Introduction and First Results. - Borucki, William; Koch, David; Basri, Gibor; Batalha, Natalie; Brown, Timothy; Caldwell, Douglas; Caldwell, John; Christensen-Dalsgaard, Jorgen; Cochran, William; DeVore, Edna; Dunham, Edward; Dupree, Andrea; et al. (Science, 2010)
The Kepler mission was designed to determine the frequency of Earth-sized planets in and near the habitable zone of Sun-like stars. The habitable zone is the region where planetary temperatures are suitable for water to exist on a planet's surface. During the first 6 weeks of observations, Kepler monitored 156,000 stars, and five new exoplanets with sizes between 0.37 and 1.6 Jupiter radii and orbital periods from 3.2 to 4.9 days were discovered. The density of the Neptune-sized Kepler-4b is similar to that of Neptune and GJ 436b, even though the irradiation level is 800,000 times higher. Kepler-7b is one of the lowest-density planets (∼0.17 gram per cubic centimeter) yet detected. Kepler-5b, -6b, and -8b confirm the existence of planets with densities lower than those predicted for gas giant planets.
2612 citations (Crossref) [2023-10-31] Place: Copyright (C) 2010 by the American Association for the Advancement of Science
Keywords: Jupiter; article; astronomy; astrophysics; density; dept.phy; gas; irradiation; planetary atmosphere; planetary surface; priority journal; spacecraft; sun; temperature; water

Beta-Test Data On An Assessment Of Textbook Problem Solving Ability: An Argument For Right∕Wrong Grading? - Cummings, Karen; Marx, Jeffrey D.; Singh, Chandralekha; Sabella, Mel; Rebello, Sanjay (2010 Physics Education Research Conference, 2010)
We have developed an assessment of students' ability to solve standard textbook style problems and are currently engaged in the validation and revision process. The assessment covers the topics of force and motion, conservation of momentum and conservation of energy at a level consistent with most calculus-based, introductory physics courses. This tool is discussed in more detail in an accompanying paper by Marx and Cummings. [1] Here we present preliminary beta-test data collected at four schools during the 2009/2010 academic year. Data include both pre- and post-instruction results for introductory physics courses as well as results for physics majors in later years. In addition, we present evidence that right/wrong grading may well be a perfectly acceptable grading procedure for a course-level assessment of this type. © 2010 American Institute of Physics.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/136-768-475-813-84X, pop00255 tex.number: [object Object]
Keywords: Problem solving in physics; assessment; dept.phy; introductory physics; right/wrong grading

Bridging the length scales between lithographic patterning and self assembly mechanisms in fabrication of semiconductor nanostructure arrays - Hull, Robert; Floro, J A; Gherasimova, M; Graham, J; Gray, J L; Portavoce, A; Ross, Frances M; Thorp, J (Journal of Physics: Conference Series, 2010)
We employ focused ion beam patterning of single crystal Si(100) surfaces to template the assembly of Ge(Si) nanostructure arrays. The evolution and final structures of the templated arrays are determined by combinations of transmission electron, low energy electron microscope, focused ion beam and scanning probe microscopies. It is shown how the positions of individual nanostructures may be controlled to the order of 10 nm. However, to achieve controlled spacings between elements that are in the 10 nm range requires careful matching of the characteristic lengths scales of self assembly mechanisms to the length scales of the external lithographic "forcing functions". © 2010 IOP Publishing Ltd.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/048-366-191-463-372
Keywords: Assembly mechanism; Characteristic length; Electrons; Focused ion beams; Germanium; Ion beams; Lithographic patterning; Low energy electron microscopes; Nanostructure arrays; Nanostructures; Self assembly; Semiconductor nanostructures; Silicon wafers; Single crystal surfaces; Single crystals; Single-crystal Si; Transmission electron; dept.phy

Development of a Survey Instrument to Gauge Students’ Problem-Solving Abilities - Marx, Jeffrey; Cummings, Karen; Singh, Chandralekha; Sabella, Mel; Rebello, Sanjay (2010 Physics Education Research Conference, 2010)
In this paper we discuss the early stages of development of a survey instrument to assess students' problem-solving abilities in a first-term, undergraduate, calculus-based physics course. Specifically, we present our motivation for the development of such a survey, details of a preliminary version of the survey, and some sample items. © 2010 American Institute of Physics.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/150-977-856-086-461, pop00163 tex.number: [object Object]
Keywords: Problem-solving; assessment; dept.phy; introductory physics

Comparison of the ability of quantitative parameters to differentiate surface texture of Atomic Force Microscope (AFM) images - Niedzielski, Bethany; Broadbridge, Christine; Daponte, John S; Gherasimova, Maria (Machine Vision Applications, 2010)
The purpose of this study was to compare the ability of several texture analysis parameters to differentiate textured samples from a smooth control on images obtained with an Atomic Force Microscope (AFM). Surface roughness plays a major role in the realm of material science, especially in integrated electronic devices. As these devices become smaller and smaller, new materials with better electrical properties are needed. New materials with smoother surface morphology have been found to have superior electrical properties than their rougher counterparts. Therefore, in many cases surface texture is indicative of the electrical properties that material will have. Physical vapor deposition techniques such as Jet Vapor Deposition and Molecular Beam Epitaxy are being utilized to synthesize these materials as they have been found to create pure and uniform thin layers. For the current study, growth parameters were varied to produce a spectrum of textured samples. The focus of this study was the image processing techniques associated with quantifying surface texture. As a result of the limited sample size, there was no attempt to draw conclusions about specimen processing methods. The samples were imaged using an AFM in tapping mode. In the process of collecting images, it was discovered that roughness data was much better depicted in the microscope's "height" mode as opposed to "equal area" mode. The AFM quantified the surface texture of each image by returning RMS roughness and the first order histogram statistics of mean roughness, standard deviation, skewness, and kurtosis. Color images from the AFM were then processed on an off line computer running NIH ImageJ with an image texture plug in. This plug in produced another set of first order statistics computed from each images' histogram as well as second order statistics computed from each images' cooccurrence matrix. The second order statistics, which were originally proposed by Haralick, include contrast, angular second moment, correlation, inverse difference moment, and entropy. These features were computed in the 0°, 45°, 90°, and 135° directions. The findings of this study propose that the best combination of quantitative texture parameters is standard deviation, 0° inverse difference moment, and 0° entropy, all of which are obtained from the NIH ImageJ texture plug in. © 2010 Copyright SPIE - The International Society for Optical Engineering.
1 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: AFM; Angular second moment; Atomic force microscopes; Atomic force microscopy; Cluster analysis; Co-occurrence-matrix; Color images; Computer vision; Crystal growth; Deposition; Electric properties; Electrical property; First order; First-order statistics; Graphic methods; Growth parameters; Histogram statistics; Image processing technique; Image texture; Imaging systems; Integrated electronics; Inverse differences; Jet vapor depositions; Material science; Materials; Mean roughness; Microscopes; Molecular beam epitaxy; Molecular beams; New material; Photoresists; Physical vapor deposition; Plug-ins; Processing; Processing method; Quantitative parameters; RMS roughness; Regression analysis; Sample sizes; Second order statistics; Smooth control; Standard deviation; Statistics; Surface morphology; Surface roughness; Surface textures; Surfaces; Tapping modes; Texture analysis; Textures; Thin layers; dept.phy

Valence electron energy-loss spectroscopy of ultrathin SrTiO3 films grown on silicon (100) single crystal - Su, Dong; Yang, Bo; Jiang, Nan; Sawicki, Monica; Broadbridge, Christine; Couillard, M; Reiner, James W; Walker, Fred; Ahn, C H; Zhu, Yimei (Applied Physics Letters, 2010)
Valence electron energy-loss spectroscopy is used to investigate the plasmon excitations of ultrathin SrTiO3 sandwiched between amorphous Si and crystalline Si. Two plasmon excitations were observed, one at 15.8 eV and the other at 28.7 eV. Our calculations, based on dielectric-function theory, suggest that the former peak originates from the coupling of the Si layers and is related to the geometry of the structure, and the latter peak results from the SrTiO3 bulk plasmon after a redshift. Our findings demonstrate the value of valence electron energy-loss spectroscopy in detecting a local change in the effective electron mass. © 2010 American Institute of Physics.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-562-101-735-184 tex.type: [object Object]
Keywords: Amorphous Si; Amorphous silicon; Crystalline Si; Dissociation; Electron energy loss spectroscopy; Electron scattering; Electrons; Function theory; Plasmon excitations; Plasmons; Red shift; Si layer; Silicon (100); Silicon wafers; Single crystals; SrTiO; Strontium alloys; Ultra-thin; Valence electron energy-loss spectroscopies; dept.phy

Complex oxide interfaces: determination of electronic structure of Oxide–Oxide interfaces by photoemission spectroscopy (adv. mater. 26–27/2010) - Wang, Huiqiong; Altman, Eric I; Broadbridge, Christine; Zhu, Yimei; Henrich, Victor E (Advanced Materials, 2010)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/162-004-174-277-863 tex.type: [object Object]
Keywords: dept.phy

Determination of electronic structure of Oxide–Oxide interfaces by photoemission spectroscopy - Wang, Huiqiong; Altman, Eric I; Broadbridge, Christine; Zhu, Yimei; Henrich, Victor E (Advanced Materials, 2010)
A method has been developed to use the finite escape depth of the photoelectrons emitted in ultraviolet photoemission spectroscopy (UPS) to determine the electronic density-of-states at the interface between two dissimilar metal oxides. Ultrathin films of one oxide are grown heteroepitaxially, one monolayer at a time, on a single-crystal substrate of the other oxide, and UPS spectra are taken after each complete monolayer. By comparing experimental UPS spectra with calculated spectra based on specific models of the interfacial structure, the interfacial density-of-states can be extracted. The two oxide systems studied here are NiO-Fe 3O 4 and CoO-Fe 3O 4. The former system is found to have an atomically abrupt interface, with no significant density of interface states. For CoO, however, an interfacial electronic spectrum, different from that of either the substrate or the overlayer, is found. The spatial extent and possible origin of those interfacial states is discussed. © 2010 WILEY-VCH Verlag GmbH &. Co. KGaA, Weinheim.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/063-294-835-347-179 tex.type: [object Object]
Keywords: Cobalt; Cobalt compounds; Density of interface state; Dissimilar metals; Electron energy levels; Electronic density; Electronic spectrum; Electronic structure; Emission spectroscopy; Escape depth; Ferumoxytol; Interfacial density; Interfacial state; Interfacial structures; Luminescence of organic solids; Models; Molecular; Monolayers; Nickel; Oxide films; Oxide systems; Oxide-oxide interfaces; Oxides; Photoelectron Spectroscopy; Photoelectron spectroscopy; Photoemission; Photoemission spectroscopy; Single-crystal substrates; Smelting; Spatial extent; UPS spectra; Ultrathin films; Ultraviolet photoemission spectroscopy; X ray photoelectron spectroscopy; article; chemical structure; chemistry; cobalt; cobalt oxide; dept.phy; ferumoxytol; nickel; nickel monoxide; oxide

Charge-dependent pair correlations relative to a third particle in p + Au and d + Au collisions at RHIC - STAR Collaboration (Physics Letters B, 2019)
Quark interactions with topological gluon configurations can induce chirality imbalance and local parity violation in quantum chromodynamics. This can lead to electric charge separation along the strong magnetic field in relativistic heavy-ion collisions – the chiral magnetic effect (CME). We report measurements by the STAR collaboration of a CME-sensitive observable in p+Au and d+Au collisions at 200 GeV, where the CME is not expected, using charge-dependent pair correlations relative to a third particle. We observe strong charge-dependent correlations similar to those measured in heavy-ion collisions. This bears important implications for the interpretation of the heavy-ion data.
22 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

A kinematically cold structure of candidate young OB stars toward the anticenter - Casetti-Dinescu, Dana I.; Girard, Terrence M. (The Astrophysical Journal, 2019)
We combine Galaxy Evolution Explorer and Gaia DR2 catalogs to track star formation in the outskirts of our Galaxy. Using photometry, proper motions, and parallaxes we identify a structure of ∼300 OB-type candidates located between 12 and 15 kpc from the Galactic center that are kinematically cold. The structure is located between l =120° and 200°, above the plane up to ∼700 pc and below the plane to ∼1 kpc. The bulk motion is disklike; however, we measure a mean upward vertical motion of 5.7 +0.4 km s-1, and a mean outward radial motion of between 8 and 16 km s-1. The velocity dispersion along the least dispersed of its proper-motion axes (perpendicular to the Galactic disk) is 6.0 +0.3 km s-1, confirming the young age of this structure. While spatially encompassing the outer spiral arm of the Galaxy, this structure is not a spiral arm. Its explanation as the Milky Way warp is equally unsatisfactory. The structure's vertical extent, mean kinematics, and asymmetry with respect to the plane indicate that its origin is more akin to a wobble generated by a massive satellite perturbing the Galaxy's disk. The mean stellar ages in this outer structure indicate the event took place some 200 Myr ago. © 2019. The American Astronomical Society. All rights reserved..
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/153-202-988-565-531, pop00133 tex.type: [object Object]
Keywords: dept.phy

TOI-150b and TOI-163b: two transiting hot Jupiters, one eccentric and one inflated, revealed by TESS near and at the edge of the JWST CVZ - Kossakowski, Diana; Espinoza, Néstor; Brahm, Rafael; Jordán, Andrés; Henning, Thomas; Rojas, Felipe; Kürster, Martin; Sarkis, Paula; Schlecker, Martin; Pozuelos, F. J.; Barkaoui, Khalid; Jehin, Emmanuel; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
We present the discovery of TYC9191-519-1b (TOI-150b, TIC 271893367) and HD271181b (TOI-163b, TIC 179317684), two hot Jupiters initially detected using 30-min cadence Transiting Exoplanet Survey Satellite (TESS) photometry from Sector 1 and thoroughly characterized through follow-up photometry (CHAT, Hazelwood, LCO/CTIO, El Sauce, TRAPPIST-S), high-resolution spectroscopy (FEROS, CORALIE), and speckle imaging (Gemini/DSSI), confirming the planetary nature of the two signals. A simultaneous joint fit of photometry and radial velocity using a new fitting package JULIET reveals that TOI-150b is a 1.254 ± 0.016 RJ, massive (2.61+−001912 MJ) hot Jupiter in a 5.857-d orbit, while TOI-163b is an inflated (RP = 1.478+−00022029 RJ, MP = 1.219 ± 0.11 MJ) hot Jupiter on a P = 4.231-d orbit; both planets orbit F-type stars. A particularly interesting result is that TOI-150b shows an eccentric orbit (e = 0.262+−00045037), which is quite uncommon among hot Jupiters. We estimate that this is consistent, however, with the circularization time-scale, which is slightly larger than the age of the system. These two hot Jupiters are both prime candidates for further characterization – in particular, both are excellent candidates for determining spin-orbit alignments via the Rossiter–McLaughlin (RM) effect and for characterizing atmospheric thermal structures using secondary eclipse observations considering they are both located closely to the James Webb Space Telescope (JWST) Continuous Viewing Zone (CVZ). © 2018 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society.
15 citations (Crossref) [2023-10-31] Citation Key Alias: pop00004 tex.type: [object Object]
Keywords: Planets and satellites: detection; Stars: individual: HD271181; Stars: individual: TIC 179317684; Stars: individual: TIC 271893367; Stars: individual: TYC9191-519-1; Techniques: photometric; dept.phy; peer-reviewed

High-resolution imaging transit photometry of Kepler-13AB - Howell, Steve B.; Scott, Nicholas J.; Matson, Rachel A.; Horch, Elliott P.; Stephens, Andrew (The Astronomical Journal, 2019)
Using the high-resolution imaging instrument, 'Alopeke, at the Gemini-N telescope, we obtained simultaneous two-channel time-series observations of the binary exoplanet host star Kepler13-AB. Our optical observations were obtained during a transit event of the exoplanet Kepler-13b and light curves were produced using both speckle interferometric and aperture photometry techniques. Both techniques confirm that the transiting object orbits the star Kepler-13A while different transit depths are seen across the optical wavelength range, being ∼2 times deeper in the blue. These measurements, as well as mass determinations in the literature, are consistent with Kepler-13b being a highly irradiated gas giant with a bloated atmosphere. Our observations highlight the ability of high-resolution speckle imaging to not only assess binarity in exoplanet host stars but robustly determine which of the stars the transiting object actually orbits. © 2019. The American Astronomical Society. All rights reserved.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/165-359-450-283-875, pop00155 tex.type: [object Object]
Keywords: binaries: close; dept.phy; galaxies: photometry; instrumentation: high angular resolution; peer-reviewed; planetary systems; techniques: image processing

Collision-energy dependence of second-order off-diagonal and diagonal cumulants of net-charge, net-proton, and net-kaon multiplicity distributions in Au + Au collisions - STAR Collaboration (Physical Review C, 2019)
We report the first measurements of a complete second-order cumulant matrix of net-charge, net-proton, and net-kaon multiplicity distributions for the first phase of the beam energy scan program at the Relativistic Heavy Ion Collider. This includes the centrality and, for the first time, the pseudorapidity window dependence of both diagonal and off-diagonal cumulants in Au+Au collisions at √sNN= 7.7–200 GeV. Within the available acceptance of |η|<0.5, the cumulants grow linearly with the pseudorapidity window. Relative to the corresponding measurements in peripheral collisions, the ratio of off-diagonal over diagonal cumulants in central collisions indicates an excess correlation between net-charge and net-kaon, as well as between net-charge and net-proton. The strength of such excess correlation increases with the collision energy. The correlation between net-proton and net-kaon multiplicity distributions is observed to be negative at √sNN= 200 GeV and change to positive at the lowest collision energy. Model calculations based on nonthermal (UrQMD) and thermal (HRG) production of hadrons cannot explain the data. These measurements will help map the quantum chromodynamics phase diagram, constrain hadron resonance gas model calculations and provide new insights on the energy dependence of baryon-strangeness correlations.
28 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Speckle Interferometry at SOAR in 2018 - Tokovinin, Andrei; Mason, Brian D.; Mendez, Rene A.; Horch, Elliott P.; Briceño, Cesar (The Astronomical Journal, 2019)
The results of speckle interferometric observations at the 4.1 m Southern Astrophysical Research Telescope (SOAR) in 2018 are given, totaling 3097 measurements of 2427 resolved pairs with separations from 11 mas to 5.″9 (median 0.″15, magnitude difference up to 7 mag) and nonresolutions of 624 targets. This work continues our long-term speckle program. Its main goal is to monitor orbital motion of close binaries, including members of high-order hierarchies and Hipparcos pairs in the solar neighborhood. Also, pre-main-sequence stars in the Orion OB1 association were surveyed, resolving 26 out of 118 targets. In addition, we report the discovery of 35 new companions among field visual multiples (some of which are likely optical) and first-time resolutions of another 31 pairs. By combining the measurements given here with the published ones, we computed 76 orbits for the first time and updated orbital elements of 34 visual binaries. Their periods range from 0.65 to 1100 yr, and their quality varies from first tentative solutions of grade 5 to accurate elements of grades 1 and 2. Finally, a list of 53 spurious pairs discovered by various techniques and unresolved at SOAR is given. © 2019. The American Astronomical Society. All rights reserved..
28 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/174-863-467-125-303, pop00135 tex.type: [object Object]
Keywords: dept.phy; material: machine-readable tables; peer-reviewed

Optical biopsy identification and grading of gliomas using label-free visible resonance Raman spectroscopy. - Zhou, Yan; Liu, Cheng-Hui; Wu, Binlin; Yu, Xinguang; Cheng, Gangge; Zhu, Ke; Wang, Kai; Zhang, Chunyuan; Zhao, Mingyue; Zong, Rui; Zhang, Lin; Shi, Lingyan; et al. (Journal of biomedical optics, 2019)
Glioma is one of the most refractory types of brain tumor. Accurate tumor boundary identification and complete resection of the tumor are essential for glioma removal during brain surgery. We present a method based on visible resonance Raman (VRR) spectroscopy to identify glioma margins and grades. A set of diagnostic spectral biomarkers features are presented based on tissue composition changes revealed by VRR. The Raman spectra include molecular vibrational fingerprints of carotenoids, tryptophan, amide I/II/III, proteins, and lipids. These basic in situ spectral biomarkers are used to identify the tissue from the interface between brain cancer and normal tissue and to evaluate glioma grades. The VRR spectra are also analyzed using principal component analysis for dimension reduction and feature detection and support vector machine for classification. The cross-validated sensitivity, specificity, and accuracy are found to be 100%, 96.3%, and 99.6% to distinguish glioma tissues from normal brain tissues, respectively. The area under the receiver operating characteristic curve for the classification is about 1.0. The accuracies to distinguish normal, low grade (grades I and II), and high grade (grades III and IV) gliomas are found to be 96.3%, 53.7%, and 84.1% for the three groups, respectively, along with a total accuracy of 75.1%. A set of criteria for differentiating normal human brain tissues from normal control tissues is proposed and used to identify brain cancer margins, yielding a diagnostic sensitivity of 100% and specificity of 71%. Our study demonstrates the potential of VRR as a label-free optical molecular histopathology method used for in situ boundary line judgment for brain surgery in the margins.
42 citations (Crossref) [2023-10-31] Place: United States Zhou, Yan. PLA Air Force Medical Center, Department of Neurosurgery, Beijing, China. Liu, Cheng-Hui. City University of New York, Institute for Ultrafast Spectroscopy and Lasers, Department of Physics, United States. Wu, Binlin. Southern Connecticut State University, CSCU Center for Nanotechnology, Physics Department, New Haven, United States. Yu, Xinguang. PLA General Hospital, Department of Neurosurgery, Beijing, China. Cheng, Gangge. PLA Air Force Medical Center, Department of Neurosurgery, Beijing, China. Zhu, Ke. Chinese Academy of Sciences, Institute of Physics, Beijing, China. Wang, Kai. Jilin University, State Key Laboratory of Superhard Materials, Changchun, China. Zhang, Chunyuan. City University of New York, Institute for Ultrafast Spectroscopy and Lasers, Department of Physics, United States. Zhao, Mingyue. PLA Air Force Medical Center, Department of Neurosurgery, Beijing, China. Zong, Rui. PLA General Hospital, Department of Neurosurgery, Beijing, China. Zhang, Lin. City University of New York, Institute for Ultrafast Spectroscopy and Lasers, Department of Physics, United States. Shi, Lingyan. University of California San Diego, Department of Bioengineering, La Jolla, California, United States. Alfano, Robert R. City University of New York, Institute for Ultrafast Spectroscopy and Lasers, Department of Physics, United States.
Keywords: *Biomarkers; Tumor/me [Metabolism]; *Brain Neoplasms/me [Metabolism]; *Brain Neoplasms/pa [Pathology]; *Glioma/me [Metabolism]; *Glioma/pa [Pathology]; *Spectrum Analysis; Raman/mt [Methods]; Amides; Amino acids; Biomarkers; Biomarkers; Tumor; Biomarkers; Tumor/ch [Chemistry]; Biopsy; Brain; Brain Neoplasms; Brain Neoplasms/su [Surgery]; Brain/me [Metabolism]; Brain/pa [Pathology]; Brain/su [Surgery]; Cancer grades; Cancer margins; Carotenoids; Carotenoids/me [Metabolism]; Diseases; Glioblastoma; Glioblastomas; Glioma; Glioma/su [Surgery]; Gliomas; Grading; Histology; Histopathology; Humans; Label free; Label-free; Lipid Metabolism; Margins of Excision; Neoplasm Grading; Nerve Tissue Proteins; Nerve Tissue Proteins/ch [Chemistry]; Nerve Tissue Proteins/me [Metabolism]; Optical Phenomena; Optical biopsies; Optical biopsy; Pigments; Principal Component Analysis; Principal component analysis; Protein Structure; Secondary; Raman spectrometry; Resonance; Resonance Raman; Spectrum Analysis; Raman; Support Vector Machine; Support vector machines; Surgery; Tryptophan; Tryptophan/me [Metabolism]; Tumors; brain; brain tumor; cancer grading; carotenoid; chemistry; dept.phy; glioma; human; light related phenomena; lipid metabolism; metabolism; nerve protein; pathology; peer-reviewed; principal component analysis; procedures; protein secondary structure; support vector machine; surgical margin; tryptophan; tumor marker

Beam energy dependence of (anti-)deuteron production in Au + Au collisions at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2019)
We report the energy dependence of mid-rapidity (anti-)deuteron production in Au+Au collisions at √sNN=7.7, 11.5, 14.5, 19.6, 27, 39, 62.4, and 200 GeV, measured by the STAR experiment at the BNL Relativistic Heavy Ion Collider. The yield of deuterons is found to be well described by the thermal model. The collision energy, centrality, and transverse momentum dependence of the coalescence parameter B2 are discussed. We find that the values of B2 for antideuterons are systematically lower than those for deuterons, indicating that the correlation volume of antibaryons is larger than that of baryons at √sNN from 19.6 to 39 GeV. In addition, values of B2 are found to vary with collision energy and show a broad minimum around √sNN=20–40 GeV, which might imply a change of the equation of state of the medium in these collisions.
49 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

The DESI fiber view camera system - Baltay, C.; Rabinowitz, D.; Besuner, R.; Casetti, D.; Emmet, W.; Fagrelius, P.; Girard, T.; Heetderks, H.; Lampton, M.; Lathem, A.; Levi, M.; Padmanabhan, N.; et al. (Publications of the Astronomical Society of the Pacific, 2019)
9 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Detection of planetary and stellar companions to neighboring stars via a combination of radial velocity and direct imaging techniques - Kane, Stephen R.; Dalba, Paul A.; Li, Zhexing; Horch, Elliott P.; Hirsch, Lea A.; Horner, Jonathan; Wittenmyer, Robert A.; Howell, Steve B.; Everett, Mark E.; Butler, R. Paul; Tinney, Christopher G.; Carter, Brad D.; et al. (The Astronomical Journal, 2019)
The sensitivities of radial velocity (RV) surveys for exoplanet detection are extending to increasingly longer orbital periods, where companions with periods of several years are now being regularly discovered. Companions with orbital periods that exceed the duration of the survey manifest in the data as an incomplete orbit or linear trend, a feature that can either present as the sole detectable companion to the host star, or as an additional signal overlain on the signatures of previously discovered companion(s). A diagnostic that can confirm or constrain scenarios in which the trend is caused by an unseen stellar rather than planetary companion is the use of high-contrast imaging observations. Here, we present RV data from the Anglo-Australian Planet Search (AAPS) for 20 stars that show evidence of orbiting companions. Of these, six companions have resolved orbits, with three that lie in the planetary regime. Two of these (HD 92987b and HD 221420b) are new discoveries. Follow-up observations using the Differential Speckle Survey Instrument (DSSI) on the Gemini South telescope revealed that 5 of the 20 monitored companions are likely stellar in nature. We use the sensitivity of the AAPS and DSSI data to place constraints on the mass of the companions for the remaining systems. Our analysis shows that a planetary-mass companion provides the most likely self-consistent explanation of the data for many of the remaining systems.
27 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-295-956-723-177, pop00041 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution; techniques: radial velocities

The L 98-59 system: Three transiting, terrestrial-size planets orbiting a nearby M dwarf - Kostov, Veselin B.; Schlieder, Joshua E.; Barclay, Thomas; Quintana, Elisa V.; Colón, Knicole D.; Brande, Jonathan; Collins, Karen A.; Feinstein, Adina D.; Hadden, Samuel; Kane, Stephen R.; Kreidberg, Laura; Kruse, Ethan; et al. (The Astronomical Journal, 2019)
We report the Transiting Exoplanet Survey Satellite (TESS) discovery of three terrestrial-size planets transiting L 98-59 (TOI-175, TIC 307210830)—a bright M dwarf at a distance of 10.6 pc. Using the Gaia-measured distance and broadband photometry, we find that the host star is an M3 dwarf. Combined with the TESS transits from three sectors, the corresponding stellar parameters yield planet radii ranging from 0.8 R ⊕ to 1.6 R ⊕. All three planets have short orbital periods, ranging from 2.25 to 7.45 days with the outer pair just wide of a 2:1 period resonance. Diagnostic tests produced by the TESS Data Validation Report and the vetting package DAVE rule out common false-positive sources. These analyses, along with dedicated follow-up and the multiplicity of the system, lend confidence that the observed signals are caused by planets transiting L 98-59 and are not associated with other sources in the field. The L 98-59 system is interesting for a number of reasons: the host star is bright (V = 11.7 mag, K = 7.1 mag) and the planets are prime targets for further follow-up observations including precision radial-velocity mass measurements and future transit spectroscopy with the James Webb Space Telescope; the near-resonant configuration makes the system a laboratory to study planetary system dynamical evolution; and three planets of relatively similar size in the same system present an opportunity to study terrestrial planets where other variables (age, metallicity, etc.) can be held constant. L 98-59 will be observed in four more TESS sectors, which will provide a wealth of information on the three currently known planets and have the potential to reveal additional planets in the system.
80 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-363-095-757-409, pop00014 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planets and satellites: detection; stars: individual (TIC 307210830; TOI-175); techniques: photometric

Formation and stability of complex metallic phases including quasicrystals explored through combinatorial methods - Wolf, Witor; Kube, Sebastian A.; Sohn, Sungwoo; Xie, Yujun; Cha, Judy J.; Scanley, B. Ellen; Kiminami, Claudio Shyinti; Bolfarini, Claudemiro; Botta, Walter José; Schroers, Jan (Scientific Reports, 2019)
Aluminum-based quasicrystals typically form across narrow composition ranges within binary to quaternary alloys, which makes their fabrication and characterization challenging. Here, we use combinatorial approaches together with fast characterization techniques to study a wide compositional range including known quasicrystal forming compositions. Specifically, we use magnetron co-sputtering to fabricate libraries of ~140 Al-Cu-Fe and ~300 Al-Cu-Fe-Cr alloys. The alloys compositions are measured through automated energy dispersive X-ray spectroscopy. Phase formation and thermal stability are investigated for different thermal processing conditions (as-sputtered and annealed at 400 °C, 520 °C and 600 °C for Al-Cu-Fe libraries; annealed at 600 °C for Al-Cu-Fe-Cr libraries) using automated X-ray diffraction and transmission electron microscopy. In both systems the compositional regions across which the quasicrystalline phase forms are identified. In particular, we demonstrate that the quasicrystalline phase forms across an unusually broad composition range in the Al-Cu-Fe-Cr system. Additionally, some of the considered alloys vitrify during sputtering, which also allows us to study their nucleation behavior. We find that phases with polytetrahedral symmetry, such as the icosahedral quasicrystal and the λ-Al 13 Fe 4 phase, exhibit higher nucleation rates but lower growth rates, as compared to other phases with a lower degree of polytetrahedral order. Altogether, the here used combinatorial approach is powerful to identify compositional regions of quasicrystals. © 2019, The Author(s).
16 citations (Crossref) [2023-10-31] Citation Key Alias: pop00073 tex.type: [object Object]
Keywords: dept.phy

Azimuthal harmonics in small and large collision systems at RHIC top energies - STAR Collaboration (Physical Review Letters, 2019)
The first (vfluc1), second (v2), and third (v3) harmonic coefficients of the azimuthal particle distribution at midrapidity are extracted for charged hadrons and studied as a function of transverse momentum (pT) and mean charged particle multiplicity density ⟨Nch⟩ in U+U (√sNN=193 GeV), Au+Au, Cu+Au, Cu+Cu, d+Au, and p+Au collisions at √sNN=200 GeV with the STAR detector. For the same ⟨Nch⟩, the vfluc1 and v3 coefficients are observed to be independent of the collision system, while v2 exhibits such a scaling only when normalized by the initial-state eccentricity (ϵ2). The data also show that ln(v2/ϵ2) scales linearly with ⟨Nch⟩−1/3. These measurements provide insight into initial-geometry fluctuations and the role of viscous hydrodynamic attenuation on vn from small to large collision systems.
32 citations (Crossref) [2023-10-31] Finch
Keywords: Azimuthal harmonics; Charged hadrons; Charged particle multiplicities; Charged particles; Colliding beam accelerators; Collision systems; Germanium compounds; Gold compounds; Harmonic coefficients; Initial state; Particle distributions; Transverse momenta; dept.phy; peer-reviewed

Collision-energy dependence of pt correlations in Au + Au collisions at energies available at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2019)
We present two-particle pt correlations as a function of event centrality for Au+Au collisions at √sNN=7.7, 11.5, 14.5, 19.6, 27, 39, 62.4, and 200 GeV at the Relativistic Heavy Ion Collider using the STAR detector. These results are compared to previous measurements from CERES at the Super Proton Synchrotron and from ALICE at the Large Hadron Collider. The data are compared with UrQMD model calculations and with a model based on a Boltzmann-Langevin approach incorporating effects from thermalization. The relative dynamical correlations for Au+Au collisions at √sNN=200 GeV show a power-law dependence on the number of participant nucleons and agree with the results for Pb+Pb collisions at √sNN=2.76TeV from ALICE. As the collision energy is lowered from √sNN=200 to 7.7 GeV, the centrality dependence of the relative dynamical correlations departs from the power-law behavior observed at the higher collision energies. In central collisions, the relative dynamical correlations increase with collision energy up to √sNN=200 GeV in contrast to previous measurements that showed little dependence on the collision energy.
16 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Discovery of a compact companion to a nearby star - Kane, Stephen R.; Dalba, Paul A.; Horner, Jonathan; Li, Zhexing; Wittenmyer, Robert A.; Horch, Elliott P.; Howell, Steve B.; Everett, Mark E. (The Astrophysical Journal, 2019)
Radial velocity (RV) searches for exoplanets have surveyed many of the nearest and brightest stars for long-term velocity variations indicative of a companion body. Such surveys often detect high-amplitude velocity signatures of objects that lie outside the planetary mass regime, most commonly those of a low-mass star. Such stellar companions are frequently discarded as false-alarms to the main science goals of the survey, but high-resolution imaging techniques can be employed to either directly detect or place significant constraints on the nature of the companion object. Here, we present the discovery of a compact companion to the nearby star HD 118475. Our Anglo-Australian Telescope RV data allow the extraction of the full Keplerian orbit of the companion, which is found to have a minimum mass of 0.445 M o. Follow-up speckle imaging observations at the predicted time of maximum angular separation rule out a main-sequence star as the source of the RV signature at the 3.3σ significance level, implying that the companion must be a low-luminosity compact object, most likely a white dwarf. We provide an isochrone analysis combined with our data that constrain the possible inclinations of the binary orbit. We discuss the eccentric orbit of the companion in the context of tidal circularization timescales and show that non-circular orbit was likely inherited from the progenitor. Finally, we emphasize the need for utilizing such an observation method to further understand the demographics of white dwarf companions around nearby stars. © 2019. The American Astronomical Society. All rights reserved.
7 citations (Crossref) [2023-10-31]
Keywords: dept.phy; stars: individual (HD 118475); techniques: high angular resolution; techniques: radial velocities; white dwarfs

Distinguish chromophobe renal cell carcinoma and renal oncocytoma based on analysis of multiphoton microscopic images using convolutional neural network - Icaza, Michael; Judd, Nicolas; Jain, Manu; Mukherjee, Sushmita; Wu, Binlin (Optical Biopsy XVII: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2019)
Convolutional neural networks (CNN) are a class of machine learning model that are especially well suited for imagebased tasks. In this study, we design and train a CNN on tissue samples imaged using Multi-Photon Microscopy (MPM) and show that the model can distinguish between chromophobe renal cell carcinoma (chRCC) and oncocytoma. We demonstrate the method to train a model using simple max-pooling vote fusion, and use the model to highlight regions of the input that cause a positive classification. The model can be tuned for higher sensitivity at the cost of specificity with a constant threshold and little impact to accuracy overall. Several numerical experiments were run to measure the model’s accuracy on both image and patient level analysis. Our models were designed with a dropout parameter that biases the model towards higher sensitivity or specificity. Our best performance model, as measured by area under the receiver operating characteristic curve (AUC of ROC, or AUROC) on patient level classification, is measured with a 94% AUROC and 88% accuracy, along with 100% sensitivity and 75% specificity.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/082-242-611-443-764, pop00094
Keywords: Biopsy; Chromophobe renal cell carcinoma; Convolution; Convolutional neural network; Convolutional neural network (CNN); Deep learning; Deep neural networks; Harmonic generation; Image analysis; Kidney tumor; Learning algorithms; Malignancy; Multiphoton microscopy; Multiphoton microscopy (MPM); Neural networks; Nonlinear optics; Renal cell carcinoma; Renal oncocytoma; Second harmonic generation (SHG); dept.phy

Characterization of ZnO and Fe doped ZnO nanoparticles using fluorescence spectroscopy - Singhal, Rahul; Fernando, Mihiri; LeMaire, Peter K.; Wu, Binlin (Oxide-based Materials and Devices X, 2019)
In this study, nanoparticles of pure zinc oxide (ZnO) and ZnO doped with iron of various doping concentrations (Zn_1- xFe_xO) are analyzed using fluorescence spectroscopy. Excitation and emission spectra using various operating wavelengths were collected. Individual spectra and excitation emission matrix were analyzed. Various peaks including strong ultraviolet (UV) emission peaks and strong blue emission peaks that are corresponding to the near-band-edge emission (NBE) and defect emission (DE) peaks were studied based on the peak intensities, peak wavelengths, and NBE peak to defect peak ratios. The Zn_1-xFe_xO materials were also analyzed using X-ray diffraction and optical absorption spectroscopy. The variation in the band gap energy and in the NBE emission energy with dopant concentration was analyzed. A red-shift was observed with the NBE emission peak. The NBE to DE ratio initially increases from pure ZnO to Zn_0.97Fe_0.03O and then decreases as the dopant concentration increases.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/019-994-177-077-315, pop00183
Keywords: Absorption spectroscopy; Band Gap; Band-edge emission (NBE); Band-edge emissions; Defect emission; Defect emission (DE); Defects; Dopant concentrations; Doping concentration; Emission spectroscopy; Energy gap; Excitation and emission spectra; Excitation emission matrices; Fluorescence; Fluorescence spectroscopy; II-VI semiconductors; Iron; Laser radiation; Light absorption; Nanoparticles; Near band edge emissions; Red Shift; Semiconductor doping; X ray diffraction; X-ray diffraction; Zinc oxide; Zinc oxide (ZnO); ZnO nanoparticles; dept.phy

Constraining the initial conditions and temperature dependent viscosity with three-particle correlations in Au+Au collisions - STAR Collaboration (Physics Letters B, 2019)
We present three-particle mixed-harmonic correlations 〈cos⁡(mϕa+nϕb−(m+n)ϕc)〉 for harmonics m,n=1−3 for charged particles in sNN=200 GeV Au+Au collisions at RHIC. These measurements provide information on the three-dimensional structure of the initial collision zone and are important for constraining models of a subsequent low-viscosity quark–gluon plasma expansion phase. We investigate correlations between the first, second and third harmonics predicted as a consequence of fluctuations in the initial state. The dependence of the correlations on the pseudorapidity separation between particles show hints of a breaking of longitudinal invariance. We compare our results to a number of state-of-the art hydrodynamic calculations with different initial states and temperature dependent viscosities. These measurements provide important steps towards constraining the temperature dependent viscosity and longitudinal structure of the initial state at RHIC. © 2018 The Author
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00019 tex.ids: [object Object] tex.type: [object Object]
Keywords: dept.phy; peer-reviewed

The proton–Ω correlation function in Au + Au collisions at sNN=200GeV - STAR Collaboration (Physics Letters B, 2019)
We present the first measurement of the proton correlation function in heavy-ion collisions for the central (0–40%) and peripheral (40–80%) Au + Au collisions at sNN=200 GeV by the STAR experiment at the Relativistic Heavy-Ion Collider (RHIC). Predictions for the ratio of peripheral collisions to central collisions for the proton correlation function are sensitive to the presence of a nucleon bound state. These predictions are based on the proton interaction extracted from (2+1)-flavor lattice QCD calculations at the physical point. The measured ratio of the proton correlation function between the peripheral (small system) and central (large system) collisions is less than unity for relative momentum smaller than 40 MeV/c. Comparison of our measured correlation ratio with theoretical calculation slightly favors a proton bound system with a binding energy of ∼ 27 MeV.
50 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/036-293-700-061-567, pop00013 tex.type: [object Object]
Keywords: Correlations; Femtoscopy; NΩ dibaryon; dept.phy; peer-reviewed

A pilot study for distinguishing basal cell carcinoma from normal human skin tissues using visible resonance Raman spectroscopy - Liu, Cheng-hui; Wu, Binlin; Sordillo, Laura A.; Boydston-White, Susie; Sriramoju, Vidyasagar; Zhang, Chunyuan; Beckman, Hugh; Zhang, Lin; Pei, Zhe; Shi, Lingyan; Alfano, Robert R. (Journal of Cancer Metastasis and Treatment, 2019)
5 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Orbits of 14 binaries based on 2018 SOAR speckle observations - Docobo, José A; Gomez, Jorge; Campo, Pedro P; Andrade, Manuel; Horch, Elliott P; Costa, Edgardo; Mendez, Rene A (Monthly Notices of the Royal Astronomical Society, 2019)
New data obtained during the 2018 March-April speckle run at the 4.1 m Southern Astrophysical Research (SOAR) telescope located at Cerro Pachón (Chile) allowed us to recalculate the orbits of the following visual binaries: WDS 06478+0020 (STT 157),WDS 07003-2207 (FIN 334Aa,Ab), WDS 07013-0906 (A 671), WDS 10174-5354 (CVN 16Aa,Ab), WDS 12155-3106 (RST 1658),WDS 12572+0818 (FIN 380),WDS 13044-1316 (HU 642),WDS 14243-3838 (RST 1785), WDS 16094-3103 (I 557), WDS 17115-1630 (HU 169), WDS 17119-0151 (LPM 629),WDS 17563 + 0259 (A 2189),WDS 18464-2755 (RST 2073), and WDS 19035-6845 (FIN 357). All but three of them are Southern stars. The recently published Gaia parallaxes were used to calculate the total mass of each of these systems, despite the fact that, in a few cases, only Hipparcos parallaxes were available. For two binaries, A 671 and RST 2073, there are no parallax data. However, in these cases, the masses deduced from the dynamical parallaxes provided relevant information. In addition, we also present the first orbit for each of three systems: HU 642, RST 1785, and RST 2073, using speckle measurements. Finally, using the dynamical parallaxes given by these orbits, we have been able to calculate the luminosity of these systems. Said luminosities allow us to indicate an approximate age for each of the components of the system, situating them within the HR diagram. © 2018 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/024-727-074-773-961, pop00143 tex.type: [object Object]
Keywords: Techniques: high angular resolution - astrometry - binaries; Visual - stars: fundamental parameters; dept.phy; peer-reviewed

Observations of binary stars with the Differential Speckle Survey Instrument. VIII. Measures of metal-poor and triple stars from 2015 to 2018 - Horch, Elliott P.; Tokovinin, Andrei; Weiss, Samuel A.; Löbb, János; Casetti-Dinescu, Dana I.; Granucci, Nicole M.; Hess, Nicole M.; Everett, Mark E.; van Belle, Gerard T.; Winters, Jennifer G.; Nusdeo, Daniel A.; Henry, Todd J.; et al. (The Astronomical Journal, 2019)
We present 248 speckle observations of 43 binary and 19 trinary star systems chosen to make progress in two main areas of investigation: the fundamental properties of metal-poor stars and star formation mechanisms. The observations were taken at the Gemini North and South telescopes during the period 2015 July to 2018 April, mainly with the Differential Speckle Survey Instrument but also with a few early results from the new 'Alopeke speckle camera at Gemini North. We find that the astrometry and photometry of these observations as a whole are consistent with previous work at Gemini. We present five new visual orbits for systems important in understanding metal-poor stars, three of which have orbital periods of less than 4 yr, and we indicate the degree to which these and future observations can impact our knowledge of stellar properties and star formation. In particular, we find a decrease in mass at fixed spectral type for metal-poor stars versus their solar-metallicity analogs that is consistent with predictions that are made from current stellar models. © 2019. The American Astronomical Society. All rights reserved..
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/073-502-692-786-428, pop00025 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; stars: individual; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Visible resonance raman spectroscopy in human brain tissues - Zhou, Yan; Liu, Cheng-hui; Zhu, Ke; Wu, Binlin; Yu, Xinguang; Alfano, Robert R. (Neurophotonics and Biomedical Spectroscopy, 2019)
This chapter first reviews the research and applications of nonresonance and resonance Raman spectroscopy for analysis of human brain normal and abnormal tissues. Next, special emphasis is made on our recent achievements of visible resonance Raman (VRR) technique in primary human brain tumor disease investigation and diagnosis. Visible resonance Raman (VRR) spectroscopy technique uses excitation of visible light (532 nm) to evaluate the resonant and nonresonant molecular vibrational modes in biological tissues. The VRR signal intensities are enhanced by two to three orders of magnitude for faster use in medical applications in quasi real time. VRR opens up a new stainless “molecular optics based histopathology” diagnosis approach. © 2019 Elsevier Ltd. All rights reserved.
Keywords: Brain cancer margin assessment; Glioblastoma multiforme (GBM); Glioblastoma multiforme (gbm); Gliomas; Meninges; Optical biopsy; Visible resonance Raman (VRR) spectroscopy; Visible resonance raman (vrr) spectroscopy; Wavelength 532 nm; Wavelength 532nm; dept.phy

The Origins of Young Stars in the Direction of the Leading Arm of the Magellanic Stream: Abundances, Kinematics, and Orbits. - Zhang, Lan; Casetti-Dinescu, Dana I; Bidin, Christian Moni; Mendez, Rene A; Girard, Terrence M; Vieira, Katherine; Korchagin, Vladimir I; van Altena, William F; Zhao, Gang (The Astrophysical journal, 2019)
We explore the origins of the young B-type stars found by Casetti-Dinescu et al. (2014) at the outskirts of the Milky-Way disk in the sky region of Leading Arm of the Magellanic Stream. High-resolution spectroscopic observations made with the MIKE instrument on the Magellan Clay 6.5m telescope for nine stars are added to the previous sample analyzed by Zhang et al. (2017). We compile a sample of fifteen young stars with well-determined stellar types, ages, abundances and kinematics. With proper motions from Gaia DR2 we also derive orbits in a realistic Milky-Way potential. We find that our previous radial-velocity selected LA candidates have substantial orbital angular momentum. The substantial amount of rotational component for these stars is in contrast with the near-polar Magellanic orbit, thus rendering these stars unlikely members of the LA. There are four large orbital-energy stars in our sample. The highest orbital-energy one has an age shorter than the time to disk crossing, with a birthplace z = 2.5 kpc and R GC ~ 28 kpc. Therefore, the origin of this star is uncertain. The remaining three stars have disk runaway origin with birthplaces between 12 and 25 kpc from the Galactic center. Also, the most energetic stars are more metal poor ([Mg/H] =-0.50 +/- 0.07) and with larger He scatter (sigma [He/H] = 0.72) than the inner disk ones ([Mg/H] = 0.12 +/- 0.36, sigma [He/H] = 0.15). While the former group's abundance is compatible with that of the Large Magellanic Cloud, it could also reflect the metallicity gradient of the MW disk and their runaway status via different runaway mechanisms.
4 citations (Crossref) [2023-10-31] Place: United States Zhang, Lan. Key Lab of Optical Astronomy, National Astronomical Observatories, CAS, 20A Datun Road, Chaoyang District, 100012 Beijing, China. Casetti-Dinescu, Dana I. Department of Physics, Southern Connecticut State University, 501 Crescent St., New Haven, CT 06515, USA. Casetti-Dinescu, Dana I. Astronomical Institute of the Romanian Academy, str. Cutitul de Argint 5, Bucharest, Romania. Casetti-Dinescu, Dana I. Radiology and Biomedical Imaging, Yale School of Medicine, 300 Cedar Street, New Haven 06519, USA. Bidin, Christian Moni. Instituto de Astronomia, Universidad Catolica del Norte, Av. Angomos 0610, Antofagasta, Chile. Mendez, Rene A. Departamento de Astronomia, Universidad de Chile, Casilla 36-D, Santiago, Chile. Girard, Terrence M. 14 Dunn Rd, Hamden, Connecticut, CT 06518, USA. Vieira, Katherine. Centro de Investigaciones de Astronomia, Apartado Postal 264, Merida 5101-A, Venezuela. Korchagin, Vladimir I. Institute of Physics, Southern Federal University, Stachki st/194, 344090, Rostov-on-Don, Russia. van Altena, William F. Astronomy Department, Yale University, 260 Whitney Ave., New Haven, CT 06511, USA. Zhao, Gang. Key Lab of Optical Astronomy, National Astronomical Observatories, CAS, 20A Datun Road, Chaoyang District, 100012 Beijing, China.
Keywords: dept.phy; stars: abundances; stars: early-type; stars: kinematics and dynamics

Combined spatial frequency spectroscopy analysis with visible resonance Raman for optical biopsy of human brain metastases of lung cancers - Zhou, Yan; Liu, Cheng-Hui; Pu, Yang; Wu, Binlin; Nguyen, Thien An; Cheng, Gangge; Zhou, Lixin; Zhu, Ke; Chen, Jun; Li, Qingbo; Alfano, Robert R. (Journal of Innovative Optical Health Sciences, 2019)
The purpose of this study is to examine optical spatial frequency spectroscopy analysis (SFSA) combined with visible resonance Raman (VRR) spectroscopic method, for the first time, to discriminate human brain metastases of lung cancers adenocarcinoma (ADC) and squamous cell carcinoma (SCC) from normal tissues. A total of 31 label-free micrographic images of three types of brain tissues were obtained using a confocal micro-Raman spectroscopic system. VRR spectra of the corresponding samples were synchronously collected using excitation wavelength of 532[Formula: see text]nm from the same sites of the tissues. Using SFSA method, the difference in the randomness of spatial frequency structures in the micrograph images was analyzed using Gaussian function fitting. The standard deviations, [Formula: see text] calculated from the spatial frequencies of the micrograph images were then analyzed using support vector machine (SVM) classifier. The key VRR biomolecular fingerprints of carotenoids, tryptophan, amide II, lipids and proteins (methylene/methyl groups) were also analyzed using SVM classifier. All three types of brain tissues were identified with high accuracy in the two approaches with high correlation. The results show that SFSA–VRR can potentially be a dual-modal method to provide new criteria for identifying the three types of human brain tissues, which are on-site, real-time and label-free and may improve the accuracy of brain biopsy.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/037-734-581-386-058, zhouCombinedSpatialFrequency2019a
Keywords: Amides; Amino acids; Article; Biopsy; Brain; Diseases; Histology; Human brain; Image analysis; Metastatic lung cancer; Pathology; Raman spectrometry; Resonance; Resonance Raman; Spatial frequency; Spatial frequency spectroscopy analysis (SFSA); Spatial variables measurement; Spectroscopic analysis; Spectrum analysis; Support vector machines; Tissue; accuracy; amide; brain metastasis; brain tissue; cancer classification; carbene; carotenoid; controlled study; dept.phy; diagnostic test accuracy study; excitation; fatty acid; high density lipoprotein; histopathology; human; human brain; human tissue; lipid; low density lipoprotein; lung adenocarcinoma; metastatic lung cancer; methyl group; molecular imaging; peer-reviewed; photomicrograph image; sensitivity and specificity; spatial frequency spectroscopy analysis; spectroscopy; squamous cell lung carcinoma; support vector machine; support vector machine (SVM); tryptophan; visible resonance Raman (VRR); visible resonance Raman spectroscopy

High performance logic and circuits for high-speed electronic systems - Jain, F; Broadbridge, C; Gherasimova, M; Tang, H (World Scientific Publishing Co., 2019)
In this volume, we have put together papers spanning a broad range from the area of modeling of strain and misfit dislocation densities, microwave absorption characteristics of nanocomposites, to X-ray diffraction studies. Specific topics in this volume include: Modeling of strain relaxation and defect dynamics in buffer layers for semiconductor devices fabricated on lattice-mismatched substrates, which enables technology for advanced computer chips, multi-junction solar cells, detectors, and microwave transistors. Physical Unclonable Functions (PUFs) are probabilistic circuit primitives that extract randomness from the physical characteristics of devices. One of the papers outlines PUF design based on resistor and capacitor variations for low pass filters (LoPUF). Spatial wavefunction switching (SWS) FETs, which can process 2-bits per FET using CMOS-SWS logic, thus enabling multivalued logic (MVL) and compact DRAMs. Perimeter gated single-photon avalanche diode (PGSPAD). The applied voltage at the gate terminal modulates the electric field, making it uniform throughout the junction. This gating technique is an efficient method to prevent premature edge breakdown, one of the major problems in operating avalanche photodiodes implemented in CMOS process. In summary, papers selected in this volume cover various aspects of high performance logic and circuits for high-speed electronic systems. © 2019 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.
Keywords: dept.phy

Phase selection motifs in High Entropy Alloys revealed through combinatorial methods: Large atomic size difference favors BCC over FCC - Kube, Sebastian A; Sohn, Sungwoo; Uhl, David; Datye, Amit; Mehta, Apurva; Schroers, Jan (Acta Materialia, 2019)
High Entropy Alloys are inherently complex and span a vast composition space, making their research and discovery challenging. Developing quantitative predictions of their phase selection requires a large quantity of consistently determined experimental data. Here, we use combinatorial methods to fabricate and characterize 2478 quinary alloys based on Al and transition metals. All data are publicly available at http://materialsatlasproject.org/. Phase selection can be predicted for considered alloys when combining the content of FCC/BCC elements and the constituents’ atomic size difference. Mining our data reveals that High Entropy Alloys with increasing atomic size difference prefer BCC structure over FCC. This preference is typically overshadowed by other selection motifs, which dominate during close-to-equilibrium processing. Not suggested by the Hume-Rothery rules, this preference originates from the ability of the BCC structure to accommodate a large atomic size difference with lower strain energy penalty which can be practically only realized in High Entropy Alloys. © 2019 Acta Materialia Inc.
136 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/048-312-417-394-434 tex.type: [object Object]
Keywords: Aluminum alloys; Atomic size difference; Atomic sizes; Atoms; Combinatorial method; Combinatorial sputtering; Composition space; Crystal structure; Entropy; High entropy alloys; Hume-Rothery rules; Phase selection; Quantitative prediction; Strain energy; Transition metals; dept.phy; peer-reviewed

Study of MnO2-Graphene Oxide nanocomposites for supercapacitor applications - Singhal, Rahul; Fagnoni, Justin; Thorne, David; LeMaire, Peter K.; Martinez, Xavier; Zhao, Chen; Gupta, Ram K.; Uhl, David; Scanley, Ellen; Broadbridge, Christine C.; Manivannan, Mani; Pandey, Rishikesh (MRS Advances, 2019)
Graphene oxide (GO)/MnO2 nanocomposites were synthesized by adding KMnO4 in a solution of water and ethanol (3:1), containing 10 mg of GO. Brown precipitates were obtained after a continuous stirring for 1 hr. The precipitates were then washed with deionized water (DI) water and dried to obtain the MnO2-GO nanocomposites. Pure MnO2 was also synthesized using the same method without GO for the comparison. X-ray diffraction pattern confirm δ-MnO2 type of MnO2 with birnessite type MnO2 structure. The TEM images show the average diameter of MnO2 nanorods as 15 nm. Electrochemical characterizations were carried out in an aqueous solution of 3M KOH. Charge-discharge studies were carried out between 1A/g to 20 A/g current range. The MnO2-GO nanocomposites showed improved electrochemical performances. The capacitance of MnO2 and MnO2-GO electrodes was found to be as 300 F/g, and 350 F/g, respectively at a current of 0.5 A/g. © 2019 Materials Research Society.
6 citations (Crossref) [2023-10-31]
Keywords: Average diameter; Charge-discharge; Continuous stirrings; Current range; Deionized water; Electric discharges; Electrochemical characterizations; Electrochemical performance; Energy storage; Graphene; Graphene oxide nanocomposites; Manganese oxide; Nanocomposites; Nanorods; Potassium hydroxide; Raman spectroscopy; Supercapacitor; Supercapacitor application; X ray diffraction; dept.phy; energy storage; graphene; peer-reviewed; x-ray diffraction (XRD)

Speckle observations and orbits of multiple stars. - Tokovinin, Andrei; Everett, Mark E; Horch, Elliott P; Torres, Guillermo; Latham, David W (Astronomical Journal, 2019)
We report results of speckle-interferometric monitoring of visual hierarchical systems using the newly commissioned instrument NN-EXPLORE Exoplanet and Stellar Speckle Imager at the 3.5 m WIYN telescope. During one year, 390 measurements of 129 resolved subsystems were made, while some targets were unresolved. Using our astrometry and archival data, we computed 36 orbits (27 for the first time). Spectro-interferometric orbits of seven pairs are determined by combining positional measurements with radial velocities measured, mostly, with the Center for Astrophysics digital speedometers. For the hierarchical systems HIP 65026 (periods 49 and 1.23 yr) and HIP 85209 (periods 34 and 1.23 yr) we determined both the inner and the outer orbits using astrometry and radial velocities and measured the mutual orbit inclinations of 11.°3 ± 1.°0 and 12.°0 ± 3.°0, respectively. Four bright stars are resolved for the first time; two of those are triple systems. Several visual subsystems announced in the literature are shown to be spurious. We note that subsystems in compact hierarchies with outer separations less than 100 au tend to have less eccentric orbits compared to wider hierarchies. © 2019. The American Astronomical Society. All rights reserved..
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/097-296-370-783-044 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; ⛔ No DOI found

Invited Article: Molecular biomarkers characterization for human brain glioma grading using visible resonance Raman spectroscopy - Zhou, Yan; Liu, Cheng-hui; Wu, Binlin; Zhang, Chunyuan; Yu, Xinguang; Cheng, Gangge; Chen, Hong; Li, Shenglin; Liang, Qijun; Zhang, Mingqian; Zhu, Ke; Shi, Lingyan; et al. (APL Photonics, 2018)
The accurate identification of the human brain tumor boundary and the complete resection of the tumor are two essential factors for the removal of the glioma tumor in brain surgery. We present a visible resonance Raman (VRR) spectroscopy technique for differentiating the brain tumor margin and glioma grading. Eighty-seven VRR spectra from twenty-one human brain specimens of four types of brain tissues, including the control, glioma grade II, III, and IV tissues, were observed. This study focuses on observing the characteristics of new biomarkers and their changes in the four types of brain tissue. We found that two new RR peaks at 1129 cm-1 and 1338 cm-1 associated with molecular vibrational bonds in four types of brain tissues are significantly different in peak intensities of VRR spectra. These two resonance enhanced peaks may arise from lactic acid/phosphatidic acid and adenosine triphosphate (ATP)/nicotinamide adenine dinucleotide, respectively. We found that lactic acid and ATP concentrations vary with glioma gratings. The higher the grade of malignancy, the more the increase in lactic acid and ATP concentrations. These two RR peaks may be considered as new molecular biomarkers and used to evaluate glioma grades and identify the margin of gliomas from the control tissues. The metabolic process of lactic acid and ATP in glioma cells based on the VRR spectral changes may reveal the Warburg hypothesis. © 2018 Author(s).
18 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/071-292-711-428-912, pop00034
Keywords: Adenosinetriphosphate; Biomarkers; Brain; Control tissues; Grading; Histology; Human brain tumors; Lactic acid; Metabolic process; Molecular biomarker; Resonance; Resonance Raman; Resonance Raman spectroscopy; Resonance enhanced; Spectral change; Tumors; dept.phy; peer-reviewed

J/ψ production cross section and its dependence on charged-particle multiplicity in p + p collisions at √s=200 GeV - STAR Collaboration (Physics Letters B, 2018)
We present a measurement of inclusive J/ψ production at mid-rapidity (|y|¡1) in p+p collisions at a center-of-mass energy of s=200 GeV with the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The differential production cross section for J/ψ as a function of transverse momentum (pT) for 0¡pT¡14 GeV/c and the total cross section are reported and compared to calculations from the color evaporation model and the non-relativistic Quantum Chromodynamics model. The dependence of J/ψ relative yields in three pT intervals on charged-particle multiplicity at mid-rapidity is measured for the first time in p+p collisions at s=200 GeV and compared with that measured at s=7 TeV, PYTHIA8 and EPOS3 Monte Carlo generators, and the Percolation model prediction.
24 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/117-089-514-318-953, pop00032 tex.ids: [object Object] tex.type: [object Object]
Keywords: Charged-particle multiplicity; Multiple parton interactions; Quarkonium; collisions; dept.phy; p+p collisions; peer-reviewed

The Three-dimensional orbit, orbital parallax, and individual masses of the double-lined spectroscopic binaries HD 183255, HD 114882, and HD 30712 - Docobo, J. A.; Campo, P. P; Gomez, J.; Horch, Elliott P. (The Astronomical Journal, 2018)
Recent speckle observations performed at the Discovery Channel Telescope, the Gemini North Telescope, and the Special Astrophysical Observatory 6 m Telescope have permitted us to calculate the visual orbit of SB2 HD 114882 for the first time and to improve the visual orbits of two other SB2 systems, HD 30712 and HD 183255, using algorithms published by the authors of this research. Recently, new high-quality spectroscopic orbits have been obtained for these binaries by other authors. We determine their 3D orbits, individual masses, and orbital parallaxes, and present them in this paper. The parallaxes are compared with those available from the Gaia mission, and a comparison between the values confirms the precision of the results obtained here. © 2018. The American Astronomical Society. All rights reserved.
4 citations (Crossref) [2023-10-31]
Keywords: astrometry; binaries: spectroscopic; binaries: visual; dept.phy; peer-reviewed; stars: fundamental parameters; techniques: interferometric

Collision energy dependence of moments of net-kaon multiplicity distributions at RHIC - STAR Collaboration (Physics Letters B, 2018)
Fluctuations of conserved quantities such as baryon number, charge, and strangeness are sensitive to the correlation length of the hot and dense matter created in relativistic heavy-ion collisions and can be used to search for the QCD critical point. We report the first measurements of the moments of net-kaon multiplicity distributions in Au+Au collisions at sNN=7.7, 11.5, 14.5, 19.6, 27, 39, 62.4, and 200 GeV. The collision centrality and energy dependence of the mean (M), variance (σ2), skewness (S), and kurtosis (κ) for net-kaon multiplicity distributions as well as the ratio σ2/M and the products Sσ and κσ2 are presented. Comparisons are made with Poisson and negative binomial baseline calculations as well as with UrQMD, a transport model (UrQMD) that does not include effects from the QCD critical point. Within current uncertainties, the net-kaon cumulant ratios appear to be monotonic as a function of collision energy.
100 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/122-461-912-508-954, pop00005 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed

Harmonic decomposition of three-particle azimuthal correlations at energies available at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2018)
We present measurements of three-particle correlations for various harmonics in Au+Au collisions at energies ranging from sNN=7.7√sNN=7.7 to 200 GeV using the STAR detector. The quantity 〈cos(mϕ1+nϕ2−(m+n)ϕ3)〉⟨cos(mϕ1+nϕ2−(m+n)ϕ3)⟩, with ϕϕ being the azimuthal angles of the particles is evaluated as a function of sNN√sNN, collision centrality, transverse momentum, pTpT, pseudorapidity difference, ΔηΔη, and harmonics (mm and nn). These data provide detailed information on global event properties such as the three-dimensional structure of the initial overlap region, the expansion dynamics of the matter produced in the collisions, and the transport properties of the medium. A strong dependence on ΔηΔη is observed for most harmonic combinations, which is consistent with breaking of longitudinal boost invariance. An interesting energy dependence is observed when one of the harmonics m,n,m,n, or m+nm+n is equal to two, for which the correlators are dominated by the two-particle correlations relative to the second-harmonic event plane. These measurements can be used to constrain models of heavy-ion collisions over a wide range of temperature and baryon chemical potential.
29 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Beam energy dependence of rapidity-even dipolar flow in Au+Au collisions - STAR Collaboration (Physics Letters B, 2018)
New measurements of directed flow for charged hadrons, characterized by the Fourier coefficient v1, are presented for transverse momenta pT, and centrality intervals in Au+Au collisions recorded by the STAR experiment for the center-of-mass energy range sNN=7.7–200 GeV. The measurements underscore the importance of momentum conservation, and the characteristic dependencies on sNN, centrality and pT are consistent with the expectations of geometric fluctuations generated in the initial stages of the collision, acting in concert with a hydrodynamic-like expansion. The centrality and pT dependencies of v1even, as well as an observed similarity between its excitation function and that for v3, could serve as constraints for initial-state models. The v1even excitation function could also provide an important supplement to the flow measurements employed for precision extraction of the temperature dependence of the specific shear viscosity.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/037-329-521-805-901, pop00022 tex.ids: [object Object] tex.type: [object Object]
Keywords: dept.phy; peer-reviewed

Longitudinal double-spin asymmetries for π0 s in the forward direction for 510 GeV polarized pp collisions - STAR Collaboration (Physical Review D, 2018)
The STAR Collaboration reports measurements of the longitudinal double-spin asymmetry, ALL, for neutral pions produced at forward directions in polarized proton-proton collisions, at a center-of-mass energy of 510 GeV. Results are given for transverse momenta in the range 2<pT<10 GeV/c within two regions of pseudorapidity that span 2.65<η<3.9. These results are sensitive to the polarized gluon parton distribution function, Δg(x), down to the region of Bjorken x∼10−3. The asymmetries observed are less than ±5×10−3 in magnitude and will help constrain the contribution to the spin of the proton from polarized gluons at low x, when combined with other measurements as part of a global analysis.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/095-769-263-543-103, pop00031 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed

Longitudinal double-spin asymmetries for dijet production at intermediate pseudorapidity in polarized pp collisions at √ s = 200 GeV - STAR Collaboration (Physical Review D, 2018)
We present the first measurements of the longitudinal double-spin asymmetry ALL for dijets with at least one jet reconstructed within the pseudorapidity range 0.8<η<1.8. The dijets were measured in polarized pp collisions at a center-of-mass energy s=200 GeV. Values for ALL are determined for several distinct event topologies, defined by the jet pseudorapidities, and span a range of parton momentum fraction x down to x∼0.01. The measured asymmetries are found to be consistent with the predictions of global analyses that incorporate the results of previous RHIC measurements. They will provide new constraints on Δg(x) in this poorly constrained region when included in future global analyses. © 2018 authors. Published by the American Physical Society.
12 citations (Crossref) [2023-10-31] Citation Key Alias: pop00012 tex.ids: [object Object] tex.type: [object Object]
Keywords: dept.phy; peer-reviewed

Correlation measurements between flow harmonics in Au+Au collisions at RHIC - STAR Collaboration (Physics Letters B, 2018)
Flow harmonics (vn) in the Fourier expansion of the azimuthal distribution of particles are widely used to quantify the anisotropy in particle emission in high-energy heavy-ion collisions. The symmetric cumulants, SC(m,n), are used to measure the correlations between different orders of flow harmonics. These correlations are used to constrain the initial conditions and the transport properties of the medium in theoretical models. In this Letter, we present the first measurements of the four-particle symmetric cumulants in Au+Au collisions at sNN=39 and 200 GeV from data collected by the STAR experiment at RHIC. We observe that v2 and v3 are anti-correlated in all centrality intervals with similar correlation strengths from 39 GeV Au+Au to 2.76 TeV Pb+Pb (measured by the ALICE experiment). The v2–v4 correlation seems to be stronger at 39 GeV than at higher collision energies. The initial-stage anti-correlations between second and third order eccentricities are sufficient to describe the measured correlations between v2 and v3. The best description of v2–v4 correlations at sNN=200GeV is obtained with inclusion of the system's nonlinear response to initial eccentricities accompanied by the viscous effect with η/s¿0.08. Theoretical calculations using different initial conditions, equations of state and viscous coefficients need to be further explored to extract η/s of the medium created at RHIC.
21 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/066-754-749-172-863, pop00026 tex.type: [object Object]
Keywords: Collectivity; Correlation; Shear viscosity; dept.phy; peer-reviewed

Beam energy dependence of jet-quenching effects in Au+Au collisions at √(sNN)= 7.7, 11.5, 14.5, 19.6, 27, 39, and 62.4 GeV - STAR Collaboration (Physical Review Letters, 2018)
We report measurements of the nuclear modification factor RCP for charged hadrons as well as identified π+(−), K+(−), and p(¯p) for Au+Au collision energies of √sNN=7.7, 11.5, 14.5, 19.6, 27, 39, and 62.4 GeV. We observe a clear high-pT net suppression in central collisions at 62.4 GeV for charged hadrons which evolves smoothly to a large net enhancement at lower energies. This trend is driven by the evolution of the pion spectra but is also very similar for the kaon spectra. While the magnitude of the proton RCP at high pT does depend on the collision energy, neither the proton nor the antiproton RCP at high pT exhibit net suppression at any energy. A study of how the binary collision-scaled high-pT yield evolves with centrality reveals a nonmonotonic shape that is consistent with the idea that jet quenching is increasing faster than the combined phenomena that lead to enhancement.
30 citations (Crossref) [2023-10-31]
Keywords: Au+Au collisions; Beam energies; Binary collisions; Charged hadrons; Colliding beam accelerators; Collision energies; Fighter aircraft; Germanium compounds; Hadrons; Lower energies; Measurements of; Nuclear modification factors; Quenching; dept.phy; peer-reviewed

Wide-field speckle techniques for small, urban telescopes - Granucci, Nicole M.; Horch, Elliott P. (Optical and Infrared Interferometry and Imaging VI, 2018)
Recent work with the NESSI speckle camera at Kitt Peak and the 'Alopeke speckle camera at Gemini-North indicates that speckle data reduction techniques can be successfully modified to produce high-resolution images over fields that are at least tens of arc seconds across. While these wide-field speckle image reconstructions are not diffraction-limited, the improvement in resolution over the seeing-limited case can be substantial. In this paper, we explore the application of these techniques to data taken with a small (0.6-m) telescope in an urban environment. Many telescopes located in urban communities, such as New Haven, Connecticut, where Southern Connecticut State University resides, have limited use scientifically due to substantial light pollution, poor seeing, poor telescope tracking, and other issues. We will present initial data using our set-up and discuss the potential for this approach for improving the imaging capabilities of small telescopes on our campus and beyond.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/033-406-183-484-56X, pop00246
Keywords: Cameras; Diffraction limited; High resolution image; Image enhancement; Image reconstruction; Imaging capabilities; Interferometry; Pollution; Reduction techniques; Shift-and-add; Speckle; Speckle imaging; Telescopes; Unsharp masking; Urban environments; dept.phy; shift-and-add techniques; unsharp masking

Prospects for wireless optical intensity interferometry with the Southern Connecticut stellar interferometer - Horch, Elliott P.; Weiss, Samuel A.; Rupert, Justin D.; LaRue, Ryan; Peronio, Pietro; Rech, Ivan; Gulinatti, Angelo (Optical and Infrared Interferometry and Imaging VI, 2018)
The Southern Connecticut Stellar Interferometer (SCSI) is a two-telescope astronomical intensity interferometer that was completed in June 2016 and has been taking photon correlation data since that time. It uses single-photon avalanche diode (SPAD) detectors at the telescope focal plane and a central timing module, which records the signals from both telescopes simultaneously. In the observations taken to date, single-pixel SPADs have been connected to signal cables that stretch from each telescope to the timing module. However, we are now in the process of making the instrument “wireless” by using a separate timing module at each telescope and synchronizing the signals recorded using GPS timing cards. We have also upgraded one of the two stations with an 8-pixel SPAD device, which allows us to achieve higher count rates in a variety of observing conditions. In this paper, we report on the current state of the instrument, including engineering tests made in preparation for wireless operation, and we discuss the expected capabilities in that mode.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-838-080-681-906, pop00166 tex.type: [object Object]
Keywords: Avalanche diodes; Engineering tests; Hanbury Brown and Twiss effect; Intensity interferometry; Interferometers; Interferometry; Particle beams; Photon correlation; Photons; Single photon avalanche diode; Stars; Stellar interferometers; Telescopes; Timing module; Wireless operation; Wireless-optical; dept.phy; single-photon avalanche diode (SPAD) detectors; timing correlation

Stellar photon correlation detection with the Southern Connecticut stellar interferometer - Weiss, Samuel A.; Rupert, Justin D.; Horch, Elliott P. (Optical and Infrared Interferometry and Imaging VI, 2018)
The Southern Connecticut Stellar Interferometer (SCSI) is a portable optical intensity interferometer located on the campus of Southern Connecticut State University in New Haven, Connecticut. Since its completion in 2016, the instrument has been used to take engineering data of bright stars. This paper will discuss the data collection and analysis methods, as well as the progress toward reliably measuring a significant stellar photon correlation. Vega has been the main star chosen for test observations to date because its diameter is well known by other methods, and it is not an extended source for the baselines used. The correlation peak in the processed data is compared to theoretical expectations. Given our expected sensitivity, a significant correlation peak is expected for small baselines (~2 m) to appear after a few hours of observation. So far, the observations indicate that the correlation peak is at the expected time delay, and the signal-to-noise ratio roughly scales as predicted.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/067-933-668-471-503, pop00212
Keywords: Avalanche diodes; Correlation peaks; Engineering data; Extended sources; Hanbury Brown and Twiss effect; Intensity interferometry; Interferometers; Interferometry; Optical intensities; Particle beams; Photon correlation; Photons; Quantum optics; Signal to noise ratio; Single photon avalanche diode; Stars; Stellar interferometers; dept.phy; single-photon avalanche diode (SPAD) detectors; timing correlation

Zodiacal Exoplanets in Time (ZEIT). VII. A temperate candidate Super-Earth in the Hyades Cluster - Vanderburg, Andrew; Mann, Andrew W.; Rizzuto, Aaron; Bieryla, Allyson; Kraus, Adam L.; Berlind, Perry; Calkins, Michael L.; Curtis, Jason L.; Douglas, Stephanie T.; Esquerdo, Gilbert A.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2018)
Transiting exoplanets in young open clusters present opportunities to study how exoplanets evolve over their lifetimes. Recently, significant progress detecting transiting planets in young open clusters has been made with the K2 mission, but so far all of these transiting cluster planets orbit close to their host stars, so planet evolution can only be studied in a high-irradiation regime. Here, we report the discovery of a long-period planet candidate, called HD 283869 b, orbiting a member of the Hyades cluster. Using data from the K2 mission, we detected a single transit of a super-Earth-sized (1.96 0.12 R ⊕) planet candidate orbiting the K-dwarf HD 283869 with a period longer than 72 days. As we only detected a single-transit event, we cannot validate HD 283869 b with high confidence, but our analysis of the K2 images, archival data, and follow-up observations suggests that the source of the event is indeed a transiting planet. We estimated the candidate's orbital parameters and find that if real, it has a period P ≈ 100 days and receives approximately Earth-like incident flux, giving the candidate a 71% chance of falling within the circumstellar habitable zone. If confirmed, HD 283869 b would have the longest orbital period, lowest incident flux, and brightest host star of any known transiting planet in an open cluster, making it uniquely important to future studies of how stellar irradiation affects planetary evolution. © 2018. The American Astronomical Society. All rights reserved..
32 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-063-848-375-694, pop00021 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planetary systems; planets and satellites: detection; stars: individual (HD 283869)

Stellar companions of exoplanet host stars in K2 - Matson, Rachel A.; Howell, Steve B.; Horch, Elliott P.; Everett, Mark E. (The Astronomical Journal, 2018)
It is well established that roughly half of all nearby solar-type stars have at least one companion. Stellar companions can have significant implications for the detection and characterization of exoplanets, including triggering false positives and masking the true radii of planets. Determining the fraction of exoplanet host stars that are also binaries allows us to better determine planetary characteristics as well as establish the relationship between binarity and planet formation. Using high angular resolution speckle imaging, we detect stellar companions within ∼1 arcsec of K2 planet-candidate host stars. Comparing our detected companion rate to TRILEGAL star count simulations and known detection limits of speckle imaging, we estimate the binary fraction of K2 planet host stars to be 40%-50%, similar to that of Kepler exoplanet hosts and field stars. © 2018. The American Astronomical Society. All rights reserved.
70 citations (Crossref) [2023-10-31]
Keywords: binaries: general; binaries: visual; dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution

A spectroscopic survey of field red horizontal-branch stars - Afşar, Melike; Bozkurt, Zeynep; Topcu, Gamze Böcek; Casetti-Dinescu, Dana I.; Sneden, Christopher; Şehitog̅lu, Gizem (The Astronomical Journal, 2018)
A metallicity, chemical composition, and kinematic survey has been conducted for a sample of 340 candidate field red horizontal-branch (RHB) stars. Spectra with high resolution and high signal-to-noise ratio were gathered with the McDonald Observatory 2.7 m Tull and the Hobby-Eberly Telescope echelle spectrographs, and were used to determine effective temperatures, surface gravities, microturbulent velocities, [Fe/H] metallicities, and abundance ratios [X/Fe] for seven α and Fe-group species. The derived temperatures and gravities confirm that at least half of the candidates are true RHB stars, with (average) parameters T eff ∼ 5000 K and log g ∼ 2.5. From the α abundances alone, the thin and thick Galactic populations are apparent in our sample. Space motions for 90% of the program stars were computed from Hipparcos and Gaia parallaxes and proper motions. Correlations between chemical compositions and Galactic kinematics clearly indicate the existence of both thin-disk and thick-disk RHB stars. © 2018. The American Astronomical Society. All rights reserved..
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/152-783-501-669-868, pop00080 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; stars: abundances; stars: atmospheres; stars: evolution; stars: horizontal-branch

Speckle interferometry at SOAR in 2016 and 2017 - Tokovinin, Andrei; Mason, Brian D.; Hartkopf, William I.; Mendez, Rene A.; Horch, Elliott P. (The Astronomical Journal, 2018)
The results of speckle interferometric observations at the 4.1 m Southern Astrophysical Research Telescope in 2016 and 2017 are given, totaling 2483 measurements of 1570 resolved pairs and 609 non-resolutions. We describe briefly recent changes in the instrument and observing method and quantify the accuracy of the pixel scale and position angle calibration. Comments are given on 44 pairs resolved here for the first time. The orbital motion of the newly resolved subsystem BU 83 Aa,Ab roughly agrees with its 36-year astrometric orbit proposed by J. Dommanget. Most Tycho binaries examined here turned out to be spurious. © 2018. The American Astronomical Society. All rights reserved..
30 citations (Crossref) [2023-10-31]
Keywords: binaries: visual; dept.phy; peer-reviewed

The NN-explore exoplanet stellar speckle imager: Instrument description and preliminary results - Scott, Nicholas J.; Howell, Steve B.; Horch, Elliott P.; Everett, Mark E. (Publications of the Astronomical Society of the Pacific, 2018)
A new speckle and wide-field imaging instrument for the WIYN telescope called NN-EXPLORE Exoplanet Stellar Speckle Imager (NESSI) is described. NESSI offers simultaneous two-color diffraction-limited imaging and wide-field traditional imaging for validation and characterization of transit and precision RV exoplanet studies. Many exoplanet targets will come from the NASA K2 and Transiting Exoplanet Survey Satellite (TESS) missions. NESSI is capable of resolving close binaries at sub-arcsecond separations down to the diffraction limit and >6 mag contrast difference in the visible band on targets as faint as 14th mag. Preliminary results from the instrument commissioning at WIYN and demonstrations of the instrument’s capabilities are presented. © 2018. The Astronomical Society of the Pacific. Printed in the U.S.A.
68 citations (Crossref) [2023-10-31]
Keywords: Binaries (including multiple): close; Instrumentation: high angular resolution; Instrumentation: interferometers; Techniques: interferometric; Techniques: photometric; dept.phy; peer-reviewed

Transverse spin-dependent azimuthal correlations of charged pion pairs measured in p↑ + p collisions at √s=500 GeV - STAR Collaboration (Physics Letters B, 2018)
The transversity distribution, which describes transversely polarized quarks in transversely polarized nucleons, is a fundamental component of the spin structure of the nucleon, and is only loosely constrained by global fits to existing semi-inclusive deep inelastic scattering (SIDIS) data. In transversely polarized p↑+p collisions it can be accessed using transverse polarization dependent fragmentation functions which give rise to azimuthal correlations between the polarization of the struck parton and the final state scalar mesons. This letter reports on spin dependent di-hadron correlations measured by the STAR experiment. The new dataset corresponds to 25 pb−1 integrated luminosity of p↑+p collisions at s=500 GeV, an increase of more than a factor of ten compared to our previous measurement at s=200 GeV. Non-zero asymmetries sensitive to transversity are observed at a Q2 of several hundred GeV and are found to be consistent with the former measurement and a model calculation. We expect that these data will enable an extraction of transversity with comparable precision to current SIDIS datasets but at much higher momentum transfers where subleading effects are suppressed. © 2018 The Author(s)
16 citations (Crossref) [2023-10-31] Citation Key Alias: pop00023 tex.ids: [object Object] tex.type: [object Object]
Keywords: Di-hadron correlations; Interference fragmentation function; Transversity; dept.phy; peer-reviewed

Measurement of the ³H lifetime in Au+Au collisions at the BNL relativistic heavy ion collider - STAR Collaboration (Physical Review C, 2018)
An improved measurement of the HΛ3 lifetime is presented. In this paper, the mesonic decay modes HΛ3→He3 + π- and HΛ3→d+p+π- are used to reconstruct the HΛ3 from Au+Au collision data collected by the STAR collaboration at Relativistic Heavy Ion Collider (RHIC). A minimum χ2 estimation is used to determine the lifetime of τ=142-21+24(stat.)±29(syst.) ps. This lifetime is about 50% shorter than the lifetime τ=263±2 ps of a free Λ, indicating strong hyperon-nucleon interaction in the hypernucleus system. The branching ratios of the mesonic decay channels are also determined to satisfy B.R.(He3+π-)/(B.R.(He3+π-)+B.R.(d+p+π-))=0.32±0.05(stat.)±0.08(syst.). Our ratio result favors the assignment J(HΛ3)=12 over J(HΛ3)=32. These measurements will help to constrain models of hyperon-baryon interactions. © 2018 American Physical Society.
47 citations (Crossref) [2023-10-31] tex.collaboration: STAR Collaboration tex.numpages: 7 tex.publisher: American Physical Society
Keywords: dept.phy; peer-reviewed

Visible resonance Raman spectroscopy detect key molecular biomarker vibrations to characterize for human brain gliomas - Zhou, Yan; Liu, Cheng-hui; Wu, Binlin; Yu, Xinguang; Gangge Cheng; Zhang, Chunyuan; Chen, Hong; Li, Shenglin; Zong, Rui; Liang, Qijun; Zhang, Ce; Zhang, Mingqian; et al. (Biomedical Imaging and Sensing Conference, 2018)
Visible resonant Raman (VRR) spectroscopy provides an effective way to enhance Raman signal from particular bonds associated with key molecules due to changes on molecular level. This paper reports on the VRR use for detection of human brain the control and gliomas of three grades. From the RR spectra additional two molecular vibrational biomarkers at 1129cm^-1 and 1338cm^-1, for the four types of brain tissues are significantly different in intensity. The new RR spectral peaks can be used as molecular biomarkers to evaluate glioma grades and identify the margin of gliomas from the controls. The metabolic process of glioma cells based on the RR spectral changes may reveal the Warburg hypothesis.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/088-024-165-475-100, pop00126
Keywords: 532nm; Biomarkers; Brain; Human brain tumors; Medical imaging; Raman probe; Raman spectroscopy; Resonance Raman; Tumors; Visible resonance Raman (VRR); confical Raman probe; dept.phy; gliomas; human brain tumor

In-situ Star Formation in the Outskirts of the Large Magellanic Cloud: Gaia DR2 Confirmation. - Casetti-Dinescu, Dana I; Girard, Terrence M; Bidin, Christian Moni; Zhang, Lan; Mendez, Rene A; Vieira, Katherine; Korchagin, Vladimir I; van Altena, William F (The Astrophysical journal, 2018)
We explore the Gaia data release 2 (DR2) proper motions of six young, main-sequence stars, members of the Large Magellanic Cloud (LMC) reported by Moni Bidin et al. These stars are located in the outskirts of the disk, between 7degree and 13degree from the LMC's center where there is very low H I content. Gaia DR2 proper motions confirm that four stars formed locally, in situ, while two are consistent with being expelled via dynamical interactions from inner, more gas-rich regions of the LMC. This finding establishes that recent star formation occurred in the periphery of the LMC, where thus far only old populations were known.
1 citations (Crossref) [2023-10-31] Place: United States Casetti-Dinescu, Dana I. Physics Department, Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, USA; dana.casetti@gmail.com. Casetti-Dinescu, Dana I. Astronomical Institute of the Romanian Academy, str. Cutitul de Argint 5, Bucharest, Romania. Casetti-Dinescu, Dana I. Radiology and Biomedical Imaging, Yale School of Medicine, 300 Cedar Street, New Haven, 06519, USA. Girard, Terrence M. Dunn Road, Hamden, CT 06518, USA. Bidin, Christian Moni. Instituto de Astronomia, Universidad Catolica del Norte, Av. Angomos 0610, Antofagasta, Chile. Zhang, Lan. Key Lab of Optical Astronomy, National Astronomical Observatories, CAS, 20A Datun Road, Chaoyang District, 100012 Beijing, People's Republic of China. Mendez, Rene A. Departamento de Astronomia Universidad de Chile, Camino El observatorio #1515, Las Condes, Santiago, Chile. Vieira, Katherine. Centro de Investigaciones de Astronomia, Apartado Postal 264, Merida 5101-A, Venezuela. Korchagin, Vladimir I. Institute of Physics, Southern Federal University, Stachki st. 194, 344090, Rostov-on-Don, Russia. van Altena, William F. Astronomy Department, Yale University, 46 Hillhouse Avenue, New Haven, CT 06511, USA.
Keywords: Magellanic Clouds; dept.phy; stars: early-type; stars: kinematics and dynamics

High-resolution speckle imaging - Howell, Steve B.; Horch, Elliott P. (Physics Today, 2018)
3 citations (Crossref) [2023-10-31]
Keywords: dept.phy

A Rapid Method Based on Fluorescence Spectroscopy for Meat Spoilage Detection - Wu, Binlin; Dahlberg, Kevin; Gao, Xin; Smith, Jason; Bailin, Jacob (International Journal of High Speed Electronics and Systems, 2018)
Food spoilage is mainly caused by microorganisms, such as bacteria. In this study, we measure the autofluorescence in meat samples longitudinally over a week in an attempt to develop a method to rapidly detect meat spoilage using fluorescence spectroscopy. Meat food is a biological tissue, which contains intrinsic fluorophores, such as tryptophan, collagen, nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD) etc. As meat spoils, it undergoes various morphological and chemical changes. The concentrations of the native fluorophores present in a sample may change. In particular, the changes in NADH and FAD are associated with microbial metabolism, which is the most important process of the bacteria in food spoilage. Such changes may be revealed by fluorescence spectroscopy and used to indicate the status of meat spoilage. Therefore, such native fluorophores may be unique, reliable and non-subjective indicators for detection of spoiled meat. The results of the study show that the relative concentrations of all above fluorophores change as the meat samples kept in room temperature (~19°C) spoil. The changes become more rapidly after about two days. For the meat samples kept in a freezer (~ -12°C), the changes are much less or even unnoticeable over a-week-long storage.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-150-261-026-674, pop00221 tex.type: [object Object]
Keywords: Amino acids; Autofluorescence; Bacteria; Biological tissues; Collagen; Flavin adenine dinucleotide; Fluorescence; Fluorescence spectroscopy; Fluorophores; Food microbiology; Meats; Metabolism; Microbial metabolism; NADH; Nicotinamide adenine dinucleotides; Nucleotides; Relative concentration; Spoilage; bacteria; collagen; dept.phy; fluorescence spectroscopy; meat food; microbial metabolism; peer-reviewed; tryptophan

Optical biopsy for prostate cancer diagnosis using fluorescence spectroscopy - Wu, Binlin; Gao, Xin; Smith, Jason (International Journal of High Speed Electronics and Systems, 2018)
Native fluorescence spectra are acquired from fresh normal and cancerous human prostate tissues. The fluorescence data are analyzed using an unsupervised machine learning algorithm such as non-negative matrix factorization. The nonnegative spectral components are retrieved and attributed to the native fluorophores such as collagen, reduced nicotinamide adenine dinucleotide (NADH), and flavin adenine dinucleotide (FAD) in tissue. The retrieved scores of the components are used to estimate the relative concentrations of the native fluorophores such as NADH and FAD and the redox ratio. A supervised machine learning algorithm such as support vector machine (SVM) is used to classify normal and cancerous tissue samples based on either the relative concentrations of NADH and FAD or the redox ratio alone. Various statistical measures such as sensitivity, specificity, and accuracy, along with the area under receiver operating characteristic (ROC) curve are used to show the classification performance. A cross validation method such as leave-one-out is used to further evaluate the predictive performance of the SVM classifier to avoid bias due to overfitting, and the accuracy was found to be 93.3%.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/140-001-317-060-791, pop00222 tex.type: [object Object]
Keywords: Biopsy; Diseases; FAD; Factorization; Fluorescence; Fluorescence spectroscopy; Fluorophores; Learning algorithms; Learning systems; Machine learning; Matrix algebra; NADH; Nonnegative matrix factorization; Nucleotides; Optical biopsies; Optical emission spectroscopy; Prostate cancer; Prostate cancers; Redox ratio; Supervised learning; Support vector machines; Tissue; Urology; dept.phy; fluorescence spectroscopy; intrinsic tissue emission; machine learning; nonnegative matrix factorization; optical biopsy; peer-reviewed; redox ratio; support vector machine

275 candidates and 149 validated planets orbiting bright stars in K 2 campaigns 0–10 - Mayo, Andrew W.; Vanderburg, Andrew; Latham, David W.; Bieryla, Allyson; Morton, Timothy D.; Buchhave, Lars A.; Dressing, Courtney D.; Beichman, Charles; Berlind, Perry; Calkins, Michael L.; Ciardi, David R.; Crossfield, Ian J. M.; et al. (The Astronomical Journal, 2018)
Since 2014, NASA's K2 mission has observed large portions of the ecliptic plane in search of transiting planets and has detected hundreds of planet candidates. With observations planned until at least early 2018, K2 will continue to identify more planet candidates. We present here 275 planet candidates observed during Campaigns 0-10 of the K2 mission that are orbiting stars brighter than 13 mag (in Kepler band) and for which we have obtained high-resolution spectra (R = 44,000). These candidates are analyzed using the vespa package in order to calculate their false-positive probabilities (FPP). We find that 149 candidates are validated with an FPP lower than 0.1%, 39 of which were previously only candidates and 56 of which were previously undetected. The processes of data reduction, candidate identification, and statistical validation are described, and the demographics of the candidates and newly validated planets are explored. We show tentative evidence of a gap in the planet radius distribution of our candidate sample. Comparing our sample to the Kepler candidate sample investigated by Fulton et al., we conclude that more planets are required to quantitatively confirm the gap with K2 candidates or validated planets. This work, in addition to increasing the population of validated K2 planets by nearly 50% and providing new targets for follow-up observations, will also serve as a framework for validating candidates from upcoming K2 campaigns and the Transiting Exoplanet Survey Satellite, expected to launch in 2018. © 2018. The American Astronomical Society. All rights reserved.
114 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-080-708-221-69X, pop00001, pop00002 tex.type: [object Object]
Keywords: dept.phy; methods: data analysis; peer-reviewed; planets and satellites: detection; techniques: photometric

Chemical abundances in the leading arm of the Magellanic stream - Fox, Andrew J.; Barger, Kathleen A.; Wakker, Bart P.; Richter, Philipp; Antwi-Danso, Jacqueline; Casetti-Dinescu, Dana I.; Howk, J. Christopher; Lehner, Nicolas; D’Onghia, Elena; Crowther, Paul A.; Lockman, Felix J. (The Astrophysical Journal, 2018)
The Leading Arm (LA) of the Magellanic Stream is a vast debris field of H i clouds connecting the Milky Way and the Magellanic Clouds. It represents an example of active gas accretion onto the Galaxy. Previously, only one chemical abundance measurement had been made in the LA. Here we present chemical abundance measurements using Hubble Space Telescope/Cosmic Origins Spectrograph and Green Bank Telescope spectra of four AGN sightlines passing through the LA and three nearby sightlines that may trace outer fragments of the LA. We find low oxygen abundances, ranging from 4.0-2.0+2.0% solar to 12.6-4.16.0% solar, in the confirmed LA directions, with the lowest values found in the region known as LA III, farthest from the LMC. These abundances are substantially lower than the single previous measurement, S/H =35 ±7% solar, but are in agreement with those reported in the SMC filament of the trailing Stream, supporting a common origin in the SMC (not the LMC) for the majority of the LA and trailing Stream. This provides important constraints for models of the formation of the Magellanic System. Finally, two of the three nearby sightlines show high-velocity clouds with H i columns, kinematics, and oxygen abundances consistent with LA membership. This suggests that the LA is larger than traditionally thought, extending at least 20° further to the Galactic northwest. © 2018. The American Astronomical Society. All rights reserved.
21 citations (Crossref) [2023-10-31] Citation Key Alias: pop00052 tex.type: [object Object]
Keywords: Galaxy: evolution; Galaxy: halo; ISM: abundances; Magellanic Clouds; dept.phy; quasars: absorption lines

Resonance raman imaging for detecting and monitoring molecular pathological changes in human brain tumors related to Warburg effect - Zhou, Yan; Liu, Cheng-hui; Zhu, Ke; Zhang, Chunyuan; Yang, Yang; Yu, Xinguang; Hu, Hailong; Cheng, Gangge; Wu, Binlin; Shi, Lingyan; Alfano, Robert R. (Optical Biopsy XVI: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2018)
The goal of the research is to determine the prognostic molecular pathological changes in components and composition, for human brain glioma gradings in comparison with normal tissues in three-dimensional Raman imaging profiles by visible Resonance Raman (VRR) imaging. VRR images from twenty-five specimens including three healthy tissues, one normal control, and twenty-one glioma tissues of grades II, II-III and III-IV with histology examination were measured and investigated using WITec300R confocal micro Raman imaging system with laser excitation of 532nm. Two-dimensional RR spectral mappings performed in 20μm x 20μm generated 400 images which integrated the intensity of the specific biochemical bonds as the third dimension. The three-dimension (3D) map demonstrated the spatial distributions of three selected sets of RR spectra of molecular biomarkers, and revealed significant differences in the spectra between normal and glioma tissues of different grades due to the composition changes in key molimageecules. These RR molecular spectral fingerprints have displayed: a clear enhancement of RR vibrational modes at 1129-1131cm^-1 and 2934cm^-1 which are supposed to be arising from lipoproteins; evident decreased RR vibrational modes at 1442cm^-1 and 2854cm^-1 which are from saturated fatty acids bonds in all-grades of glioma brain tissues compared with normal tissues; and the enhanced RR spectral modes of 1129 cm^-1 and 2938cm^-1 which suggest contribution from lactate. These findings may provide a novel proof for anaerobic glycolysis metabolic process in brain glioma cancer tissues that has been explained by Warburg effects.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/111-483-027-715-094, pop00057
Keywords: 2-d imaging; 2D imaging; Biopsy; Brain; Gliomas; Histology; Human Brain Tissues; Human brain; Laser excitation; Molecular imaging; Resonance; Resonance Raman; Saturated fatty acids; Tumors; Visible resonance Raman (VRR); Warburg effect; Warburg effects; dept.phy

Statistical analysis and machine learning algorithms for optical biopsy - Wu, Binlin; Liu, Cheng-hui; Boydston-White, Susie; Beckman, Hugh; Sriramoju, Vidyasagar; Sordillo, Laura; Zhang, Chunyuan; Zhang, Lin; Shi, Lingyan; Smith, Jason; Bailin, Jacob; Alfano, Robert R. (Optical Biopsy XVI: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2018)
Analyzing spectral or imaging data collected with various optical biopsy methods is often times difficult due to the complexity of the biological basis. Robust methods that can utilize the spectral or imaging data and detect the characteristic spectral or spatial signatures for different types of tissue is challenging but highly desired. In this study, we used various machine learning algorithms to analyze a spectral dataset acquired from human skin normal and cancerous tissue samples using resonance Raman spectroscopy with 532nm excitation. The algorithms including principal component analysis, nonnegative matrix factorization, and autoencoder artificial neural network are used to reduce dimension of the dataset and detect features. A support vector machine with a linear kernel is used to classify the normal tissue and cancerous tissue samples. The efficacies of the methods are compared.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/030-448-994-607-54X, pop00047
Keywords: Artificial neural network; Biological basis; Biopsy; Cancer diagnosis; Cancerous tissues; Factorization; Learning algorithms; Learning systems; Least squares approximations; Machine learning; Matrix algebra; Neural networks; Nonnegative matrix factorization; Optical biopsies; Optical biopsy; Partial least square (PLS); Partial least squares; Principal component analysis; Resonance Raman spectroscopy; Spatial signature; Support vector machine; Support vector machines; Tissue; Tissue engineering; dept.phy

Characterization and discrimination of human breast cancer and normal breast tissues using resonance Raman spectroscopy - Wu, Binlin; Smith, Jason; Zhang, Lin; Gao, Xin; Alfano, Robert R. (Optical Biopsy XVI: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2018)
Worldwide breast cancer incidence has increased by more than twenty percent in the past decade. It is also known that in that time, mortality due to the affliction has increased by fourteen percent. Using optical-based diagnostic techniques, such as Raman spectroscopy, has been explored in order to increase diagnostic accuracy in a more objective way along with significantly decreasing diagnostic wait-times. In this study, Raman spectroscopy with 532-nm excitation was used in order to incite resonance effects to enhance Stokes Raman scattering from unique biomolecular vibrational modes. Seventy-two Raman spectra (41 cancerous, 31 normal) were collected from nine breast tissue samples by performing a ten-spectra average using a 500-ms acquisition time at each acquisition location. The raw spectral data was subsequently prepared for analysis with background correction and normalization. The spectral data in the Raman Shift range of 750- 2000 cm-1 was used for analysis since the detector has highest sensitivity around in this range. The matrix decomposition technique nonnegative matrix factorization (NMF) was then performed on this processed data. The resulting leave-oneout cross-validation using two selective feature components resulted in sensitivity, specificity and accuracy of 92.6%, 100% and 96.0% respectively. The performance of NMF was also compared to that using principal component analysis (PCA), and NMF was shown be to be superior to PCA in this study. This study shows that coupling the resonance Raman spectroscopy technique with subsequent NMF decomposition method shows potential for high characterization accuracy in breast cancer detection.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/106-835-441-234-339, pop00115
Keywords: Background correction; Biopsy; Breast Cancer; Breast cancer; Breast cancer detection; Cancer diagnosis; Couplings; Decomposition methods; Diagnostic techniques; Diseases; Factorization; Learning systems; Machine learning; Matrix algebra; Molecular optical pathology; Nonnegative matrix factorization; Principal component analysis; Principal component analysis (PCA); Raman scattering; Raman spectroscopy; Resonance; Resonance Raman spectroscopy; Spectrum analysis; Support vector machine; Support vector machines; Tissue; dept.phy

Azimuthal transverse single-spin asymmetries of inclusive jets and charged pions within jets from polarized-proton collisions at √s = 500 GeV - STAR Collaboration (Physical Review D, 2018)
We report the first measurements of transverse single-spin asymmetries for inclusive jet and jet+π± production at midrapidity from transversely polarized proton-proton collisions at √s=500 GeV. The data were collected in 2011 with the STAR detector sampled from 23 pb−1 integrated luminosity with an average beam polarization of 53%. Asymmetries are reported for jets with transverse momenta 6<pT<55 GeV/c and pseudorapidity |η|<1. Presented are measurements of the inclusive-jet azimuthal transverse single-spin asymmetry, sensitive to twist-3 initial-state quark-gluon correlators; the Collins asymmetry, sensitive to quark transversity coupled to the polarized Collins fragmentation function; and the first measurement of the “Collins-like” asymmetry, sensitive to linearly polarized gluons. Within the present statistical precision, inclusive-jet and Collins-like asymmetries are small, with the latter allowing the first experimental constraints on gluon linear polarization in a polarized proton. At higher values of jet transverse momenta, we observe the first nonzero Collins asymmetries in polarized-proton collisions, with a statistical significance of greater than 5σ. The results span a range of x similar to results from semi-inclusive deep-inelastic scattering but at much higher Q2. The Collins results enable tests of universality and factorization breaking in the transverse momentum-dependent formulation of perturbative quantum chromodynamics.
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-453-906-912-066, pop00015 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed

Proper motion of the Sextans dwarf galaxy from Subaru Suprime-Cam data - Casetti-Dinescu, Dana I.; Girard, Terrence M.; Schriefer, Michael (Monthly Notices of the Royal Astronomical Society, 2018)
We have measured the absolute proper motion of the Sextans dwarf spheroidal galaxy using Subaru Suprime-Cam images taken at three epochs, with a time baseline of ~10 yr. We astrometrically calibrate each epoch by constructing distortion-correction 'maps' from the best available Subaru Suprime-Cam dithered data sets and from Gaia Data Release 1 positions. The magnitude limit of the proper motion study is V ~ 24. The area covered is 26.7 × 23.3 arcmin2, which is still within the core radius of Sextans. The derived proper motion is (μα, μδ) = (-0.409 ± 0.050, -0.047 ± 0.058) mas yr-1. The direction of motion is perpendicular to the major axis of the galaxy. Our measurement, combined with radial velocity and distance from the literature, implies a low eccentricity orbit, with a moderate inclination to the Galactic plane, and a period of 3 Gyr. Sextans is now some 0.4 Gyr away from its pericentre (rperi ~ 75 kpc), moving towards its apocentre (rapo ~ 132 kpc). Its orbit is inconsistent with membership to the vast polar structure of Galactic satellites. © 2018 The Author(s).
14 citations (Crossref) [2023-10-31]
Keywords: Astrometry; Galaxies: dwarf; Galaxies: individual: Sextans; Proper motions; dept.phy; peer-reviewed

High performance materials and devices for high-speed electronic systems - Jain, F; Broadbridge, C; Tang, H; Gherasimova, M (World Scientific Publishing Co. Pte. Ltd., 2018)
In this review volume, the editors have included the state-of-the-art research and development in nano composites, and optical electronics written by experts in the field. In addition, it also covers applications for emerging technologies in High-Speed Electronics. In summary, topics covered in this volume includes various aspects of high performance materials and devices for implementing High-Speed Electronic systems. © 2019 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.
Keywords: Emerging technologies; High performance material; High-speed electronics; Materials; Nanocomposites; Optical electronics; State of the art; dept.phy

Exploring multiphoton microscopy as a novel tool to differentiate chromophobe renal cell carcinoma from oncocytoma in fixed tissue sections - Jain, Manu; Robinson, Brian D.; Wu, Binlin; Khani, Francesca; Mukherjee, Sushmita (Archives of Pathology & Laboratory Medicine, 2018)
Context.-Distinguishing chromophobe renal cell carcinoma (chRCC), especially in the presence of eosinophilic cytoplasm, from oncocytoma on hematoxylin-eosin can be difficult and often requires time-consuming ancillary procedures that ultimately may not be informative. Objective.-To explore the potential of multiphoton microscopy (MPM) as an alternative and rapid diagnostic tool in differentiating oncocytoma from chRCC at subcellular resolution without tissue processing. Design.-Unstained, deparaffinized tissue sections from 27 tumors (oncocytoma [n = 12], chRCC [n = 12], eosinophilic variant of chRCC [n = 1], and atypical oncocytic renal neoplasm [n = 2]) were imaged with MPM. Morphologic evaluation and automated quantitative morphometric analysis were conducted to distinguish between chRCC and oncocytoma. Results.-The typical cases of oncocytomas (12 of 12) and chRCC (12 of 12) could be readily differentiated on MPM based on the morphologic features similar to hematoxylin-eosin. The most striking MPM signature of both of the tumors was the presence of autofluorescent intracytoplasmic granules, which are not seen on hematoxylin-eosin-stained slides. Although we saw these granules in both types of tumors, they appeared distinct, based on their size, shape, cytoplasmic distribution, and autofluorescence wavelengths, and were valuable in arriving at a definitive diagnosis. For oncocytomas and chRCC, high diagnostic accuracies of 100% and 83.3% were achieved on blinded MPM and morphometric analysis, respectively. Conclusions.-To the best of our knowledge, this is the first demonstration of MPM to distinguish chRCC from oncocytoma in fixed tissues. Our study was limited by small sample size and only a few variants of oncocytic tumors. Prospective studies are warranted to assess the utility of MPM as a diagnostic aid in oncocytic renal tumors. © Copyright 2018 College of American Pathologists.
19 citations (Crossref) [2023-10-31]
Keywords: Adenoma; Oxyphilic; Carcinoma; Renal Cell; Diagnosis; Differential; Humans; Kidney Neoplasms; Microscopy; Fluorescence; Multiphoton; Tissue Fixation; dept.phy; differential diagnosis; human; kidney tumor; multiphoton microscopy; oncocytoma; pathology; peer-reviewed; procedures; renal cell carcinoma; tissue fixation

Assessment of basal cell carcinoma from normal human skin tissues using Resonance Raman spectroscopy - Liu, Chenghui; Wu, Binlin; Sordillo, Laura A; Boydstonwhite, Susie; Sriramoju, Vidyasagar; Zhang, Chunyuan; Beckman, Hugh; Zhang, Lin; Pei, Zhe; Shi, Lingyan; Alfano, R R (Frontiers in Optics, 2018)
VRR spectroscopy was used for BCC and normal skin tissues with 532nm excitation. The spectra showed significant changes in collagen, carotenoids and lipids. These enhanced fingerprints demonstrate a potential use as label-free pathology method. © 2018 The Author(s).
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-291-504-672-46X tex.type: [object Object]
Keywords: Basal cell carcinoma; Histology; Human skin; Label free; Normal skin; Resonance Raman spectroscopy; Tissue; dept.phy

A pilot study for distinguishing chromophobe renal cell carcinoma and oncocytoma using second harmonic generation imaging and convolutional neural network analysis of collagen fibrillar structure - Wu, Binlin; Judd, Nicolas; Smith, Jason; Icaza, Michael; Mukherjee, Sushmita; Jain, Manu; Gallagher, Ryan M; Szeligowski, Richard V (Optical Biopsy XVI: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2018)
A clear distinction between oncocytoma and chromophobe renal cell carcinoma (chRCC) is critically important for clinical management of patients. But it may often be difficult to distinguish the two entities based on hematoxylin and eosin (H and E) stained sections alone. In this study, second harmonic generation (SHG) signals which are very specific to collagen were used to image collagen fibril structure. We conduct a pilot study to develop a new diagnostic method based on the analysis of collagen associated with kidney tumors using convolutional neural networks (CNNs). CNNs comprise a type of machine learning process well-suited for drawing information out of images. This study examines a CNN model's ability to differentiate between oncocytoma (benign), and chRCC (malignant) kidney tumor images acquired with second harmonic generation (SHG), which is very specific for collagen matrix. To the best of our knowledge, this is the first study that attempts to distinguish the two entities based on their collagen structure. The model developed from this study demonstrated an overall classification accuracy of 68.7% with a specificity of 66.3% and sensitivity of 74.6%. While these results reflect an ability to classify the kidney tumors better than chance, further studies will be carried out to (a) better realize the tumor classification potential of this method with a larger sample size and (b) combining SHG with two-photon excited intrinsic fluorescence signal to achieve better classification. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/110-186-936-817-103
Keywords: Biomedical signal processing; Biopsy; Chromophobe renal cell carcinoma; Classification accuracy; Collagen; Convolution; Convolutional Neural Networks (CNN); Convolutional neural network; Convolutional neural networks (CNN); Fluorescence; Harmonic analysis; Harmonic generation; Intrinsic fluorescence signals; Kidney tumor; Learning systems; Machine learning; Multiphoton microscopy; Multiphoton microscopy (MPM); Multiphoton processes; Neural networks; Nonlinear optics; Patient monitoring; Renal cell carcinoma; Renal oncocytoma; Second harmonic generation; Tumor classification; Tumors; dept.phy

Diagnosis of glioma brain cancer using visible resonance Raman spectroscopy - Zhou, Yan; Wu, Binlin; Liu, Chenghui; Yu, Xinguang; Cheng, Gangge; Wang, Kai; Zhang, Chunyuan; Shi, Lingyan; Alfano, R R (Frontiers in Optics / Laser Science (2018), paper JW4A.3, 2018)
Resonance Raman spectroscopy using 532nm excitation was used to distinguish normal brain tissue from different grades of glioma tissues. Principal component analysis was used to analyze the spectral data and achieved high accuracy. © 2018 The Author(s).
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/090-574-865-473-542
Keywords: Brain cancer; Brain tissue; Different grades; Glioma tissues; High-accuracy; Principal component analysis; Raman spectroscopy; Resonance Raman spectroscopy; Spectral data; Tumors; dept.phy

A search for binary star companions to the KELT planet hosts and a comparison sample. i. results of DSSI observations - Coker, Carl T.; Gaudi, B. Scott; Pogge, Richard W.; Horch, Elliott (The Astronomical Journal, 2017)
We are conducting a search for binary companions around 11 hot-Jupiter hosts from the Kilodegree Extremely Little Telescope (KELT) survey and a large comparison sample of stars shown by KELT to not host a transiting hot Jupiter. The primary stars are bright (7.5 < V < 11) and of similar distance from Earth (100 < d < 300 pc). In this paper, we present the results of our observations using the Differential Speckle Survey Instrument. We observed 9 of the 14 KELT planet hosts that are visible from the northern hemisphere and 51 comparison stars, discovering two new potential companions and re-observing two previously known possible binary systems and one confirmed binary system. We provide an estimate of the chance alignment probability for our observed candidate binaries. © 2017 The American Astronomical Society. All rights reserved.
3 citations (Crossref) [2023-10-31]
Keywords: Astrometry; binaries: close; binaries: general; dept.phy; peer-reviewed; planets and satellites: detection; planets and satellites: formation

Validation of small Kepler transiting planet candidates in or near the habitable zone - Torres, Guillermo; Kane, Stephen R.; Rowe, Jason F.; Batalha, Natalie M.; Henze, Christopher E.; Ciardi, David R.; Barclay, Thomas; Borucki, William J.; Buchhave, Lars A.; Crepp, Justin R.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2017)
A main goal of NASA's Kepler Mission is to establish the frequency of potentially habitable Earth-size planets (). Relatively few such candidates identified by the mission can be confirmed to be rocky via dynamical measurement of their mass. Here we report an effort to validate 18 of them statistically using the BLENDER technique, by showing that the likelihood they are true planets is far greater than that of a false positive. Our analysis incorporates follow-up observations including high-resolution optical and near-infrared spectroscopy, high-resolution imaging, and information from the analysis of the flux centroids of the Kepler observations themselves. Although many of these candidates have been previously validated by others, the confidence levels reported typically ignore the possibility that the planet may transit a star different from the target along the same line of sight. If that were the case, a planet that appears small enough to be rocky may actually be considerably larger and therefore less interesting from the point of view of habitability. We take this into consideration here and are able to validate 15 of our candidates at a 99.73% (3σ) significance level or higher, and the other three at a slightly lower confidence. We characterize the GKM host stars using available ground-based observations and provide updated parameters for the planets, with sizes between 0.8 and 2.9 R ⊕. Seven of them (KOI-0438.02, 0463.01, 2418.01, 2626.01, 3282.01, 4036.01, and 5856.01) have a better than 50% chance of being smaller than 2 R ⊕ and being in the habitable zone of their host stars. © 2017. The American Astronomical Society. All rights reserved..
20 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/052-258-082-978-883, pop00029 tex.type: [object Object]
Keywords: dept.phy; methods: statistical; peer-reviewed; planetary systems; stars: individual (KOI-0172.02 = Kepler-69c ...); techniques: photometric

Characterizing K2 candidate planetary systems orbiting Low-mass stars. II. Planetary Systems observed during campaigns 1–7 - Dressing, Courtney D.; Vanderburg, Andrew; Schlieder, Joshua E.; Crossfield, Ian J. M.; Knutson, Heather A.; Newton, Elisabeth R.; Ciardi, David R.; Fulton, Benjamin J.; Gonzales, Erica J.; Howard, Andrew W.; Isaacson, Howard; Livingston, John; et al. (The Astronomical Journal, 2017)
We recently used near-infrared spectroscopy to improve the characterization of 76 low-mass stars around which K2 had detected 79 candidate transiting planets. 29 of these worlds were new discoveries that had not previously been published. We calculate the false positive probabilities that the transit-like signals are actually caused by non-planetary astrophysical phenomena and reject five new transit-like events and three previously reported events as false positives. We also statistically validate 17 planets (7 of which were previously unpublished), confirm the earlier validation of 22 planets, and announce 17 newly discovered planet candidates. Revising the properties of the associated planet candidates based on the updated host star characteristics and refitting the transit photometry, we find that our sample contains 21 planets or planet candidates with radii smaller than 1.25 R ⊕, 18 super-Earths (1.25-2 R ⊕), 21 small Neptunes (2-4 R ⊕), three large Neptunes (4-6 R ⊕), and eight giant planets (>6 R ⊕). Most of these planets are highly irradiated, but EPIC 206209135.04 (K2-72e, ), EPIC 211988320.01 (), and EPIC 212690867.01 () orbit within optimistic habitable zone boundaries set by the "recent Venus" inner limit and the "early Mars" outer limit. In total, our planet sample includes eight moderately irradiated 1.5-3 R ⊕ planet candidates (F p ≲ 20 F ⊕) orbiting brighter stars (Ks < 11) that are well-suited for atmospheric investigations with the Hubble, Spitzer, and/or James Webb Space Telescopes. Five validated planets orbit relatively bright stars (Kp < 12.5) and are expected to yield radial velocity semi-amplitudes of at least 2 m s-1. Accordingly, they are possible targets for radial velocity mass measurement with current facilities or the upcoming generation of red optical and near-infrared high-precision RV spectrographs. © 2017. The American Astronomical Society. All rights reserved..
68 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed; planetary systems; planets and satellites: fundamental parameters; stars: fundamental parameters; stars: late-type; stars: low-mass; techniques: spectroscopic

Investigating local parity violation in heavy-ion collisions using Λ helicity - Finch, L. E.; Murray, S. J. (Physical Review C, 2017)
We propose the measurement of net Λ and Λ helicity, correlated event by event with the magnitude and sign of charge separation along the event's magnetic field direction, as a probe to investigate the chiral magnetic effect (CME) in heavy-ion collisions. With a simple simulation model of heavy-ion events that includes effects of local parity violation, we estimate the experimental correlation signal that could be expected at RHIC given the results of previous measurements that are sensitive to the CME. © 2017 American Physical Society.
8 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Bulk properties of the medium produced in relativistic heavy-ion collisions from the beam energy scan program - STAR Collaboration (Physical Review C, 2017)
We present measurements of bulk properties of the matter produced in Au+Au collisions at √sNN=7.7,11.5,19.6,27, and 39 GeV using identified hadrons (π±, K±, p, and ¯p) from the STAR experiment in the Beam Energy Scan (BES) Program at the Relativistic Heavy Ion Collider (RHIC). Midrapidity (|y|<0.1) results for multiplicity densities dN/dy, average transverse momenta ⟨pT⟩, and particle ratios are presented. The chemical and kinetic freeze-out dynamics at these energies are discussed and presented as a function of collision centrality and energy. These results constitute the systematic measurements of bulk properties of matter formed in heavy-ion collisions over a broad range of energy (or baryon chemical potential) at RHIC.
332 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Exclusion of stellar companions to exoplanet host stars - Wittrock, Justin M.; Kane, Stephen R.; Horch, Elliott P.; Howell, Steve B.; Ciardi, David R.; Everett, Mark E. (The Astronomical Journal, 2017)
Given the frequency of stellar multiplicity in the solar neighborhood, it is important to study the impacts this can have on exoplanet properties and orbital dynamics. There have been numerous imaging survey projects established to detect possible low-mass stellar companions to exoplanet host stars. Here, we provide the results from a systematic speckle imaging survey of known exoplanet host stars. In total, 71 stars were observed at 692 and 880 nm bands using the Differential Speckle Survey Instrument at the Gemini-north Observatory. Our results show that all but two of the stars included in this sample have no evidence of stellar companions with luminosities down to the detection and projected separation limits of our instrumentation. The mass-luminosity relationship is used to estimate the maximum mass a stellar companion can have without being detected. These results are used to discuss the potential for further radial velocity follow-up and interpretation of companion signals. © 2017. The American Astronomical Society. All rights reserved..
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-303-042-496-092, pop00140 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution

Energy dependence of J/ψ production in Au + Au collisions at √sNN=39,62.4 and 200GeV - STAR Collaboration (Physics Letters B, 2017)
The inclusive J/ψ transverse momentum spectra and nuclear modification factors are reported at mid-rapidity (|y|<1.0) in Au + Au collisions at sNN = 39, 62.4 and 200 GeV taken by the STAR experiment. A suppression of J/ψ production, with respect to the production in p+p scaled by the number of binary nucleon–nucleon collisions, is observed in central Au + Au collisions at these three energies. No significant energy dependence of nuclear modification factors is found within uncertainties. The measured nuclear modification factors can be described by model calculations that take into account both suppression of direct J/ψ production due to the color screening effect and J/ψ regeneration from recombination of uncorrelated charm–anticharm quark pairs. © 2017 The Author
28 citations (Crossref) [2023-10-31] Citation Key Alias: pop00010 tex.ids: [object Object] tex.type: [object Object]
Keywords: dept.phy; peer-reviewed

Direct virtual photon production in Au+Au collisions at √sNN=200 GeV - STAR Collaboration (Physics Letters B, 2017)
We report the direct virtual photon invariant yields in the transverse momentum ranges 1<pT<3 GeV/c and 5<pT<10 GeV/c at mid-rapidity derived from the dielectron invariant mass continuum region 0.10<Mee<0.28 GeV/c2 for 0–80% minimum-bias Au+Au collisions at sNN=200 GeV. A clear excess in the invariant yield compared to the nuclear overlap function TAA scaled p+p reference is observed in the pT range 1<pT<3 GeV/c. For pT>6 GeV/c the production follows TAA scaling. Model calculations with contributions from thermal radiation and initial hard parton scattering are consistent within uncertainties with the direct virtual photon invariant yield. © 2017 The Author
34 citations (Crossref) [2023-10-31] Citation Key Alias: pop00009 tex.ids: [object Object] tex.type: [object Object]
Keywords: dept.phy; peer-reviewed

Determination of critical cooling rates in metallic glass forming alloy libraries through laser spike annealing. - Bordeenithikasem, Punnathat; Liu, Jingbei; Kube, Sebastian A; Li, Yanglin; Ma, Tianxing; Scanley, B Ellen; Broadbridge, Christine C; Vlassak, Joost J; Singer, Jonathan P; Schroers, Jan (Scientific reports, 2017)
The glass forming ability (GFA) of metallic glasses (MGs) is quantified by the critical cooling rate (R C). Despite its key role in MG research, experimental challenges have limited measured R C to a minute fraction of known glass formers. We present a combinatorial approach to directly measure R C for large compositional ranges. This is realized through the use of compositionally-graded alloy libraries, which were photo-thermally heated by scanning laser spike annealing of an absorbing layer, then melted and cooled at various rates. Coupled with X-ray diffraction mapping, GFA is determined from direct R C measurements. We exemplify this technique for the Au-Cu-Si system, where we identify Au56Cu27Si17 as the alloy with the highest GFA. In general, this method enables measurements of R C over large compositional areas, which is powerful for materials discovery and, when correlating with chemistry and other properties, for a deeper understanding of MG formation.
44 citations (Crossref) [2023-10-31] Place: England Bordeenithikasem, Punnathat. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Liu, Jingbei. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Kube, Sebastian A. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Li, Yanglin. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Ma, Tianxing. Department of Mechanical and Aerospace Engineering, Rutgers University, Piscataway, New Jersey, 08854, USA. Scanley, B Ellen. Department of Physics, Southern Connecticut State University, New Haven, Connecticut, 06515, USA. Broadbridge, Christine C. Department of Physics, Southern Connecticut State University, New Haven, Connecticut, 06515, USA. Vlassak, Joost J. School of Engineering and Applied Science, Harvard University, Cambridge, Massachusetts, 02138, USA. Singer, Jonathan P. Department of Mechanical and Aerospace Engineering, Rutgers University, Piscataway, New Jersey, 08854, USA. Schroers, Jan. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. jan.schroers@yale.edu. Erratum in (EIN)
Keywords: dept.phy; peer-reviewed

Global Λ hyperon polarization in nuclear collisions - STAR Collaboration (Nature, 2017)
The extreme energy densities generated by ultra-relativistic collisions between heavy atomic nuclei produce a state of matter that behaves surprisingly like a fluid, with exceptionally high temperature and low viscosity. Non-central collisions have angular momenta of the order of 1,000h, and the resulting fluid may have a strong vortical structure that must be understood to describe the fluid properly. The vortical structure is also of particular interest because the restoration of fundamental symmetries of quantum chromodynamics is expected to produce novel physical effects in the presence of strong vorticity. However, no experimental indications of fluid vorticity in heavy ion collisions have yet been found. Since vorticity represents a local rotational structure of the fluid, spin-orbit coupling can lead to preferential orientation of particle spins along the direction of rotation. Here we present measurements of an alignment between the global angular momentum of a non-central collision and the spin of emitted particles (in this case the collision occurs between gold nuclei and produces Λ baryons), revealing that the fluid produced in heavy ion collisions is the most vortical system so far observed. (At high energies, this fluid is a quark-gluon plasma.) We find that Λ and hyperons show a positive polarization of the order of a few per cent, consistent with some hydrodynamic predictions. (A hyperon is a particle composed of three quarks, at least one of which is a strange quark; the remainder are up and down quarks, found in protons and neutrons.) A previous measurement that reported a null result, that is, zero polarization, at higher collision energies is seen to be consistent with the trend of our observations, though with larger statistical uncertainties. These data provide experimental access to the vortical structure of the nearly ideal liquid created in a heavy ion collision and should prove valuable in the development of hydrodynamic models that quantitatively connect observations to the theory of the strong force. © 2017 Macmillan Publishers Limited, part of Springer Nature. All rights reserved.
512 citations (Crossref) [2023-10-31] Finch
Keywords: Article; baryon; dept.phy; gluon; heavy ion; hydrodynamics; hyperon; polarization; priority journal; proton; quantum mechanics; quark; viscosity

Measurement of d0 azimuthal anisotropy at midrapidity in Au+Au collisions at √sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2017)
We report the first measurement of the elliptic anisotropy (v2) of the charm meson D0 at midrapidity (|y|<1) in Au+Au collisions at sNN=200 GeV. The measurement was conducted by the STAR experiment at RHIC utilizing a new high-resolution silicon tracker. The measured D0 v2 in 0%-80% centrality Au+Au collisions can be described by a viscous hydrodynamic calculation for a transverse momentum (pT) of less than 4 GeV/c. The D0 v2 as a function of transverse kinetic energy (mT-m0, where mT=pT2+m02) is consistent with that of light mesons in 10%-40% centrality Au+Au collisions. These results suggest that charm quarks have achieved local thermal equilibrium with the medium created in such collisions. Several theoretical models, with the temperature-dependent, dimensionless charm spatial diffusion coefficient (2πTDs) in the range of ∼2-12, are able to simultaneously reproduce our D0 v2 result and our previously published results for the D0 nuclear modification factor. © 2017 American Physical Society.
80 citations (Crossref) [2023-10-31] Citation Key Alias: pop00003 tex.ids: [object Object] tex.type: [object Object]
Keywords: Anisotropy; Au+Au collisions; Azimuthal anisotropy; Bosons; Colliding beam accelerators; Hadrons; Hydrodynamic calculation; Kinetic energy; Kinetics; Local thermal equilibrium; Nuclear modification factors; STAR experiment; Star trackers; Temperature dependent; Transverse momenta; dept.phy

Young stars in the periphery of the Large Magellanic Cloud - Moni Bidin, C.; Casetti-Dinescu, D. I.; Girard, T. M.; Zhang, L.; Méndez, R. A.; Vieira, K.; Korchagin, V. I.; van Altena, W. F. (Monthly Notices of the Royal Astronomical Society, 2017)
Despite their close proximity, the complex interplay between the two Magellanic Clouds, the Milky Way and the resulting tidal features, is still poorly understood. Recent studies have shown that the Large Magellanic Cloud (LMC) has a very extended disc strikingly perturbed in its outskirts.We search for recent star formation in the far outskirts of the LMC, out to ~30° from its centre.We have collected intermediate-resolution spectra of 31 young star candidates in the periphery of the LMC and measured their radial velocity, stellar parameters, distance and age. Our measurements confirm membership to the LMC of six targets, for which the radial velocity and distance values match well with those of the Cloud. These objects are all young (10-50 Myr), main-sequence stars, projected between 7° and 13° from the centre of the parent galaxy. We compare the velocities of our stars with those of a disc model, and find that our stars have low to moderate velocity differences with the disc model predictions, indicating that they were formed in situ. Our study demonstrates that recent star formation occurred in the far periphery of the LMC, where thus far only old objects were known. The spatial configuration of these newly formed stars appears ring-like with a radius of 12 kpc and a displacement of 2.6 kpc from the LMC's centre. This structure, if real, would be suggestive of a star formation episode triggered by an off-centre collision between the Small Magellanic Cloud and the LMC's disc. © 2016 The Authors.
13 citations (Crossref) [2023-10-31]
Keywords: Magellanic Clouds; Stars: early-type; dept.phy; peer-reviewed

Observations of binary stars with the Differential Speckle Survey Instrument. VII. Measures from 2010 September to 2012 February at the WIYN Telescope - Horch, Elliott P.; Casetti-Dinescu, Dana I.; Camarata, Matthew A.; Bidarian, Akbar; Altena, William F. van; Sherry, William H.; Everett, Mark E.; Howell, Steve B.; Ciardi, David R.; Henry, Todd J.; Nusdeo, Daniel A.; Winters, Jennifer G. (The Astronomical Journal, 2017)
We report on speckle observations of binary stars carried out at the WIYN Telescope over the period from 2010 September through 2012 February, providing relative astrometry for 2521 observations of 883 objects, 856 of which are double stars and 27 of which are triples. The separations measured span a range of 0.01-1.75 arcsec. Wavelengths of 562, 692, and 880 nm were used, and differential photometry at one or more of these wavelengths is presented in most cases. 66 components were resolved for the first time. We also estimate detection limits at 0.2 and 1.0 arcsec for high-quality observations in cases where no companion was seen, a total of 176 additional objects. Detection limits vary based on observing conditions and signal-to-noise ratio, but are approximately 4 mag at 0.2 arcsec and 6 mag at 1.0 arcsec on average. Analyzing the measurement precision of the data set, we find that the individual separations obtained have linear measurement uncertainties of approximately 2 mas, and photometry is uncertain to approximately 0.1 mag in general. This work provides fundamental, well-calibrated data for future orbit and mass determinations, and we present three first orbits and total mass estimates of nearby K-dwarf systems as examples of this potential. © 2017. The American Astronomical Society. All rights reserved..
55 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/110-417-913-195-546, pop00017 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

HAT-P-67b: An extremely low density Saturn transiting an F-subgiant confirmed via doppler tomography - Zhou, G.; Bakos, G. Á.; Hartman, J. D.; Latham, D. W.; Torres, G.; Bhatti, W.; Penev, K.; Buchhave, L.; Kovács, G.; Bieryla, A.; Quinn, S.; Isaacson, H.; et al. (The Astronomical Journal, 2017)
We report the discovery of HAT-P-67b, which is a hot-Saturn transiting a rapidly rotating F-subgiant. HAT-P-67b has a radius of Rp=2.085 -0.071 +0.096 RJ, and orbites a M∗ = 1.642-0.072 +0.155 M, R∗ = 2.546-0.099 +0.0084 R host star in a ∼4.81 day period orbit. We place an upper limit on the mass of the planet via radial velocity measurements to be Mp < 0.59 MJ, and a lower limit of >0.056 MJ by limitations on Roche lobe overflow. Despite being a subgiant, the host star still exhibits relatively rapid rotation, with a projected rotational velocity of v sin I∗ = 35.8 ±1.1 km s-1, which makes it difficult to precisely determine the mass of the planet using radial velocities. We validated HAT-P-67b via two Doppler tomographic detections of the planetary transit, which eliminate potential eclipsing binary blend scenarios. The Doppler tomographic observations also confirm that HAT-P-67b has an orbit that is aligned to within 12, in projection, with the spin of its host star. HAT-P-67b receives strong UV irradiation and is among one of the lowest density planets known, which makes it a good candidate for future UV transit observations in the search for an extended hydrogen exosphere. © 2017. The American Astronomical Society. All rights reserved.
32 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/148-095-950-678-74X, pop00018 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planetary systems; stars: individual (HAT-P-67); techniques: photometric; techniques: spectroscopic

Using Gaia as an astrometric tool for deep ground-based surveys - Casetti-Dinescu, Dana I.; Girard, Terrence M.; Schriefer, Michael (Proceedings of the International Astronomical Union, 2017)
Gaia DR1 positions are used to astrometrically calibrate three epochs’ worth of Subaru SuprimeCam images in the fields of globular cluster NGC 2419 and the Sextans dwarf spheroidal galaxy. Distortion-correction “maps” are constructed from a combination of offset dithers and reference to Gaia DR1. These are used to derive absolute proper motions in the field of NGC 2419. Notably, we identify the photometrically-detected Monoceros structure in the foreground of NGC 2419 as a kinematically-cold population of stars, distinct from Galactic-field stars. This project demonstrates the feasibility of combining Gaia with deep, ground-based surveys, thus extending high-quality astrometry to magnitudes beyond the limits of Gaia.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/110-283-973-036-247
Keywords: Galaxy: kinematics and dynamics; astrometry; dept.phy; galaxies: dwarf

Four sub-Saturns with dissimilar densities: Windows into planetary cores and envelopes - Petigura, Erik A.; Sinukoff, Evan; Lopez, Eric D.; Crossfield, Ian J. M.; Howard, Andrew W.; Brewer, John M.; Fulton, Benjamin J.; Isaacson, Howard T.; Ciardi, David R.; Howell, Steve B.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2017)
We present results from a Keck/HIRES radial velocity campaign to study four sub-Saturn-sized planets, K2-27b, K2-32b, K2-39b, and K2-108b, with the goal of understanding their masses, orbits, and heavy-element enrichment. The planets have similar sizes (RP=4.5-5.5 ), but have dissimilar masses (MP=16-60 ), implying a diversity in their core and envelope masses. K2-32b is the least massive (MP = 16.5 ± 2.7 M) and orbits in close proximity to two sub-Neptunes near a 3:2:1 period commensurability. K2-27b and K2-39b are significantly more massive at MP = 30.9 ± 4.6 M and MP = 39.8 ± 4.4 M, respectively, and show no signs of additional planets. K2-108b is the most massive at MP = 59.4 ± 4.4 M, implying a large reservoir of heavy elements of about ≈50 . Sub-Saturns as a population have a large diversity in planet mass at a given size. They exhibit remarkably little correlation between mass and size; sub-Saturns range from ≈6-60 M, regardless of size. We find a strong correlation between planet mass and host star metallicity, suggesting that metal-rich disks form more massive planet cores. The most massive sub-Saturns tend to lack detected companions and have moderately eccentric orbits, perhaps as a result of a previous epoch of dynamical instability. Finally, we observe only a weak correlation between the planet envelope fraction and present-day equilibrium temperature, suggesting that photo-evaporation does not play a dominant role in determining the amount of gas sub-Saturns accrete from their protoplanetary disks. © 2017. The American Astronomical Society. All rights reserved..
62 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/117-273-244-483-27X, pop00045 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planets and satellites: composition; planets and satellites: detection; planets and satellites: dynamical evolution and stability; planets and satellites: formation; planets and satellites: gaseous planets; planets and satellites: interiors

Assessing the effect of stellar companions from high-resolution imaging of Kepler objects of interest - Hirsch, Lea A.; Ciardi, David R.; Howard, Andrew W.; Everett, Mark E.; Furlan, Elise; Saylors, Mindy; Horch, Elliott P.; Howell, Steve B.; Teske, Johanna; Marcy, Geoffrey W. (The Astronomical Journal, 2017)
We report on 176 close (<2″) stellar companions detected with high-resolution imaging near 170 hosts of Kepler Objects of Interest (KOIs). These Kepler targets were prioritized for imaging follow-up based on the presence of small planets, so most of the KOIs in these systems (176 out of 204) have nominal radii <6 . Each KOI in our sample was observed in at least two filters with adaptive optics, speckle imaging, lucky imaging, or the Hubble Space Telescope. Multi-filter photometry provides color information on the companions, allowing us to constrain their stellar properties and assess the probability that the companions are physically bound. We find that 60%-80% of companions within 1″ are bound, and the bound fraction is >90% for companions within 0.″5; the bound fraction decreases with increasing angular separation. This picture is consistent with simulations of the binary and background stellar populations in the Kepler field. We also reassess the planet radii in these systems, converting the observed differential magnitudes to a contamination in the Kepler bandpass and calculating the planet radius correction factor, X R = R p(true)/R p(single). Under the assumption that planets in bound binaries are equally likely to orbit the primary or secondary, we find a mean radius correction factor for planets in stellar multiples of X R = 1.65. If stellar multiplicity in the Kepler field is similar to the solar neighborhood, then nearly half of all Kepler planets may have radii underestimated by an average of 65%, unless vetted using high-resolution imaging or spectroscopy. © 2017. The American Astronomical Society. All rights reserved.
49 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/119-135-164-854-429, pop00043 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; planets and satellites: detection; planets and satellites: fundamental parameters; techniques: high angular resolution; techniques: photometric

Resonance raman of BCC and normal skin - Liu, Cheng-hui; Sriramoju, Vidyasagar; Boydston-White, Susie; Wu, Binlin; Zhang, Chunyuan; Pei, Zhe; Sordillo, Laura; M.d, Hugh Beckman; Alfano, Robert R. (Optical Biopsy XV: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2017)
The Resonance Raman (RR) spectra of basal cell carcinoma (BCC) and normal human skin tissues were analyzed using 532nm laser excitation. RR spectral differences in vibrational fingerprints revealed skin normal and cancerous states tissues. The standard diagnosis criterion for BCC tissues are created by native RR biomarkers and its changes at peak intensity. The diagnostic algorithms for the classification of BCC and normal were generated based on SVM classifier and PCA statistical method. These statistical methods were used to analyze the RR spectral data collected from skin tissues, yielding a diagnostic sensitivity of 98.7% and specificity of 79% compared with pathological reports.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/015-837-955-575-755, pop00046 tex.type: [object Object]
Keywords: Basal cell carcinoma; Basel cell carcinoma (BCC); Biopsy; Cell carcinoma; Diagnostic algorithms; Histology; Human skin; Human skin tissues; Laser excitation; Principal component analysis; Principal component analysis (PCA); Resonance; Resonance Raman spectra; Resonance Raman spectroscopy; Skin cancer; Skin cancers; Spectral differences; Statistical methods; Support vector machine (SVM); Support vector machines; Tissue; Tissue engineering; dept.phy

Rapid measurement of meat spoilage using fluorescence spectroscopy - Wu, Binlin; Dahlberg, Kevin; Gao, Xin; Smith, Jason; Bailin, Jacob (Imaging, Manipulation, and Analysis of Biomolecules, Cells, and Tissues XV, 2017)
Food spoilage is mainly caused by microorganisms, such as bacteria. In this study, we measure the autofluorescence in meat samples longitudinally over a week in an attempt to develop a method to rapidly detect meat spoilage using fluorescence spectroscopy. Meat food is a biological tissue, which contains intrinsic fluorophores, such as tryptophan, collagen, nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD) etc. As meat spoils, it undergoes various morphological and chemical changes. The concentrations of the native fluorophores present in a sample may change. In particular, the changes in NADH and FAD are associated with microbial metabolism, which is the most important process of the bacteria in food spoilage. Such changes may be revealed by fluorescence spectroscopy and used to indicate the status of meat spoilage. Therefore, such native fluorophores may be unique, reliable and nonsubjective indicators for detection of spoiled meat. The results of the study show that the relative concentrations of all above fluorophores change as the meat samples kept in room temperature (~19° C) spoil. The changes become more rapidly after about two days. For the meat samples kept in a freezer (~-12° C), the changes are much less or even unnoticeable over a-week-long storage.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/026-929-135-501-547, pop00136 tex.type: [object Object]
Keywords: Amino acids; Bacteria; Biological tissues; Biomolecules; Collagen; Flavin adenine dinucleotide; Fluorescence; Fluorescence spectroscopy; Fluorophores; Food microbiology; Histology; Meat food; Meats; Metabolism; Microbial metabolism; Molecular biology; NADH; Nicotinamide adenine dinucleotides; Nucleotides; Physiology; Rapid measurement; Relative concentration; Spectrum analysis; Spoilage; Tissue; Tryptophan; dept.phy

Optical biopsy using fluorescence spectroscopy for prostate cancer diagnosis - Wu, Binlin; Gao, Xin; Smith, Jason; Bailin, Jacob (Therapeutics and Diagnostics in Urology: Lasers, Robotics, Minimally Invasive, and Advanced Biomedical Devices, 2017)
Native fluorescence spectra are acquired from fresh normal and cancerous human prostate tissues. The fluorescence data are analyzed using a multivariate analysis algorithm such as non-negative matrix factorization. The nonnegative spectral components are retrieved and attributed to the native fluorophores such as collagen, reduced nicotinamide adenine dinucleotide (NADH), and flavin adenine dinucleotide (FAD) in tissue. The retrieved weights of the components, e.g. NADH and FAD are used to estimate the relative concentrations of the native fluorophores and the redox ratio. A machine learning algorithm such as support vector machine (SVM) is used for classification to distinguish normal and cancerous tissue samples based on either the relative concentrations of NADH and FAD or the redox ratio alone. The classification performance is shown based on statistical measures such as sensitivity, specificity, and accuracy, along with the area under receiver operating characteristic (ROC) curve. A cross validation method such as leave-one-out is used to evaluate the predictive performance of the SVM classifier to avoid bias due to overfitting.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/116-092-737-895-249, pop00138 tex.type: [object Object]
Keywords: Artificial intelligence; Biopsy; Cross validation; Diseases; Factorization; Fluorescence; Fluorescence spectroscopy; Fluorophores; Learning algorithms; Learning systems; Matrix algebra; Multivariant analysis; Nonnegative matrix factorization; Nucleotides; Optical biopsies; Prostate cancers; Redox ratio; Robotics; Support vector machines; Tissue; Urology; cross validation; dept.phy; fluorescence spectroscopy; machine learning; nonnegative matrix factorization; optical biopsy; prostate cancer; redox ratio; support vector machine

Chemical composition of young stars in the leading arm of the Magellanic system - Zhang, Lan; Moni Bidin, Christian; Casetti-Dinescu, Dana I.; Méndez, Réne A.; Girard, Terrence M.; Korchagin, Vladimir I.; Vieira, Katherine; van Altena, William F.; Zhao, Gang (The Astrophysical Journal, 2017)
Chemical abundances of eight O- and B-type stars are determined from high-resolution spectra obtained with the MIKE instrument on the Magellan 6.5 m Clay telescope. The sample is selected from 42 candidates for membership in the Leading Arm (LA) of the Magellanic System. Stellar parameters are measured by two independent grids of model atmospheres and analysis procedures, confirming the consistency of the stellar parameter results. Abundances of seven elements (He, C, N, O, Mg, Si, and S) are determined for the stars, as are their radial velocities and estimates of distances and ages. Among the seven B-type stars analyzed, the five that have radial velocities compatible with membership of the LA have an average [Mg/H] of -0.42 ±0.16, significantly lower than the average of the remaining two, [Mg/H] = -0.07 ±0.06, which are kinematical members of the Galactic disk. Among the five LA members, four have individual [Mg/H] abundance compatible with that in the LMC. Within errors, we cannot exclude the possibility that one of these stars has an [Mg/H] consistent with the more metal-poor, SMC-like material. The remaining fifth star has an [Mg/H] close to Milky Way values. Distances to the LA members indicate that they are at the edge of the Galactic disk, while ages are of the order of ∼50-70 Myr, lower than the dynamical age of the LA, suggesting a single star-forming episode in the LA. V LSR of the LA members decreases with decreasing Magellanic longitude, confirming the results of previous LA gas studies. © 2017. The American Astronomical Society. All rights reserved..
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/103-917-768-897-580, pop00058 tex.type: [object Object]
Keywords: dept.phy

The Kepler follow-up observation program. I. a catalog of companions to Kepler stars from high-resolution imaging - Furlan, E.; Ciardi, D. R.; Everett, M. E.; Saylors, M.; Teske, J. K.; Horch, E. P.; Howell, S. B.; van Belle, G. T.; Hirsch, L. A.; Gautier, T. N.; Adams, E. R.; Barrado, D.; et al. (The Astronomical Journal, 2017)
We present results from high-resolution, optical to near-IR imaging of host stars of Kepler Objects of Interest (KOIs), identified in the original Kepler field. Part of the data were obtained under the Kepler imaging follow-up observation program over six years (2009-2015). Almost 90% of stars that are hosts to planet candidates or confirmed planets were observed. We combine measurements of companions to KOI host stars from different bands to create a comprehensive catalog of projected separations, position angles, and magnitude differences for all detected companion stars (some of which may not be bound). Our compilation includes 2297 companions around 1903 primary stars. From high-resolution imaging, we find that ∼10% (∼30%) of the observed stars have at least one companion detected within 1″ (4″). The true fraction of systems with close (≲4″) companions is larger than the observed one due to the limited sensitivities of the imaging data. We derive correction factors for planet radii caused by the dilution of the transit depth: assuming that planets orbit the primary stars or the brightest companion stars, the average correction factors are 1.06 and 3.09, respectively. The true effect of transit dilution lies in between these two cases and varies with each system. Applying these factors to planet radii decreases the number of KOI planets with radii smaller than 2 R⊕ by ∼2%-23% and thus affects planet occurrence rates. This effect will also be important for the yield of small planets from future transit missions such as TESS. © 2017. The American Astronomical Society. All rights reserved.
161 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/078-308-144-589-565, pop00008 tex.type: [object Object]
Keywords: binaries: general; catalogs; dept.phy; peer-reviewed; planets and satellites: detection; surveys; techniques: high angular resolution; techniques: photometric

Combinatorial screening of Pd-based quaternary electrocatalysts for oxygen reduction reaction in alkaline media - Li, Jinyang; Stein, Helge S.; Sliozberg, Kirill; Liu, Jingbei; Liu, Yanhui; Sertic, Genevieve; Scanley, Ellen; Ludwig, Alfred; Schroers, Jan; Schuhmann, Wolfgang; Taylor, André D. (Journal of Materials Chemistry, 2017)
The implementation of electrochemical systems such as fuel cells has been hindered by the slow development of low cost high activity catalysts. Here we examine the oxygen reduction reaction performance of a combinatorial Pd-Au-Ag-Ti thin film library using high-throughput screening and correlate the electrochemical behavior to the crystallographic properties. We find compositions of ca. 40-60 at% Pd and 30-35 at% Au exhibit both a low overpotential of close to the value of pure Pt as well as high current density. We also observe a volcano-like relationship between the overpotential and the solid formation strain. This study provides compositional guidance towards the future synthesis of nanostructured quaternary Pd-Au-Ag-Ti alloys and suggests the potential for broader application of high-throughput electrochemical characterization by means of an automatic scanning droplet cell. © The Royal Society of Chemistry.
30 citations (Crossref) [2023-10-31] Citation Key Alias: pop00049 tex.type: [object Object]
Keywords: Catalyst activity; Combinatorial screenings; Crystallographic properties; Electrocatalysts; Electrochemical behaviors; Electrochemical characterizations; Electrochemical systems; Electrolytic reduction; Fuel cells; Gold; High current densities; High throughput screening; Oxygen reduction reaction; Reduction; Silver; Silver alloys; Throughput; Titanium alloys; dept.phy

Noble metal high entropy alloys - Sohn, Sungwoo; Liu, Yanhui; Liu, Jingbei; Gong, Pan; Prades-Rodel, Silke; Blatter, Andreas; Scanley, B. Ellen; Broadbridge, Christine C.; Schroers, Jan (Scripta Materialia, 2017)
A series of noble metal high entropy alloys with up to six constituent elements has been produced by casting. PtPdRhIrCuNi forms single-phase face-centered cubic solid solution, and its stability is confirmed by annealing experiments. This alloy deforms homogeneously to ~30% to a high ultimate compression strength of 1839MPa. We discuss rules for the formation of single-phase solid solution.
70 citations (Crossref) [2023-10-31]
Keywords: Annealing experiments; Compressive properties; Compressive property; Constituent elements; Entropy; FCC structure; Face-centered cubic; Fcc structures; High entropy alloys; Phase stability; Precious metals; Single phase; Solid solution; Solid solutions; Ultimate compression; dept.phy

Introducing an analytical solution and an improved one-factor gaussian copula model for the pricing of heterogeneous CDOs - Gao, Xin; Wu, Binlin; Schäfer, Tobias (International Journal of Financial Engineering, 2017)
This paper introduced an analytical solution and improved one-factor Gaussian copula models to the pricing of tranches of a Collateralized debt obligations (CDO) portfolio. Prices of CDO tranches are calculated and compared using the analytical model and different one-factor Gaussian copula models including a two-category heterogeneous model and a completely heterogeneous model that uses individual rate parameter and correlation coefficient for each reference entity in a CDO portfolio. When correlation among reference entities is low, the price calculated from the analytical model matches very well with the one-factor Gaussian copula models. However, as the correlation among reference entities increases, prices calculated using both the analytical solution and the homogeneous or two-category one-factor Gaussian copula models significantly deviate from the completely heterogeneous one-factor Gaussian copula model. This result verifies our belief that uniform parameters cannot completely capture all the heterogeneities in a CDO portfolio. Completely heterogeneous one-factor Gaussian copula model using individual rate parameters and correlation coefficients for each reference entities provides more reliable and accurate prices for structured securities.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/183-625-470-365-466, pop00170
Keywords: dept.phy

Carbon nanotube synthesis from block copolymer deposited catalyst - Woods, K; Silliman, J; Schwendemann, Todd C (International Journal of High Speed Electronics and Systems, 2017)
A block copolymer/metal-salt solution was used to deposit metal nanoparticles on substrates, from which carbon nanotubes (CNTs) were grown in a chemical vapor deposition (CVD) chamber. Mono and hybrid catalysts of Fe, Ni, and Co-nitrates were tested, and separately Co, Ni, and Cu-chlorides. In both cases cobalt/cobalt-hybrids produced the highest density of multi-wall carbon nanotubes (MWCNTs). Slight vertical growth, though sparse, was observed after growth at 800°C from a nickel catalyst on single-crystal aluminium oxide (~130nm diameter). © 2017 World Scientific Publishing Company.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/153-067-574-456-766 tex.type: [object Object]
Keywords: Aluminium oxide; Block copolymers; Carbon nanotube synthesis; Carbon nanotubes; Catalysts; Chemical vapor deposition; Chemical vapor depositions (CVD); Hybrid catalysts; Metal nanoparticles; Multiwalled carbon nanotubes (MWCN); Nanotubes; Nickel; Nickel catalyst; Vertical growth; Yarn; block copolymer; carbon nanotube; dept.phy; peer-reviewed

Quantitative characterization for identification of brain cancer surgical margin using resonance Raman spectroscopy - Zhou, Yan; Liu, Chenghui; Wu, Binlin; Yu, Xinguang; Cheng, Gangge; Zhang, Chunyuan; Alfano, R R (Frontiers in Optics, 2017)
A new criterion was developed to characterize brain tissue using resonance Raman spectroscopy, by which, negative margins of cancer can be differentiated from normal tissues. This method may help a surgeon better decide surgical margins. © OSA 2017.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/043-005-059-782-813 tex.type: [object Object]
Keywords: Brain cancer; Brain tissue; Diseases; Normal tissue; Quantitative characterization; Raman spectroscopy; Resonance Raman spectroscopy; Surgery; Tissue; dept.phy

Teaching Materials Science and Engineering (MSE) in the pre-college classroom as a vehicle for NGSS implementation - Granucci, Nicole; Jenkins, Carol; Bauer, Melanie; Gard, Ashley L.; Pinkerton, Bryn; Broadbridge, Christine (MRS Advances, 2017)
Adoption of Materials Science and Engineering (MSE) into the pre-college classroom is an ideal strategy for addressing Next Generation Science Standards (NGSS), specifically the Science and Engineering Practices. MSE offers core science and engineering topics that can be incorporated into existing Science, Technology, Engineering, and Mathematic (STEM) curricula through teaching modules. Using MSE as a teaching vehicle, the Center for Research on Interface Structures and Phenomena (CRISP) conducted a series of small-scale studies of its teacher professional development workshops and a student summer program, along with related teaching modules, in an effort to measure the contribution MSE has on students and K-12 STEM educators. Based on participant survey feedback, CRISP found improvement in students' MSE knowledge, interests, and career goals. For teachers, in addition to improving their MSE knowledge, they also increased their comfort and confidence in teaching MSE concepts in their classroom. These results provide evidence for the use of MSE modules as productive teaching tools for NGSS Science and Engineering Practices, as well as producing workforce-competitive STEM students. Copyright © Materials Research Society 2017.
1 citations (Crossref) [2023-10-31]
Keywords: Aerogels; Curricula; Education; Government interactions; Interface structures; Materials science and engineering; STEM (science; technology; engineering and mathematics); Science; technology; engineering; and mathematics; Science and engineering; Science standards; Standards; Students; Surveys; Teacher professional development; Teaching; Teaching materials; aerogel; dept.phy; education; government interactions; peer-reviewed

A component‐by‐component characterisation of high‐risk atherosclerotic plaques by multiphoton microscopic imaging - Jain, Manu; Wu, Binlin; Pisapia, David J; Salvatore, Steven P; Mukherjee, Sushmita; Narula, Navneet; Mukherjee, Sushmita; Narula, Navneet (Journal of Microscopy, 2017)
Aims: Atherosclerotic plaques vulnerable to rupture are almost always inflamed, and carry a large lipid core covered by a thin fibrous cap. The other components may include neovascularisation, intraplaque haemorrhage and spotty calcification. In contrast, stable plaques are characterised by a predominance of smooth muscle cells and collagen, and lipid core is usually deep seated or absent. This study is a proof of principle experiment to evaluate the feasibility of multiphoton microscopy (MPM) to identify aforementioned plaque components. Methods and Results: MPM is a nonlinear optical technique that allows imaging based on intrinsic tissue signals including autofluorescence and higher-order scattering. In our study, MPM imaging was performed on morphologically diverse aortic and coronary artery plaques obtained during autopsy. Various histologically verified plaque components including macrophages, cholesterol crystals, haemorrhage, collagen and calcification were recognised by MPM. Conclusions: Recognition of the distinct signatures of various plaque components suggests that MPM has the potential to offer next-generation characterisation of atherosclerotic plaques. The higher lateral resolution (comparable to histology) images generated by MPM for identifying plaque components might complement larger field of view and greater imaging depth currently available with optical coherence tomography imaging. As the next step MPM would need to be evaluated for intact vessel imaging ex vivo and in vivo. © 2017 The Authors Journal of Microscopy © 2017 Royal Microscopical Society
3 citations (Crossref) [2023-10-31] Citation Key Alias: jainComponentbycomponentCharacterisationHighrisk2017, lens.org/088-949-097-388-885 tex.type: [object Object]
Keywords: Aorta; Article; Atherosclerotic plaque; Calcinosis; Cholesterol; Collagen; Coronary Vessels; Hemorrhage; Humans; Image Processing; Computer-Assisted; Macrophages; Nonlinear Optical Microscopy; Plaque; Atherosclerotic; aorta; atherosclerotic plaque; autofluorescence; autopsy; bleeding; calcinosis; cholesterol; clinical article; collagen; coronary artery; coronary artery calcification; coronary blood vessel; dept.phy; ex vivo; ex vivo study; feasibility study; histopathology; human; human tissue; image processing; immunology; macrophage; macrophages; multiphoton microscopy; nonlinear optical microscopy; pathology; priority journal; procedures